How Countries Can Fully Implement the New York Convention: A Critical Tool for Enforcement of International Arbitration Decisions - Forneris, Xavier; Mocheva, Nina (Washington DC, 2019)
The year 2018 marked the 60th anniversary of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, the most important international convention in the area of international commercial arbitration. The Convention is also said to be the most successful international treaty in the area of private international law. This note primarily targets policy makers and their legal advisors in countries looking at ways to improve their business environment, to become more attractive locations for trade and investment, through better dispute resolution options for international transactions. First, the note explains that international commercial arbitration, as part of countries' legally recognized dispute resolution options, is critical to cross-border contract enforcement. As countries strengthen their international arbitration regimes, they improve their competitiveness in international markets and increase investment and trade by reducing transaction risks and the cost of new infrastructure projects. Countries can improve their international commercial arbitration systems by passing modern legislation consistent with international best practice, ratifying international arbitration conventions, strengthening judicial capacity to enforce arbitral awards, and investing in local arbitration centers.

The Recovery of Debts Inherent in Cheques without Cover in Cameroon via the OHADA Simplified Recovery Procedure and Enforcement Measures - Penda, Akama Samuel; Ndikum, Nji Keneth (International Journal of Trend in Scientific Research and Development, 2019)
The vast number of commercial transactions that take place daily in the modern business world will be inconceivable without negotiable instruments like cheques. This is the reason why the recovery of debts inherent in cheques without cover has been given the attention it deserves within the CEMAC Region under the OHADA Uniform Act on Business Law. The OHADA Uniform Act on Simplified Recovery Procedure and Enforcement Measures has instituted a procedure in the member states of the OHADA zone to recover debts of a company when it eventually goes bankrupt or when it winds up. It should however be understood that all the member states of CEMAC are OHADA signatories. This ipso facto means that Cameroon being a member of CEMAC, with its bi jural nature, where the Common Law and Civil law legal systems operates in the Former West Cameroon and Former East Cameroon respectively, both parts of the country are bound to implement the OHADA Uniform Act in their various jurisdictions. The Uniform Act on Simplified Recovery Procedures and Enforcement Measures was issued on the 10th of April 1998. Like the Uniform Act on Securities, this Act overlaps the bound of pure business law in that it effects a general reform of civil procedure in relation to recovery and enforcement. The reform was indispensable of the OHADA Member States, only Mali had, in 1994, put in place a modern system that was suited to present day economic and social conditions. Otherwise, the relevant legislation dated, at best from the 1970s and in several cases from colonial times. The OHADA Uniform Act governs commercial companies and Economic Interest groups. Since banks are commercial companies governed under Public Limited Companies S. As , they are equally governed by the OHADA Uniform Act. Thus, this paper questions the potentials of the OHADA Simplified Recovery Procedure and Enforcement Measures in relation to the special mechanisms for the Recovery of Debts inherent in cheques without cover in Cameroon.
Keywords: Chèques; Procédure simplifiée; Recouvrement de créances; Recovery of Debts; Voies d'exécution

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Personal Property Security Law: International Ambitions and Local Realities - Castellano, Giuliano; Tosato, Andrea (International Business Law, 2019)
Personal property security law is a key element of “access to credit” and “financial inclusion”. The prevailing view is that a legal framework enabling the effective use of personal property as collateral markedly benefits both lenders and borrowers. Lenders can offer financing at a lower cost thanks to reduced credit risk; borrowers can access funding by leveraging the otherwise unavailable value of the assets integral to their operations. Over the past century, the priorities of personal property security law have evolved fundamentally. As small and medium-sized enterprises (SMEs) and individual entrepreneurs have become the growth engine of both developed and developing economies, legislators have grown sensitive to the financing needs of these entities. In parallel, the advent of the information society has demanded that lawmakers address squarely the rules governing the use as collateral of intangibles such as “receivables”, “intermediated securities”, “non-intermediated securities”, and “intellectual property rights”, rather than confine their gaze to tangibles such as industrial machinery, mobile equipment and inventory. Concurrently, the increasingly transnational nature of both economic development policies and commercial activity have engendered the need for global principles and standards for asset-based lending. To address these novel priorities and promote a healthy and vibrant credit ecosystem, international and regional organizations have undertaken projects aimed at modernizing and harmonizing personal property security law. Over time, these efforts have yielded a panoply of legal instruments. Binding conventions have been adopted to unify the rules of discrete facets of personal property security law, while soft-law texts, such as model laws and legislative guides, have been formulated to supply comprehensive legal templates to lawmakers keen to revise their domestic legal regimes. Nevertheless, states have struggled to assimilate these international efforts into their domestic legal systems. Common law jurisdictions have been loath to abandon the familiarity and safety of the path paved by centuries of case law; in similar vein, civil law jurisdictions have resisted inducements to renovate the normative infrastructure erected by the codifications of the 19th century. This Chapter explores the tension between international ambitions and local realities, with a special focus on the issues encountered in civil law jurisdictions. To this end, the case of Italy is examined as a living experiment in comparative personal property security law. In this jurisdiction, the recent enactment of a non-possessory security device, absent a comprehensive reform of the country’s civil code affords important lessons for any civil law system which might be pondering personal property security law reforms. More profoundly, it epitomizes the gap that separates the aspirations of international legal instruments from their effective implementation in domestic contexts. This analysis is divided into two parts. The first reviews international and regional legal initiatives that have shaped the personal property law landscape and then identifies a set of core tenets shared among them. In the second part, attention shifts to Italy, scrutinizing both the personal property security legal edifice originally constructed in this jurisdiction and the attempts to overhaul it that have taken place over the past three decades. This is followed by a critical appraisal of the current state of the law, by reference to the aforementioned core tenets of personal property law reform.
Keywords: Commercial Law; Law Reform; Non-possessory Pledge; Personal Property Security Law; Secured transactions

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
OpenAlex: https://openalex.org/W2998516176
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

The contribution mediation can make in addressing economic crime in corporate and commercial relationships in South Africa - Hoffman, Cornelia Hendrina (Stellenbosch University, 2019)
Economic crime is complex and costly. It is costly because it harms victims, both directly and indirectly, as well as the broader economy. The cost is not only financial, but also to confidence and trust in corporate and commercial relationships in South Africa. Economic crime is complex because it includes offences from common-law fraud to statutory contraventions such as incorrect bookkeeping. There are several mechanisms in the South African legal justice system to address economic crime. The conventional legal models include adversarial criminal prosecution of the offender and civil compensation claims, the model of inquisitorial administrative investigations and sanctions like penalties and compensation orders. In 2001 section 105A of the Criminal Procedure Act, namely plea and sentencing agreements, was added as a model of negotiated justice. This mechanism allows the prosecution and the offender to negotiate and enter into an agreement regarding the charges and the sanctions, subject to approval of the court that the plea of guilty is proper and that the proposed sanction is a just sentence. This dissertation proposes that mediation be added to the existing alternative models to help combat economic crime. Mediation involves negotiated justice, as well as restorative justice. More specifically, mediation as a restorative justice process, constitutes a practical alternative to standard litigation as the affected parties themselves, with the facilitation of a third person, resolve the disputes between them. Mediation, a facilitative and flexible procedure, allows the voices of both the victim and the offender to be heard securely and meaningfully. Mediation is rehabilitative and allows for agreed restorative provisions for both the perpetrator and the victims of economic crime. The outcome is a proposed amendment to the Criminal Procedure Act 51 of 1977, namely the insertion of section 105B, “Mediated Settlement Agreements”, that will provide for mediation and a mediated settlement agreement to be incorporated into and form part of the criminal justice processes. It is envisaged that an accredited mediator will mediate between the parties, including the public prosecutor, the perpetrator, the victim and possibly members of the community. The mediated settlement agreement will include both compensation for the victims and a proposed sentence for the perpetrator. This mediated settlement agreement will then be tabled before the court for adjudication and approval to serve as an effective court order. The proposal is a logical legal development of section 105A of the Criminal Procedure Act on plea and sentencing agreements, as the process of mediation builds on the process of negotiation established in it. To put it bluntly, if a plea and sentence agreement can be negotiated between the prosecutor and the offender, a plea and sentence agreement can be mediated between the prosecutor, the offender and the victim. Mediation can integrate and expand the constitutional principles of reparation and ubuntu and curb economic crime by providing an effective restorative and just response to it.
URI: http://hdl.handle.net/10019.1/107281
Keywords: Alternatives to prosecution; Commercial law; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; South Africa

Multidimensionality of Sustainable Public Procurement (SPP) - exploring concepts and effects in Sub-Saharan Africa and Europe - Stoffel, Tim; Cravero, Carol; La Chimia, Annamaria; Quinot, Geo (Sustainability, 2019)
Strategic objectives in public procurement, such as environmental or social considerations, are being increasingly referred to under the umbrella term of sustainable public procurement (SPP). The concept of sustainability is intrinsically multidimensional, encompassing environmental, social, and economic aspects. However, the existing literature on SPP highlights the generalization that the regulation and practices of public procurement are biased toward the environmental dimension. There is conflicting evidence from countries in Sub-Saharan Africa (SSA) that calls for further investigation. Analyzing how SPP is actually constituted in SSA and contrasting it with the situation in the European Union (EU), as a spotlight on the Global South and North, contributes to a better understanding of sustainability in public procurement. The comparative analysis will help with understanding processes related to the integration or disintegration of sustainability dimensions in SPP. Our results indicate a contrary orientation on the environmental and the social dimensions in the EU and SSA. Although there is no sign of a comprehensive integration of all dimensions in SPP, there are developments toward the integration of the ‘missing’ dimension in the respective regional setting. Thus, at the moment, achieving a multidimensional implementation of SPP appears to be more a matter of expanding SPP practices of the ‘missing’ dimension than of pushing for integrated concepts.
http://hdl.handle.net/10019.1/124395
Keywords: GPP; Government purchasing; Green public procurement; Multidimensional sustainability; SRPP; Socially responsible public procurement; Socioecological transformation; Sustainable development; Sustainable supply chains

The Influence of IAS/IFRS on the New OHADA General Chart of Accounts - Tchokoté, Ivan Djossa (Journal of Modern Accounting and Auditing, 2019)
Accounting standardization in black African French-speaking countries is presented through two streams of research. The first stream presents the general chart of accounts common to all these countries as an accounting model which reconciles the divergences between the Anglo-Saxon and continental approaches to accounting, and thereby satisfies the requirements of users of accounting information. The second stream considers that the convergence towards IAS/IFRS is a vital way of attracting international investors and increasing development. This article stands by the second perspective and analyzes the changes introduced in the PCG-OHADA (2017) compared to the PCG-OHADA (2000). It shows that the new provisions of the PCG-OHADA are mainly inspired by IAS 1, IAS 16, IAS 19, IAS 36, IAS 38, IAS 40, and IFRS 6.
Keywords: Accounting harmonization; Accounting standards; IFRS; PCG

A comparative appraisal of debt relief measures for no income no assets (NINA) debtors in Nigeria - Osunlaja, Tobi Titilayo (University of Pretoria, 2019)
Nigeria currently has a non-functioning insolvency system; it is yet to record a successful insolvency case. This failure principally is attributable to the weak laws and enforcement policies in existence. The problem is exacerbated by burgeoning consumer debt in the formal sector. The causal factors for this increase in debt are negative economic growth indices such as rising inflation, interest rates and unemployment. With these indices predicted to worsen, a new Bankruptcy and Insolvency Act (BIA) was proposed in 2016. The BIA seeks to regulate individual insolvency proceedings in Nigeria. However, the BIA (as currently conceptualized) does not make provision for debtors with neither income nor assets, often referred to as No Income No Assets (NINA) debtors who, it can be argued, are in the majority in the Nigerian state. The aim in this thesis is to propose debt relief measures that cater for NINA debtors in Nigeria. This proposal aims to prevent further discrimination against these debtors in terms of the current law and the proposed BIA. It envisages that catering for NINA debtors in Nigeria will boost the Nigerian government’s drive to encourage entrepreneurship. In providing for NINA debtors it will provide a safe landing for poor debtors in the event of entrepreneurial failure. The thesis achieves its stated aim by studying international principles and guidelines as espoused by leading bodies. Furthermore, the thesis performs a comparative analysis of relevant NINA provisions in South Africa, Sweden, France, Ireland and Canada. The thesis proposes amendments to the proposed BIA in light of the aforementioned analysis and posits that procedures that are formal and extra-judicial, which have no financial requirements and are easily accessible to debtors should be incorporated.
https://repository.up.ac.za/handle/2263/92927
Keywords: Debt relief measures; Insolvency; Insolvency system; Laws and enforcement policies; No Income No Assets (NINA)

Problems of Enforcement of ICSID Awards: An Analysis of Micula Case - Hasankhani, Ali (Public Law Researsh, 2019)
In the case Micula A.O. v. Romania, the arbitration tribunal established under the auspices of the International Center for Settlement of Investment Disputes (ICSID) sentenced Romania to pay a compensation for the revocation of investment incentives and for the breach of fair and equitable treatment principle that had been laid down in a bilateral investment treaty between Sweden and Romania. Considering investment incentives as a breach of the EU regulations regarding state aids, the European Commission then rendered a directive, prohibiting the enforcement of the arbitration award by the member states. As articles 53 and 54 of ICSID emphasize that the awards are binding, the EU Commission’s act of rendering the aforementioned directive, and the member states refusal to comply with the award equals to giving the EU law primacy over international law, which should be considered as a breach of their international obligations. Using a descriptive-analytical method, this article seeks to explain the viewpoints of the parties and the courts which were asked to enforce the award, as well as to determine the nature of their acts.

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

What Process is Due – Sanctions Regimes of Multilateral Development Banks - Madir, Jelena (University of Westminster, 2019)
Much has been written about the consequences for companies of criminal convictions for bribery and other corrupt practices. However, less attention has been paid to the sanctions regimes that have been developed by multilateral development banks in order to combat fraud and corruption in their operations. This is likely to change in view of the fact that on 9 April 2010, the heads of five leading multilateral development banks (MDBs) – the African Development Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the Inter-American Development Bank and the World Bank Group – signed the Agreement for Mutual Enforcement of Debarment Decisions, which provides for mutual and reciprocal enforcement of debarment decisions taken by any one of them against parties that engage in fraud, corruption, coercion or collusion in connection with MDB-financed projects. For parties that are seeking financing form an MDB or are competing for contracts funded by an MDB, this means that a sanctionable practice committed in a single country could result in global sanctions. Against this background, this thesis examines the type of due process rights that should characterise MDBs’ sanctions procedures. More particularly, the thesis analyses the extent to which MDBs’ sanctions regimes should be bound by the rules of law, analogous to those of national judicial bodies, and the level of due process and transparency that should be required from these ever-evolving regimes. In other words, (how) can the tension between the administrative and business considerations of MDBs’ sanctions regimes (coupled with their immunity from judicial review) be reconciled with due process considerations and principles of fairness that underpin a national judicial model?

Block Chain Accounting: The Face of Accounting and Auditing in Industry 4.0 - Antoney, Laly; Augusthy, Theresa Josephine (International Multilingual Journal of Science and Technology, 2019)
Keywords: Accounting Education; Block Chain Accounting; DLT; Future Audit; Tripple Entry Book Keeping

The power of will and choice of law in international contracts - Dazzi, Pietro Giulio (LUISS Guido Carli, 2019)
Party autonomy and sovereignty. Historical developments on party autonomy, the evolution of choice of law. The freedom of choice. The freedom not to choose, absence of choice. Limits to the freedom of choice. Limits to the freedom of choice, an expression of sovereignty. Same functions, different results.

A critical analysis of the effectiveness of the business rescue regime as a mechanism for corporate rescue - Bagwandeen, Kiren Kesh (University of KwaZulu-Natal, 2019)
Almost eight years after the enactment of the business rescue regime under the Companies Act 71 of 2008, and a plethora of judgments which have probed and prodded its provisions, it is an opportune time to ascertain whether the business rescue regime is an effective corporate rescue mechanism suitable to the modern day demands of the South African economy. In the current economic downturn, South Africa can ill afford a repeat show of the failed judicial management system. It requires a modern and effective corporate rescue mechanism that can be utilised in appropriate circumstances as a viable alternative and not merely a precursor to liquidation. This dissertation seeks to provide a critical analysis of the effectiveness of the business rescue regime to ascertain its worthiness as a corporate rescue mechanism.
Keywords: Bankruptcy; Business failures; Corporation law; Insolvency; South Africa

Proceedings of 1st Annual Research Symposium on International Commercial Arbitration - Casoria, Maria (Royal University for Women, 2019)
Contents: Understanding forum differences for international commercial dispute resolution / R. Brand, p. 4-13 – UNCITRAL – the multi-lateral setting body and its two new mediation instruments / J. Knieper, p. 14-26 – Introducing the Singapore Convention on Mediation / J. C. Checkley, p. 27-34 – An overview of the ICC Mediation Rules / D. Fahs, p. 35-37 – Modern arbitration laws: not just talking the talk / M. Patchett-Joyce, p. 38-42 – Parties’ choice of law governing the arbitration agreement: a curse or a blessing? / Z. Meškić, p. 43-53
Keywords: Arbitrage; Arbitragem; Arbitration; Convention on the Recognition and Enforcement; Foreign Arbitral Awards; International Commercial Mediation; International Settlement Agreements; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements; UNCITRAL Model Law

The Legal Regime of Real Estate Investment Financing by Musharaka Contract - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Il s'agit de la traduction d'une thèse déjà présente dans référencée sur notre sité
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

Causes of Delay in the Resolution of Commercial Disputes via Litigation Arbitration as a Way out within OHADA Laws - Sigala, Buma Roland (International Journal of Trend in Scientific Research and Development, 2019)
An essential requirement of justice is that it should be dispensed as quickly as possible. It is a well-known adage that, « justice delayed is justice denied». Delay in litigation is caused by a number of factors. For example in litigation the parties have the right to make a counterclaim, right to make appeal etc. Arbitration has been able to overcome the factors which cause delay in litigation because in arbitration, parties are given the right to exclude the possibility to make a counterclaim, the right to make appeal has expressly been prohibited by the Organization for the Harmonization of Business Laws in Africa (OHADA)1 legislator etc. But since the OHADA legislator has not expressly prohibited counter claim in arbitration, it is recommended that counterclaim should be expressly prohibited in arbitration as it is the case with appeal. This article aims at identifying the causes of delay in the disposal of commercial disputes via litigation and how these causes of delay have been combated in arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; Delay commercial; Disputes Litigation; Law and management

Electronic Tax System As A Panacea For Tax Revenue Leakages In Nigeria - Nwamgbebu, Obinna; Oketa, Chiamake; Odom, Amarachi; Nwambe, Cynthia; Nweke–Charles, Uchenna (African Journal of Politics and Administrative Studies, 2019)
The broad objective of the study is to assess the problems of the traditional tax system in Nigeria and establish electronic taxation as a solution to these problems. The study adopted content analysis in analyzing text books, journals, newspapers and other essential materials that were used to obtain the needed information for the study. Extensive review of the literature showed that electronic tax system solves the problem of low tax collection, unavailability of tax statistics and poor record keeping, complex of payment and high cost of tax compliance. The implication of these findings is that an adoption of electronic tax system is an intelligent means of achieving a system of tax administration that allows for the collection and accountability of required taxes at a minimum cost. The study concluded that there are some challenges with the manual system of administering taxes and that modern technology could simplify these challenges and alienate them in the form e-tax. The study therefore recommended that government should support with everything on their disposal the establishment of e-tax administration so as to start ripping the benefit of high rate of compliance among taxpayers at all levels of government in Nigeria.

Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.
Accepted: 2023-06-22T17:00:40Z ISBN: 9781509921379 Publisher: Hart Publishing

Adoption, compliance, and consequences of International Financial Reporting Standards in Africa - Tawiah, Vincent K. (Griffith University, 2019)
This thesis investigates the adoption, compliance and consequences of International Financial Reporting Standards (IFRS) in Africa, a continent which has mostly been ignored in prior studies due to the use of generic proxies. Drawing on DiMaggio and Powell (1983), this thesis examines the institutional pressures of IFRS adoption in Africa. Stakeholder salience theory, developed by Mitchell, Agle and Wood (1997), is employed to analyse the determinants of IFRS compliance outside the traditional capital market settings. As regards to the consequences of IFRS in Africa, this thesis analyses the impact of IFRS on audit fees, audit reporting lags and auditor switch. The study used panel data from 54 countries and 205 firms covering the financial years 2003-2016. Secondary data was sourced from reputable database and annual reports of sample companies. Different analytical tools such as ordinary least squares, logit and multinomial regressions were used based on their suitability to address the research questions. The study found that only 18 out of the 54 countries required all listed and large companies to report per IFRS, while 25 did not permit IFRS. The results supported the theoretical prediction that coercive, mimetic, and normative isomorphism influenced IFRS adoption in Africa. Specifically, the World Bank (WB) and International Monetary Fund’s (IMF) influence on African countries in adopting IFRS was not through foreign aid and grants; instead, their recommendations made in the Report on Observance of Standard and Codes (Accounting and Auditing) initiatives. The finding(s) also demonstrated that the presence of global audit firms and the number of years of IFAC membership had a strong association with a country’s decision to adopt IFRS. Moreover, countries with strong professional accounting organisations (PAO) were more likely to adopt IFRS. On IFRS compliance, the study found that the average compliance score among the companies over the period was 70.94%, with a minimum score of 58.59% and a maximum of 83.55%. The findings reported a significant positive association between audit committee competence (ACC) and compliance, and between chartered accountants on board (AOB) and compliance. The thesis also documented that compliance has been increasing over the years. Regarding the impact of IFRS on the audit market, the findings suggested IFRS was positively and significantly associated with an increase in audit fees regardless of early or late adoption. Also, on average, ARL increased by 26% across all samples, with late adopters experiencing 28% and earlier adopters 22% during the adoption year. Contrary to the late adopters, early adopters experienced a significant increase in audit fees during the pre-IFRS period due to the set-up and implementation at the time. In addition, IFRS adoption was likely to cause companies to switch from small audit firms to the Big 4. The findings on adoption suggest that global accounting agencies such as IFAC and IASB should focus on building vibrant national level accounting institutions such as PAOs to facilitate the adoption of IFRS in Africa. The thesis, therefore, adds to the adoption literature the finding that the isomorphic pressures in Africa are different from those suggested in prior studies. The results on compliance imply that companies that appoint more professional accountants to their boards are more likely to comply with the requirement of IFRS. Therefore, it is suggested that companies should engage more chartered accountants in their governance. Also, corporate boards must strive to strengthen their audit committees by appointing more NEDs and CAs to the committee. The findings also provide valuable information for professional accounting organisations on the role of its members (professional accountants) in the effectiveness of IFRS compliance. The findings of the consequences of IFRS on the audit market alert small and medium practitioners (SMPs) in non-IFRS countries of the possible loss of clients to the Big4 due to the adoption of IFRS. To mitigate this effect, the national PAO should build the capacity of their local accountants through training and education to handle the complexities and continuous upgrading of IFRS. Such training is seen as being crucial for SMPs in OHADA countries, Ethiopia, Djibouti and other countries which are in the process of implementing IFRS.
Keywords: Adoption; Africa; Audit market; Compliance; Consequences; IFRS; Institutional pressures; International Financial Reporting Standards; Stakeholder salience

What the African Continental Free Trade Agreement Protocol on Dispute Settlement says about the culture of African States to Dispute Resolution - Akinkugbe, Olabisi (Articles, Book Chapters, & Popular Press, 2019)
An effective Dispute Settlement Mechanisms (DSM) upholds a rules-based trade regime; enunciates, clarifies and develops the jurisprudence of its constituent trade agreement; and also ensures predictability in the trading regime. Article 20 of the African Continental Free Trade Agreement (AfCFTA) establishes the DSM. The AfCFTA Protocol on Dispute Settlement (“Dispute Protocol”) provides for the rules and procedures for the settlement of disputes. Unlike the majority of the African regional economic community courts that are modelled after the Court of Justice of the European Union, the AfCFTA-DSM follows a handful of other regional judicial bodies – such as the Southern African Community Development Community (SADC) and the Tripartite Free Trade Area Agreement (TFTA) – that are modelled after the World Trade Organization (WTO) dispute settlement mechanism.
Keywords: AfCFTA; Dispute Settlement Mechanisms; Free Trade; Trade Agreement

The models of attribution in the establishment of corporate liability revisited - Heese, Francisca Alida (Stellenbosch University, 2019)
The separate legal personality of a company is one of the cornerstones of modern corporate law. Nevertheless, due to the artificial nature of a company it has no inherent moral blameworthiness necessary to impose corporate liability. With a rise in corporate wrongdoing, there is a need to hold companies liable. Therefore, certain models of attribution have developed whereby the conduct and will of a corporate actor can be imputed to the company to establish corporate liability. Especially in the realm of corporate criminal liability, these models of attribution have played a pivotal role to establish corporate wrongdoing. The two broad theories underlying the models of attribution are the fiction and realist theories respectively. The directing minds doctrine or identification doctrine and the vicarious liability model are traditionally associated with the fiction theory, which is rooted in the abstract nature of a company. Whether the traditional models of attribution are suited for complex modern organisational structures, is explored in this thesis, whilst a more functional and realistic approach to corporate liability is proposed. Often the question of “what is a corporation” has overshadowed the determination of corporate liability, thus a more contextual analysis based on law and economics is proposed to ensure corporate liability. The development of the rules of attribution through case law illustrate the importance of a purposive approach to establishing corporate liability. Furthermore, the underlying relationship between the rules of attribution and the rules of agency indicate that the interests of risk-bearers and managers are not always aligned and should be redressed. Moreover, a realist approach as opposed to the fictional approach to attribution has been developed in English and Australian law. This approach focuses on the overarching corporate culture and identity when determining corporate fault, instead of individual corporate actors. These regulatory frameworks provide an alternative approach to the current South African model, which is based on the fiction theory. Lastly, the economic considerations, such as the separation of ownership and control and the agency problem, are evaluated to determine whether the current models of attribution create an economically efficient outcome or an unsustainable a risk-taking environment.
Keywords: Corporate culture; Corporate liability; Corporation law

Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch University, 2019)
Companies are legal persons and as much part of commercial traffic as the natural persons owning and controlling them. Compared to one another, companies and natural persons nevertheless have very different legal abilities and characteristics. It is therefore not unexpected that they are treated differently for purposes of the law of taxation. As a result it may often be more beneficial to have the profits generated by a business enterprise taxed in a company rather than in the hands of a natural person, especially in instances where a shareholder would be commercially indifferent to whether those profits are generated in a company or not. By using the separate legal personality of a company shareholders may often perpetrate an abuse of that separate legal personality. Such abuse of legal personality can also take place when legal personality is employed primarily for tax reasons. While a limited form of abuse of the corporate veil is tolerated, whether the use of separate legal personality for tax reasons amounts to an abuse thereof beyond what is permitted in South Africa can be determined in terms of three tests. These tests are the traditional “piercing of the corporate veil” judgments forming part of the common law, section 20(9) of the Companies Act 71 of 2008 and the General Anti-Avoidance Rules (“GAARs”) (and other specific provisions) in the Income Tax Act 58 of 1962. This dissertation considers when any of these various tests will dictate that the separate personality of a company be ignored (or “pierced”) for purposes of taxes levied in terms of the Income Tax Act. Through critical analysis of both the South African rules on piercing as applied for tax purposes as well as the circumstances under which selected other jurisdictions provide for piercing for tax reasons the dissertation formulates what best practice and desired policy for piercing for tax reasons are.
URI: http://hdl.handle.net/10019.1/106096
Keywords: Close Corporations Act; 1984; Companies Act; 2008; Corporate veil; Corporations; Income Tax Act; 1962; South Africa; Tax evasion; Taxation; Unconscionable abuse

Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch University, 2019)
ENGLISH ABSTRACT :This dissertation assesses the regulation of takeovers and mergers and the institutions created to enforce the law, from a comparative perspective. It uses South Africa as its point of departure and takes the laws of Delaware in the United States, the United Kingdom and Australia into account. The dissertation indicates that numerous takeover provisions in South Africa are poorly formulated, making them difficult to interpret and apply. Accordingly, the dissertation recommends amendment and improvement of certain Takeover Provisions. Special emphasis is placed on the mandatory offer requirement. The dissertation critically and comparatively analyses this requirement and especially its impacts on the market for corporate control, efficient usage of capital, corporate governance and (in South Africa) Broad Based Black Economic Empowerment. It appears from the literature explored that the mandatory offer requirement originated from the Perlman case in the United States as an expression of the equal opportunity rule. According to the equal opportunity rule, the controlling stake of a company is enriched with a premium of control, which must be shared with other shareholders when there is a change of the controlling shareholder. Shareholders must be given an equal opportunity to share in this control premium. Hence, a mandatory offer must be made to the remaining shareholders of the company by the new controlling shareholder at a price at which control was bought. Perlman case was decided in the United States of America during 1955. It is contended in the dissertation, that the mandatory offer requirement in section 123 of the Companies Act 71 of 2008 (“the Act”), can ultimately be traced back to this case. Researchers have criticised the mandatory offer requirement in a number of respects. It has been pointed out that the rationale for the decision in the Perlman case was not clear and applied in limited circumstances. Other scholars point out that the case was not a final decider on the sharing of the control premium due to later judicial pronouncements that differed with that case. Despite these commentaries, it appears that the case became a basis for imposing and enforcing this most debated rule in takeover and merger law. The dissertation concludes that the sharing of a premium of control, as envisaged by the mandatory offer requirement, is not enforced in the state of Delaware. It further concludes that in the UK, the mandatory offer rule forms the cornerstone of enforcement of the equal opportunity rule, but that widely dispersed shareholding ameliorates it negative consequences in that jurisdiction. The dissertation favours the Australian approach. That jurisdiction does not require a mandatory offer similar to that in section 123 of the Act, but, Australian Takeover Provisions, unlike their South African equivalent, have been tailor-made for Australian market conditions. The dissertation accordingly concludes that the mandatory offer requirement in section 123 of the Act in its current form is not appropriate for South Africa.
URI: http://hdl.handle.net/10019.1/105995
Keywords: Consolidation of corporations; Delaware; Great Britain; Merger of corporations; Regulation; South Africa

The definitions of ‘inside information’ and ‘insider’ in the Financial Markets Act 19 of 2012 - Van Der Walt, Johann Nico (Stellenbosch University, 2019)
The definitions of ‘insider’ and ‘inside information’ in the Financial Markets Act 19 of 2012 are, as is the case with their international counterparts, central to the Act’s regulation of insider trading. It has long been recognised, however, that those definitions, inherited from repealed companies and market abuse legislation, are cumbersome and counter-intuitive. This state of affairs obtains as the South African legislature has failed to undertake the most fundamental enquiry in formulating a coherent regulatory scheme aimed at prohibiting supposedly wrongful conduct: identifying a single theory of wrongfulness upon which to base its prohibitions. Instead, the definitions include elements of all possible regulatory bases for insider trading, including those having as their object the protection of proprietary rights in information and born out of the fiduciary doctrine. It is argued that the definitions, part of legislation aimed at addressing a financial market wrong, should be formulated with reference to the rights and obligations at play in those markets and the legislature’s objectives for those markets. A proposal is made in that regard.
URI: http://hdl.handle.net/10019.1/105745
Keywords: Finance; Financial Markets Act; 2012; Insider trading in securities; Markets; South Africa

The China-OHADA BIT, a step in the right direction : a new model of China-Africa BIT at a regional or sub-regional level - Sun, Sisi (Université de Montréal, 2019)
L’Afrique jouit non seulement de ressources naturelles, mais aussi d’un grand potentiel de marché. Ces dernières années, il y a une injection croissante d'investissements privés en provenance de Chine vers l’Afrique. La Chine souhaite exploiter le potentiel de l’Afrique en tant que marché émergent grâce aux investissements considérables réalisés par des entreprises privées. Parallèlement, les pays africains ont besoin d'investissements chinois dans divers domaines pour stimuler chaque aspect de leurs économies. L'investissement privé axé sur le marché nécessite un environnement d'investissement ouvert, stable, sécurisé et prévisible. Or, les traités bilatéraux d'investissement (TBI) existants entre la Chine et l'Afrique adoptent le modèle post-établissement axé sur la protection. La plupart de ces traités prévoient simplement des obligations générales de protection des investissements, laissant toutes les autres questions à la discrétion de l’État hôte. Les régimes juridiques instaurés par les TBI conclus entre la Chine et les États africains manquent de lisibilité, de prévisibilité et de cohérence. La conclusion de l'accord économique et commercial global entre l'UE et le Canada (AECG) suggère l’idée que la Chine pourrait s’inspirer de ce modèle pour conclure un accord bilatéral autonome avec les pays africains au niveau régional ou sous régional afin d’attirer des investissements chinois vers l’Afrique. Cet accord pourrait intervenir dans le cadre de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) étant donné son niveau d’intégration et son autorité en matière de commerce et d’investissement sur le continent. Ce TBI modèle comportera des normes uniformes en matière d’accès aux marchés et de protection des investissements, ce qui limitera les risques d’interprétation divergente et partant, contribuera à l’instauration d’un climat d'investissement stable, sûr, prévisible et plus ouvert. Africa enjoys not only natural resources, but also market potential. There has been a growing injection of private investment inflows from China to Africa recently. China needs to exploit Africa’s potential as an emerging market for its tremendous investments by private enterprises. Moreover, the African countries need Chinese investments in various areas to boost aspects of their economies. Private, market-oriented investment calls for an open, stable, secure and predicable investment environment. However, existing bilateral investment treaties (BIT) between China and Africa adopt the protection-oriented, post-establishment model. The treaties merely provide for some general obligations of investment protection, leaving all other matters to the policy discretion of the host state. The China-Africa BIT regime is sporadic, uninformed and incoherent. The conclusion of the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA) develops the idea that China might conclude a standalone BIT with the African countries at a regional or sub-regional level to attract Chinese investment inflows into Africa through an open, coherent and uniformed investment scheme. Given the integration of Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) to be one single jurisdiction over trade and investment, the China-OHADA BIT is the one most likely to be expected. This standalone BIT regime inherently calls for an absolute standard for market access and investment protection, and uniformity to limit the discretion of interpretation, and as such, contribute to a more open, stable, secure and predictable investment climate.
Keywords: BIT regime; China-OHADA BIT; Chine-OHADA TBI; Climat d'investissement; Discrétion politique; Investment climate; Investments; Policy discretion; TBI modèle

The Development of Mortgage Finance in Nigeria and its Impact on the Economy - Siyan, Peter; Adegoriola, Adewale E; Erivwode, Ovosa Mercy (International Multilingual Journal of Science and Technology, 2019)
This study examines the development of mortgage finance in Nigeria and its impact on economic growth. Aggregate housing finance data for by both banks and non-financial institutions was used to measure housing finance. Other variables considered include financial debt proxy by M2Per capita, financial instability proxy Interest rate and the level of development of the capital market measured by market capitalization. Time series data covering the period 1990-2016 was obtained from Central Bank statistical bulletin, National Bureau of Statistic and World Bank. The methodology adopted in the study is Vector Autoregressive Model (VAR) was estimated using linear regression method. The results of the analysis indicated that there is a one-way causal link runs from mortgage finance to economic growth. In addition, mortgage finance was found to be a significant determinant of increasing pattern of economic growth over a long period of time. Due to the level of the country’s financial depth, it was recommended that Nigerian government should intensify effort aimed at consolidating the level of financial re-structuring in the non-financial sector which mortgage financing belong. The central bank should make a policy stipulating commercial banks to set aside certain proportion of their total assets to finance housing demands.
Keywords: Economic growth; Hypothèque; Mortgage Finance; Vector Autoregressive

Proceedings ISDS reform conference 2019: mapping the way forward - Asian Academy of International Law (2019)
Keywords: Dispute settlement; Investment disputes; LAW REFORM; UN Commission on International Trade Law

The copyright protection of musical works : a historical and contextual analysis - Baloyi, Jele Joel (University of South Africa, 2019)
This work is concerned with an analysis of the copyright protection of musical works. Musical works form part of the categories of works protected under copyright law. It would be easy to dismiss musical works as not warranting a serious study, as would for example, be warranted for “industrial property” rights such as patents and geographical indicators, or more “serious” copyrights such as architectural works and computer software. Such a perspective would however, not be cognisant of the significant contribution that the music industry, as part of the broader cultural and creative industries makes to the global economy. It has, for example, been shown that in 2013, the global cultural and creative industries contributed some US$2,250b, employing some 29,5 million people, with the music industry being one of the top three employers and with its revenues exceeding those of radio.1 A single successful musician can earn in excess of US$100m per annum,2 making the industry ripe for litigious claims. For this reason therefore a consideration of the legal rules that apply to the protection of musical works is crucial. There is currently no clear exposition and systematic analysis of the legal principles applicable to the field of music copyright and no work devoted to the in-depth delineation of the rights and sub-rights relating to musical copyright protection. This study seeks to address this research and knowledge gap by providing a historical and contextual analysis of the protection of musical works. The aim is to provide a complete picture of the milieu of music copyright protection to enable the reader to feel empowered in dealing with the subject-matter. This the writer does by mapping the historical development of music copyright protection in particular from eighteenth century England when the first copyright legislation was enacted, until the enactment of the British Copyright Act of 1911, which signalled the emergence of the “common law” copyright system. The writer then shows how this enactment shaped the development of modern music copyright law, and concludes by presenting a contextual consideration of the current South African law of music copyright and highlighting the challenges it is faced with.
Keywords: Copyright; Copyright protection; Dramatico-musical works; Imperial Copyright Act; Intellectual property; Intellectual property rights; Music; Music trade; Musical compositions; Musical works

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Shareholder activism, corporate social responsibility and financial performance - Yang, Yi (Victoria University of Wellington, 2019)
The thesis examines the influence of shareholder activism on corporate social responsibility (CSR) disclosure of targeted firms and its spillover effects on CSR disclosure, corporate social performance (CSP) and financial performance (FP) respectively in peer firms. The research is motivated by filling the research gaps in prior literature and providing insights to shareholders, the management and regulatory bodies in practice. The thesis consists of three parts. Firstly, this thesis reviews the literature surrounding shareholder activism by conducting narrative reviews of 92 working papers and publications and meta-analysis on 55 working papers and publications, published during 2000-2017 period. Theories from prior literature, namely agency theory, stakeholder theory and stakeholder salience theory are analysed through narrative review analysis at the beginning of the chapter. Then, the analysis of narrative review also documents mixed findings of the associations among shareholder activism and FP and CG and CSP, including spillover effects. That is, the associations could be positive, negative and not significant in prior literature. The results of meta-analysis indicate that shareholder activism improves FP and CSP respectively. In addition, the thesis also examines the major types of shareholder activists and main forms of shareholder activism. Overall, through the analysis, the thesis identifies the research gaps of prior literature, thereby pointing out future research directions. Secondly, by employing shareholder proposals from Standard & Poor's 1,500 (S&P 1,500, hereafter) companies in the United States as a proxy of shareholder activism during 2006-2014 period with 13,572 separate observations, this thesis examines whether the whole sample of shareholder activism, institutional shareholder activism and coordinated shareholder activism could influence CSR disclosure level respectively. Simultaneously, this thesis also investigates whether shareholder activism affects CSR disclosure level given the other corporate governance mechanisms, namely board size, the presence of female directors, outside directors and CEO incentives. The results typically demonstrate that: (1) while shareholder activism negatively relates to CSR disclosure level, larger board size or the presence of female directors combined with shareholder activism directly relates to maintaining better CSR transparency; (2) coordinated shareholder activism could decrease social disclosure level. The findings also indicate that CSR disclosure provides an approach to strategically manage risks. Thirdly, the thesis explores spillover effects from different types of shareholder activism on CSR disclosure level, CSP and financial performance by using data gathered from S&P 1,500 companies during 2007-2014 period. The findings show that shareholder activism increases social disclosure level and environmental disclosure level in peer firms. It also shows that there is a weak positive association between shareholder activism and CSP. It therefore demonstrates the weak influences of shareholder activism in changing firms’ CSP. It also illustrates that institutional shareholder activism has an advantage over coordinated shareholder activism in terms of increasing corporate transparency. In this manner, it indicates that the collective action problem among coordinated shareholders could also attenuate the impact of shareholder activism in peer firms. The thesis contributes to the literature on shareholder activism practically and theoretically. The findings provide useful insights to shareholders, management teams and regulatory bodies for their policy-making. Beyond the practical contribution, the thesis also provides empirical evidence to stakeholder salience theory and analyses the collective action problem.
Keywords: CSR disclosure; Corporate Social Responsibility; Corporate governance; Corporate social performance; Financial performance; Shareholder activism

Choice of law in International Commercial contracts in the BRICS countries - Agbeko, Fafa Delight (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The tax trade interface : an investigation of the influence of the Nigerian income tax incentives on taxpayer behaviour - Aniyie, Ifeanyichukwu Azuka (University of Pretoria, 2019)
The Companies Income Tax Act provides the architecture for corporate income taxation (CIT) in Nigeria. It specifies the rate, the tax base and contains the bulk of the incentives to which qualified corporate taxpayers are entitled. This thesis investigates the influence of incentives on the compliance behaviour of micro and small companies (MSCs) in Nigeria. By Nigeria’s standard, these are companies which: (1) employ between 1 to 49 persons and/or own assets (excluding land and building) valued at less than NGN 100million; or (2) are either private limited companies or one-man businesses. In the context of the Nigerian tax system, MSCs are corporate taxpayers with turnover of less than NGN 200 million. This choice of research population is a consequence of the globally acknowledged niche occupied by MSCs vis-à-vis the of the socio-economic objectives of any state. In the course of the study, the formulated research questions were resolved using a multi-stage mixed methods framework which allowed for the fusion of qualitative and quantitative epistemology as well as facilitated the introduction of pragmaticism into the research process. The thesis, inter alia, identified gaps in the administrative regime of CIT incentives in Nigeria and highlighted the fact that they have the potential to introduce uncertainty into the tax system. In addition, it revealed that the regulatory regime for the role and services of tax intermediaries within the tax system, in terms of current standards and reality, is sub-optimal. On the basis of a survey of a small sample of MSCs, it was concluded that the influence of tax intermediaries with regard to the compliance behaviour of MSCs was marginal. Reason for this was traced to the fact that the role and services of the latter vis-à-vis clients who are MSCs are actuated by variables which are within the psycho-social space of the tax intermediairies and the desires/requests of the MSC. This dismisses, in the context of Nigeria, the notion that the tax intermediary is the initator of every tax dodge. Based on the findings, the thesis, inter alia, recommended a re-orientation in the conceptualisation of tax compliance as the prevailing theoretical premise for the extant tax law and policy does not contemplate that non-economic factors and referents outside the realm of taxation are capable of influencing tax compliance behaviour. In addition, recommendations with the capacity to change the law, policy and administrative regime relating to CIT incentives as well as the role and services provided by tax intermediaries were made after an examination of the situation in Kenya and South Africa.
URI: https://repository.up.ac.za/handle/2263/72637
Keywords: Companies Income Tax Act; Corporate income taxation; Income tax; Nigeria; Tax trade; Taxpayer

Rethinking international employment contracts in the wake of the Fourth Industrial Revolution - Antwi-Larbi, Nana Amobea (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Choice of forum in International Commercial Contracts : a comparison of the position in Ghana and under the Brussels IBIS regulation - Asante-Aboagye, Benedicta (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Belgium; Border trade; Conflict of laws; Ghana; International commercial contracts; Litigation

May an employer dismiss an employee if the disciplinary chair imposed a lesser sanction? South African Revenue Service v Commission for Conciliation Mediation and Arbitration 2017 38 ILJ 97 (CC) - Calitz, Karin Beatrix (Stellenbosch Law Review, 2019)
In South African Revenue Services v Commission for Conciliation, Mediation & Arbitration, Kruger, the employee, called his superior a “kaffir” on more than one occasion. The employer unilaterally dismissed the employee after the chairperson of the disciplinary hearing had imposed a lesser sanction. In doing so, the employer disregarded the collective agreement which did not make provision for the sanction of the disciplinary chair to be substituted. The employee claimed that his dismissal was invalid and therefore unfair. The Commission for Conciliation Mediation and Arbitration (“CCMA”), Labour Court and Labour Appeal Court (“LAC”) agreed. However, in the Constitutional Court (“CC”) the employer no longer argued that it was entitled to substitute the sanction in the light of the breach in the trust relationship, but only alleged that reinstatement was a remedy that no reasonable decision-maker would order. The CC agreed and held that the dismissal was substantively fair but procedurally unfair. The CC did not answer questions of lawfulness, fairness and invalidity, but in Steenkamp v Edcon the CC held that employees claiming remedies for unfair dismissal in terms of the Labour Relations Act 66 of 1995 (“LRA”) should not rely on invalidity. However, employees still have the right to common-law remedies based on their employment contract. Considering the importance of collective agreements, negotiated disciplinary codes, certainty and consistency, and to avoid employers exercising unfettered power over employees, state organs should apply for a review of an unsatisfactory sanction by the disciplinary chairperson in terms of section 158(1)(h) of the LRA. Private employers could negotiate a disciplinary code which allows both the employer and employee to appeal against the decision of the disciplinary chair which should make provision that a more severe sanction can be imposed on appeal.
http://hdl.handle.net/10019.1/124100
Keywords: Arbitrage; Arbitragem; Arbitration; Commission for Conciliation; Dismissal of employees; Labor discipline; MARD; Mediación; Mediation; Mediação; Médiation; South Africa; South African Revenue Services

The treatment and recognition of company groups in South African corporate law - Diale-Ali, Regomoditswe Ursula (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

A critical appraisal of call centre contracts for insurance - Dladla, Mbongeni George (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Copyright as a constraint on creating technological value - Drążewski, Kasper (European University Institute, 2019)
How do we legislate for the unknown? This work tackles the question from the perspective of copyright, analysing the judicial practice emerging from case law on new uses of intellectual property resulting from technological change. Starting off by comparing results of actual innovation-related cases decided in jurisdictions with and without the fair use defence available, it delves deeper into the pathways of judicial reasoning and doctrinal debate arising in the two copyright realities, describing the dark sides of legal flexibility, the attempts to ‘bring order into chaos’ on one side and, on the other, the effort of judges actively looking for ways not to close the door on valuable innovation where inflexible legislation was about to become an impassable choke point. The analysis then moves away from the high-budget, large-scale innovation projects financed by the giants of the Internet era. Instead, building upon the findings of Yochai Benkler on the subject of networked creativity, it brings forth a type of innovation that brings together networked individuals, sharing and building upon each other’s results instead of competing, while often working for non-economic motivations. It is seemingly the same type of innovation, deeply rooted in the so-called ‘nerd culture’, that powered the early years of the 20th century digital revolution. As this culture was put on trial when Oracle famously sued Google for reuse of Java in the Android mobile operating system, the commentary emerging from the surrounding debate allowed to draw more general conclusions about what powers the digital evolution in a networked environment. Lastly, analysing the current trends in European cases, the analysis concludes by offering a rationale as to why a transformative use exception would allow courts to openly engage in the types of reasoning that seem to have become a necessity in cases on the fringes of copyright.
Accepted: 2019-01-14T15:17:37Z
Keywords: Copyright; Fair use (Copyright); Intellectual property

COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element - Drličková, Klára (Masaryk University Press, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna

The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

The challenge of three-dimensional printing : questioning established concepts in intellectual property law - Elam, Viola (European University Institute, 2019)
Over the last years, academics, practitioners and policy makers have focused their attention on an emerging technology: three-dimensional printing (“3DP”). 3DP is often portrayed as a game changer, showing the potential to disrupt established socioeconomic paradigms and exert profound implications in disparate areas of law. 3DP not only is well integrated in the manufacturing industry, but also increasingly adopted at consumer level. Recent developments have made it possible for ordinary people to take an active role in the production, customization and distribution of goods, and likewise paved the way for the proliferation of new market entrants, such as 3DP online platforms. Against this background, this thesis aims to shed some light on the implications that 3DP may have for Intellectual Property Law. In particular, this work attempts to predict and grasp the consequences that the digitization of real world things may carry in the area of IP law, both from the side of protection and infringement. This contribution is intended to create general awareness about the current state of the art and likewise delineate possible future scenarios in the 3DP ecosystem. The research question at the core of the analysis is whether the current legal framework of different IPRs already offers suitable means for regulating the thin dividing line between the digital and the analogue world, or rather needs to be amended, in order to cope with such a fascinating reality. To this end, the analysis contributes insights to the best legal treatment that CAD files shall receive, in case such files embed products protected by copyright, designs, patents and trademarks. Hence, it addresses right owners’ concern that the online transmission of CAD files, combined with the ease of converting such files into the final printout, will facilitate mass-scale and worldwide infringement of all IPRs.
Accepted: 2019-01-15T14:09:48Z
Keywords: 3D; Copyright; Intellectual property; Three-dimensional printing

A Critical Look at the Mechanism for Challenge of Arbitrators Under ICSID Convention and Arbitration Rules - Gautama, Ivan (Juris Gentium Law Review, 2019)
Administered arbitrations under ICSID are amongst the most-utilized means to resolve investor-state disputes. Part of why it is so is because the ICSID as an institution is heavily affiliated with the World Bank. This affiliation serves as a double-edged sword in ICSID’s hands: while on one side such affiliation lends ICSID the credibility any successful arbitral institutions need, on the other side ties between the two institutions are proving to become too close for comfort. This paper explores what could go and has gone wrong in the past within the current ICSID arbitration system with regards to the mechanism for challenging arbitrator(s), and whether such mechanism allows ICSID to effectively deliver what it is expected to provide.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Conflict of interest; ICSID; Investor-State; World Bank

The role of the Hague principles on choice of law in international commercial contracts in Japanese private international law - Geraghty, Brandon Brian (University of Johannesburg, 2019)
Please refer to full text to view abstract LL.M. (International Commercial Law)
Keywords: Conflict of laws; Contracts (International law); Japan

A comparative analysis of mergers and acquisitions in South Africa, Botswana and Kenya : how can we achieve successful integration in Africa? - Gumede, Nomfundo Pretty (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Acquisitions; Amalgamation; Bots; Business; Corporate mergers; Integration; Kenya; Mergers; South Africa

Voluntary membership: up to which point do cooperatives support liberalism? - Hiez, David (International Journal of Cooperative Law, 2019)

Women in private international law - Keyes, Mary E. (Research Handbook on Feminist Engagement with International Law, 2019)
There has been almost no consideration of the position of women in private international law. There is very little published research applying a feminist analysis to, or even considering the position of women in, private international law. This field gives almost no attention to the particular interests, positions and experiences of women as subjects of the law, or the contribution of women as makers of the law. In the common law, private international law was largely developed in the 19th century, by male judges who were strongly influenced by commentary written exclusively by men. This chapter establishes that the apparently gender-neutral nature of private international law conceals profoundly ingrained assumptions about gender, in which the masculine is represented as a rational and sophisticated businessman, and the feminine is represented as a legally incapable wife. It then considers the gendered dimension of private international law in international family law, referring in particular to the regulation of international child abduction, international family property agreements, and international commercial surrogacy. Each of these examples demonstrates the differential impact of the law on women, indicating the need for greater awareness of and attention to gender. It concludes that while there have been some advances recently, particularly in terms of increased representation of women in making and commenting on private international law, there remains a great need for further research into the position of women as legal subjects and law-makers in this field.
Keywords: Private International Law; Woman

Expanding access to justice: an exploration of large firm pro bono practice across Europe - Khadar, Lamin (European University Institute, 2019)
This PhD thesis explores pro bono practice among large, international law firms in Europe. The central question addressed by the thesis is: does “Big Law Pro Bono” contribute to access to justice in Europe? The thesis commences with a review of the literature which both contextualizes and situates the thesis. This review also identifies gaps in the existing literature particularly related to the globalization and localization of law firm pro bono and its practice beyond the United States (i.e. its practice in other parts of the world such as Europe, Asia, Africa and Latin America). After identifying issues with the current definition of access to justice, used throughout much of the existing literature, the thesis proposes a new definition which is then used throughout the thesis to evaluate pro bono practice in Europe. Towards this end, the thesis first provides historical context to law firm pro bono practice by exploring the history of pro bono, legal aid and other models of progressive lawyering across Europe. Following this, the thesis closely explores the process by which large firm pro bono practice arrived in Europe (i.e. globalization), the contemporary practice and the process by which it adapted to the European legal, social and political ecosystem (i.e. localization). Ultimately, it is suggested that large firm pro bono does not contribute to access to justice in Europe insofar as access to justice is defined narrowly - in the way that it has been conceived of in much of the existing literature. However, by embracing a broader definition of access to justice, it is possible to perceive the actual (and possible) social and political impact of large firm pro bono practice in Europe.
Accepted: 2019-05-28T07:38:42Z
Keywords: Justice; Legal assistance to the poor; Legal services

The contractual landscape and the protection of consumers in online auction contracts - Khan, Haleema (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Aquilian liability : the best remedy against delinquent company directors - Kharametsane, Godirilwe (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations

Online Dispute Resolution: Methods and Effects - Kumari, Poonam; Sood, Geetika (International Journal of Science and Research, 2019)
The concept of online dispute resolution came with the development of e-commerce. It is a branch which resolves the dispute between parties without interference of court. It includes arbitration mediation and negotiation. It also includes consumer to consumer disputes. With the emerging to globalisation the concept of online dispute resolution emerging day by day. The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. Thearticle is a study of ODR, online mediation and electronic arbitration. It includes their uses and their relationships with e-commerce. The paper is regarding primary aspects of online dispute resolution, its definition and its growth and development. It also includes the relationship between ODR and technology. Research paper isdiscussing the two forms of ODR: online mediation and electronic arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Online Dispute Resolution

Rationality and legality of non-market economy treatment in Antidumping law: novel perspectives on the changed legal environment - Long, Shao (Universität Wien, 2019)
AD Recht ermöglicht die Anwendung des Instruments nichtmarktwirtschaftlicher Behandlung (NME) zwecks Bestimmung des normalen Ausfuhrpreises von importierten Waren aus Ländern deren Märkte als weitgehen von Regierungen beeinflusst und deren Preise und Kosten für diese Berechnung als unverlässlich angesehen werden. Stattdessen sollten diese Berechnungen auf der Basis von Preisen in einem Vergleichsland mit funktionierender Marktwirtschaft ( „surrogate country‟ ) erfolgen. Die vorliegende Dissertation legt dar, dass die Anwendung der NME Behandlung zum Schutz gegen unfairen Importwettbewerb nicht auf rechtlich gesicherter Grundlage erfolgt, sondern als willkürlich eingeseztes protektionistisches Instrument gehandhabt wird. Besonders die Anwendung dieser Methode auf Chinesische Exporte nach 2016 ist rechtlich fragwürdig. Die Dissertation untersucht die Rechtmäßigkeit und Zweckmäßigkeit diese Methode, erstens durch die Analyse der wirtschaftlichen Begründung des AD Rechts und der geschichtlichen Entwicklung seit seinen protektionistisch motivierten Anfängen. Sie untersucht sowohl die relevanten Regeln und Praktiken aus der Zeit vor der Gründung der WTO als auch solche die danach zur Anwendung kamen und kommt zum Schluss, dass sie angesichts des grundlegend geänderten globalen rechtlichen Umfelds nicht mehr tragbar sind. Die Autorin empfiehlt daher, dass die auf NME Behandlung bezogenen Regeln und Praktiken vollständig aufgegeben werden und im Rahmen der gegenwärtigen Bemühungen um eine Modernisierung des gesamten WTO Regelwerks durch angemessene andere Regeln ersetzt werden sollten.
https://phaidra.univie.ac.at/detail/o:1354372
Keywords: Antidumpingrecht; Nichtmarktwirtschaftlichen Behandlung; Non-market economy

An analysis of reinstatement as a primary remedy for unfair dismissal of employees in South African Labour Law - Mampholo, Yvonne Mokhubane (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Intermediaries and advisors' duties to disclose onerous clauses to prospective policyholders - Matshitse, Collen Kgaolo Stephen (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Commercial law; Insurance law

The recovery of cultural property in international law: collaborative settlements of disputes - Mauro, Benedetta (LUISS Guido Carli, 2019)

Curbing transfer pricing manipulation in South Africa : lessons from selected jurisdictions - Mboweni, Abel Mabawuzeni (University of Pretoria, 2019)
Transfer pricing manipulation is a worldwide problem which results in a massive loss of revenue which is meant to finance government socio-economic programmes. South Africa is not immune to this problem. South Africa is losing billions of Rands in tax revenue due to this scourge. This research is an attempt to find ways and means which can be employed to combat or control the problem. In order to find the envisaged solutions, this research investigates the causes of the problem by analysing the weaknesses and the strong points of the arm’s length principle which is the basis of transfer pricing practice in South Africa and elsewhere. The research also investigates and analyses the corporate reasons for Multinational Enterprises (MNEs) to engage in transfer pricing with a view to demonstrating that transfer pricing is a neutral tax avoidance concept if it is applied for genuine business considerations. The investigation also entails analysing the legal framework of transfer pricing in South Africa which is embodied in section 31 of the Income Tax Act 58 of 1962. The research analyses the efficacy of section 31 in dealing with the sophisticated transfer pricing manipulation schemes. In addition, an extensive reference to the Organisation for Economic Co-operation and Development (OECD) Transfer Pricing Guidelines is made as South Africa relies heavily on the guidelines. A comparative analysis of selected topics is also conducted with the United States (US) and India with a view to drawing lessons from those jurisdictions. Based on the outcome of the analysis and the lessons drawn from the comparative analysis, findings are presented followed by legislative proposals or recommendations which will help to eradicate the problem. It is hoped that implementation of the recommendations taking into account the socio-economic conditions of South Africa will help to deal with the problem.
URI: https://repository.up.ac.za/handle/2263/69915
Keywords: Loss of revenue; South Africa; Tax Revenue; Transfert pricing

An investigation into the effectiveness of trade unions in advancing the cause of workers during strikes in the face of an emerging culture of violence and criminality - Mfusi, Pearl Dawn Arnold (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Labour protests; Liability; Strikes; Trade unions; Violent protests; Violent strikes; Workers

Towards development-centred trade relations: a study of South Africa and the USA trade relations with particular focus on the African Growth and Opportunity Act (AGOA) - Mkhwanazi, Nhlakanipho (University of KwaZulu-Natal, 2019)
With trade taking place continuously on a daily basis, its often-reported success gives the impression that all participants involved are to a certain extent somewhat successful too. This dissertation draws attention to the discrepancies that have often gone unnoticed throughout the decades and the effects that have arisen as a result. South Africa’s (SA) and the United States of America’s (US) trade relationship through the African Growth and Opportunity Act (AGOA) is the focus of this study, with this relationship being analysed from as far back as history has been recorded to the modern day. Least developed countries (LDCs) are an integral part of this study because most trade-related activities involve them, and they contain most of the world’s natural resources, but most importantly they also make up a large portion of the world’s population. It's baffling to see that where these factors are present, there's also inequality. Seemingly, there are efforts that deal specifically with the challenges faced by developing countries, but what is concerning is these solutions are formulated by developed countries which created them and continue to perpetuate them. The approach adopted was mostly that of contrasting events that have involved trade over the decades and a discussion of how these events have shaped international, political and trade relations, that is, the existing status quo. Examples include the two World Wars; oppressive regimes such as apartheid; and the formation of global institutions ranging from the International Trade Organization (ITO) to the General Agreement on Tariffs and Trade (GATT), and the World Trade Organization (WTO). The first three chapters contain an introduction, a background focus on development and the history of relations between South Africa and the United States of America. The last two chapters contain a discussion on AGOA as well as findings and recommendations that can be implemented to assist with this issue. What this dissertation was aiming to establish was the perpetual involvement of developed countries in the affairs of developing countries. This is illustrated through the renegotiation of the AGOA in 2015, where SA had to accept ultimatums set for it by the US. This dissertation further shows that such tactics are nothing new when the US is involved, as is evidenced by its involvement in major global events that have shaped the course of history. This approach is not only harmful but also stagnates development, as developing countries must adhere to agreements that sometimes are not to their benefit. The findings indicate a contradictory pattern: when solutions to challenges faced by developing countries are presented, they translate instead into a further stronghold over developing countries because of past atrocities such as colonisation and apartheid. What appears throughout the dissertation are the ever-present structures that are intended to perform functions supposed to be for the improved good of developing countries, but which result in those countries facing never-ending challenges, some of which are self-inflicted through alliances such as the AGOA with developed countries.
Keywords: AGOA; African Growth and Opportunity Act; Developing countries; Dumping; GATT; General Agreement on Tariffs and Trade; Trade relations; WTO; World Trade Organization

Sustainable tourism development in transfrontier conservation areas : a legal perspective - Mugadza, Amanda Tapiwa (North-West University, 2019)
Transfrontier conservation areas (TFCAs) originate from the idea of conservation across international boundaries. Within the SADC region, they are defined as areas or components of large ecological regions that straddle the boundaries of two or more countries, encompassing one or more protected areas, as well as multiple resource use areas. While the objectives of TFCAs are manifold, key among these are biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development. Within SADC, tourism is identified as a key driver of these objectives. To explore this further, the study embarks on a case study of the Great Limpopo Transfrontier Conservation Area (GLTFCA), the oldest and second largest TFCA in the region, involving South Africa, Mozambique and Zimbabwe. From the GLTFCA, it is established that challenges exist with the manner in which tourism development is undertaken. However, it is further established that these challenges do not necessarily stem from the tourism development itself but from the weaknesses in the governance structures of this TFCA. In particular, the exclusion of local communities as key governance actors in the GLTFCA is seen to be detrimental to conservation and perpetuates poverty. Superimposed on these weaknesses, the tourism development therefore fails to adequately promote biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development in the GLTFCA. To resolve these challenges, the study explores the concept of sustainable tourism development from a legal perspective guided by the question: what is the legal framework necessary, at domestic level – in TFCA participating countries to ensure that sustainable tourism development promotes the key SADC TFCA objectives? Through the aims or policy implications of sustainable tourism development, the study determines a legal framework comprising of the relevant TFCA governance actors as well as the governance-based tools that are necessary to promote the TFCA objectives. The domestic legal frameworks of the GLTFCA participating countries are measured against this legal framework to establish whether they promote sustainable toruism development. It is established that the domestic legal frameworks of South Africa, Mozambique and Zimbabwe, individually and as a whole, neither provide effectively for all relevant TFCA governance actors, especially local communities; nor for the tools that promote biodiversity conservation, the improvement of livelihoods-alleviation of poverty and economic development in the GLTFCA. Thus, the legal framework of the GLTFCA does not provide for sustainable tourism development as it should. For this reason, the study’s principal recommendation is the adoption, by all SADC TFCA participating countries, of a domestic legal framework for sustainable tourism development with specific elements which provides for the key TFCA governance actors as well as the relevant governance-based tools.
Keywords: Biodiversity conservation; Domestic legal framework; Economic Development; GLTFCA; Governance actors; Governance-based tools; Improvement of livelihoods; Sustainable tourism development; TFCAs; Tourism

Price reduction as a remedy for breach of contract by the seller under the CISG and English law - Mukuna, Nomator (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Interrogation proceedings in insolvency law: a comparative study - Mwelase, Musamuni Barrah (North-West University, 2019)
Interrogation proceedings in insolvency circumstances have always been a thorny issue in South Africa, even prior to the advent of the new constitutional democracy. After the adoption of the new Constitution in 1993, a number of court cases seeking adjudication on constitutional compliance came before our courts. The insolvency of both natural and juristic persons necessitates the employment of specified proceedings such as insolvency interrogations. The latter is done to enable an efficient and effective collection and collation of information that would assist in the administration, sequestration and winding-up of the affairs of the affected person. These proceedings are intended to benefit creditors of an insolvent (natural and juristic). The matters of Ferreira v Levin; Vryenhoek v Powell 1996 (1) SA 984 (CC) (1996) (1); Bernstein and Others v Bester 1996 (2) SA 751 (CC); Harksen v Lane 1998 (1) SA 300 (CC; De Lange v Smuts 1998 (1) SA 736 (C) are still leading cases in relation to the constitutionality of interrogations in insolvency circumstances. The Constitutional Court has on a number of occasions, declared the interrogation proceedings in insolvency matters constitutional, with minor amendments on a case-by-case basis. The effect of these judgements is that, in every case in which an insolvent debtor has to undergo an interrogation process, the presiding officer must ensure that compliance with the constitutional requirements are in place. The current position in which the sequestration of insolvent estates and the winding-up of insolvent companies are respectively regulated by two statutes, is a matter for concern. This situation has led to duplication and contradictions in the two statutes. Further, the absence of specialist tribunals or officers dedicated to the administration of insolvency related matters is a further hurdle to the effective and efficient finalisation of the affairs of insolvent estates or insolvent companies’ affairs. The matter of Leong comes to mind. In this case, the Master of the High Court issued a warrant of arrest for a witness who was subpoenaed to appear at the meeting of creditors in his insolvent estate. This was the case, despite the fact that Leong had previously submitted a medical certificate to the effect that he was unable to attend the meeting due to illness. This case is a clear indication of a lack of proper guidelines to deal with insolvency related matters - for non-judicial officers (such as the Master of the High Court). This incident took place in 2016, long after the decision in De Lange v Smuts 1998 (1) SA 736 (CC). Interrogation processes in insolvency circumstances in Namibia and Botswana are almost similar to South Africa’s processes. Divergent provisions in Namibia and Botswana exist, but not to a great extent. Like South Africa, the above-mentioned jurisdictions adopted a constitutional democracy long before South Africa. One would have expected that interrogation proceedings in insolvency circumstances would be in line with human rights. Further, as is the case in South Africa, insolvency of natural persons and of juristic persons are regulated by two separate statutes in these jurisdictions. This thesis investigates issues relating to the interrogation process in insolvency proceedings in the three SADC countries, namely South Africa, Namibia and Botswana. It compares the position to two foreign jurisdictions, namely England and Canada – as leading jurisdictions in human rights. Thereafter, suggestions on processes and methods of information gathering in line with human rights and in specialist tribunals will be made. In addition, recommendations for inclusion in a unified statute regulating insolvencies of both natural and juristic persons will be made. This will be done taking into consideration the economical and socio-political circumstances of South Africa and the SADC countries forming part of this thesis.
Keywords: Insolvency; Private enquiries; Public enquiries; Subpoena; Summons; UNCITRAL Model Law; World Bank

An appraisal of the provision of "benefits" as an unfair labour practice in South African labour law - Newaj, Kamalesh (University of Pretoria, 2019)
This thesis seeks to resolve the ambiguities surrounding the use of the unfair labour practice relating to the provision of “benefits” as a dispute resolution mechanism in South African labour law. This mechanism has been plagued with uncertainty, primar-ily because of the lack of a statutory definition of benefits. Evidently, the interpretation and application of benefits have been left to the courts, resulting in two diverse ap-proaches being endorsed. The first one sought to confer a narrow connotation on ben-efits, the rationale being to separate benefits from the definition of “remuneration”. It further sought to limit the use of this unfair labour practice to instances where the benefit claimed was exclusively provided for ex contractu or ex lege. The primary ob-jective was to protect the divide between disputes of right and disputes of interest, a distinction that is recognised and encouraged in our law. The second approach was one that fostered an expansive interpretation of the term, deeming it to be part of re-muneration. Needless to say it resulted in countless items being subject to determina-tion as benefit disputes. Furthermore, it extended benefits beyond those rooted in con-tract or legislation, including those granted or offered subject to the exercise of mana-gerial discretion. The supplementary challenges firstly relate to the absence of statutory direction on the standards of fairness to be applied in evaluating employer conduct. Secondly, the judiciary has provided opportunities for employees to utilise recourse other than the unfair labour practice provisions to address benefit disputes. Such leeway comes in the form of contractual recourse as well as the ability to institute strike action. In search of solutions to the problems identified above, the study explores and anal-yses the history of the unfair labour practice concept. Thereafter, an extensive exam-ination of the developments in this area of the law is undertaken. This includes a com-prehensive analysis of legislation, case law and academic writings. Having docu-mented and analysed the South African position both pre- and post-democracy, the study critically evaluates these sources of law. The study further involves a diagnostic assessment of international legal instruments and foreign law in order to extract best practices. The conclusions reached are, firstly, that an expansive interpretation of benefits is warranted. This is in line with a purposive interpretation of the LRA, which promotes the constitutional right to fair labour practices and international law. This study there-fore proposes a wide-ranging definition of the term benefits. Secondly, standards of substantive and procedural fairness have been found to be applicable in evaluating employer conduct. As such, fairness guidelines based on these standards have been developed. Thirdly, in respect of the alternate avenues available to resolve benefit disputes, it has been found that although there are strong indicators that point to a conclusion that contractual recourse has been supplanted by statutory recourse, such a finding cannot be definitively made. Furthermore, section 64(4) as it stands provides for the right to strike over unilateral changes to terms and conditions of employment, which includes unilateral changes to pre-existing benefits. However, the judiciary can limit the use of this section in benefit disputes by prioritising the substance of the dis-pute over its form. This thesis ultimately proposes the incorporation of a Code of Good Practice into the LRA. The Code of Good Practice: Benefits adopts the principal research findings of this study. It encourages the enforcement of benefit disputes through the dispute res-olution institutions set up by the LRA. The adoption of this Code (The Code of Good Practice: Benefits) will bring certitude to this field of labour law.
URI: https://repository.up.ac.za/handle/2263/72658
Keywords: Labour law; Labour practice; South Africa

The interruption of liquidation by business rescue application: a lacuna in the Companies Act - Ntingane, Neo Samantha (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The rights of illegal workers not to be unfairly dismissed, with emphasis on illegal immigrants and sex workers - Ntshalintshali, Phindile Ziningi Glenn (University of KwaZulu-Natal, 2019)
Illegal workers have been and continue to be the most vulnerable category of employees in the labour market, the reason for this is the invalidity of their employment contract due to illegality. For the longest time, the Labour Relations Act (hereinafter the LRA) has not been able to afford these workers protection because they did not fall within the ambit of the legal definition of ‘employee’ and the Act only recognises employees as holders of the rights provided for under the LRA. As a result of the Act not being able to protect these workers, they have become victims of exploitation and vicious abuse in the hands of their employers, making them vulnerable in their employment relationship. The law concerning illegal workers has since changed. Courts have found that these workers are in fact employees for the purposes of the LRA, and that, for an employment relationship to exist there need not be a valid employment contract in existence. An employment relationship may take various forms and the goal that the Labour Relations Act seeks to achieve is to protect those employees who find themselves vulnerable as a result of the illegality of their employment contract. It has also been argued that the law aims mostly at penalising the employer rather than the employee who is economically and socially weaker than the employer, therefore, courts have found that the Labour Relations Act should be interpreted in a manner that is consistent with the Constitution of the Republic of South Africa (hereinafter the Constitution) which requires a wider interpretation of who may be afforded the right to fair labour practices.
Keywords: Illegal workers; Immigrants; Sex Workers; Unfair dismissal

The rights and duties of parties to liability insurance contracts at claim stage - Ntuli, Bonginkosi (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Insurance claims; Insurance policies

Business rescue: a delay tactic for liquidation? - Nxumalo, Misiwe Mpilenhle (University of KwaZulu-Natal, 2019)
No abstract provided.
Keywords: Business rescue; Company creditors; Company law; Liquidation; Shareholders

The possible impact of the Hague Convention on the recognition and enforcement of foreign judgments in civil or commercial matters on private international law in common-law West Africa - Okorley, Solomon (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Article 6.8 and Annex II of the WTO agreement on antidumping - Persoz, Dimitri (European University Institute, 2019)
Article 6.8 of the Antidumping Agreement (AD) allows domestic investigating authorities to make determinations on the basis of the best information available (BIA) when any interested party does not cooperate during an antidumping investigation under the discipline of Annex II of the AD. Since its introduction, this provision has been the source of extensive and neverending litigation in front of both domestic investigating authorities and the Dispute Settlement Body. In this thesis, we research to what extent the findings of the Panels and the Appellate Body regarding Article 6.8 AD are consistent with the mandate set out in Articles 3.2, 11 DSU and 17.6 AD and to what extent they are reasonable from an economic perspective. To answer the first question, we first discuss Articles 3.2, 11 DSU and 17.6 AD to establish what is the mandate of the Panels and the Appellate Body under the Dispute Settlement Body. We then examine the findings of the Panels and the Appellate Body in the interpretation of the seven terms of Article 6.8 AD under the previously established mandate. To answer the second question, we summarize the latest developments in the economic theory of adjudication and litigation. We then discuss the findings of the Panels and the Appellate Body using this economic standard. In the conclusion, we compare the results of our analysis with current negotiations on Article 6.8 AD in the Doha Round framework and further discuss the opportunity to create a single united international investigating authority.
Accepted: 2019-07-10T10:52:46Z

The position of a director in South African Law : is it worth the risk - Raselo, Moeketsi Thebe (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Role of Alternative Dispute Resolution as a Mechanism for Administration of Justice - Renu, Shailja Chauhan (International Journal of Science and Research (IJSR), 2019)
Desire for quick and affordable justice is universal. Right to speedy trial is a right to life and personal liberty of every citizen guaranteed under Article 21 of the Constitution, which ensures just, fair and reasonable procedure. Alternative Dispute Resolution mechanisms have become more crucial for businesses operating in India as well as those doing businesses with Indian firms. There are various reasons for which ADR is preferred over the conventional way of resolving the disputes. India being a developing country, going through major economic reforms within the framework of the rule of law, for expeditious resolution of disputes and lessening the burden on the courts, alternative mechanisms for resolution (ADR) are the only alternative through arbitration, conciliation, mediation and negotiation.

Exemption clauses : contractual exclusion of delictual damages - Sande, Janet (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

Emerging Issues in Arbitration, Mediation and Conciliation - Sunil, Bhawna Bhelly (International Journal of Science and Research, 2019)
The resolution of disputes through alternative dispute resolution mechanisms has gained momentum over recent decades. It has increasingly occupied space in the academic literature as the “new” method to achieve “justice” for disputing parties. It is important to note that a variety of definitions of “justice” can be relied upon. However, in many cases, justice will mean the parties being able to resolve their dispute fairly, justly and amicably by applying law or legal principles. Traditional legal mechanisms for resolving disputes have been increasingly questioned as to whether they are actually capable of achieving justice in individual cases. Resolution in the courts is not only the method of resolving disputes . If the parties can resolve their own disputes then there will arise no need for court system in world. All though court system is good and fair way of dealing with civil disputes yet it might not be the best method to resolve the disputes. Basically there are four ways to of alternate dispute resolution. They are Negotiation, Mediation, Conciliation and Arbitration . The of ADR is to resolve the matters in a cost effective manner and foster long term relationship.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; MARD; Mediación; Mediation; Mediação; Médiation; Méthodes alternatives de règlement de conflit

An appraisal of the implementation of the retail distribution review's recommendations - Wilkins, Chanel (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Determining the proper law of an International Funds Transfer - Yeboah, Abena Takyiwa (University of Johannesburg, 2019)
There are many ways of making payments. One of the available options for parties to international commercial transactions is international funds transfers. These transfers occur across borders and so, raise conflict of law issues. There are some laws known internationally that regulate international funds transfers. These laws include the UNCITRAL Model Law on International Credit Transfers (no country has ratified it), article 4A of the Uniform Commercial Code and the Rome I Regulation. There are diverse ways in determining which law applies to an international funds transfer. This is done either by assessing the transaction as a single transfer or as a set of linked transactions. In African countries like Ghana and South Africa, there is a gap in the approach of the law in addressing the conflict of laws issues regarding international funds transfers. This dissertation addresses the gap in these legal regimes using the present private international law as a guide. Additionally, the present legislation and legal jurisprudence are analysed, and suggestions are given as to its improvement. This author also advocates for a legislation that adequately addresses the issues raised by transnational funds transfers in these countries. Conclusively, this will promote a predictable approach in determining the applicable law in transnational funds transfers.
Keywords: Fund transfer; Transfert de fonds; Transfert international

Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

The Implementation of Provisions of IFRS Framework and Financial Perfomance of Banks - Anichebe, Alphonsus Sunday; Okpala, Ngozi Eugenia (International Journal of Trend in Scientific Research and Development, 2018)
The need for global financial language gave birth to International Financial Reporting Standards (IFRS). The adoption of IFRS has been argues to have changed the manner in which the financial statements are prepared, presented and reported. IFRS represents a single set of high quality, globally accepted accounting standards that can enhance comparability of financial reporting across the globe. The significant disparities between the Nigerian Statement of Accounting Standards and International Financial Reporting Standards have resulted in the Statement of Accounting Standards being regarded as outdated and incomplete as an authoritative and internationally accepted guide to the preparation of financial statements. The study however examined the extent to which Nigerian banks have implemented the provisions of IFRS frameworks. The sample comprises of fourteen quoted deposit money banks in Nigeria. Specifically, financial statement figures of 2007 – 2011 (pre-adoption period) and 2012 – 2016 (post-adoption period) were utilized. The study adopted the ex-post facto research design. Annual panel data were collected from the financial statements and accounts of 14 deposit money banks quoted on the Nigerian Stock Exchange as well from the Securities and Exchange Commission statistical bulletin from 2007 to 2016. The findings revealed that the return on shareholders’ funds has improved since implementation of International Financial Reporting Standards (IFRS) on Nigerian banks. IFRS implementation has significant effect on the profitability of quoted banks in Nigeria. The implementation of International Financial Reporting Standards (IFRS) has significantly influenced banks’ earnings and it was concluded that IFRS has positive impact on equity and earnings of banks. It was recommended that government and regulatory authorities should organize more quality training to get bankers informed.
Keywords: Banks; Financial performance; IFRS

Contractual capacity and the conflict of laws in common-law jurisdictions (part 1) : the United Kingdom - Fredericks, Eesa A. (Obiter, 2018)
This series of two articles provides a comparative overview of the position in the common-law conflict of laws in respect of the contractual capacity of natural persons. The comparative study is undertaken in order to provide guidelines for the future development of South African private international law. Reference is primarily made to case law and the opinions of academic authors. The legal position in the law of the United Kingdom, as the mother jurisdiction in Europe, is investigated in part I. Although Scotland is a mixed civil/common-law jurisdiction, the situation in that part of the United Kingdom is also discussed. Part II will deal with the rules and principles of private international law in respect of contractual capacity in Australasia (Australia and New Zealand), North America (the common-law provinces of Canada and the United States of America), Asia (India, Malaysia and Singapore) and Africa (Ghana and Nigeria). Part II also contains a comprehensive summary of the legal position in the common-law countries, followed by ideas for the reform of South African private international law in this regard.

The regulation of non-standard employment in Southern Africa : the case of South Africa with reference to several other SADC countries - Mokofe, William Manga (University of South Africa, 2018)
This doctoral thesis deals with the regulation of non-standard employment in Southern Africa: the case of South Africa with reference to several other SADC countries. The growth and presence of non-standard employment since the 1970s has revealed an important concern in a number of countries, both at the global and national levels. The overall significance of non-standard employment has increased in recent decades in both developed and developing states, as its use has grown exponentially across economic sectors and employment. Non-standard employment is the opposite of the standard employment relationship, which is work that is full time and indefinite. Non-standard employment includes an unequal employment relationship between an employee and an employer. Some workers choose to work in non-standard employment, and the choice has positive results. Nonetheless, for the majority of workers, non-standard employment is associated with job insecurity, exploitation, and the absence of trade unions and collective bargaining. Non-standard employment can also create challenges for firms, the labour market and the economy, including society at large. Backing decent work for all entails a comprehensive understanding of non-standard employment and its ramifications. This study explores the regulation and protection of non-standard employment in Southern Africa with focus on South Africa. The study draws on international and regional labour standards, the South African Constitution of 1996, and the national experience to make policy recommendations that will ensure workers are protected, firms are sustainable and labour markets operate well. Social justice and the democratisation of the workplace cannot be achieved if workers in non-standard employment are excluded from the labour relations system.
Keywords: Collective bargaining; Labor laws and legislation; Non-standard employment; Part-time employment; South Africa; Standard employment; Temporary employment; Temporary workers; Vulnerable workers

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31341
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Business combinations and group of companies : perspectives from accounting, law and corporate finance - Coda, Stefano (Université Paris 1, 2018)
Dans le cadre général des regroupements d'entreprises et des groupes de sociétés, cette thèse porte sur des questions d'intérêt à la croisée de la comptabilité, du droit (notamment les dispositions légales et la réglementation comptable) et de la finance d'entreprise. En ce qui concerne la théorie comptable, le chapitre 2 étudie comment les chercheurs en économie d'entreprise ont compris les groupes d'entreprises, les comptes de groupe et le processus de leur préparation, en particulier par rapport aux juristes italiens. Ensuite, le chapitre 3 reconstruit le processus politique et législatif qui a engendré la naissance du concept de groupe de sociétés dans le corpus juridique italien.Concernant le droit et la politique comptable, une analyse comparative est effectuée au chapitre 4qui montre clairement l'évolution de la notion de contrôle et de son utilisation dans les comptes consolidés (comptes de groupe) et les regroupements d'entreprises (I) en droit européen, (II) selon les normes comptables internationales publiées par l'IASB (International Accounting Standards Board) et (III) par rapport aux principes comptables généralement admis aux États-Unis («USGAAP»). De plus, les chapitres 5 et 6 étudient les effets du lobbying sur les normes comptables concernant les états financiers consolidés et les regroupements d'entreprises publiés par l'IASB. Fait intéressant, les résultats concordent avec une forme de capture du normalisateur comptable international par une catégorie d'institutions financières. En effet, confrontées à un modèle de consolidation prétendument basé sur le contrôle, ces dernières ont plaidé en faveur d'une exception de consolidation fondée sur un modèle de propriété et documentée comme ayant été proposée par les sociétés d'audit américaines dans ce contexte au moins depuis 1995. Ce modèle s’avère avoir trouvé un terrain fertile au sein de l'IASB. En conséquence, d'autres catégories d'institutions financières,telles que les fonds d'investissement à long terme et ceux gérés par une famille tout en préférant un modèle de consolidation différent, ne sont plus autorisées à présenter des états financiers consolidés. En ce qui concerne la finance d’entreprise, le chapitre 7 analyse les implications de différentes décisions de financement dans un nouveau échantillon de fusions et acquisitions entre institutions financières (banques et assurances) consommées dans le monde entier au cours des deux dernières décennies. En particulier, il étudie (I) la relation entre la méthode de choix de paiement (si le prix est payé en cash, en actions ou une combinaison des deux) et le choix du mode de financement d'un regroupement d'entreprises (y compris les instruments hybrides) et (II) la réaction des investisseurs à l'annonce de la combinaison. En ce qui concerne ce dernier point, l'utilisation de deux tests non paramétriques permet de détecter une relation intéressante entre la réaction du marché à l'annonce et les différents modes attendus de financement de la transaction.
Keywords: Accountings standard setting; Comptabilité; Consolidation exemption; Egroupements d'entreprises; Finance d'entreprise; Finances; Financial institutions; Gestion d'entreprise; Groupes de sociétés; IASB; IFRS 10; IFRS 3; Mergers and acquisitions; Method of payment; Politics; Politique comptable; Sources of fundings; Économie d'entreprise

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Relations between quality of trademarks and cognitive and conative variables of consumers - Naumovski, Goce (Université de Strasbourg, 2018)
But de la recherche : déterminer la dépendance des caractéristiques des marques (perceptibilité visuelle, représentation graphique, le caractère distinctif, non-généricité etc.), sur les types généraux spécifiques de capacités intellectuelles et sur les caractéristiques conatives des consommateurs de la population générale, par application de nombreux tests. La recherche a été réalisée sur un échantillon de 206 sujets-consommateurs. Ils ont évalué la qualité des marques de commerce (déposées et refusées) pour différents types de produits et services (TM-1 test). Les sujets ont été testés avec 3 tests cognitifs et 6 tests conatifs. Méthodes quantitatives appliquées : paramètres élémentaires de la statistique descriptive ; corrélation ; analyse factorielle ; analyse de régression multivariée, analyse canonique des corrélations. Les résultats ont indiqué que les variables cognitives et conatives ont des relations statistiquement significatives avec les résultats de TM test (qualité des marques).
Keywords: Capacités cognitives; Caractéristiques conatives; Cognitive abilties; Comportement des consommateurs; Conative characteristics; Consommateur; Consumers; Intellectual property; Marques; Marques de commerce (droit international); Propriété intellectuelle (droit international); Trademarks

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.
Number: 3 https://irep.ntu.ac.uk/id/eprint/41477/

Trade Openness and Financial Development in Sub Saharan Africa: The Role of Institutional Quality - Abeka, Mac Junior (University of Cape Coast, 2018)
The financial development of many Sub-Saharan African countries over the years has not been able to match up with other regions like the Middle East and North Africa, East Asia and Pacific, and Europe and central Asia (IMF, 2016). Trade openness has been argued in several empirical literature as a factor that could spur up the level of financial development, although the high levels of trade openness in Sub-Saharan Africa is not contributing much to the desired levels of financial development in Sub-Saharan Africa. However, there is an indication in literature that trade openness will be more relevant to financial development of economies that have a strong institutional quality. Thus, by using system General Method of Moment estimation technique, this study examined how institutional quality moderates the relationship between trade openness and financial development of Sub-Saharan African economies. The study found that institutional quality enhances the effect of trade openness on financial development of Sub-Saharan African economies. It is therefore recommended that, Sub-Saharan African economies should put in measures to strength their institutional quality so that the high levels of trade openness will better enhance financial development. Specifically, trade openness can better enhance financial development by improving government effectiveness, reducing corruption, enhancing regulatory quality, abiding by the rule of law, and allowing voice and accountability. As an extra benefit, the improvements in institutional quality on their own too will yield positive impact on financial development.
http://ir.ucc.edu.gh/jspui/handle/123456789/4084

Effect of IFRS on Value Relevance of Accounting Information: Evidence from Quoted Manufacturing Firms in Nigeria - Ezejiofor, Raymond Asika (International Journal of Trend in Scientific Research and Development, 2018)
This study evaluated the extent to which value relevance of financial information in Nigerian manufacturing firms has improved after the implementation of International Financial Reporting Standards (IFRS). Specifically, the study intended to: Ascertain the extent the adoption of IFRS has significantly improved the book value per share of manufacturing companies in Nigeria; Determine the extent the adoption of IFRS has significantly improved the Earnings Per Share of manufacturing companies in Nigeria and Examine the extent the adoption of IFRS has significantly improved the cash flow of manufacturing companies in Nigeria. Ex-post facto research design was adopted for the study. A sample of 54 manufacturing companies was randomly selected from manufacturing companies quoted on the Nigerian Stock Exchange for the periods of 2008-2015. Data for the study were obtained from the annual reports and accounts of the sampled companies. Specifically, a modified price model for detecting value relevance of accounting data for two different periods was employed. Regression Analysis and Chow test statistical tools were used to analyze and validate the data with aid of SPSS version 20.0. The study found that the adoption of IFRS has improved the book value per share, market share price, Earnings Per Share and cash flow of manufacturing companies in Nigeria. The implication of findings is that the value relevance of accounting information of manufacturing companies is more sensitive during Post-IFRS era than the Pre-IFRS era. The findings also imply that the book value per share, market price, earnings and cash flow have become informative to equity investors in determining the value of firms following IFRS adoption. The study recommends among other things that the accounting information for book value per share should be communicated to the investing public; and such information should be of high quality to avoid negative consequences on the part of investors.
Keywords: Accounting information; Manufacturing company; Value relevance

Impact of Contractual Capacity of Minor - Godha, Atisha (International Journal of Trend in Scientific Research and Development, 2018)
A contract involves s a promise between two persons for the exchange of either good or services. A contract signifies the free consent of the parties to the contract to be bound by law. For a contract to be valid, it must have these basic elements: mutual assent, consideration, capacity, and legality. Mutual assent is characterized by offer and acceptance through mutual accent; "consideration," on the other hand denotes any form of compensation with something of value for the goods or services traded. A contract between persons, either natural persons or legal persons, who have no capacity to contract can either be voidable or void depending on the case. Legality gives the condition that should be satisfied for a contract to be excised by the law. Illegal contracts are for example those involving illegal activities. For example one can't bring a plea of damages to a court of law for breach of a contract entered into to kill another person.The possible remedies for breach of contract are; general damages, consequential damages, reliance damages, and specific performance. This paper will examine the capacity to contract as pertains to contracts entered by minors minor's.
Keywords: Capacity; Consideration; Contract; Legality; Minor; Mutual accent void/voidable

Aspects of the regulation of cross-border insolvency in South Africa - Chitimira, Howard (Obiter, 2018)
This article analyses the regulation of cross-border insolvency under the Cross-Border Insolvency Act 42 of 20001 in order to examine the adequacy of such regulation as regards to the enforcement of insolvency proceedings in South Africa and other relevant jurisdictions. To this end, the paper provides an overview analysis of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act. Moreover, where possible, the paper also provides a comparative analysis of selected aspects of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act and those that are provided under the Insolvency Act 24 of 1936 and other related international instruments. This is done to expose the challenges and future prospects of the regulatory and enforcement framework under the Cross-Border Insolvency Act in South Africa.
Keywords: Insolvency; Regulation; South Africa

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
http://www.journalijar.com/
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

International Arbitration Practices in Nigeria: A Construction Industry Appraisal - Ewa, O. O.; Haytham, B.; Okon, E. E.; Enang, O. P.; Emiri, D. A. (World Journal of Innovative Research, 2018)
This paper aims to investigate Corporate Alternative Conflict Management and Dispute Resolution compliance through an appraisal of International Arbitration practices in Project-based Organizations in the Nigerian Construction Industry. In this study, simple percentages and frequencies of occurrence were used to analyse data derived through subject matter interviews and a questionnaire survey. Using the Survey Monkey tool, 85 questionnaires were distributed to key players in the AEC (Architecture-Engineering-Construction) Industry including Engineers, Project Managers, Architects and Quantity Surveyors and 53 were returned complete. The survey indicated that 66% preferred a more private Construction Arbitration to a public Litigation as a preferred method of dispute resolution, with 65% agreeing that a lack of proper project funding hinders the arbitration process in the Nigerian Construction Industry. 66% agree that Arbitration Time contributes more to project delays while 32% believe that Cost of the arbitration process is the greater source of project delays. We recommend that issues of confidentiality be carefully managed in dealing with outside counsels, while Project-based Organisations in Nigeria should ensure to develop master plans compatible with long-term strategies, including setting aside adequate funding for the timely resolution of project disputes through the implementation of only Arbitration-friendly contracts. This paper contributes to knowledge by bringing to bear the current compliance levels of project-based organisations in the practice of Arbitration in the Nigerian Construction Industry.
https://www.neliti.com/publications/262476/

A comparative study of the effects of liquidation or business rescue proceedings on the rights of the employees of a company - Joubert, Engela Petronella (University of South Africa, 2018)
Whenever legal disciplines overlap interesting scenarios occur and differences in opinions create intellectual tension. One such interesting scenario occurs when employees’ rights are affected during a company’s liquidation or business rescue. The employees of a company are normally the last persons to find out that a company is struggling financially. They are also the only stakeholders who are in no position to negotiate their risk should the company be liquidated. It is therefore necessary to evaluate the rights given to employees during a company’s liquidation and business rescue. The fundamental ideologies of company law, insolvency law and labour law are challenged and examined to attempt a harmonizing result that respects the core of each discipline. It is crucial to determine whether an appropriate balance is struck between the interests of all the stakeholders of the company during these procedures. The aim of this thesis is to evaluate whether South Africa manages to strike this balance. If employee rights are protected whilst a company is restructured back to solvency and success, this balance will be struck. An evaluation will also be made whether employees are always better protected during business rescue than in liquidation. The study analyses employee rights in a company’s liquidation and during a company’s restructuring process. The comparative study of employee rights in liquidation and rescue is done with the jurisdictions of Australia and England – countries with similar procedures. Important conclusions show that South Africa protects employee rights during business rescue procedures the best. An appropriate balance is indeed struck between the interests of all stakeholders of a company during business rescue procedures and employees are most of the time better off after a restructuring than in a liquidation. Should the recommendations for law reform be implemented in our legislation, South Africa will overcome the few obstacles currently in its way to be seen as a world leader where employee rights are concerned in liquidation proceedings as well as business rescue.
Keywords: Australia; Bankruptcy; Business rescue; Corporate reorganizations; Employee rights; Employment contract; Great Britain; Liquidation; Ranking of claims; South Africa

Combating corruption in public procurement in developing countries : a legal analysis - Mugadza, W. T. (North-West University, 2018)
This study was motivated by the quest to find new innovative and practical ways of combating public procurement corruption in developing countries to complement the existing measures. This was achieved by comparing three jurisdictions, Hong Kong-China, Botswana and South Africa. The focus was on how each jurisdiction uses the following four measures to curb public procurement corruption: criminal measures; administrative measures; institutional measures and civil activism measures. It was established that Hong Kong uses what this study has classified as the traditional approach of combating public procurement corruption. The traditional approach is characterised by the use of a separate procurement legal framework and a separate corruption legal framework to curb public procurement corruption. Its strengths are in the strict enforcement of criminal measures that are anchored on a robust legal framework, a clear anti-corruption strategy, an independent anti-corruption agency (institutional measure), effective internal oversight and a strong political will. However, the following weaknesses of the traditional approach were identified: over reliance on criminal measures; excessive dependence on one enforcement institution; it neglects the development of administrative measures and has weak civil activism measures. It was established that Botswana uses what this study has classified as the classical approach of combating public procurement corruption. The classical approach is characterised by a procurement legal framework that incorporates very minimum anti-corruption provisions. The anti-corruption provisions in the procurement legislation are enforced by an external institution (the DCEC in the case of Botswana) which relies heavily on the criminal measures. Its strengths are the following: a strong legal framework which provides for a clear anti-corruption strategy; it has anti-corruption units in each Ministry and it has a dedicated Corruption Court. However, the classical approach has the following weaknesses: the anti-corruption agency is not adequately independent as it under the control of the executive (the President in the case of Botswana); lacks effective internal oversight mechanisms; weak political will; neglects the development of administrative measures and civil activism measures are almost non-existent save for the media. It was established that South Africa uses what this study has classified as the traditional cum silo approach of combating public procurement corruption. The traditional cum approach is characterised by multiple procurement legislation which has certain but minimum anti-corruption provisions and a separate corruption legal framework. Multiple anti-corruption agencies are prone to political interference which renders them ineffective and unfit for purpose. Its strength is in the promotion and protection of civil activism measures (right to access information, right to freedom of speech and legal protection of whistle-blowers). Notable weaknesses of the traditional cum silo approach are: the poor enforcement of criminal measures; there is no lead anti-corruption agency that spearheads and coordinates all cases of public procurement corruption; there is no clear anti-corruption strategy; the administrative measures such as debarment are poorly enforced; it has multiple anti-corruption institutions that lack focus and professionalism which results in political manipulation. The thesis concluded by suggesting a new approach, the contemporary approach to combating public procurement corruption which entails the enactment of a single procurement legislation (model law) the Public Procurement and Combating of Public Procurement Corruption Act (hereafter PPCPPC). The contemporary approach advocates for the regulation of public procurement and the combating of public procurement corruption in one legislation. This legislation (PPCPPC) takes into account, the current demands for public procurement as well as future developments of public procurement. These include but are not limited to self-cleaning, cyber-crime and public procurement corruption as well as the role of foreign convictions for debarment purposes. The envisaged PPCPPC will in addition to regulating public procurement, encompass the best criminal measures, administrative measures, institutional measures and civil activism measures. In addition, the contemporary approach through the PPCPPC proposes two new innovations: the corruption clearance certificate and a mandatory anti-corruption clause in all government contracts.
Keywords: Accountability; Administrative measures; Anti-corruption clause; Botswana; Civil activism measures; Classical approach; Combating corruption; Competitiveness; Contemporary approach; Corruption clearance; Criminal measures; Debarment; Equality; Fairness; Hong Kong; Institutional measures; Integrity; Procurement principles; Public procurement; South Africa; Traditional approach; Transparency; Value for money

Who is in? Who is out? How the Uncitral Transparency Rules Can Influence the Upcoming Amendments of the ICSID Arbitration Rules - Yu, Hong-Lin (Contemporary Asia Arbitration Journal, 2018)
The International Center for Settlement of Investment Disputes (hereinafter "ICSID") has started its fourth amendment of its Arbitration Rules since 2016. The issue of transparency has been highlighted as a delicate issue in ICSID ongoing current amendment. It is also listed in the topics that have been identified for potential amendment. This article analyses how the issues of access to hearings and confidentiality over information arising from arbitration is treated under the current framework. A comparison is made against the Transparency Rules. The analysis is also made against the comments received from the public whose views are analysed as a possible direction the amendment may take.

L’arbitrage international dans l'OHADA : évolution vers l’arbitrage des investissements en Afrique - Dalil, Mustapha (Journal of Strategic Affairs, 2018)
En vertu des dispositions de l’article 53 Al. 1 du Traité de création de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires) : « Le présent traité est, dès son entrée en vigueur, ouvert à l’adhésion de tout Etat membre de l’Union Africaine et non signataire du traité. Il est également ouvert à l’adhésion de tout autre Etat non membre de l’Union Africaine invité à y adhérer du commun accord de tous les Etats Parties ». Cette action d’harmonisation du droit des affaires, tout en s’inspirant d’autres législations telles que le droit français et la common law, les Etats-membres de l’OHADA ont à leur disposition un arsenal législatif efficace et approprié à leur développement économique communautaire. Ce droit revêt un intérêt particulier pour les entreprises marocaines actives dans l’espace OHADA. Le Maroc, par le renouvellement de son adhésion à l’Union Africaine (UA) et en procédant à une demande d’adhésion à la Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) dont le but est de « promouvoir la coopération et l’intégration dans la perspective d’une Union économique de l’Afrique de l’Ouest », (le Maroc) a réaffirmé sa détermination d’intégrer les espaces économiques africains de référence
Keywords: Arbitrage international; Droit des affaires; Développement économique; Relations internationales; Union africaine; الاتحاد الإفريقي; التحكيم الدولي; التنمية الاقتصادية; العلاقات الدولية; قانون الأعمال

The realisation of rights in terms of the Consumer Protection Act 68 of 2008 - Scott, Tshepiso (University of South Africa, 2018)
The thesis examines the enforcement of consumer rights in South Africa, and is set against the backdrop of the underlying principles and theories on the enforcement of consumer protection law. It then analyses the various forms of consumer protection law enforcement mechanisms that were in place prior to the implementation of the Consumer Protection Act 68 of 2008, and sets out why there was a need for the enactment of the Consumer Protection Act. The thesis then critically discusses the consumer protection law enforcement mechanisms introduced and/or catered for by the Consumer Protection Act. The in-depth comparative analysis against the consumer protection law enforcement dispensations in both India and the United Kingdom culminates in a critical analysis of the successes and shortcomings of consumer protection law enforcement regime in present-day South Africa; as well as recommendations (in the form of legislative amendments and practical solutions) on how the South African consumer protection enforcement framework can be improved in order to facilitate the realisation of consumer rights.
Keywords: Consumer protection; Consumer rights; Enforcement mechanisms

Internet regulation and development: the battle over the network neutrality - Melo, Lílian Manoela Monteiro Cintra de (Universidade de São Paulo, 2018)
We have arrived at crossroads in the debates about the future of the internet governance. It is high time to address the reasons why policy choices have not been sufficient to preserve the internet\'s promise to bring about development, democratic engagement, and social justice. The network neutrality is central to this debate since it intersects all internet layers and is related to most contemporary issues that will shape future of the internet. My assumption is that network neutrality\'s failures are not an unintended consequence of the regulatory system, but part of the problem. My core hypothesis is that network neutrality\'s limits mainly occur because of, first, its inability to secure all envisioned goals and, second, its decontextualized focus on innovation on the last mile of the internet distributional chain. The network neutrality debate has produced a wide variety of work embedded within economic and legal studies regarding what would be necessary to guarantee a free and innovative internet. Although this work has been often disguised under the mask of technique, it is widespread influenced by the evolutionary economics and denies the network neutrality's effects on ongoing struggles for social and economic justice. My proposition is that network neutrality debate has failed because it proved unable to address the problems related to concentrated power structures on the internet and increasing inequalities. To achieve this objective, this dissertation investigates the network neutrality debate over the last decades to identify processes and mechanisms by which its sterile arrangements came to take specific form in time and place, focusing on what such arrangements might inform about contemporary policy efforts. In Chapter 1, prevalent internet governance myths are deconstructed, presenting how specific architecture design and the corresponding network neutrality outcomes came to prevail in particular periods. Drawing upon and integration of distinct source materials, Chapters 2 and 3 identify the specific contingencies over the past decades by which a dynamic set of evolving actors, events, and institutions converged (or not) and gave rise to current network neutrality rules and dissent in the United States and Brazil. At the center of the analysis is the identification of structures and power struggles. Finally, Chapter 4 aims at presenting a new framework towards the network neutrality debate and its potential distributive effects in the global economy, taking technology not as deterministic but embedded and being embedded in all the building blocks of what we term the social.
Keywords: Economic power; ICT; Inequality; Innovation; Internet access; Internet governance; Law and development; Network neutrality; S&TS; Structure

Contract, Conflict and Cooperation: A Critical Analysis of the Common Law Approach to the Breakdown of Modern, Complex, Symbiotic Contracts - Soper, Charles Haward (University of Leicester, 2018)
The springboard of a real-world, doctrinal, and theoretical investigation of the role played by cooperation in complex modern contracts allows me to articulate and justify a deep and concrete Transcendent Duty to Cooperate (TDTC) for these contracts. The source of the TDTC is the express words and/or the background of such contracts, the commercial expectations of the parties; which reveal that successful performance re-quires cooperation. The inevitable inference from this is that parties implicitly agree to cooperate. As the duty is implicit, it follows, I argue, that there are no gaps to be filled; merely meaning to be unearthed from the words and/or the background (construction). In doctrinal work, I review cases in categories (prevention, facilitation, defect-rectification, communication, decision-making, and active cooperation), showing that the law is far from coherent but also far from incoherent. Shifting from judicial policy making and gap-filling to context/purpose based contract construction, using evidence, is possible and would provide coherence. I create a clear and enforceable definition of cooperation through analysing the opinions of around five-hundred commercial experts and synthesising those with doctrine and theory. My empirical work analyses experts’ views; collected by interview, an online survey and workshops, using vignettes developed from adjudicated/real-life cases including opinion on what cooperation is and how it is achieved. The findings of my survey are compared with others. At an abstract level, it aligns with comparable surveys and at a detailed level, it is unique. In theoretical work, I show that basing the TDTC on construction is superior and more efficient, brings coherence to the law and that it is underpinned by shared, normative, “community” values. I test the TDTC against various “hard” cases, analysing remedial issues, showing that it would not decrease certainty in English Commercial Law, and is defensible by an appeal for coherence.

OHADA and the Making of Transnational Commercial Law in Africa - Bashi Rudahindwa, Jonathan (Law and Development Review, 2018)
The Organisation for Harmonisation of Business Law in Africa (OHADA) was established in October 1993 with the ambitious aim of inciting economic development in its Member States. Through the adoption of Uniform Commercial Laws, the organisation is expected to create an enabling environment for business development, thereby providing for a path to economic growth and subsequent development. In light of this professed aim, both the transnational methodological approach and comparative law theories are used in this paper to critically analyse the various processes conducted under the OHADA banner and to engage in discussions on the highly debated role of law as a vehicle for development in sub-Saharan Africa. This exercise, which proves crucial in order to trace its origin within the global governance and law and development theories, allows us to present OHADA as a transnational legal system, while also highlighting both its strengths and limitations.
Keywords: Law and development; Law reform; Legislative unification; OHADA; Transnational law

Enabling intellectual property and innovation systems for South Africa's development and competitiveness - Sibanda, McLean (University of South Africa, 2018)
During the last two decades, there have been a number of policy and legislative changes in respect of South Africa’s intellectual property (IP) and the national system of innovation (NSI). In 2012, a Ministerial Review of the Science, Technology and Innovation (STI) landscape in South Africa made recommendations to improve the STI landscape and effectively the national system of innovation. The study provides a critical review of drafts of the national IP policy published in 2013 as well as the IP Framework released in 2016 for public comment. The review of the IP and the NSI are within the context of the National Development Plan (NDP), which outlines South Africa’s desired developmental goals. South Africa is part of the BRICS group of countries (Brazil, Russia, India, China and South Africa). The South African economy is characterised by a desire to move away from being dependent on resources and commodities, to becoming a more knowledge based and innovation driven economy. It is hoped that such a move would assist the country to address some of the social and economic development challenges facing South Africa, as captured in the NDP. South Africa has a functioning IP system, but its relationship with South Africa’s development trajectory is not established. More particularly, the extent to which the IP system relates to the innovation system and how these two systems must be aligned to enable South Africa to transition successfully from a country based on the production of primary resources and associated commodity-based industries to a viable knowledge-based economy is unclear. The Trade-related Aspects of Intellectual Property Rights (TRIPS Agreement) of the World Trade Organisation (WTO) provides that IP must contribute to innovation and to transfer of technology and knowledge in a manner that is conducive to social and economic welfare. Certain provisions set out the foundations of intellectual property systems within the context of each member state. This study has thus explored the complex, complementary and sometimes contested relationships between IP and innovation, with particular emphasis on the potential of an intellectual property system to stimulate innovation and foster social and economic development. The study has also analysed the interconnectivity of IP and innovation with other WTO legal instruments, taking into account South Africa’s positioning within the globalised economy and in particular the BRICS group of countries. The research involved a critical review of South Africa’s IP and innovation policies, as well as relevant legislation, instruments, infrastructure, IP and innovation landscape, and relationship with international WTO legal instruments, in addition to its performance, given the developmental priorities and the globalised economy. The research documents patenting trends by South Africans using European Patent Office (EPO), Patent Cooperation Treaty (PCT), United States Patents and Trademarks Office (USPTO) databases over the period 1996-2015. A comparative analysis of patenting trends amongst BRICS group of countries has also been documented. The study also documents new findings, observations and insights regarding South Africa’s IP and innovation systems. Some of these, particularly in relation to higher education and research institutions, are directly attributable to the Intellectual Property Rights from Publicly Financed Research and Development Act. More particularly, the public institutions are becoming relevant players in the NSI and are responsible for growth of certain technology clusters, in particular, biotechnology. At the same time, the study makes findings of a decline of private sector participation in patenting as well as R&D investment over the 20-year period. Recommendations are included regarding specific interventions to ensure coherence between the IP and innovation systems. Such coherence and alignment should strengthen the systems’ ability to stimulate innovation and foster inclusive development and competitiveness, which are relevant for addressing South Africa’s socio-economic development priorities.
Keywords: BRICS; Biopharmaceutical; Biotechnology; Commercialisation; Economic development; Flexibilities; Inclusive growth; Innovation; Intellectual property; Licensing; Patents; Start-ups; TRIPs Agreement

60 Years of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958: Are We There Yet in Sub-Saharan Africa? - Okubote, Abayomi (Social Science Research Network, 2018)
Sub-Saharan Africa has, in recent years, been classified as a natural-resource play for foreign investors. These investment potentials have made the region one of the most attractive investment destinations in the world. The region is also diverse, with a mix of different legal systems and legal traditions. While investors are constantly seeking to understand the different legal regimes, international arbitration offers comfort by providing a framework for the enforcement of rights in a neutral forum and on a different platform. According to the World Bank, the ability to enforce an arbitral award is an important factor for investors considering potential markets in which to invest.Given the sixtieth anniversary celebration of the New York Convention (NY Convention), this article examines the enforcement regimes for arbitral awards in sub-Saharan Africa. It considers the momentous developments in the enforcement regimes in the region, due to the implementation of the NY Convention. It examines the proposed amendments to the enforcement provisions in the Nigerian Arbitration Act (Repeal and Re-enactment) Bill 2017, recently passed by the Nigerian Senate. It also examines the important provisions in the revised Uniform Act on the Law of Arbitration and the revised Rules of Arbitration of the Common Court of Justice and Arbitration – both recently adopted by the OHADA Council of Ministers. It attempts a comparison between the enforcement regimes in the OHADA Member States, the NY Convention Member States, and in countries that do not belong to any of the two regimes.A chart of the legal regimes on enforcement of foreign arbitral awards in sub-Saharan Africa is attached as appendix.
Keywords: ACA; Annulment; Arbitral Awards; CCJA; Commercial Arbitration; Convention; Enforcement; Enforcement of Arbitral Awards; Foreign Awards; ICSID Convention; Judiciary; New York Convention; OHADA; Reciprocity; Reservations; Sub-Saharan Africa; Treaty; UAA; UNICTRAL Model law

A critical analysis of the removal of directors by the board of directors and the judiciary under the Companies Act 71 of 2008 - Cassim, Rehana (University of South Africa, 2018)
Section 71(3) of the Companies Act 71 of 2008 has introduced into South African company law a provision which for the first time permits the board of directors to remove another director from office in certain specific instances. A further significant innovation in the Companies Act 71 of 2008 is contained in section 162, which empowers a court to make an order declaring a director delinquent or placing him under probation in specific instances. The effect of section 162 is that a court is empowered to remove a director from the board of directors. The focus of this thesis is the removal of directors from office by the board of directors and by the judiciary. The thesis explores the underpinning philosophy of the statutory provisions relating to the removal of directors from office. It also examines the impact of the power given to the board of directors and to the courts to remove a director from office. The grounds and the procedures for the removal of directors by the board of directors and the judiciary are examined. The fiduciary duties applicable to directors in removing a director from the board of directors are also explored. In addition, this thesis examines the removal of directors holding multiple positions or capacities in relation to a company, such as an employee or a shareholder with loaded voting rights. The remedies which may be relied on by a director who has been removed from office by the board of directors are examined. Recommendations are made to strengthen and improve the provisions in the Companies Act 71 of 2008 relating to the removal of directors from office by the board of directors and the judiciary. Amendments to the Companies Act 71 of 2008 are suggested to remove ambiguities; to guard against the abuse of sections 71(3) and 162; to improve the grounds and procedures for the removal of directors by the board of directors and the judiciary, and to enhance the remedies that may be relied on by a director who has been removed from office by the board of directors.
Keywords: Corporate governance; Directors and shareholders power; Directors of corporations; Fiduciary duties; Investor relations; Removal of directors from office; Stockholders' voting; Voting rights

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

Application of the OHADA Accounting System by Companies in DRC, Current Status and Prospects: Case of the City of Bukavu - Kulondwa, Safari; Nshobole Bahirwe, Nathalie (Journal of Accounting, Finance and Auditing Studies, 2018)
The objective of this research was to determine the current status of the application of the OHADA accounting system in DRC, five years after its adoption. A survey was conducted on thirty small and medium-sized enterprises in Bukavu to determine the level of compliance with the SYSCOHADA principles, the degree of harmonization of accounting practices and the difficulties related to the application of this system. The results shown consistently that compliance with Syscohada principles is not absolute, the level of Harmonization is still low and finally companies in DRC still need time to fit into the OHADA accounting system.
Keywords: Accounting Practices; Accounting Principles; Harmonization

Cross border merger and shareholder's rights - Severino, Francesco (LUISS Guido Carli, 2018)
Historical context. Scope of application of cross border merger. A comparison of class rights with minority protection in cross border merger. The transposition of the cross border merger in the German law for an implementation.

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
URI: http://hdl.handle.net/10019.1/103466
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

The integration of work and parenting: a comparative legal analysis - Rossouw, Elzaan (Stellenbosch University, 2018)
Given the importance of parental care to children, parents and broader society and the apparent conflict between work and adequate parental care, this study evaluates the legal facilitation of the integration of work and care across nine countries, including South Africa. The study recognises that legal operationalisation of the integration of work and care primarily takes place at domestic legislative level and shows that this happens against the backdrop of widespread recognition of the importance of the family and care at the international, regional and constitutional levels. The study builds on the reality that domestic legislation in this context consists of (a combination of) equality law and specific rights contained in employment standards legislation. The comparative review of equality law as applied in the area of the work-care conflict shows that, despite the potential and promise that equality law holds to facilitate the integration of work and care, this potential has not been realised and probably will not be in future. This necessarily shifts the focus to an approach founded on the extension of specific rights related to time off or leave, as well as flexible working, to employees in order to enable them effectively to combine work and caregiving. The comparative review of specific rights in this area leads to the conclusion that South Africa lags far behind certain developed and comparable developing countries in its legislative recognition of the importance of caregiving and in its subsequent level of employment rights extended to caregivers. Given the ample room for improvement, suggestions for legislative reform are made based on the comparative experience of other countries
URI: http://hdl.handle.net/10019.1/103776
Keywords: Child care services; Comparative law; Employee rights; Employment standards; Equity; Labour law; Labour legislation

Does the 1980 Vienna Sales Convention Reflect Universal Values? The Use of the CISG as a Model for Law Reform and Regional Specificities - Schroeter, Ulrich (Loyola of Los Angeles International and Comparative Law Review, 2018)

African Trade Growth or Trade Deficit: GATT/WTO Rules as Trojan Horse on African Trade Development - Obida, Idibia Daniel (World Journal of Research and Review, 2018)
The principle of Most Favored Nation (MFN) as a GATT rule as annexed to World Trade Organisation (WTO) is viewed as very crucial in the operations of the WTO amongst member countries. Another rule of striking importance is the standard of non-discrimination inserted in the MFN rules. As against the background, this study addresses the routine conviction with respect to the viability of GATT laws and WTO rules in the light of non-discrimination principle and Multifibre Agreement (MFA) and, The National Treatment Principle. The study explores the standards of these rules which are whittled down with concrete exemption clauses. These clauses make the adequacy of unhindered commerce guideline perplexed amongst member nations especially, the Sub-Saharan Africa. The study finds that rules of GATT having been made since 1947 at the time when Africa‟s economic development was annexed to their colonial masters and therefore, not in contemplation by the progenitors. The realization that Africa ought to be given chance to develop come too late within the GATT rules. The study finds that the current GATT structure cannot advance the promotion of African trade. The study addresses the grouping of African nations with other nations like Asia, India and South America as a misnomer and erroneous as Africa is the least developed in terms of international trade bargaining power among other developing countries. The study after analyzing MFN, MFA, National Treatment principle and Transparency rules of GATT, concludes they are development deficit as against trade promotion. The study further concludes that the difficulties in finding an acceptable definition of the „like product‟ by several Dispute Resolution Panels as laid down by GATT makes nonsense of the rule and a lacuna in the definition of Article III (2) and III (4) as they are components of paralysis of non-clarifications.
Keywords: GATT; General Agreement on Tariffs and Trade; Most Favoured Nations; Multifibre Agreement; WTO; World Trade Organization

The Impact of Private Securities Lawsuits on Accounting Conservatism and the Moderating Influence of Corporate Governance - Kerr, Ryan (Victoria University of Wellington, 2018)
This study investigates the impact of conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit, on the level of accounting conservatism in financial reporting. This study also investigates the moderating influence of corporate governance on the level of accounting conservatism following conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit. The study uses a sample of 617 privately enforced disclosure-related securities lawsuits against listed US firms, taken under SEC rule 10b-5 of the 1934 Securities Exchange Act, over the period 2002 to 2010. The results of the study indicate that following both the conduct that gives rise to a securities lawsuit, and the filing of a securities lawsuit, firms adopt higher levels of accounting conservatism. However, the study finds no evidence that corporate governance moderates the impact of securities lawsuits on the level of accounting conservatism.
Keywords: Accounting Conservatism; Governance; Securities Lawsuits

An evaluation of market responses to corporate disclosures in a continuous disclosure environment - Li, Hanqiao (Victoria University of Wellington, 2018)
Corporate disclosure has attracted the attention of researchers from the accounting and capital markets. Researchers have been trying to better understand how capital markets respond to corporate disclosures. This study explores the short- and the long- term market effects of corporate disclosures in a continuous disclosure environment. This study aims to find the answers to the following research questions. (1) How market (price/volume) sensitive is the information contained in each disclosure category in a continuous disclosure environment? (2) How quickly is the value-relevant information incorporated into share prices before the annual earnings announcement is released, and how can company announcements promote this timeliness of price discovery? Specifically, this study examines the extent to which the Australian share market reacts to new public information immediately after the information is released, and the impacts of announcement frequency as to different continuous disclosure categories on the timeliness of price discovery (also known as the speed of price discovery). Prior research has mostly concentrated on a single type of information event to examine the information’s market consequences by monthly, weekly or daily data. Instead, by covering all public announcements and using tick (transaction) data to calculate intraday abnormal returns and abnormal trading volumes, this study examines which type of announcement has the largest immediate market responses, and compares the magnitude (with positive/negative signs) of market reactions to different announcement categories on the Australian Securities Exchange (ASX). This study is more attractive under the Australian Continuous Disclosure Regime (CDR) because of the classification system regarding the market-sensitive announcements. Whether or not an announcement is market-sensitive is predetermined by ASX ‘specialist staff’ before the announcement is released on the market. This study investigates how the market interprets the announcement, examining market sensitivity from both the share price and trading volume movements after the announcement is available to the market. In other words, to some extent, the ‘market sensitivity tag’ shows the announcement that the market should react to, and this study reveals the announcement that the market does react to. Focusing on market-sensitive announcements, except for the ASX Query, the significant results show a positive association between announcement categories and intraday Cumulative Abnormal Returns (CARs). Share prices react the most to Progress Reports and to Asset Acquisition & Disposal, and the least to Periodic Reports and Issued Capital. Share price reactions to Distribution Announcements and Other are in the middle. There are at least two possible reasons for the different market reaction magnitudes. One is the information materiality nature: if one type of information is more important to investors than other information, this may cause higher abnormal returns on the market. The other is the information predictability: if there has been a lot of relevant information available in previous days or months, share prices could adjust to the information more smoothly. In terms of the trading volume reactions, intraday Abnormal Trading Volumes (ATVs) are observed after the release of Progress Reports, Asset Acquisition & Disposal, Issued Capital and Periodic Reports. After separating good and bad news subsamples, the results show that Progress Reports and Asset Acquisition & Disposal tend to indicate good signs to the market and cause larger trading volumes. Periodic Reports and Issued Capital could contain either good or bad news, but the trading volumes are driven by bad news. The results also reveal that company size is an important factor. Large companies tend to have relatively small market responses after information is released, which confirms that the larger companies are more stable. This study also evaluates long-term market effects of corporate disclosures by examining the timeliness of price discovery (also known as the speed of price discovery). It is the timeliness with which the full value relevant information is priced over a year before the annual earnings announcement is released. Previous literature has revealed that earnings announcements convey information, because significant stock returns or increased trading volumes are observed around the time that earnings announcements are released. However, it has also been suggested that there are other more timely information sources available that contain essentially similar or even the same value-relevant information. By the time preliminary final reports become available to the market, any potential value-relevant information has been included in the share price. The CDR again provides an attractive environment to examine the impact of corporate disclosures on the timeliness of price discovery, because listed companies have to disclose to the market before any other media sources. This enables an exploration of the relationship between the timeliness and the frequency of continuous disclosures. If the CDR is efficient in keeping investors fully informed, there should be no stock price surprise after the earnings announcement is released. Given the importance of the Preliminary Final Reports to the timeliness metric and the fact that the immediate market reaction tests only cover announcements released during trading hours, this study investigates in depth the Preliminary Final Reports and finds some evidence that companies tend to release bad news after the market closes and/or on Fridays. In terms of the impacts of announcement frequency on the timeliness of price discovery, following the step ‘All announcements – Periodic/Non-periodic announcements – Detailed categories of Non-periodic announcements’, the findings reveal that only earnings-related and cash flow announcements (Periodic Reports, Distribution Announcements and Quarterly Cash Flow Reports) can accelerate the timeliness of price discovery. Unfortunately, the results do not confirm that more announcements on the market could promote the timeliness with which the value-relevant (i.e. earning/income) information is incorporated into share prices. In addition to announcement frequency influences, the price discovery process is faster for companies with better share performance, are larger or have greater profitability. Financial companies have a timelier price discovery process than other companies; the price discovery process of financial companies was affected more by the 2008 – 2010 Global Financial Crisis than that of other companies. This study contributes to the market reaction literature by covering all categories of company announcements and comparing immediate market consequences for each type of announcement, and builds upon the timeliness of the price discovery literature by linking the announcement frequency of each continuous disclosure category to the timeliness with which annual earnings information is incorporated into share prices.
Keywords: Announcement categories; Announcement frequency; Continuous Disclosure Regime; Immediate market reactions; Market sensitivity; Timeliness of price discovery

Location data and human mobility : an evaluation of a dissonance that frames data protection and privacy rights - Andrew, Jonathan (European University Institute, 2018)
With citizens’ movements mediated by many technologies that aid our navigation the potential for omnipresent surveillance may potentially institute fundamental changes to the human condition. Locational privacy is pivotal in developing inter-personal associations and relational ties with others and its function is therefore complex, rather than solely affording a degree of independence from the observations made by others. In this respect, a more nuanced understanding of the utility of location data is required; the current hierarchy that delineates personal data from special categories of personal data does not adequately appreciate the capacity for location data to act as a proxy for other sensitive personal data. Furthermore, the binary distinction that reflects the conceptualisation of the right to privacy as a negative right, with related concepts such as identity and personality formation viewed as positive constructs, is increasingly difficult a notion to preserve. The classification and terminology of technologies can illustrate how terms and legal metaphors are developed and applied so as to bridge gaps in applying existing context and precedent. Though the designation ‘location data’ once constituted a reasonable accommodation in nomenclature as an intelligible and easily comprehensible term, even while constituting a significant oversimplification of the data it represented, technological advances have rendered the term increasingly problematic. This study asks whether the existing legal framework at the regional level in Europe is apt to provide sufficiently cogent and coherent regulation given recent developments in technologies. The review analyses the risks associated with this predilection in data processing activities that allows for the identification of ever more intimate and nuanced details of a citizen’s life, behaviours and convictions through the analysis of their location data; in turn, it shall discern the necessity of considering the resulting impacts on citizens’ fundamental rights to privacy and personal data protection.
Accepted: 2018-02-16T08:28:25Z
Keywords: Data Protection; European Union countries; Location data; Privacy

Analysis of the rights and duties of insurers in Nigeria - Anifalaje, K. (University of Ibadan Law Journal, 2018)
The paper analyses the rights and duties of Nigerian insurers at common law emanating from the contractual relationship between the insurer and the insured as amplified or abridged under the statute. It argues that the statutory incursion into the common law rules of uberrimae fidei, insurable interest, conditions and warranties and assignment of policies, circumscribing some of the rights exercisable by the insurer against the insured to defeat just claims as well as expanding the scope of the insurer’s duties in order to improve on service delivery is salutary. The paper, however, concludes that further reform measures, aimed at addressing some other salient issues, are still essential in the overall interest of the insuring public.
Accepted: 2023-03-20T09:15:48Z
Keywords: Assurances; Assureur; Common law; Duties; Insurers; Nigeria; Rights; Statute

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (European Investment Bank, 2018)

Gaps in the IFRS Conceptual Framework - Barker, Richard; Teixeira, Alan (Accounting in Europe, 2018)
The stated purpose of the IFRS Conceptual Framework is to assist the IASB to develop Standards that are based on consistent concepts, and also to assist preparers to develop consistent accounting policies when Standards either do not apply or allow a choice of accounting policy. Yet, the Framework actually does surprisingly little to help the IASB (or preparers) determine which assets, liabilities, income and expenses should be recognised, and how they should be measured. The Framework’s focus on assets and liabilities implies that the accounting can, and should, be determined from the balance sheet. Yet, many current financial reporting requirements focus initially on the income statement, and so they are not so much derived from the Framework as instead in need of being reconciled back to it. At its heart, the problem here is that, while the Framework states that accrual accounting provides a better basis for assessing past and future performance than cash-based information, it does not explain why. To do so would require a conceptualisation of how entities’ business models are employed to create value, and of the strengths and limitations of accounting data in enhancing investors’ understanding of that value-creation. The lack of explanation of the purpose and informational objectives of accruals, how they relate to business models and how they cause the income statement and the balance sheet to interact are gaps in the Framework. Filling those gaps would provide a more robust, and natural, way for the IASB to develop recognition and measurement requirements in its Standards.
Keywords: Accruals; Conceptual framework; IFRS; Measurement; Unit of Account

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (European Investment Bank, 2018)

International norm conflicts through the lens of Alexy's principles theory - Böök, Birte (European University Institute, 2018)
The likelihood of clashes between international norms has increased in correlation with the upsurge in the number of specialised regimes emerging within the international legal field. The present thesis takes a closer look at the different ways in which such norm conflicts can be addressed at the international level. In particular, it distinguishes between conflict resolution based on establishing priority by means of traditional maxims, and resolution based on the weighing of clashing norms to determine which prevails in the case at hand. To do so, the thesis takes a step back from the existing literature and examines the distinction within norms between rules and principles, relying predominantly on Robert Alexy’s theory on this subject. Taking a legal-theoretical approach to the subject of international norm conflicts, this thesis shows that Alexy’s principles theory is not only transferrable to international law in theory, but that we can, moreover, identify international norms as rules and principles respectively. Distinguishing between the different ways in which conflicts are resolved depending on whether the norms involved are rules or principles, it is shown that while both approaches are susceptible to certain conceptual uncertainties and pitfalls, this dichotomy nevertheless plays an important role in the efficiency of the international legal system, ensuring that a certain balance between stability and flexibility is maintained. Ultimately, it is demonstrated that by viewing international law, and international norm conflicts in particular, through the lens of Alexy’s principles theory, we can gain a clearer understanding of the structure and application of international norms on the one hand and, as a result, how to resolve international norm conflicts on the other. Thus, drawing a distinction between rules and principles among international legal norms can be a means by which scholars (as well as judicial bodies or even states) may analyse ambiguous judicial decisions or international legal provisions, and can thus foster greater clarity in the field of international law.
Accepted: 2018-11-28T14:26:22Z
Keywords: Dispute Resolution; International Law

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

Arbitration cost : a short comparative view of the schedule of fees of arbitration centers within the OHADA zone - Dogué, Karel Osiris Coffi (Revue de l'ERSUMA, 2018)
Amongst the seventeen OHADA member states there are over fourteen arbitration centers or institutions that handle disputes arising from contractual agreement without going through the courts of the state. The arbitration cost within the various arbitral centers differs from one arbitration center to another. The schedule or method for calculating fees are regulated by the rules of the various arbitration centers or by the OHADA Uniform Act Arbitration Rules pertaining to arbitration fees annexed to the rules of arbitration for the Common Court of Justice and Arbitration and for arbitration centers without arbitration rules. This contribution describes and contrast the various schedule of fees applicable with the arbitration centers under the OHADA zone in particular and also makes a comparative view of the arbitration fees out of the OHADA zone.
Keywords: Arbitragem; Arbitraje; Arbitration; Arbitration cost; Arbitration fee; Arbitration proceedings; Coût de l’arbitrage; Frais d’arbitrage; OHADA Arbitration's Center; Procédure arbitrale

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations

Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
URI: https://repository.up.ac.za/handle/2263/70102
Keywords: Contract; Locatio conductio

Financial Accounting: International Financial Reporting Standards - Harrison Jr., Walter T.; Horngren, Charles T.; Thomas, C. William (Bill); Tietz, Wendy M.; Suwardy, Themin (Pearson, 2018)

The fairness of forfeiture clauses in short-term insurance contracts - Huneberg, Samantha (University of Johannesburg, 2018)
Insurance fraud is a major issue in the insurance industry. Insurance companies around the world are all facing significant losses due to the prevalence of fraudulent claims. These fraudulent claims and subsequent losses suffered by insurers inevitably lead to a dilution of the insurance pool and result in other policyholders bearing the brunt of these losses. The inevitable solution for insurers is to hike the premiums for all other policyholders in order to compensate for their losses caused by fraudulent claims. Insurance fraud is an international problem and it is common for insurers in most jurisdictions to use forfeiture clauses. These clauses aim to protect the insurer by stating that if the policyholder should submit any type pf fraudulent claim, the policyholder will forfeit the entire claim. There has been much controversy around the validity and fairness of these clauses. This thesis seeks to provide an overview of the prevalence of fraudulent insurance claims in South Africa, England, Australia and New Zealand. Moreover, it will consider the fairness of forfeiture clauses in light of the fundamental movement towards policyholder protection in recent years both in South Africa and in those jurisdictions that form part of the comparative study. The thesis concludes that forfeiture clauses form an indispensable part of short-term insurance contracts and are justifiable and therefore lawful. It is, however, submitted that insurance companies have a duty to disclose the nature and extent of forfeiture clauses at the inception of the policy and again at claim stage. By using so-called staggered disclosure, insurers provide policyholders with the opportunity to consider their claim and the means with which to prove it in order to avoid instituting a fraudulent claim. The thesis recommends that these rules pertaining to staggered disclosure should form part of the 2018 Policyholder Protection Rules, together with a statutory definition of insurance fraud.
Keywords: Forfeiture; Insurance policies; South Africa

Cross-border contracting: how to draft and negotiate international commercial contracts - International Trade Centre (ITC) (International Trade Centre (ITC), 2018)
Keywords: Iinternational contracts; International sale of goods; UN Convention on Contracts for the International Sale of Goods (1980)

A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Jansen van Rensburg, Enelia Cornelia (University of Pretoria, 2018)
The use of conduit company treaty shopping structures is often regarded as an impermissible erosion of a country’s tax base. For a developing country, such as South Africa, the protection of its tax base is an important policy consideration. Arguably, one way of combatting conduit company treaty shopping structures is by including in a country’s double taxation agreements the beneficial ownership requirement set out in Article 10(2) of the OECD MTC. The study examines how a South African court would interpret this requirement in provisions in South African double taxation agreements in the context of conduit company treaty shopping involving conduit companies receiving dividends. The study firstly considers whether the beneficial ownership requirement can be regarded as an anti-avoidance rule aimed at combatting conduit company treaty shopping falling outside agents and nominee scenarios. It further considers whether the term “beneficial owner” should have a legal or economic meaning. It explores the meanings given to this term by scholars and foreign courts and the OECD in its Commentaries to the OECD MTC. The study also considers the application of the rules of interpretation contained in the Vienna Convention on the Law of Treaties when giving meaning to this term. Lastly, the study considers whether the term should have the meaning assigned to it under the domestic law of a treaty country, or under international tax law. As part of this enquiry, the meanings of the expression “beneficial owner” in South African case law and legislation are explored.
https://repository.up.ac.za/handle/2263/65660
Keywords: Beneficial ownership; Conduit company treaty shopping; OECD; OECD Model Tax Convention; Société écran; South Africa

A comparative analysis of constructive dismissal in South Africa and within other international jurisdictions - Kader, Riaz (University of KwaZulu-Natal, 2018)
Abstract available in PDF.
Keywords: Constructive dismissal; Employee termination; Employees; Employers; Employment relationship; Termination of employment

Factors Influencing Indian Firms Decision Making In Foreign Direct Investment In Africa - Kukreja, Mukta; Joshi, Mahesh Chandra (International Journal of Applied Business and International Management, 2018)
India's economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the International typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.
Keywords: African nations; Developing countries; FDI; India; Indo-Afro relations; Investments; Multinational companies; OLI eclectic paradigm

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

The Organisation for the Harmonisation of Business Law in Africa (OHADA) System: Overview of some Benefits and Problem Areas - Leno, Ngaundje Doris (International Journal of Advanced Research and Publications, 2018)
As much as the Organisation for the Harmonisation of Business Law in Africa (OHADA) aims to improve the legal environment for business, the harmonisation process should be seen as a tool of economic integration with several advantages. Despite the achievements and benefits, OHADA, like other regional integration efforts in Africa, has some temporary drawbacks that may become permanent if no effort is made to overcome them. The primary focus of the paper is to present OHADA‟s background; offer an overview of some of the salient benefits of OHADA‟s institutional and regulatory framework; consider OHADA‟s problem areas; and propose possible solutions to the problems. The value of the paper, therefore, lies in the insight it offers into OHADA, the benefits and problems of its institutional and regulatory framework. It is also important because it is laying the foundation in making the OHADA structure available for all Africans.
Keywords: Business law; Harmonisation; OHADA

A comparative legal perspective on the impact of good or bad faith on the independence of documentary credits and demand guarantees - Lupton, Cayle Selwyn (University of Johannesburg, 2018)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Accounting Translation of Corporate Social and Environmental Expenditures in Small and Medium Industry: What Evaluation Approach and what Accounting Scheme? - Missomba, Jean Christian Ewane; Hanko, Osée (Research Journal of Finance and Accounting, 2018)
The question remains whether societal reporting integrates the field of financial reporting. This old debate is repeated to scrutinize the case of African companies with strong cultural roots, which do not publish alternative societal documents to traditional financial reports. Through stakeholder theory (Jones and Wicks, 1999), this study aims to analyze the phenomenon, by describing the process of accounting recordings for social and environmental information (SEI) identified by the ISO 26 000 standard in an oil Company operating within OHADA Jurisdiction. The results indicate the presence of mandatory SEIs in the financial statements, which visibility depends on the pressure exerted by the State and the accounting regulations in force. Voluntary SEIs are not visible.
Keywords: Financial reporting; ISO 26000; Social and Environmental Information (SEI); Stakeholder Theory

Some considerations on the flexibility of carrier's liability in OHBLA Law - Monkam, Cyrille (Revue de l'ERSUMA, 2018)
This article argues that the liability of the carrier is more flexible in OHBLA Transportation Law. It appears from the analysis that the carrier who is under strict or presumed liability may enjoy a large number of exemptions that may be classifiedunder classic and modern defenses on condition to act fairly and honnestly in performing the contract of carriage. The fairness and honnestly are expressed under the good faith principle. The contrary attitude -the performance in bad faith- will be sanctioned by the exclusion from the benefit of the various exemptions. The assessment of this unscrupulous behaviour of the carrier is vested on judges who have to determine in case of claims whether the behaviour constitutes a willful misconduct or a gross negligence. As examiners of the carrier's attitude, judges play a major role in establishing security and justice in contract of carriage. By setting up a flexible liability regime, the OHBLA Uniform Act is seen as a balanced instrument that sets up a compromise between carrier's interests and cargo's interests.
Keywords: Acte uniforme; Contrat de transport; Droit OHADA; Droit des transports; Transport de marchandises par route; Transportation Law

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

The protection of workers' claims in the event of the insolvency of their employer : OHADA's approach - Ngaundje, Leno Doris (Revue de l'ERSUMA, 2018)
An employer's insolvency has far-reaching consequences on workers. The consequence of business failures have complelled policy makers to provide for workers protection in the event of their employer's financial demise. The policy makers of the Organisation for the Harmonization of Busniess Law in Africa approach (OHADA) are not left out. This article seeks to examine OHADA's super-priority approach (article 95 of OHADA's Revised Insolvency Act - RIA) on the protection of workers claims with the aim of showing that approach is limited. Article 95 does not prescribe the limit on the amount protected, the time period and the category of workers concerned. This article ecognizes the need to reform article 95 of OHADA's RIA.In so doing, the article describe the position of two international bodies (International Labor Organisation -ILO) and the European Union -EU) on employee entitlements in insolvency as the bases needed to reform article 95 of OHADA's RIA. The value of this article lies in the nisights it offers into the current framework on insolvency and the opportuniy given to address the limitations that invariably arise from article 95 of OHADA's RIA.
Keywords: Droit OHADA; Faillite; Insolvabilité; Insolvency; Procédures collectives; Protection des créanciers

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Lex mercatoria in OHADA arbitration : A legal basis for unauthorized amiable composition? - Nshokano Kashironge, Dan (Bulletin ERSUMA de Pratique Professionnelle, 2018)
Keywords: Amiable composition; Arbitrage; Arbitration; Lex mercatoria; Lex mercatória

(Non) Compliance with multi-tiered dispute resolution clauses under OHADA's new ADR law : a question of juridiction or admissibility ? - Nshokano Kashironge, Dan (Bulletin ERSUMA de Pratique Professionnelle, 2018)

Corporate governance and resource management in Nigeria: a paradigm shift - Oyewunmi, Olabode Adeleke; Oyewunmi, Adebukola Esther (Business Perspectives, 2018)
The underlying significance of instituting measures for effective corporate governance and rewarding resource management outcomes cannot be relegated. The countries and organizations that deemphasize this practice have mortgaged their potential for long-term growth and corporate sustainability. This paper adopts a critical narrative method to deconstruct the essence of corporate governance and economic resource management ideals. The paper furthers the ongoing conversations on two interrelated business concepts, and provides an apt perspective towards unlocking the essence of corporate governance relative to the Nigeria’s corporate environment. It depicts a corporate paradigm shift that accommodates the dynamics of global best practices taking into account some peculiarities of Nigeria’s corporate climate. The paper also captures relevant theoretical dimensions and pragmatic policy propositions, especially for underperforming socio-economic contexts. In the light of the central theme, specific issues are discussed under the sub-headings of conceptual and theoretical clarifications, corporate governance and resource management in Nigeria, shifting the paradigms, conclusion and recommendations.
Number: 1 http://www.businessperspectives.org
Keywords: Corporate governance; Nigeria; Resource management

Reckless and fraudulent trading by a company and the business judgment rule as a defence for directors - Peter, Lunga Cosmo (University of KwaZulu-Natal, 2018)
Abstract available in pdf.
Keywords: Business judgment rule; Company directors; Corporate governance; Fiduciary duties; Fraudulent trading; Good faith; Personal liability

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

Analysing and comparing the impact of misrepresentation and non-disclosure on the validity of a contract: similarities, differences and remedies - Ramphal, Kayra (University of KwaZulu-Natal, 2018)
This dissertation explores the concepts of non-disclosure and misrepresentation in South African law. The principal focus surrounds the effect non-disclosure as a form of misrepresentation has on the liability of contracting parties. In order to explore this effectively, the study explores the concept of duty of disclosure, and whether such a duty exists in South African law. Instances when a duty to disclose arises are explained, such as positive steps taken to conceal facts, the seller having sole knowledge of the material fact, an omission or misleading language, and a change in circumstances. Similarly to the English law duty of disclosure in relation to information in contracts uberrimae fidei, the similar South African law concept in insurance or agency contracts known as ‘utmost good faith’, is discussed and explored. The study determines whether such a concept should be a mandatory requirement in pre-contractual negotiations. Additionally, this study explores the various avenues of relief that are available to those who have fallen victim to misrepresentation. This results in an analysis of the effectiveness and success of the current traditional methods of claiming and quantifying damages that are adopted by South African legislature and the judiciary. The discussion then explores the proposed alternate method which aims to combine a claim into one of delict and that of contractual liability, or on the other hand institute a claim solely based on contractual liability. Lastly, this study explores the effect the Consumer Protection Act 68 of 2008 has had on contractual agreements, remedies and penalties, and how this ground-breaking legislation has altered the approach previously adopted by the common law and whether it has done enough to protect consumers.
Keywords: Contracting parties; Contracts; Duty to disclose; Liability; Misrepresentation; Non-disclosure

What Do Trade Agreements Really Do? - Rodrik, Dani (The Journal of Economic Perspectives, 2018)

The interconnection between express choice of forum and tacit choice of law. A comparative analysis between common-law and civil-law jurisdictions - Roux, Keegan (University of Johannesburg, 2018)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

International Trade, Environment and Sustainable Development - Ruppel, Oliver C. (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
Issues related to international trade and the environment undoubtedly are of significance to developing countries like Cameroon because they argue that developed countries have depleted resources and indulged in environmentally harmful practices during the past century, in order to achieve unprecedented high standards of living.² The developing countries therefore demand a general but differentiated responsibility, seeking open trade and compensation for adopting environmentally restraining policies.³ Upon further reflection on the link between economic growth activities, environmental protection and social development, the triangular debate on these topics will be highlighted briefly, by introducing the various perspectives.⁴ Trade creates the wealth, which

The link between reckless credit and emolument attachment orders - Singh, Nishtha (University of KwaZulu-Natal, 2018)
South Africa has experienced significant levels of reckless credit thus leading to over-indebtedness of consumers. Furthermore, research conducted in 2008 and 2013 by the University of Pretoria indicated that there were abuses prevalent in emolument attachment orders (EAOs). An interesting aspect of the research was that credit providers were particularly interested in employed consumers, as their wages or salaries were deemed to be a form of security. The aim of this dissertation is to examine the link between reckless credit and EAOs. The main research problem revolves around the fact that credit providers do not conduct thorough pre-agreement assessments and have a tendency to subscribe to the tick box approach to compliance. Moreover, these pre-agreement assessments do not make provision for the inclusion of external market factors, which is essential to safeguard consumers against economic events. This dissertation argues that, at the point when reckless credit is granted, it is inevitable that default will occur thus leading to the culmination of an EAO. In this regard, the case of University of Stellenbosch Legal Aid Clinic and Others v Minister of Justice and Correctional Services and Others; Association of Debt Recovery Agents NPC v University of Stellenbosch Legal Aid Clinic and Others; Mavava Trading 279 (Pty) Ltd and Others v University of Stellenbosch Legal Aid Clinic and Others (CCT127/15) [2016] ZACC 32 is important. The judgement illustrates how vulnerable consumers fell prey to unscrupulous credit providers who then took advantage of their salaries. An important aspect about the judgement was that section 65J of the Magistrates Court Act has now been amended through a joint interpretative mechanism of severance and reading in. The Constitutional Court’s order now requires judicial supervision in the EAO process, whereby a magistrate issues the EAO. This dissertation examines the effect of this and how EAOs are currently regulated. It also discusses whether judicial supervision is the solution to ameliorating the law on EAOs. Qualitative research methods were utilised such as legislation, case law, textbooks and journal articles. While there are no statistics to prove the link, anecdotal evidence proves the link between reckless credit and EAOs.
Keywords: Credit market; Emolument Attachment Orders; Protection of Personal Information Act; Reckless Credit

Restraint of trade clauses: does the enforcement thereof promote anti-competitive behaviour in South African law? - Sithole, Mthokozisi Wesley Nhlakanipho (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Anti-competitive behaviour; Business agreements; Competencia; Competition law; Employment agreements; Restraint of trade; Trade clause

A discussion of the success and failures of business rescue as a remedy for ailing companies - Sobantu, Vuyo (University of KwaZulu-Natal, 2018)
Companies are constantly facing risks, including financial constraints, which may contribute to companies being unable to trade in the manner desired. Unfortunately, companies that find themselves in this predicament have, in reality, been without a remedy from as early as statutory provisions regulating company law were promulgated in 1926. Judicial management, as a remedy, is notorious for being an outright failure, but the current Companies Act 71 of 2008 introduced the remedy of business rescue for financially distressed companies. The scrutiny and spotlight on the new remedy turns on whether it can be truly accessible for the companies in question and what significant changes it has made to favour financially distressed companies. This mini dissertation will aim to discuss whether the remedy of business rescue has been a success or failure.
Keywords: Ailing companies; Business rescue; Companies Act 61 of 1973; Companies Act 71 of 2008; Judicial management; South African company law; Winding up

Strict product liability in South Africa : an analysis of the concept of "defect" and the statutory defences available to the supply chain - Tennant, Sarah-lynn (University of Pretoria, 2018)
Defective products cause harm to persons and property on a daily basis. Product Liability law has accordingly evolved as a specialised area of the law of delict which seeks to prevent product accidents from happening and provides compensation in the event that defective products nevertheless reach the consumer market. Accordingly product liability regimes generally have both ex ante components such as product standards, recall mechanisms and liability provisions which are aimed at deterrence and risk-spreading as well as provisions that are applied ex post to provide redress and compensation. Designing an appropriate legal framework to underpin a product liability regime is a daunting task that involves achieving of an appropriate balance between the interests of various parties inter alia those of consumers, suppliers and the broader community. In recent decades many countries have migrated from a fault-based product liability regime to a regime which purportedly imposes strict liability on the whole supply chain. This bold move in modern product liability was pioneered in the United States who has since returned to fault-based liability for design and warning defects whilst returning strict liability in respect of manufacturing defects. After many years South Africa has joined the group of countries that applies strict liability to all defects regardless of their type. Notably the product liability regime introduced into South African law by means of the Consumer Protection Act 68 of 2008 (“CPA”) resembles the main features of the EU Product Liability Directive 85/374/EEC. The EU Model has also been taken over by Australia when they transitioned to a purportedly strict product regime in 1992. During this process the thesis also considers whether, by adopting the European model, South Africa has taken over a model which has been criticised by some American authors as outdated and based on 1965 strict product liability rhetoric as contained in section 402A of the Restatement (Second) of Torts which approach has since been discarded in the US in favour of the hybrid approach contained in the US Restatement (Third): Product Liability. This thesis focuses on product liability ex delicto. Its main aim is to interrogate and evaluate the product liability provisions contained in section 61 of the CPA, specifically with regard to the pivotal concept of defect and the statutory defences the Act has introduced. It details South Africa’s journey from the fault-based common law of product liability to the purportedly strict regime espoused by the CPA, which regimes operate parallel to each other. This is done to facilitate an understanding of the differences between the two regimes and specifically to aid interpretation and application of the product liability provisions in the CPA that deal with defectiveness and the new statutory defences. In order to obtain further guidance on how the concept of “defect” and the statutory defences in the CPA should, or could, be interpreted and applied the thesis initially considers the general foundational principles underlying product liability law and how this area of law has evolved in the United States, being the origin of modern product liability law. However, given that the South African regime of “strict” product liability ex delicto has its roots in the EU Directive and resembles some of the adapted features of the Australian product liability regime contained in the comprehensive Australian Consumer Law, the main comparative focus is on these two jurisdictions.
URI: https://repository.up.ac.za/handle/2263/70768
Keywords: Defective product; Product liability; South Africa; Supply chain

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Aspects of the taxation of company distributions in South Africa - Tredoux, Liezel Gaynor (University of Johannesburg, 2018)
As a company distribution is a means by which wealth is transferred, it is a fertile ground for tax law reform to broaden the tax base and protect South Africa against base erosion and profit shifting. The South African government has identified the corporate tax structure, and many specific corporate tax rules, as areas in South African law in need of reform, and through which the policy objectives of stimulating foreign direct investment, promoting economic growth, and creating more employment opportunities can be achieved. This study involves an analysis on two levels: the corporate tax structure; and the specific tax legislation governing company distributions in South Africa. These aspects are contrasted with comparable rules in Australia and Canada. The study also evaluates the extent to which these laws conform to the normative values of equity, efficiency, certainty, and transparency, with the aim of suggesting improvements to promote South Africa’s current policy objectives. There are a variety of design models for a corporate tax structure. In the context of distributions, the ideal design should resolve whether tax should be paid on profit earned by a company, and also be levied on a second level, on distributions made to the company’s shareholders. Certain jurisdictions merge these two levels of tax to create a single taxable event which avoids the economic double taxation of income. There is, however, no dominant or universal model and several solutions can be mooted. Australia follows an imputation system which taxes corporate income at the first level of tax but grants a tax credit to shareholders on distribution, which means this income is taxed only once. Canada applies a hybrid integration system which also combines the two levels of tax and grants a tax credit to certain individual shareholders on distribution. However, the principles applied in these two models differ. The South African corporate tax structure is a hybrid, dual-rate system in terms of which different rates apply to corporate income and distributions to shareholders. All three systems offer relief for taxpayers which partially eliminates double taxation, with Australia having eliminated it fully for resident shareholders. In broad terms, a company distribution can be made by a company to its shareholders through either a return on capital or a return of capital. The policy approach adopted by the South African government is that all net accretions of wealth by the taxpayer should be taxable. Despite government’s intentions, there is a significant difference in the taxation rules applied to returns of an income nature (dividends and income), on the one hand, and returns of a capital nature (returns of capital, distribution of assets in specie) on the other. In addition, the net accretion of wealth is not always taxable on distribution to shareholders. In most instances the tax liability in respect of the return of capital is either deferred, or alternative rules are created which deviate from the principles and immediate tax liability that apply to returns on capital (dividends and income). In certain instances this deviation is justified, but in others it could lead to inequity between taxpayers and a narrowing of the tax base – both undesirable effects. A number of proposals are made to improve the law applicable to the taxation of company distributions as regards specific transactions. These are aimed, principally, at protecting the South African tax base against base erosion and profit shifting, and aligning South Africa’s tax law with international trends. The study finds that through the application of its hybrid dual-rate corporate tax system, South Africa has reduced economic double taxation to some extent, and that it is unnecessary for South Africa to integrate company- and shareholder-level tax. In addition, a variety of changes are suggested to improve the tax legislation applicable to specific company distributions, and to promote equity, certainty, and revenue collection. The South African tax legislation regulating company distributions is, in the main, fit for purpose, although there is room for improvement when it comes to simplicity, structure, and certainty.
Keywords: Company distributions; Contributed tax capital; Corporate tax; Dividend reinvestment plans; Dividends tax; Economic double taxation; Taxation

A critical analysis on simulated transactions - Tshabalala, Alwanduxolo Thembalihle (University of KwaZulu-Natal, 2018)
No abstract provided.
Keywords: Simulated transactions; Tax avoidance; Tax evasion; Taxation

Without Silence, There Is No Golden Rule; Without Dissent, There Is No Progress - Uluc, Inan; Sutton, Kristi R. (Oregon Review of International Law, 2018)
The frequency of dissenting opinions accompanying arbitration awards in international arbitration has multiplied, particularly in international investment arbitration. Accordingly, dissenting opinions are now inevitable companions to majority awards. Notwithstanding the fact that dissenting opinions neither form part of an arbitral award nor constitute a separate award, the escalation of dissenting opinions spawns anxiety in scholars and practitioners. This trepidation ignited a crusade whereby those opposed to the practice of rendering dissent challenge the role and usefulness of these opinions. In this respect, this Article initially considers and critiques specific arguments raised by those opposed to dissenting opinions in international arbitration. Following analysis of the criticisms, this Article explores the beneficial and constructive aspects of dissenting opinions. Evident from this discussion is that dissenting opinions are not only integral to supplement an arbitrator’s quasi-judicial capacity, but also encourage issuance of well-reasoned awards. Clear from the benefits of dissenting opinions in international arbitration, any departure from the present clemency espoused toward the practice will eventuate in the field’s regression.
Keywords: Civil law; Common law; International arbitration

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
https://escholarship.mcgill.ca/concern/theses/s1784p10r
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims

The effects of business rescue on the companies’ stakeholders : a comparative analysis between business rescue and judicial management - Xaba, Ntombikhona Thandeka (University of KwaZulu-Natal, 2018)
Upon the recognition that the implementation of the judicial management process would not be the success that it was anticipated it would be, it became apparent that there was need for a system of corporate rescue appropriate to the needs of a modern South African economy. The legislature then introduced a new business rescue regime when the Companies Act 71 of 20082 (the Act) came into effect in the South African law. This new Act remarkably changed corporate law. One of the central features of the Act is the introduction of business rescue- a procedure which provides for the rehabilitation of financially distressed companies in a manner that seeks to balance the rights of all stakeholders. These provisions are said to be the appropriate method for modern South African economy and they differently affect the stakeholders of a company. This thesis will be discussing the different rights given to affected persons in the new Companies Act and examine how the provisions of business rescue affect different stakeholders of the company and compare such effects with those experienced under judicial management, specifically in light of the improvements of the positions of the stakeholders. Although the new business rescue is a remarkable improvement from the old judicial management system, there is still room for improvement.
Keywords: Business rescue; Companies Act 71 of 2008; Company stakeholders; Judicial management; South African company law

The Impartiality and Independence of Arbitrators and Its Implication on the Validity of Arbitral Awards - Yoga, I. Ketut Dharma Putra (Juris Gentium Law Review, 2018)
Arbitration is a way to resolve disputes outside the courts as a form of an alternative dispute resolution. The submitted dispute will be decided by one or more arbitrators, who will then render an arbitral award. One of the most fundamental principles of arbitration that must be adhered to by all arbitrators worldwide is the impartiality and independence of arbitrators, which have been regulated in various International laws. Arbitrators are not allowed to communicate with any party related to the case they are hearing. Further, arbitrators should not be influenced by others in making their decision and drafting the arbitral award to ensure objectivity and prevent any bias. An arbitrator's failure to act impartial and independent can lead to the invalidity or annulment of an arbitral award.
https://www.neliti.com/publications/441283/

O.E.C.D. promotion for arbitration as an additional tool of settling disputes in the field of international taxation - Zeyen, Gaëtan (Revue de l'ERSUMA, 2018)
In a globalized world, arbitration plays an increasing role in settling international disputes. Almost all areas of Law are or might be concerned. Until very recently, [international] taxation was - as a rule - seen as a not ‘arbitrable-friendly’ matter. As the ‘classical’ method of settling international tax disputes - i.e., based on the so-called ‘Mutual Agreement Procedure’ (shortly, ‘M.A.P.’) - has shown its limits (mainly: lack of efficiency and involvement from the taxpayers themselves), arbitration became a subject of study for well-known and established academics and even an appropriate method of settling such international tax issues. As a result, both on international (O.E.C.D.) and European levels, legal initiatives have been taken, in order to promote arbitration as an additional tool of settling disputes in the field of international taxation. The purpose of the present article is, therefore, to describe and scrutinize these [very] recent legal initiatives and raise some potential issues that, at least in the author’s view, need to be addressed. One of these issues concerns the enforcement of such arbitral decisions.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration proceedings; Dispute settlement; International taxation; O.E.C.D; OCDE

A critical discussion of the directors’ duties and business judgement rule - Zondi, Sphesihle Brilliant (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Companies Act 71 of 2008; Directors; Judgement rule; South Africa

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Reflections on Legal Uncertainties for e-Commerce Transactions in Cameroon - Nwabueze, Caroline Joelle (The African Journal of Information and Communication, 2017)
This thematic report appraises legal provisions currently governing e-commerce transactions in Cameroon, in particular the matter of online contracts for sales of goods and services. There are uncertainties for Cameroonian consumers in the legal provisions at both regional level – via the Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA, the Organisation for the Harmonisation of Business Law in Africa) – and at Cameroonian national level. The report recommends steps to be taken to remedy the uncertainties.
Keywords: Consumer protection; E-commerce; Online contracts; Online transactions

Legal framework of Directors' Duties in OHADA Law (Senegal) - Niang, Oumar (International Journal of Business, Economics and Management Works, 2017)
This article is aimed to study the legal framework of directors’ duties in Ohada law. The Organization for the Harmonization of Business Laws (OHADA),is a supranational system of business laws that, as implemented in Senegal is trying to regulate all the core businesses.Ohada displays two level of mixing.Firstly,Ohada Law is supranational, it becomes part of the internal law of each state member but still remains supranational characteristics.Secondly,Ohada being at least partially French-inspired, we can understand that the most of the countries which adopted Ohada Laws are French-speaking. The duties of Directors in Senegal are regulated mainly by the uniform companies’ act which is part of the Ohada law. It should be noted that before the adoption of Ohada, company law was governed by the code of civil obligations and in its fourth part. For companies listed on the RSE, they must comply both with the general regulations of the BRVM and with the provisions of the Uniform Companies Act concerning publicly traded companies. This article aims to illuminate the lanterns on the question of the duties of directors in Ohada law, during my research I have observed that subjects such as corporate governance in general and the duties of directors in Ohada are left stranded by most researchers. This is why this topic has an interest in reabsorbing this gap insofar as the legal framework of the duties of directors often mentions many questions because of the lack of loyalty and diligence of certain directors.
Copyright © 2017 KWP Journals. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. International Journal of Business, Economics and Management Works Kambohwell Publisher Enterprises www.kwpublisher.com
Keywords: Company law; Corporate; Directors Duties; Governance; Senegal

Essays on Bank risk, capital and Lending - Alraheb, Tammuz (Université de Limoges, 2017)
Cette thèse examine trois questions importantes dans le secteur bancaire, à savoir le risque, les fonds propres et le crédit. Elle comprend trois essais empiriques. Le premier chapitre analyse l'impact du «printemps arabe» et de la crise financière mondiale de 2007-2008 sur la stabilité du secteur bancaire dans la région MENA. Les résultats montrent que le «printemps arabe» n'a pas eu d'effet négatif sur la stabilité des banques, alors que la crise financière mondiale a considérablement réduit leur stabilité. Le deuxième chapitre étudie le rôle joué par l'environnement institutionnel dans la mise en place de coussin de fonds propres par les régulateurs ou par les banques en interne. D’après les résultats, pour que les ratios de capital réglementaire soient efficaces, l'environnement institutionnel ne doit pas être négligé lors de la mise en place de ces ratios. Le troisième chapitre étudie les différents effets des droits des consommateurs et des créanciers sur le coût des prêts. Les résultats révèlent que le coût des prêts augmente en présence de lois strictes sur la protection des consommateurs, tandis que l'augmentation des droits des créanciers réduit ce coût.
Keywords: Bank Capital Structure; Bank foreign expansion; Bank loan growth; Banque expansion à l'étranger; Banques; Consommateur (protection); Cost of intermediation; Coût de l'intermédiation; Creditors' rights; Crise économique (2008); Croissance du crédit bancaire; Droits des créanciers; Structure du capital de la Banque

Treatment of corporate groups in insolvency under EU law - Sicignano, Luca (LUISS Guido Carli, 2017)
L’analisi svolta in questo lavoro ha ad oggetto le procedure adottabili in caso di fallimento, quando esse coinvolgono società costituite in gruppi di impresa. È una questione non recente che ha tuttavia avuto la sua consacrazione nel panorama internazionale solo negli ultimi anni. La grande crisi finanziaria del 2008 ha fatto sorgere la necessità di emanare nuove specifiche regole. Pertanto, l’obiettivo che questo lavoro si propone, è di analizzare tali regole, sia iure condito che iure condendo, per consentire al lettore di avere una panoramica chiara su come l’insolvenza di gruppo possa essere trattata.

The Admissibility of Shareholder Claims: Standing, Causes of Action, and Damages - Bottini, Gabriel (University of Cambridge, 2017)
This thesis addresses risks of multiple recovery, prejudice to legitimate interests of third parties, and inadequate consideration of the applicable law in shareholder claims in investment treaty arbitration. It challenges the application by investment tribunals of two basic premises: i) that shareholders are entitled to claim for damages vis-à-vis measures against the company in which they hold shares and ii) that ‘contract claims’ are to be distinguished from ‘treaty claims’. The central argument is that the failure to recognize substantive overlaps between shareholder treaty claims and contract claims risks more than one recovery, potentially prejudices third parties, and can lead to an incomplete application of the applicable law. The foundations of standing and the cause of action in shareholder treaty claims involve two complementary ideas of independence, i.e., independence of shareholder treaty rights vis-à-vis the local company’s contractual/national law rights and independence of treaty claims vis-à-vis contract claims. However, the substance of shareholder treaty claims, defined as the state measure and particularly the losses involved, is often identical to or at least overlaps considerably with related contract/national law claims. Prevailing ideas on shareholder standing and the cause of action in international investment law have provided useful conceptual tools for jurisdictional determinations. Yet they have not allowed tribunals and the literature to fully consider the implications of shareholder indirect claims. The thesis argues, first, that investment tribunals should acknowledge substantive overlaps between contract and treaty claims. Second, shareholder claims may be inadmissible when such overlap exists and there is a risk of double recovery or prejudice to third parties. Third, the substantive coincidence of treaty and contract claims calls for an integrated approach to the applicable law, where proper weight is given not only to IIA provisions but also to general international law and the national law governing the investment.
Keywords: Admissibility; Admissibility and jurisdiction; Applicable law; Arbitrage; Arbitragem; Arbitration; Contract claims; Contract-treaty distinction; Double recovery; Investment arbitration; Investment claims; Investments; Mixed claims commissions; Prejudice to third parties; Shareholder claims; Shareholder standing; Treaty claims

Entrepreneurship in Africa - Akinyoade, Akinyinka; Dietz, Ton; Uche, Chibuike (Brill, 2017)
Historically, entrepreneurs have always played a central role in the development of nation states. Aside from rentier states, which depend extensively on the availability of mineral resource rents, most economically prosperous nations in the world have strong, innovative and competitive business enterprises and entrepreneurs as the bedrock of their economic development and prosperity. It was arguably because of the above historical fact that the World Bank in 1989 declared that entrepreneurs will play a central role in transforming African economies. Chapters in this book contribute to our understanding of the theory, structure and practice of entrepreneurship in diverse African countries. Case studies examined include: African multinational banks and businesses, female entrepreneurs, culture and entrepreneurship, finance and entrepreneurship and SMEs.
Télécharger le PDF : https://brill.com/downloadpdf/display/title/33333.pdf
Keywords: African Studies; Economic History; Economics & Political Science; History; Social Sciences; Sociology & Anthropology

The Seller's right to cure under article 48 United Nations Convention on contracts for the international sale of goods - Mirambell i Fargas, Miquel (Universitat Pompeu Fabra, 2017)
In principle, contracts are enforceable mutually beneficial agreements. In the event of a breach of contract, many national, supranational, and international legal systems—as well as recent European harmonization projects on private law—turn to cure regimes for the furtherance of such (assumed) contractually generated welfare. Namely, a mandatory Nachfrist-mechanism, a hierarchy of remedies, and debtor’s (in sales law: seller’s) rights to cure—before and after performance date—are normative devices intended to perform and preserve contracts, employing purportedly better, more cost-effective remedies for breach. Discussion of the utility of these legal institutions undisputedly belongs to the debate on modern contract law. In this thesis, one of these cure-oriented devices is exhaustively analyzed: the seller’s right to cure after performance date under Article 48 CISG1. Whereas according to paragraph (1) the seller—provided that certain preconditions are met—can impose subsequent performance on the aggrieved buyer, under paragraphs (2-4) they can merely offer cure within a period of time, irrespective of any preconditions. Article 48 CISG’s systematic setting, comparative law framework, origin, forerunners, preconditions for existence—general and specific—performance in practice, legal consequences—with regards to both the breach-of-contract regime and the availability of other remedies under the CISG—, and economic-behavioural implications are exegetically analysed. A particular focus is given to the allocation of contractual risk (see epigraph 3.2.9). Finally, conclusions are drawn at two levels: one concerning the CISG’s regime and another related to general Contract law. En principio, los contratos son acuerdos ejecutables mutuamente beneficiosos. En caso de incumplimiento del contrato, muchos sistemas jurídicos nacionales, supranacionales e internacionales—así como los recientes proyectos europeos de armonización en derecho privado—recurren a regímenes de subsanación para promover el bienestar que presumiblemente se ha generado con el contrato. A saber, un mecanismo de un Nachfrist obligatorio, una jerarquía de remedios y derechos del deudor (en compraventa: del vendedor) de subsanar—antes y después de la fecha de cumplimiento—son instrumentos normativos destinados a dar cumplimiento a los contratos y a preservarlos por medio de remedios, a priori, económicamente más eficientes. La discusión sobre la bondad y utilidad de estas instituciones indudablemente pertenece al planteamiento de un derecho de contratos moderno. En esta tesis se analiza exhaustivamente uno de estos instrumentos de subsanación: el derecho del vendedor a subsanar después de la fecha de entrega en virtud del artículo 48 CISG2. Mientras que de acuerdo con su párrafo (1) el vendedor –reuniendo ciertas condiciones previas– puede imponer una ulterior ejecución al comprador perjudicado; en virtud de los párrafos (2-4), éste solamente puede ofrecer una subsanación dentro de un plazo, pero independientemente de cualquier condición previa. Del citado artículo 48 se analizan exegéticamente el entorno sistemático, el marco en derecho comparado, el origen, los precursores, las condiciones previas para la existencia—generales y específicas—, su ejecución en la práctica, las consecuencias jurídicas—en el régimen del incumplimiento del contrato y en la disponibilidad de otros remedios bajo la Convención—así como las implicaciones económicas y conductuales. Se hace una contribución en relación con la asignación del riesgo contractual (véase infra 3.2.9). Finalmente, se extraen conclusiones a dos niveles: uno enfocado al régimen de la Convención y otro relativo al Derecho de contratos en general.
URI: https://www.tdx.cat/handle/10803/404845
Keywords: Artículo 48 CISG2; CISG; Derecho del vendedor; Seller's right

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Dispute resolution in the oil and gas industry: an appraisal of mediation and litigation procedures. - Mohammed, Jamilu Ibn (Journal of private and business law, 2017)
The Oil and Gas Industry Resolution originally recognised negotiation and concede to the alternative dispute resolution rather, their litigation. The paper analysed appraised the different alternative dispute resolution, formulae including mediation the doctrinal method of research which analyses all legal in others as applied. All methods relating to the dispute resolution were analysed from the library and it has formed that mediation which involves the process of resolution dispute weather the involvement of litigating is prefer for being use costly and time consuming. Litigation been so expensive and time wasting is not recommence for oil and Gas Industry.
Keywords: Dispute Resolution; Gas; Industry; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Oil

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

The regulation of unsolicited electronic communications (SPAM) in South Africa : a comparative study - Tladi, Sebolawe Erna Mokowadi (University of South Africa, 2017)
The practice of spamming (sending unsolicited electronic communications) has been dubbed “the scourge of the 21st century” affecting different stakeholders. This practice is also credited for not only disrupting electronic communications but also, it overloads electronic systems and creates unnecessary costs for those affected than the ones responsible for sending such communications. In trying to address this issue nations have implemented anti-spam laws to combat the scourge. South Africa not lagging behind, has put in place anti-spam provisions to deal with the scourge. The anti-spam provisions are scattered in pieces of legislation dealing with diverse issues including: consumer protection; direct marketing; credit laws; and electronic transactions and communications. In addition to these provisions, an Amendment Bill to one of these laws and two Bills covering cybercrimes and cyber-security issues have been published. In this thesis, a question is asked on whether the current fragmented anti-spam provisions are adequate in protecting consumers. Whether the overlaps between these pieces of legislation are competent to deal with the ever increasing threats on electronic communications at large. Finally, the question as to whether a multi-faceted approach, which includes a Model Law on spam would be a suitable starting point setting out requirements for the sending of unsolicited electronic communications can be sufficient in protecting consumers. And as spam is not only a national but also a global problem, South Africa needs to look at the option of entering into mutual agreements with other countries and organisations in order to combat spam at a global level.
Keywords: Anti-spam laws; Commercial electronic messages; Consumer law; Direct marketing; Electronic commerce; Electronic communications; Electronic mail (e-mail); International cooperation; Right of privacy; Spam (Electronic mail); Telemarketing; Unsolicited commercial communications; Unsolicited electronic communications

A Pluralist Approach to the Law of International Sales - Coetzee, Juana (Potchefstroom Electronic Law Journal, 2017)
International trade can support economic development and social upliftment. However, people are often discouraged from contracting internationally due to differences in legal systems which act as a non-tariff barrier to trade. This article focuses on the private law framework regulating international contracts of sale. During the twentieth century, the problem of diverse laws was primarily addressed by global uniform law such as the United Nations Convention on Contracts for the International Sale of Goods (CISG). However, uniform law is rarely complete and has to be supplemented by national law, trade usage or party agreement. Because of gaps that exist in the CISG the Swiss government made a proposal for a new global contract law. But is this a feasible solution to the fragmentary state of international trade law? In Europe, signs of reluctance are setting in towards further harmonisation efforts. The Proposal for a Common European Sales Law (CESL) was recently withdrawn, and now Britain has voted to leave the European Union; rumour having it that more countries might follow. The current private law framework for international sales contracts consists of a hybrid system where international, national, state and non-state law function side by side. This article submits that universalism is not per se the most efficient approach to the regulation of international sales law and that economic forces require a more varied approach for business-to-business transactions. The biggest challenge, however, would be to manage global legal pluralism. It is concluded that contractual parties, the courts and arbitral tribunals can effectively manage pluralism on a case-by-case basis.
Keywords: Global legal pluralism; Legal harmonisation; international contracts; international sales; unified law

Foreign Direct Investment and Economic Development in Africa - Adegboye, F. B.; Ojo, Joshua A. T.; Olokoyo, F. O. (Journal of Internet Banking and Commerce, 2017)
Africa unlike other developing regions of the world has experienced declining flows of foreign direct investment (FDI).The flow of FDI is expected to result into gradual reduction in reliance on external borrowed capital and acceleration of economic development. The study examined the declining flow of FDI to the African regions as well as the impact that it has had on economic development of the region, using the proxies of Income per capita, Life expectancy and Education indices. The study made use of pooled data from thirty nine African countries within the period 1993 and 2012.The method of analysis utilized for the study was the fixed effect least-square dummy variable model, employed to estimate the impact of foreign direct investment on economic development for the selected host African countries. The study finds that foreign direct investment is statistically significant in relation to economic development for host African countries. It is therefore recommended that the governments of host countries should consider closely the sectors that FDI flows into, encourage investment domestically in such sectors such that dependence on external financial flows could be reduced, resulting in sustained increases in income, literacy level and hence improved life expectancy which are expected to result into sustained economic development.
Number: 1 http://www.icommercecentral.com
Keywords: Economic Development; Foreign direct investment; Host African Countries; Income Per Capital; Investments; Life Expectancy

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

United States' bankruptcy jurisdiction over foreign entities: exorbitant or congruent - Walters, Adrian J. (The Journal of Corporate Law Studies, 2017)
Alarmed at the ease with which global bankruptcy jurisdiction can be engineered in the US through a combination of the Bankruptcy Code’s low bar to entry and the worldwide effects of a bankruptcy case, critics argue that the US promotes abusive bankruptcy forum shopping and harmful imposition of US norms on overseas stakeholders. This article advances a revised account of US bankruptcy jurisdiction over non-US debtors from a distinctively Anglo-American standpoint. The article’s central thesis is that critics overemphasise formal jurisdictional rules and pay insufficient attention to how US courts actually exercise jurisdiction in practice. It compares the formal law ‘on the books’ in the US and UK for determining whether or not a domestic insolvency or restructuring proceeding relating to a foreign debtor can be maintained in each jurisdiction and provides a functional account of how US bankruptcy jurisdiction over foreign entities is exercised in practice using the concept of jurisdictional congruence as a benchmark.

A critical appraisal of secured transactions over personal property in Nigeria: legal problems and a proposal for reform - Otabor-Olubor, Iyare (Nottingham Trent University, 2017)
The thesis contemplates the need for Nigerian policy makers to undertake a reform of secured transactions law to meet international best standards, building upon earlier, unsuccessful, efforts by lawmakers, and drawing upon international benchmarks. It critically analyses the Registration of Security Interests in Movable Property by Banks and Other Financial Institutions in Nigeria (Regulation No.1 2015) 'CBNR' published on 2 February 2015. The CBNR, with a primary aim of facilitating affordable credit, and to modernise secured transactions law through the use of personal property as collateral, has departed from its previous position which it inherited from England. This thesis has drawn comparisons between the CBNR and prior reform initiatives particularly the Draft Law 2009 prepared by the Centre for the Economic Analysis of Law (CEAL). These reforms, which were not implemented, recommended wholesale changes to harmonise all existing secured transactions law in Nigeria. The CBNR does not follow this approach, but instead, adopts a piecemeal approach to reform. Correspondingly, this forms the framework within which this study has been undertaken with reference to whether a piecemeal or wholesale reform is now required. This thesis has followed the International Finance Corporation (IFC) approach which focuses on a three-stage secured transactions reform strategy - modernisation of the existing legal framework; establishment of an electronic collateral registry; a concerted effort towards building capacity. With the assistance of international secured transactions legal frameworks such as the UNCITRAL Legislative Guide on Secured Transactions 2007, and its Registry Guide 2014, the CBNR has been benchmarked against these adaptable legal frameworks for the purpose of harmonising secured transactions law, in search of the international best practice which may be desirable for Nigeria. The thesis identifies and discusses at length several problems and inconsistencies associated with the CNBR, and the thesis makes suggestions for a wholesale reform of the Nigerian secured transactions law. This thesis builds on existing knowledge on secured transactions law reform with particular reference, and usefulness, to sub-Saharan African countries and other developing countries that wish to attempt a similar reform of this nature.
https://irep.ntu.ac.uk/id/eprint/31955/
Keywords: Nigeria; Secured transactions; Security interest; Sûretés mobilières

The impact of climate change law on the principle of state sovereignty over natural resources - Van Wyk, Sanita (Stellenbosch University, 2017)
This dissertation serves to expand the means within international law by which to address the global interdisciplinary crisis that is climate change. The principle of sovereignty over natural resources is identified as a principle of international law, evolutionary in nature, fundamentally connected to the international legal climate change regime, and able to be impacted by the effects of climate change. The gravity of climate change is illustrated, as is the intricacy and composition of the international legal climate change regime. In the process, a particular shortcoming of the international legal climate change regime is identified, namely the lack of state compliance with climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. The gravity of the effects of climate change warrants the repositioning of any principle of international law that is able to address this shortcoming of the international legal climate change regime and increase the effectiveness of the regime. In this regard it is determined, more specifically, that the gravity of the effects of climate change warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources. Climate change, forming part of the general, growing, global concern for environmental conservation and sustainable development, influences the interpretation and configuration of state rights and state duties in terms of the principle by eliciting an interpretation that restricts state rights and expands state duties. Furthermore, the gravity of the effects of climate change on the well-being of people, warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources as a people-oriented principle as opposed to the conventional state-oriented principle, and ought to be applied with due regard to the rights of people in terms of the principle. The right of people in terms of the principle of sovereignty over natural resources, is identified as the right to economic selfdetermination, which gives effect to the right of people to dispose freely of natural resources. Should this right be promoted in future applications of the principle of sovereignty over natural resources, the right may well be established as constituting a significant basis on which people are able to hold states accountable for climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. In this way, the principle of sovereignty over natural resources, specifically the implementation of the right of people to dispose freely of natural resources in terms of the principle, presents a negative incentive for state compliance with climate commitments and can contribute to addressing the lack of state compliance within the international legal climate change regime. In summary, this dissertation proposes that the grave effects of climate change warrant a repositioning of the principle of sovereignty over natural resources that allows it to constitute a contribution to climate change law and the global fight against climate change.
URI: http://hdl.handle.net/10019.1/101171
Keywords: Climatic changes; Convention on Climate Change 1997; Convention on Climate Change 2015; Environmental law; Kyoto Protocol; Natural resources; Paris Agreement 2015; Self-determination; Sovereignty; United Nations Framework

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

The taxation of small business in developing countries - AKM, Atiqul Haque (Monash University, 2017)
The thesis attempts to explore an efficient policy and administrative framework to tax the small businesses in developing countries. In order to approach the policy and administrative problems concerning the taxation of small business in developing countries this thesis asks How can small businesses be efficiently taxed in developing countries? This thesis over eight chapters qualitatively explores this research question. The analyses conclude that first, in a typical developing country a well-designed simple to follow presumptive tax regime is more efficient than the actual account based tax system. Second, this thesis argues that the noncompliance of small businesses in developing countries may not be adequately explained by the standard expected utility based compliance models. The leading tax compliance models which mainly emphasise on the perceived reward from evasion might ignore some crucial factor that constitutes the tax compliance environment of small businesses in developing countries. This thesis illustrates broadly the typical tax compliance environment of small businesses. It argues that a simple to follow tax system that requires a minimal level of taxpayer compliance would attract a section of small taxpayers into the formal tax net. Third, this thesis demonstrates that there are crucial differences between typical urban and rural businesses. A small business tax regime should have a separate set of presumptive instruments for each class of small business in order to make an efficient estimate of their economic activities. Fourth, this thesis analytically examines the presumptive methods and their practical applications. The findings suggest that in developing countries presumptive tax methods have been adopted mostly in arbitrary manner, without the objective considerations to many crucial design issues. Fifth, this thesis has developed a focused analysis on the taxation of urban small businesses in the contexts of developing countries. This thesis analyses some crucial characteristics of urban small businesses and stresses that enterprise formalization should be a key element of urban small business tax policy. For a meaningful expansion of the tax net, tax administration should put more focus on urban small businesses as these businesses have relatively more potential to grow as more stable and sustained taxpayers. This thesis concludes that a turnover based presumptive taxation is more efficient to tax the urban small businesses. Lastly, this thesis explores the issues concerning the taxation of rural small businesses. This thesis reports that the overall tax burden on the agricultural income had substantially declined over the last few decades. Developing countries should not ignore the tax potential of the rural taxpayers. In a typical developing country an asset based presumptive tax system is more efficient to tax the agricultural income of the rural small businesses. This thesis has argued that it would be more efficient to adopt a single asset based presumptive income tax replacing all the prevailing taxes on the agricultural income such as agricultural land tax, wealth tax and income tax.
Keywords: Fiscal policy; Small business taxation; Taxation administration; Taxation in developing countries; Taxation law; Taxation of rural small business; Taxation of shadow economy; Taxation of urban small business; Taxation policy

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
URI: https://repository.up.ac.za/handle/2263/65659
Keywords: Consumer credit; Debt; Namibia

Alternative Dispute Resolution (ADR) and access to justice: An introduction - Betancourt, J. (Arbitration, 2017)
Text of a talk given by the author at the University of West London on 8 March 2016 on the topic of Alternative Dispute Resolution, its relation to the concept of access to justice and the idea of practising law in the interest of justice.
https://ora.ox.ac.uk/objects/uuid:fdf8485f-c538-4312-8241-9419561af728

International Accounting Standards in Africa: Selective Recursivity for the 'Happy Few'? - Botzem, Sebastian; Quack, S; Zori, Solomon George (Global Policy, 2017)
This study explores recursivity in international accounting standard-setting, focusing on participation of actors from African countries. While the International Financial Reporting Standards (IFRS) Foundation bases its legitimacy claims as a global standard-setter on a combination of expertise and a formally transparent set of recursive procedures for consultation of stakeholders, empirical results show that participation in the latter is geographically very uneven. The article argues that conceptual mismatch between the standard-setter's objectives on the one hand and the socio-economic, cultural and political conditions in many African countries on the other leads to selective recursivity that is problematic for the former's legitimacy and effectiveness. These findings are of wider relevance for debates on global standard-setting and development.
Keywords: Accounting Standard; Africa; Economics of Culture; IFRS; International Accounting

The Application of CISG in International Arbitration - Cisár, Ivan (Current Issues of International Commercial Arbitration, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION

Disqualification Decisions under the ICSID Convention and Arbitration Rules - Cleis, Maria Nicole (The Independence and Impartiality of ICSID Arbitrators, 2017)
This Chapter aims to distill a consistent approach to arbitrators’ independence and impartiality from past decisions on disqualification requests. In a first part, the interpretation of the manifest lack requirement provided for in Article 57 icsid Convention is scrutinized. The definition of this threshold (i.e. the burden of proof imposed on the challenging party) is crucial, because it determines the effectiveness of the right to an independent and impartial decision-maker. The second part of the Chapter inquires how specific categories of alleged conflict are dealt with. It seeks to derive consistency and predictability from the outcome or reasoning of disqualification

The Independence and Impartiality of ICSID Arbitrators: Current Case Law, Alternative Approaches, and Improvement Suggestions - Cleis, Maria Nicole (Brill, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.
Accepted: 2020-05-15T17:36:32Z
Keywords: Arbitrage; Arbitragem; Arbitration; Civil procedure; International Arbitration; International disputes; International law

An investigation into the relationship between the UNIDROIT Principles of International Commercial Contracts (UPICC) and the UN Convention on the International Sale of Goods (CISG) - Daniel, Jason (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: Commercial law; Conflict of laws; Contracts (International law); International Institute for the Unification of Private Law; UNIDROIT principles of international commercial contracts 2010; United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

Oiling the machine: overriding mandatory provisions and public policy in the Hague Principles on Choice of Law in International Commercial Contracts - Dickinson, Andrew (Uniform Law Review, 2017)
Art. 11 of the Principles on Choice of Law in International Commercial Contracts, adopted by the Council of the Hague Conference in March 2015 contains provisions governing the relationship between the system of law1 chosen by the parties under Art. 2(1) (the “chosen law”) and the laws and policies of other systems. It provides as follows: 1. These Principles shall not prevent a court from applying overriding mandatory provisions of the law of the forum which apply irrespective of the law chosen by the parties. 2. The law of the forum determines when a court may or must apply or take into account overriding mandatory provisions of another law. 3. A court may exclude application of a provision of the law chosen by the parties only if and to the extent that the result of such application would be manifestly incompatible with fundamental notions of public policy (ordre public) of the forum. 4. The law of the forum determines when a court may or must apply or take into account the public policy (ordre public) of a State the law of which would be applicable in the absence of a choice of law. 5. These Principles shall not prevent an arbitral tribunal from applying or taking into account public policy (ordre public), or from applying or taking into account overriding mandatory provisions of a law other than the law chosen by the parties, if the arbitral tribunal is required or entitled to do so. In brief summary, therefore, the first and third paragraphs address the relationship between the chosen law and certain laws and policies of the forum, the second paragraph addresses the relationship between the chosen law and certain laws of legal systems other than the forum, the fourth paragraph addresses the relationship between the chosen law and the certain policies of the legal system whose laws would have applied but for the parties’ choice under Art. 2(1) and the fifth paragraph addresses the limits of the application of the chosen law in arbitration proceedings.

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration - Drličková, Klára; Halla, Slavomír (Masaryk University Press, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

The impact of threshold agreements on the organisational rights of minority trade unions - Esitang, Temogo Geoffrey (University of Pretoria, 2017)
The rights of freedom of association, to organise and to bargain collectively are recognised internationally and form part of the constitutional framework of progressive and democratic states. The full enjoyment of these rights by trade unions often is hindered by the imbalance in the power relations between the employer and the representatives of the workers, hence the need for statutory intervention. The Labour Relations Act 66 of 1995 (LRA of 1995) postulates a collective bargaining regime which is voluntarist in nature and strengthens its effectiveness through a set of organisational rights and the right to strike. Incidentally, the current statutory framework for the enjoyment of organisational rights has had a direct impact on the enjoyment of the right to freedom of association and the right to organise. It is accepted that possession of the right to collective bargaining is internationally recognised as the basis of the authority to set thresholds of representivity in the workplace. The organisational rights framework in this context has been directly impacted upon. It is this direct impact that necessitates an enquiry to determine whether South Africa’s framework on the acquisition of organisational rights conforms to international standards set by the ILO and the Constitution, 1996. This thesis argues that the policy choice of the South African labour relations system in respect of some of the consequences of majoritarianism insofar as representation in individual cases is concerned does not necessarily foster the ideals of the Constitution, 1996 and the principles of international labour standards. The model of democracy as envisaged in the Constitution, 1996 is not one that promotes exclusivity. However, the effect of section 18 of the LRA of 1995, which allows threshold agreements, arguably may foster such exclusivity in the workplace. This situation has resulted in industrial democracy being a terrain of endless conflict between employers and labour, even more among trade unions themselves. As a result, the rivalry between unions in workplaces is exacerbated. The original intent behind the organisational rights of trade unions and their right to strike was to bolster their capacity to bargain collectively. It was meant to get them to focus on collective bargaining gains they can secure and to bargain more effectively. However, the current framework that favours majority trade unions has the effect of minority trade unions generally finding their existence threatened and their being systematically excluded from the acquisition of organisational rights. This study questions the power of majority trade unions to enter a collective agreement with an employer in the workplace and set unjustifiable thresholds of representivity in respect of organisational rights. This arrangement creates a hurdle in respect of the provisions of the LRA that seek to promote industrial democracy, the enjoyment of the rights to freedom of association, to organise and to engage in collective bargaining. Recent amendments to the LRA of 1995 are an attempt to mitigate the effect of sections 18 and 20 on the enjoyment of organisational rights. The CCMA, inter alia, has been granted powers to grant organisational rights to trade unions that do not meet the set threshold in terms of the empowering provisions of the LRA of 1995 if they meet certain requirements. However, these amendments do not go far enough to prevent employers and majority trade unions from continuing to set unjustifiable thresholds that can have potential to replace the determinations of the CCMA. Therefore, the study discusses the question whether the provision in the LRA of 1995 on the setting of thresholds of representivity for the acquisition of organisational rights and the concomitant amendments are in line with the democratic model envisaged by the Constitution, 1996 and to international labour standards which recognise the rights to freedom of association of minority trade unions. This research concludes by advancing recommendations pertaining to threshold agreements and the rights of minority trade unions and to what extent it is justifiable to permit them to enjoy them.
URI: https://repository.up.ac.za/handle/2263/68000
Keywords: Collective bargaining; Employer; Employeur; Labour Relations Act; Representatives workers

An appraisal of selected tax-enforcement powers of the South African revenue service in the South African constitutional context - Fritz, Carika (University of Pretoria, 2017)
There is tension between the South African Revenue Service’s duty to collect taxes on the one hand, and its duty to respect taxpayers’ rights on the other. An environment where there is clearly respect for the rights of the taxpayer may indeed result in increased voluntary compliance. This thesis constitutes a comparative appraisal of whether the following enforcement powers of the South African Revenue Service (“SARS”) in the South African constitutional context, namely (i) SARS’ power to conduct searches and seizures in order to verify compliance and investigate the commission of offences; (ii) the “pay now, argue later” rule; and (iii) the appointment of a third party on behalf of a taxpayer are in accordance with the Constitution of the Republic of South Africa, 1996 (“Constitution”). It is argued that these powers do not necessarily conform to the Constitution’s values and the fundamental rights contained in the Bill of Rights in Chapter 2 of the Constitution. To address the apparent shortcomings in the current dispensation, the thesis compares these enforcement powers of SARS with similar powers afforded to the revenue authorities of Canada, Australia, New Zealand and Nigeria. Important conclusions are drawn from this comparative review and a number of recommendations for law reform are proposed which, if implemented, would align these enforcement powers with the provisions of the Constitution. The recommendations entail, inter alia, that the seizure component of a search and seizure process should be treated separately, that half of the payment obligation should be suspended until the dispute is heard by an impartial forum, and that an objective measure must be in place to ensure that a taxpayer is able to afford basic necessities when a third party appointment is made.
URI: https://repository.up.ac.za/handle/2263/62233
Keywords: Recouvrement fiscal; South Africa; Tax-enforcement power

Governing activities in outer space: responsibility, liability, regulation and the role of insurers - Harrington, Andrea (McGill University, 2017)
As we have seen from the numerous high profile launch failures and accidents that have occurred between 2014 and 2016, space activities are still ultra-hazardous in nature, despite sixty-plus years of technological development. These activities range from essential to modern life (ex., telecommunications) to futuristic and forward thinking (ex., space tourism). In order for these activities to not only continue, but also develop and grow, this inherent risk must be managed.Further complicating the risk dynamic in outer space, States are required to take liability and responsibility for the activities of their nationals in space, including private entities and individuals. The reality of this relationship is that while States wish to promote the development of their domestic space industries, they will also usually require certain levels of insurance and indemnification to protect the State against potentially costly mishaps.With regard to outer space, political will is lacking at an international level to create new binding rules for activities in space. Likewise, States are reluctant to unilaterally impose stricter (even if ultimately beneficial) regulations on their entities for fear that their domestic industries will flee abroad to greener pastures, creating a regulatory prisoner's dilemma. These factors create a scenario where the major space insurers responsible for writing policies across national boundaries may be uniquely positioned to enforce or at least promote mechanisms to increase safety and sustainability in the commercial space industry. Increasing safety and sustainability in outer space may help to keep premium costs from growing out of control for these hazardous activities, as well. Thus, this thesis addresses three fundamental questions: 1)From a legal and policy perspective, is there a regulatory void that needs to be filled, at least temporarily?2)Are insurance companies in a position to be able to fill or partially fill that void?3)If so, how, and what actions can they undertake to improve their ability to execute that governance function?In answering these questions, this manuscript-based thesis explores the existing body of space law and common practices in space activities, including notable lacunae, and applies theories of "insurance as governance." This approach permits both analysis of the existing status of the industry and recommendations to increase the viability of space activities moving forward.
Identifier: https://escholarship.mcgill.ca/concern/theses/hm50tv199
Keywords: Air and Space Law; Droit des assurances; Insurance law; Insurers; Liability insurance; Liability insurer; Responsability

Special and differential treatment provisions within the World Trade Organization : the pursuit of development for developing countries - Hiine, Karabo (University of KwaZulu-Natal, 2017)
Abstract not available.
Keywords: Differential Treatment Provisions; Multilateral system; Special Treatment Provisions; Trade liberalization; WTO; World Trade Organization

China's legal obligations in the field of foreign investment : how trade agreements influence the formation of investment agreements? - Hua, Yuting (European University Institute, 2017)
Since deeper 'open-door' domestic reform in 1992, China has consistently maintained its position as the largest foreign direct investment (FDI) recipient among developing countries. In recent years China is going global as well. Accompanied with a large amount of outbound FDI, the level of debt is also increasing. Thus it is necessary for China to adopt a sustainable development policy and behave based on rules. China needs to work with the world to promote a rules-based investment climate. At a multilateral level, China joined the World Trade Organization (WTO) in 2001 and promised general and specific obligations on market entry and non-discrimination principles. Bilaterally, only after 2001, China has started negotiating preferential trade agreements (PTAs). The first part of the thesis analyses China’s legal obligations in investment agreements in pre- and post-WTO entry phases. Chapter 1 introduces China’s investment policy before 2001. Chapter 2 clarifies China’s commitments on non-discrimination principles under the WTO agreements, especially China’s Protocol of Accession. Chapter 3 compares Chinese BITs and PTAs with regard to investment principles. The second part of the thesis concerns interpretation on substantive and procedural provisions. Chapter 4 tries to answer the question of whether and how do tribunals consider jurisprudential concepts developed in the case law of the trade regime when resolving investment cases. Chapter 5 examines different remedies in trade and investment agreements. It is important for China to keep compliance with its commitments in international agreements, otherwise, it would face countermeasures which are highly costly. Also, China can implement competition rules in its domestic market for improving firms’ efficiency. Meanwhile, a balancing approach which emphasizes corporate social responsibility is equally important for China’s companies going global.
Keywords: Foreign investment; Foreign trade regulation; WTO; World Trade Organization

The African Union and the Development of African International Criminal Law - Kahombo, Balingene (Freien Universität Berlin, 2017)
This study is situated in the context of the regionalisation of international criminal law. It deals with the development of African international criminal law under the aegis of the African Union (AU). It aims to examine the factors which inform this development, the concept and the content of regional law so laid down for the African continent. The primary objective has been the exploration of theoretical and practical bases for the establishment of a viable system of African regional criminal justice in order to deal with crimes against peace and security in Africa, which put in danger African regional public order. The thesis also examines the relationship between African international criminal law and the global system of international criminal justice, currently dominated by the International Criminal Court (ICC) and the United Nations Security Council. The systemic analysis of these different issues have enabled to reach three main conclusions. First, the development of African international criminal law is not simply a conjectural consequence of the crisis observed within global international criminal law. It is also and chiefly the result of the policy of self-reliance of the AU and its member states aiming to protect and defend African regional public order through the recourse to regional institutions of criminal accountability. Second, the African Union is consequently promoting a system of African regional criminal justice based on three optional models of justice, namely the delegation of jurisdiction to a member state, the creation of hybrid courts with participation of regional judges and the establishment of a regional criminal court. Together with those crimes against peace and security that are of specific concern to the African continent, these models of justice form the core of the content of African international criminal law. However, the viability of the system towards delivering efficient justice remains problematic. There are numerous challenges to overcome, including ratifying the Malabo Protocol of June 2014 instituting the “Criminal Court of the African Union”, promoting judicial cooperation of African states and finding financial resources to support the Court’s actions. Third, African international criminal law is not a replacement of global international criminal law in the continent. There is rather a coexistence of norms and institutions which commands a certain degree of coordinated relationships to avoid competing actions and so inefficiency of justice. This thesis discusses two main approaches to consistent relationships between African regional criminal law and the global system of international criminal justice, namely the hierarchical model and the cooperative approach. It proposes a third alternative approach, that is, the regionalisation of the ICC in conjunction with the principle of regional territoriality.
Keywords: African Court of Justice and Human and Peoples' Rights; African Union; International Criminal Court; International Criminal Law; Regional Territoriality; Regionalisation; Universal Jurisdiction

Sustainable biofuel regulation and production in the SADC region : a comparative analysis - Kandala, Lupwana Jean Jacques (University of Johannesburg, 2017)
Keywords: Biofuel; Biomass energy; SADC

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

Recognition and enforcement of foreign judgments : proposals for OHADA - Kazadi, Nshingu (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
University of Johannesburg Institutional Repository (UJ IR)

Trade, labour and sustainable development: an integrated perspective - Khan, Zobaida (McGill University, 2017)
Some contemporary challenges for global trade regulation and labour governance arise from the barriers between questions of law and social justice, and development policy and distributional issues. This thesis attempts to address some of these regulatory or governance challenges by exploring the interactions between sustainable development (SD), trade regulation, and social or distributive justice. Borrowing from multiple disciplines, i.e. law, international relations, and development economy, and focusing on the problems of low-income countries, this thesis examines the potential and importance of a broad ideational objective in introducing transformative changes in different regulatory or governance mechanisms. This thesis does not discuss ways to link trade regulation or labour governance with SD; rather here the possibilities of operationalizing SD, within the global trade regulatory site or transnational governance mechanisms, are explored from a capability perspective. It is argued that a capability-based understanding can resituate some questions on trade-SD interaction and introduce important behavioural changes in the functioning of the World Trade Organization (WTO). Yet, ongoing operationalization of capability-based SD requires effective market complementary interventions from governance mechanisms operating at different spaces and with diverse actors. Certain emerging transnational governance mechanisms, which connect broader social or distributional issues such as labour governance with trade opening or economic cooperation, attempt to provide crucial market complementary interventions. Taking examples from the recent transnational safety initiatives for Bangladeshi garment workers and relying on a broad conceptualization of the social or distributional issues, it is argued that attention to capability enhancement produces a much more compelling form of labour governance mechanism at these hybrid sites. With a focus on capability-based SD, a model of transformative linkage is proposed for effective labour governance. The model demands that fundamental and redistributive rights of labour are interconnected and appropriate labour governance requires a stronger form of corporate responsibility. Analyzing the interaction of diverse rules, governance processes and mechanisms, with the demands of marginalized forces the global hegemony of capital is juxtaposed with available options and possible alternatives.
https://escholarship.mcgill.ca/concern/theses/g158bk90k
Keywords: Corporate Social Responsibility; Labour; Social justice; Sustainable development; Trade regulation

International Arbitration - Liatowitsch, Manuel; Rosenthal, Jeffrey; Forneret, Martine; Scherker, Emily; Ashford, Peter; Janzik, Sabrina; Weldon, Matthew; Houston, Robert; Boog, Christopher; Gottlieb, Benjamin; Meijer, Gerard; Verberne, Valerie; et al. (The Year in Review, 2017)
Keywords: Arbitration; Dispute resolution; International Law

Three Essays in Bank Financial Reporting - Liu, Yi (McMaster University, 2017)
This thesis investigates three important issues on bank financial reporting quality: 1) the impact of banks’ retail versus wholesale funding structure on their earnings quality, 2) the implications of economic and monetary policy uncertainty for banks’ earnings opacity, and 3) the relationship between banks’ bad time history and accounting conservatism. In the first essay, we examine the implications of banks’ funding strategies for banks’ earnings quality. We find that banks’ greater reliance on retail deposits over wholesale funds is negatively and significantly associated with the magnitude of earnings management through discretionary loan loss provisions, the likelihood of meeting-or-beating earnings benchmark, and the extent of income smoothing through loan loss provisions. This finding is consistent with the arguments that retail deposits are relatively more stable and information-insensitive, represent a more conservative business model, and attract more intensive monitoring from the Federal Deposit Insurance Corporation (FDIC) than wholesale funds, thereby improving banks’ financial reporting quality. In the second essay, we investigate whether economic and monetary policy uncertainties affect banks’ earnings opacity. When economic and monetary policies are relatively uncertain, it is easier for bank managers to distort financial information, as unpredictable policy changes make assessing the existence and impact of hidden “adverse news” more difficult for investors and creditors. Policy uncertainty also increases the fluctuation in banks’ earnings and cash flows, providing additional incentives for bank managers to engage in earnings management. Our results show that uncertainty in economic and monetary policy is associated with greater magnitude of discretionary loan loss provisions, higher likelihood of just meeting-or-beating the prior year’s earnings, and lower levels of accounting conservatism, suggesting that economic and monetary policy uncertainties lead to higher banks’ earnings opacity. In the third essay, we examine the impact of banks’ bad times on the conservatism of accounting policy. Specifically, we investigate two types of bad times: banks’ own past experiences of undercapitalization and their experiences of witnessing the failures of other banks in state-wide and county-wide crises. We find that both types of banks’ bad times are positively related to timelier recognition of earnings decreases versus earnings increases in accounting income. We also find that following exposure to bad times, banks increase their allowance for loan losses. Collectively, our results suggest that bank-specific bad times and macro-level banking crises lead to greater bank accounting conservatism. These findings support the arguments that banks exposed to past crises overweight their bad time history, and become more cautious and pessimistic about their future earnings performance and loan quality.

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
https://escholarship.mcgill.ca/concern/theses/12579v86z
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

A critical analysis of the fiduciary duties of directors and evaluation of the development of these duties in terms of the common law and statutory law - Mdunge, Mzwendoda Smiso Patson (University of KwaZulu-Natal, 2017)
Corporate law is based on the premise that directors are fiduciaries of their companies. This is an unbending duty which has to be adhered to at all cost by individuals appointed as directors of a company. Previously the director’s duties were governed by the common law which often relied on the interpretation of the courts on a case by case basis. Therefore the courts would often arrive at different conclusions based on a similar set of facts. The advent of the 2008 Companies Act (Act 71 of 2008)1 brought about a major evolution in South African company law by partially codifying the fiduciary duties of the directors. Understanding fiduciary duties of a director is of significant importance in the modern democracy based on the fact that directors engage on the international spectrum. Company directors have discretionary power which may be abused if they are not familiar with the fiduciary duties. This study seeks to comprehend fully the fiduciary duties of a director of a company. These are the duty to act bona fide, the duty to act for a proper purpose, the duty to avoid conflicts of interest and the duty not to use a corporate opportunity and information for personal profit. This task will be undertaken both in terms of the common law as well as statute (Companies Act 2008 Act). The study will delineate the fundamental consequences of partial codification of these duties and set out the current legal position of the common law which operates in tandem with the statute. In addition, it will deal with whether the common law provisions are still applicable side by side with the statutes. The duties of a company director represent a subject that is not merely academic in nature, but one that is of vital importance in our ever changing commercial world. More and more people are appointed as company directors every day and often they do not know or understand the implications of what they have agreed to.
Keywords: Common law; Companies Act 71 of 2008; Corporate law; Duties of directors; Duty to act in good faith; Fiduciary duties

Contractual regulation : infusing the law of contract with constitutional values - Ndlebe, Zithulele Fikile (University of Johannesburg, 2017)
The Constitution of the Republic of South Africa is the supreme law in the land. Thus, all law is subject to the Constitution and this inevitably includes the law of contract. The South African law of contract has been inherited from common law, namely Roman–Dutch law and has been applicable in South Africa to date. The Constitution states that the common law should be developed when it is not in line with the provisions of the Constitution. The values underpinning the Constitution are human dignity equality and freedom and these values must therefore be reflected in contractual relations. The common law principle of pacta sunt servanda, which means that agreements must be kept, at times this principle yields unjust and unreasonable results. The strict adherence to pacta sunt servanda has led to difficulties. The unenforceability of these contract terms has been shown in reported case law to stem from standard term contracts, unequal bargaining power and from persons who contract out of necessity. This dissertation concludes that South African law of contract and the current legal treatment of balancing contract law with constitutional values is unsatisfactory. The Bill on the Control of Unreasonableness, Unconscionableness, or Oppressiveness in Contracts or Terms which was tabled in 1998 should be revised and legislated, so as to regulate contracts and infuse the law of contract with the constitutional values of human dignity, equality and freedom.

The impact of leadership styles on organizational performance - Nzimande, Sandile Jerome (University of KwaZulu-Natal, 2017)
Many contemporary private and public enterprises have been hit by scandals and underperformance which have been linked to organizational leadership. This study therefore sought to establish the impact of leadership styles on organizational performance. Leadership and organizational performance crises that have rocked institutions such as Eskom, the South African Broadcasting Corporation and the South African Airways, Steinhoff, Enron and others necessitated the study. The study focused on MBA year three students (class of 2017) at the University of KwaZulu-Natal. The assumption has been that since these are masters’ students, they have once been exposed to various leadership styles, some of them are leaders, all have studied leadership styles and therefore likely to understand how these styles impact on organizational performance. This is a quantitative study. The total population was 140 students of which a total of 100 were targeted. Simple random sampling was used. Most of the participants revealed that there is a significant link between leadership styles and organizational performance. They unanimously agreed that there is definitely a noteworthy relationship between leadership styles and the organizational performance. The respondents also revealed that transformational leadership style is the most complimentary leadership style to organizational performance followed by strategic and open leadership styles respectively. Participants agreed that toxic leadership style and autocratic leadership style are undermining the organizational performance. It is therefore recommended that organizations ensure continuous checks on leadership in order to ensure that available leadership can assist in the realization of organizational goals. In addition, it is also recommended for organizations to assess the "type" of a leader in terms of leadership styles before he/she is promoted to take leadership roles in the organization in order to make proper placements. This will allow the organization to assess whether that type of a leader is suitable for the organization. Future research is needed on how models can be developed on how to make proper placements to leadership levels/roles. Research should also focus on how leadership styles dovetail with other organizational efforts that are meant to boost organizational performance.
URI: https://researchspace.ukzn.ac.za/handle/10413/21460
Keywords: Leadership styles; Organizational performance; Private enterprises; Public enterprises

Document Production and Disclosure in Investor-State Arbitration - Oepangat, Dioputra Ilham; Janet, Janet (Juris Gentium Law Review, 2017)
It is not uncommon for states to engage in arbitration proceedings with their investors (“Investor-State Arbitration” or “International Investment Arbitration”) administered under the International Centre for the Settlement of Investment Disputes. When these parties engage in document production during evidentiary proceedings, there arises an issue with regards to documents requested by the investor, which is considered as a “state secret” by the state. Based on the IBA Rules on the Taking of Evidence in International Arbitration (“IBA Rules”), states may have particular interest to refuse the production of a document. This is based on the argument that a document may be exempted from production if the document qualifies as a state secret by virtue of Article 9 of the IBA Rules. This paper will discuss appropriate measures to be taken by tribunals in order to allow for material and relevant evidence to be produced during proceedings, which may be crucial in being able to prove the case of the investor in the case of a conflict pertaining to the production of documents containing state secrets.
Keywords: Arbitrage; Arbitragem; Arbitration; Disclose; Document; IBA; ICSID; International; Investments; Prove; Secrets; Sensitive

Institutional and Contextual Factors Effects on Entrepreneurship in Cameroon: The Case of the Transport Sector - Okah-Efogo, Françoise; Okah-Atenga, Crescence Marie-France (Entrepreneurship in Africa, 2017)
In Africa, whatever the considered age group, there are more entrepreneurs in the early stages of entrepreneurship than anywhere else in the world (Global Entrepreneurship Monitor (GEM) Report 2014). According to the gem survey (2014), 55.57 per cent of the population between 18–64 years expresses entrepreneurial intentions in Cameroon. Similarly, 37.4 per cent of the same age population is in the early course of their business activity. Between 2014 and 2015, total entrepreneurial activity has decreased in Cameroon (from 37.4 per cent to 25.4 per cent of all adults). Nonetheless, 61.1 per cent of the respondents think that entrepreneurship

Virtual property : towards a general theory - Pałka, Przemysław (European University Institute, 2017)
The primary contribution of the thesis is a theory enhancing the legal understanding of the phenomenon of virtual property, encompassing presentation of data and a new conceptual framework to interpret it. The author argues that the normative debates concerning the phenomenon have underestimated the importance of understanding and conceptualizing it first, and aims at amending this gap. The ‘virtual property phenomenon’ refers to the users of internet platforms and online computer games ‘possessing’ virtual items – digital objects that exist within these services – and getting into economic and social relations concerning these items, with other users, service providers and third parties. These relations are regulated by different types of service-specific rules – contractual and the ‘code’ – created unilaterally by the service providers, who additionally retain the ability to interpret and enforce them, using ‘digital force’, i.e. by modifying and deleting virtual items, and blocking users’ accounts. The primary challenge stems not from the fact that the phenomenon is not regulated, but from the fact that lawyers lack words – terms and concepts – to even conduct a meaningful debate about it, or how to respond to it. The thesis consists of six chapters. Firstly, the author describes the phenomenon and analyzes the theoretical and regulatory legal challenges posed by its emergence. Secondly, he critically assesses the state of the art. Thirdly, a methodology to address these challenges is proposed, which can also be used in other research projects concerning law and technology. Fourthly, the author explains how the process of digitalization has fundamentally challenged the assumptions that private law held about the structure of reality, and proposes new doctrinal tools to conceptualize it. Fifthly, the author presents a legally useful concept of virtual items, and argues that granting users property rights over them might not be the optimal means of realizing the property goals. Finally, the author proposes a normative solution, a correction of private law, responding to the new type of inequality in relations, namely a user protection law.
Accepted: 2017-12-21T14:08:02Z
Keywords: Computer games; Internet; Possession (Law); Property

Libraries in the digital renaissance law and policy for book digitization - Panezi, Argyri (European University Institute, 2017)
This dissertation examines the phenomenon of book digitization and the legal challenges for the creation of digital libraries. It explores whether the current copyright framework supports libraries in the digital era as they strive to remain the institutional guardians of our literary treasures. The thesis hypothesis is that the current framework is unsuccessful or inadequate in supporting libraries. To test this hypothesis and identify the legal inefficacies the dissertation examines context, i.e. the history and rationale for applying copyright rules to books and libraries, the copyright rules as applied to libraries before and after digitization was possible, various digitization projects and the practical challenges that digitization brought about, and, the relevant litigation which has started on both sides of the Atlantic covering over a decade now. Furthermore, the thesis explores normative directions of copyright rules, including their exceptions, applicable to libraries in the digital era. It ultimately proposes that among various players claiming this role, libraries, given their institutional functions and capabilities, should be attributed rights to digitization and a favorable legal framework for providing access to digital material.
Accepted: 2018-01-08T09:36:41Z
Keywords: Copyright; Digital libraries; Electronic data processing; Electronic information resources; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.

Consumer arbitration in South Africa and its effect on the consumer's right to redress and enforcement - Rantsane, Ditaba Petrus (University of Pretoria, 2017)
The thesis entitled "Consumer arbitration in South Africa and its effect on the consumer‘s right to redress and enforcement" notes with concern the outdated and inadequate nature of the Arbitration law currently applied in South Africa. The fact that the Act was enacted in 1965 and has never been amended highlights the desperate need to review the prevailing arbitration law with a view to aligning it with the current needs of the business world. The thesis addresses the concern that consumers are not adequately protected by the current arbitration law and thus substantially develops the discourse on the topic of arbitration in situations of unequal bargaining power. It raises three primary research questions in this context. The first question reads thus, if private arbitration is properly conducted should it still provide the parties with the envisaged benefits? Secondly, is private arbitration constitutional, especially as it impacts upon consumers‘ contracting with large corporations? Thirdly, is the private arbitration process as it is currently applied, constitutional as far as it denies parties an appeal on merits against an award that is clearly wrong? The thesis attempts to answer these questions and offer recommendations for the South African Law Reform Commission (SALRC) within the specific context of commercial arbitration. In addressing these research questions, the thesis incorporates a brief overview followed by a detailed discussion of the Arbitration law framework in South Africa and abroad. The discussion of arbitration abroad is done in order to identify best practices, which could be adapted to suit the South African environment. International Arbitration law receives attention and a few observations regarding how selected foreign jurisdictions treat arbitration. Finally, the thesis explores the possibility of establishing an independent institution that will be fully equipped to handle arbitration proceedings from inception to completion.
URI: https://repository.up.ac.za/handle/2263/67886
Keywords: Consumer arbitration; Consumer rights

Non-discrimination in international economic law - Risvas, Michail (University of Oxford, 2017)
This thesis examines the jurisprudence of the World Trade Organization (WTO) Panels and Appellate Body (AB) and investment tribunals on non-discrimination clauses contained in the WTO agreements and investment agreements respectively. The thesis puts forward an alternative conceptual perspective through which the interpretation of non-discrimination provisions in international economic law could be analysed. It is argued that nondiscrimination obligations (as every legal rule to a greater or lesser extent) are inherently indeterminate. This is a fortiori the case in regard to non-discrimination provisions due to their link to the concept of equality. The concept of equality is open-ended and value-laden: its content depends on the prioritisation of different values. Thus, equality in the economic sphere can accommodate different conceptions which reflect different ideological approaches in relation to regulation, economic development and the proper role of the State in the economy. International courts and tribunals enjoy broad discretion in selecting which conception of equality to adopt when interpreting non-discrimination clauses. This indeterminacy is a positive characteristic of international economic regimes. Both the WTO and the investment arbitration regime are equipped with institutional characteristics which enable the contestation of different ideological approaches and promote pluralism. In the WTO context, this role is fulfilled by the institutional structure of the organization which facilitates the dialogue between the WTO members and the WTO Dispute Settlement System. In the realm of international investment arbitration, the mechanism of party-appointed arbitrators, despite its shortcomings which can be addressed, ensures value pluralism.
https://ora.ox.ac.uk/objects/uuid:23e7e195-c657-46d0-9a21-bde0c793dc45

Creditors' rights in business rescue proceedings in terms of South Africa's Companies Act 71 of 2008 - Rugumamu, Victor William (University of KwaZulu-Natal, 2017)
The focus of this study is the protection of creditors’ rights in South Africa’s statutory business rescue regime provided for in Chapter 6 of the Companies Act 71 of 2008. In this analysis, three issues in particular are addressed in depth. The first is the creditors` power to initiate the business rescue process. The second is the position of creditors between the commencement and the termination of the business rescue process. The third issue is to suggest (on the basis of experience drawn from reported case law and academic criticism of the current business rescue statutory provisions) an improved model that will more effectively safeguard creditors’ rights in South Africa’s business rescue regime. In exploring these issues, I give a critical review of pertinent literature. With respect to the first issue, I conclude that the legislative provisions granting creditors the right to seek a court order initiating the business rescue process are open to criticism. By contrast, a resolution of the board of directors for the commencement of business rescue is a simpler route. With regard to the second issue I conclude that the company’s creditors have considerable influence in the business rescue process. Overall, the current statutory business rescue regime is intended to give a voice to all major stakeholders in the company’s continued solvent existence. In the event of certain irresoluble disputes in the course of that process, the judiciary has the final say. A substantial number of judicial decisions have provided interpretations of the statutory provisions, and the trend has been to try to restore financial ailing companies to solvency and viability where there is a reasonable prospect for success in this regard. In my conclusion, I propose a legislative model that seeks to strike an optimum balance between the competing and sometimes conflicting interests of the various interested parties and I suggest reforms directed at enhancing the protection of creditors’ rights. This thesis takes account of South African legislation and legislative amendments as at 31 December 2016 and of decisions of the South African courts up to and including those handed down during April 2017 and reported in the saflii on-line law reports. Since a substantial part of this thesis was written from outside South Africa, the author relied heavily on the safllii data base of judgments of the South African courts, rather than on hard copy law reports which take time to reach their destination by post.
Keywords: Financial distress; Liquidation; Rationale for business existence

The compatability of the restatement second of the conflict of laws and South African private international law with Article 2(2) of the Hague Principles on Choice of Law in International Commercial Contracts - Seckel, Ashely Zwelinhle (University of Johannesburg, 2017)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Integrating healthcare quality concerns into a competition law analysis : mission impossible? - Stavroulaki, Theodosia (European University Institute, 2017)
Healthcare markets have started being created in Europe. Indeed, some European countries, such as the UK and the Netherlands, have started adopting the choice and competition model for healthcare delivery. Taking as a starting point that as health systems in Europe move towards market driven healthcare delivery, the application of competition law in these systems will increase, the goal of this doctoral thesis is (a) to identify some of the competition problems that may be raised in light of the reality that especially in hospital and medical markets the pursuit of competition and the pursuit of essential dimensions of healthcare quality may inevitably clash (b) to demonstrate that competition authorities would be unable to address some of these competition problems if they did not pose and address a fundamental question first: how should we define and assess quality in healthcare? How should we take healthcare quality into account in the context of a competition analysis? In delving into these questions, this doctoral thesis explores how the notion of healthcare quality is defined from antitrust, health policy and medicine perspectives and identifies three different models under which competition authorities may actually assess how a specific anticompetitive agreement or hospital merger may impact on healthcare quality. These are: (a) the US market approach under which competition authorities may define quality in healthcare strictly as choice, variety, competition and innovation (b) the European approach under which competition authorities may extend the notion of consumer welfare in healthcare so that it encompasses not only the notions of efficiency, choice and innovation, but also the wider objectives and values European health systems in fact pursue (c) the UK model under which competition authorities may cooperate with health authorities when they assess the impact of a specific transaction on healthcare quality. The thesis identifies the main merits and shortcomings of these models and emphasizes that what is crucial for the adoption of a holistic approach to healthcare quality is not only the model under which healthcare quality is actually integrated into a competition analysis but also competition authorities’ commitment to protect all dimensions of this notion.
Accepted: 2018-01-08T08:10:01Z
Keywords: European Union countries; Medical care; Medical laws and legislation; Medical policy; Unfair competition

Problems regarding exemption clauses in consumer contracts : the search for equitable jurisprudence in the South African Constitutional realm - Tembe, Herman C. (University of Pretoria, 2017)
URI: https://repository.up.ac.za/handle/2263/65730
Keywords: Consumer contracts; Exemption clause; South Africa

The responsibility of private actors in the internal market : private actors taking over? - Trommer, Jan (European University Institute, 2017)
The picture presented and often referred to in EU internal market law and legal scholarship is clear. Within the internal market private actors are the recipients of rights and public authorities are constrained in their (regulatory) powers. The notion of this new individualism is bound up with capacities, powers, and resources that empower private actors to engage in the internal market and cross-border situations; ultimately serving the objectives the internal market seeks to attain. Yet, within thinew individualism a conceptually different class of private actors has emerged that is constrained in economic freedoms, i.e. through obligations, rather than being empowered in the context of the internal market. This thesis will enquire the reasons that led to the development of this counter-culture. Why did it emerge? To what extent does this phenomenon affect the roles of private actors in the internal market? I will demonstrate that under the counter-culture private actors are responsibilized and transformed into ‘competent authorities’, i.e. alternative forms of regulatory authority, in the internal market. Private actors are placed into systems of shared responsibilities the relationships of which are coordinated by EU internal market law. In this regard, the concept of responsibility will serve as a tool to bridge the gap between the new positions EU internal market law allocates to private actors and the emerging legal consequences, i.e. allocation of obligations or tasks. The legal contexts of EU free movement law, EU discrimination law, EU food safety law and EU data protection law will serve as case studies against which the construed conceptual framework will be tested. Under the counter-culture the new individualism is no longer only about the exercise of self-interests. Rather, this form of the new individualism comes with a requirement to give account to the interests of other actors within the internal market.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

East African Community Law: Institutional, Substantive and Comparative EU Aspects - Ugirashebuja, Emmanuel; Ruhangisa, John; Ottervanger, Tom; Cuyvers, Armin (Brill, 2017)
East African Community Law provides a comprehensive and open-access text book on EAC law. Written by leading experts, including the president of the EACJ, national judges, academics and practitioners, it provides the most complete overview to date of this increasingly important field. Uniquely, the book also provides a systematic comparison with EU law. EU companion chapters provide concise overviews of EU law and its development, offering valuable inspiration for the application and further development of EAC law. The book has been written for all practitioners, judges, civil servants, academics and students faced with questions of EAC law. It discusses institutional, substantive and jurisdictional issues, including the nature of EAC law, free movement and competition law as well as the reception of EAC law in Partner States.
Keywords: Comparative law

Identification of the parties to the employment relationship: An appraisal of teleological interpretation of statutes - Van Staden, Marthinus Jacobus (University of Pretoria, 2017)
The study, entitled “Identification of the parties to the employment relationship: an appraisal of teleological interpretation of statutes”, is a legal-interdisciplinary doctrinal investigation situated within the fields of labour law and the interpretation of statutes. It concerns itself with the proper interpretation of labour legislation in general and the interpretive question as to who should be party to the employment relationship in particular, within the context of the advent of constitutionalism and the proliferation of and the increase in the importance of labour legislation. In law, meaning-generation is a function of statutory interpretation and every application of a text to particular circumstances entails interpretation. The protection extended by labour legislation is only extended to those persons who are defined as “employees”. The study describes the teleological model of statutory interpretation, which aims to give effect to the purpose of a legislative provision in light of constitutional values. The study explores the five elements of (teleological) interpretation that should be considered when interpreting concepts such as “employee”: the text, the context, the telos (or values), the history and the comparative dimension. The chief findings of the study includes: that legislation has become an indispensable source of contemporary labour law; that the courts have adopted a teleological approach to the interpretation of statutes; that the courts have, in interpreting the term “employee”, adopted a teleological approach to the interpretation of statutes; and that the interpretations advanced by the courts have not had the profound effect envisaged by the Constitution on the transformation of society.
URI: https://repository.up.ac.za/handle/2263/65631
Keywords: Employment relationship; Labour law; Parties

The international legal framework on business and human rights and its domestic operationalisation : strategic litigation on mining and a healthy environment in South-Africa - Verdonck, Lieselot (Ghent University, 2017)
The debate on business and human rights attracts the interest of many parties, and regularly makes the headlines. On 19 January 2017 De Morgen, for instance, ran the following headline: “These banks do business with companies that violate human rights and nature”. The discourse suggests that few question that business enterprises should respect human rights. The legal meaning and consequences of associating 'business' with 'human rights' remain contentious, however. By clarifying the existing legal framework this thesis seeks to rationalize the debate. Special attention is paid to enforcing the responsibility of business enterprises for human rights through domestic judicial remedies. The analysis is concretised through a case study on adverse human rights impacts of environmental degradation caused by mining in South Africa. Based on the findings of the study, the thesis reflects on how the international legal framework on business and human rights should be developed further.
http://hdl.handle.net/1854/LU-8535402
Keywords: Business; CSR; CSR disclosure; Human rights; International law; RSE; South Africa

Can third party funding deliver justice in international commercial arbitration? - Yu, Hong-Lin (International Arbitration Law Review, 2017)
Third party funding arrives at international commercial arbitration without clear guidelines. The recognition and acceptance of its legality is hampered by the omissions of all stakeholders' rights involved in international commercial arbitration. In balancing the funder’s contractual rights to gather information under the third party funding agreement and stakeholders' rights to know, the current research examined how non-disclosure of the third party funding agreement would prevent the arbitrators from fulfilling procedural justice required for the integrity of arbitration on their part and impede the opposing party’s right to know during the proceedings. The research highlights the issues from the delivery of procedural and substantive justice as well as suggesting legal and jurisprudential grounds in third party funding governance. It also points out that all issues examined will ultimately contribute to the failure in delivering justice in international commercial arbitration if third party funding is left to self-governance.
Keywords: Arbitration; International commercial arbitration; Third Party Funding

The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
https://uir.unisa.ac.za/handle/10500/23172
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

The stakeholder theory of corporate control and the place of ethics in OHADA: The case of Cameroon - Sama-Lang, Irene; Zesung, Njonguo Abel (African Journal of Business Ethics, 2016)
The rapid increase in globalization in the last two and a half decades has caused businesses to easily transcend national boundaries. States respond to such flexibility by harmonising their laws to easily adapt to such changes in order to attract investments. This is the case with the OHADA jurisdiction where its architects foresaw an economic spur through integration of business laws. Though expected to stay within the bounds of the law, the law cannot absolutely determine how businesses should prioritise their stakes. As such, ethics comes in to complement the law. This article uses the stakeholder theory of corporate control to investigate the place of ethics in OHADA, as applied in Cameroon. It concludes that an altruistic social conscience is still highly wanting.
Keywords: Business; Corporate control; Corporate law; Ethics; OHADA; stakeholder

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

Tax Mobilization in Sub-Saharan Africa: The Impact of Tax and Business Law Reforms - Bertinelli, Luisito; Bourgain, Arnaud (Economics Bulletin, 2016)
This paper contributes to measuring the influence of business (and tax) law reforms on sub-Saharan African countries tax mobilization ability. Relying on a new business law reform indicator, our results validate the significant impact of corporate law modernization on governmental revenue, and unearth a complementary effect between business and tax law reforms.

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Force Majeure, Change of Circumstances and Termination of Contract - Han, Shiyuan (Journal of Law, Society and Development, 2016)
It is impossible to draw a distinct line between force majeure and change of circumstances, because the two overlap. In order to regulate both force majeure and change of circumstances, the United Nations Convention on Contracts for the International Sale of Goods (CISG) has adopted a unified model in article 79, whereas Chinese law adopts a dual model by treating them as different things and regulating them in different articles. Where the purpose of a contract becomes impossible to achieve because of a force majeure and both the CISG and Chinese Contract Law (the CCL) adopt the same model of termination of the contract, the contract should be terminated by one party with a notice to the other party instead of ipso facto avoidance. In a case of a change of circumstances, in order to terminate the contract, both the CISG and the CCL actually follow the path of raising an action by a notice of avoidance or termination to theother party. Both approaches have their merits and demerits but the differences between them in practice are not as large as presumed. Where force majeure and change of circumstances overlap each other, possible ways for termination of the contract are for a party either to choose their preferred solution or to follow the lex specialis derogat generali. The latter way is preferred in this article; and while in an action for termination the judge may balance the interests of both parties in making a final decision, the uniform application of the law, the safety of the transaction and the fairness of the judgment may be ensured in so doing.
Keywords: CISG; Change of circumstances; Chinese Contract Law; Force majeure; Gestaltungsklagerecht; Termination

Oil in the Gulf of Guinea States and South Africa in the Matrix of Overlapping Membership of African Regional Communities: An Impediment to Regional Integration? - Jobodwana, Zingisile Ntozintle (Journal of Law, Society and Development, 2016)
The Gulf of Guinea states (GOGs) discussed in this article comprise a diverse group of more than 20 African states bordering on the oil-rich Gulf of Guinea. They are former colonies of Belgium, France, Great Britain and Germany. These states are of strategic importance to the United States, the European Union, India and China because of their tremendous natural resources that include biodiversity, oil, gas and other strategic minerals. But to what extent are they also of strategic importance not only to South Africa but to SADC member states? After all, the GOGs boast of their sea routes being safer and more convenient for sea transport. Post-colonial independence finds these states still adopting a mixture of foreign legal systems side by side with indigenous laws and customs. The region is still underdeveloped, with poor physical infrastructure, weak government structures, an inefficient legal system, and internecine strife and other inter-state disputes exerting a debilitating influence. The NEPAD Plan of Action of 2001 looks to the regional economic communities (RECs) to become the leaders in regional economic co-operation and integration. Although the GOGs are characterised at present by overlapping membership of various communities, they have enjoyed some successes based on the newly found petroleum commodity which, wisely managed, can help to increase intra-African trade and produce a viable extensive African market buttressed by South Africa's economic advances into the rest of Africa. In some of the regions in Africa RECs such as ECOWAS and SADC have been able to transform their economic and monetary co-operation efforts into a powerful driving force for economic policy co-ordination and integration, but a strong, credible, effective and efficient legal framework with sustainable supporting institutions is now needed. South Africa is well poised to assist with deepening the political and economic integration in the GOGs by intensifying foreign direct investment (FDI), capacity-building and training projects, and the transfer of skills and technology. But the RECs overlapping membership needs to be rationalised, the negative influences of the superpowers need to be resisted, and support is required to maintain peace and stability and ensure the security of the maritime regimes. A strong, independent supra-national body that is also able to supervise and monitor revenues from oil for the benefit of the region as a whole should be established.
Keywords: African Union; COMESA; EAC; ECCAS; ECOWAS; Gulf of Guinea Commission; Gulf of Guinea states; OHADA; Overlapping membership; Regional economic communities (RECs); Regional integration; SACU; SADC; South Africa; Supra-national independent regiona; Treaties

The Attitude of OHADA Law Countries Towards the CISG - Kahindo, Nguru Aristide (Journal of Law, Society and Development, 2016)
Disparities in national laws are likely to result in uncertainty which, in turn, creates obstacles to international commerce. It is acknowledged that strong investment flows cannot be achieved without a secure legal and commercial environment. Mindful of such a need, states decided to harmonise sales law internationally. To this end, in 1980 they adopted the United Nations Convention on Contracts for the International Sale of Goods known as the Vienna Sales Convention or the CISG. The CISG has led a number of countries, including the Organisation for the Harmonisation of Business Law in Africa (OHADA) law states, to modernise their local sales law. However, only three of 17 countries that constitute the OHADA community have ratified the CISG. OHADA law countries give the impression of favouring a more regional approach to the unification of sales law rather than the CISG™s global approach by implementing a local Commercial Uniform Act. Their indifference towards the CISG is not without consequences for commerce in the OHADA region. This article seeks to demonstrate that the lack of ratification of a universal convention, as for example the CISG, poses a danger to commercial dealings. It also intends to show that the CISG is not hostile to regional uniform sales laws of the OHADA Commercial Uniform Act type. It concludes that OHADA countries do not need to be afraid of their acceptance of the CISG and recommends that it be ratified.
Keywords: Business law; CISG; Commercial Uniform Act; Harmonisation; OHADA law; Uniform sales law

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
https://rgu-repository.worktribe.com/output/246435/arbitrability-and-public-policy-an-african-perspective
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

The timing of the passing of property and risk under the English Sale of Goods Act 1979, the CISG and the Libyan law: the interplay between the principle of party autonomy and the default rule - Aboukdir, Anwar (University of Stirling, 2016)
This thesis attempts to critically and comparatively analyse the issues relating to the passing of property and risk under the United Nations Convention on the Contract for International Sale of Goods (CISG) and English Law (SGA). The passing of property and risk plays a central role in the area of international legislation in relation to sales contracts. These elements can be the most significant components in contracts of sale between parties, whether in the international or domestic field. The reason is founded on their legal nature and the close relationship between them. The passing of property and risk has been a central issue for practitioners, judges and lawyers dating back to the Roman period and several ideas have been proposed to resolve it. Where the situation is different for contracts of sale in relation to the passing of property and risk, whether in the domestic or international field, it still creates many unresolved problems, because of ongoing changes in the field of modern commerce, which may contribute to unfair implications between the parties. It has been observed in this thesis that both English law and the CISG adopt the party autonomy principle, where the intention of the parties - whether in relation to the passing of property or risk - is the basic rule. However, the difference lies in the default rules. While English law involves default substitutional rules, which apply in cases where there is an absence of an expressed or implied indication regarding the intention between the parties, the CISG lacks such default rules regarding the transfer of property, which could be viewed as its main weakness, although the CISG does involve such provisions with respect to the transfer of risk. This thesis willdiscusses, the legal nature of the rules in relation to the passing of property and risk, and the role of the party autonomy principle, and the impacts and legal difficulties that might arise through the application of these rules, whether they are default rules or based on the party autonomy principle. It will also examine the legal gaps and weaknesses of both legal systems in an attempt to identify such legal difficulties and to find appropriate solutions and remedies.

Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa - Onyema, Emilia (2016)
This second conference in the SOAS Arbitration in Africa Conference series examined how African judges can better support the growth of arbitration. The conference was hosted by the The Lagos Court of Arbitration in their premises in Lagos, Nigeria from 22-24 June 2016. This conference booklet contains some of the papers and slides, and photographs from the conference.
Pages: 1-142
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Courts; Judges; Rôle; Support

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
URI: http://webcat.warwick.ac.uk/record=b3059548~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds

Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.
Number: 3

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

Integration through comparative private law: Four lessons from Cappelletti - Infantino, Marta (International Journal of Constitutional Law, 2016)
The aim of this article is to explore Cappelletti’s most enduring teachings relevant to those who promote global or regional integration of private laws. The article will review Cappelletti’s insights into the dynamic history of law, the need to respect diversity and take into account society’s imbalances, and the duty of comparative lawyers to engage in “applied” interdisciplinary legal research.

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

The OHADA Common Court of Justice and Arbitration: Exogenous Forces Contributing to Its Influence - Dickerson, Claire Moore (Law and Contemporary Problems, 2016)

Reflections on the Nexus Between Public Procurement Reforms and Economic Development in Nigeria - Okolie, Aloysius-Michaels; Nnamani, Kelechi (African Journal of Politics and Administrative Studies, 2016)
Corruption has widely been recognized as one of the impediments to the socio-economic cum political development of Nigeria. By 2000, it was observed that the conduct of government business in Nigeria had become difficult and expensive due to pervasive corruption, particularly procurement fraud. Although procurement fraud is one of the most common avenues of corruption in most countries, its incidence in Nigeria by 2000 was particularly widespread. To reverse this ugly trend, the Nigerian government initiated the public procurement reforms with a view that a corrupt-free procurement process will among other things, promote economic development in the country. Consequent upon the reform, the Public Procurement Act was enacted while the Bureau of Public Procurement was established to ensure due process, accountability and transparency in the award of government contract. In this light, this study evaluated the impact of the public procurement reforms on the economic development of Nigeria. We relied on documentary method of data collection and content analysis of data. Meanwhile, employing the basic propositions emanating from the Marxist theory of the Post-Colonial State, this study noted that the nature and character of Nigerian state undermined the procurement reform from achieving its expected goals. We however, recommended for the removal of the immunity in the constitution and strengthening of the anti-graft agencies in Nigeria.
Keywords: Corruption; Economic Development; Public Procurement; Reforms; Transparency

The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

Accountability of multinational corporations for human rights violations under international law - Mnyongani, Freddy (University of South Africa, 2016)
Jurisprudence
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights; International business enterprises; Liability for human rights violations; RSE; Social responsibility of business; Tort liability of corporations

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
https://dspace.stir.ac.uk/bitstream/1893/23090/1/Enforceability%20of%20Arbitral%20Awards%20Containing%20Interest.pdf
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.

Protection of agency workers in South Africa : an appraisal of compliance with ILO and EU Norms - Aletter, Candice Joy (University of Pretoria, 2016)
This thesis is a policy-based study of the regulation of agency work in South Africa. It is set against the contextual background of a recent legislative overhaul and an increase in the number of precarious workers. The study aims to appraise the extent to which the South African regulatory framework complies with international norms in respect of agency work. The research considers how German and Namibian regulation might improve the current model of the regulation of agency work in South Africa. The study identifies the purpose of labour law in South Africa as offering diversified rights as well as being economic in nature. The premise upon which the thesis is based is a social justice approach to the function of labour law. An analysis of ILO and EU regulations on agency work is conducted, and identifies a combined list of norms in respect of the protection of agency workers. South Africa?s labour law policy approach is explored together with the amended regulation on agency work. A comparison is drawn with foreign countries? regulations and policy approaches: the appraisal identifies shortcomings in South Africa?s regulatory model. The study focuses on the evolutionary improvement of agency workers? protection based on international approaches. The research culminates by formulating an amended model for the regulation of agency work in South Africa, in which these proposed adaptations seek to remedy the shortcomings which were observed in the appraisal process.
URI: https://repository.up.ac.za/handle/2263/60060
Keywords: Agency work; EU Regulations; ILO; Labour law; South Africa

A rights-based approach to foreign agro-investment governance in Cameroon, Uganda and South Africa - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2016)
The practice of foreign agro-investment (FAI) for the production of food crops and biofuel crops has been a recent phenomenon in sub-Saharan Africa and other developing countries. In fact, the present era of climate change has caused foreign countries to acquire vast tracts of land - often through multinational corporations - in order to propagate biofuel or expand their home industries abroad. Practices of FAI have resulted in a form of land grabbing, as local communities are often evicted from their land without their consent. FAI activities are reported to have considerable impact on people in areas where they occur, which range from environmental to social and economic impacts. There is compelling evidence that FAI land deals are not transparent and inclusive, which raises pertinent concerns with respect to participatory rights, access to information, the compatibility of property rights, environmental protection and the protection of the rights and interests of local communities generally, among other issues. The lack of respect for and protection of local communities’ rights and interests during FAI land deals and activities form the crux of this study. In this light, the overall aim of this thesis is to investigate and ascertain how the procedural aspects of a rights-based approach (RBA) could be used to provide adequate protection to local communities’ rights and interests during FAI activities in Cameroon, Uganda and South Africa. The study is premised on the notion of a RBA to FAI governance and captures the procedural aspects of the right to access to information, public participation and the right to access to justice in international, regional, sub-regional and national human rights legal regimes. It is argued that because these rights have the potential to significantly contribute towards the protection of the rights and interests of people that are adversely affected by development activities, their incorporation remains useful and relevant in the FAI context. It is further claimed that the implementation of the procedural RBA in FAI land deals could strengthen the ability and capacity of the state to increase opportunities for more meaningful dialogue with local communities, while concomitantly helping the state to fulfil its international and national obligations as a duty-bearer to respect, protect and fulfil the rights and interests of its people. In addition, procedural rights encompass elements of good governance and democracy and could be used as a necessary and vital tool to prevent a government’s exercise of arbitrary power generally and in the context of development activities. This is predicated on the belief that procedural rights serve inter alia to strengthen democratic structures and processes and to curb corruption and the mismanagement of national resources, and ultimately to promote sustainable development. In this study, it is argued that a RBA generally and its procedural aspects specifically could play an important role in setting the standards and defining the processes that are appropriate to repudiate the unacceptable impacts of FAI and simultaneously address distributive concerns with the hope of promoting and ensuring more responsible and sustainable FAI. Conversely, the absence of such a normative baseline suggests that large-scale land transfer under the guise of FAI practices would endlessly levy an unacceptable toll on the fundamental rights of the vulnerable host population. The first step in this thesis is to analysis the theoretical concepts of governance and good governance in order to establish the eventual objective of what FAI governance and good FAI governance should entail. A further component of the theoretical analysis includes an analysis of a RBA and a RBA to FAI governance. These components are investigated in order to determine a possible solution to the impacts of FAI activities from a rights-based perspective. Second, the thesis investigates and analyses the procedural aspects of a RBA espoused in international, regional and sub-regional legal regimes. It distils generic characteristics and minimum requirements of the RBA for good FAI governance to be used as benchmarks in the context of project development-related activities, including FAI. As benchmarks, the international, regional and sub-regional legal regimes provide minimum criteria to which the legal frameworks of countries must adhere to and conform with. This part also examines the procedural RBA frameworks in Cameroon, Uganda and South Africa and critically evaluates the legal frameworks in these countries against the distilled generic characteristics and minimum requirements of the RBA in terms of good FAI governance. Third, the thesis concludes with a set of recommendations on the procedural RBA frameworks in Cameroon, Uganda and South Africa. These recommendations are meant to address the current lacunae in these domestic procedural RBA frameworks, and to propose measures designed to enable a situation where the rights and interests of local communities are better protected in the event that FAI land deals are concluded.
Keywords: ACCESS TO INFORMATION; ACCESS TO JUSTICE; Foreign agro-investment; Good governance; Land grabbing; Procedural rights; Public participation; Rights-based approach

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

eAccess to Justice - Benyekhlef, Karim; Bailey, Jane; Burkell, Jacquelyn; Gélinas, Fabien (University of Ottawa Press, 2016)
Part I of this work focuses on the ways in which digitization projects can affect fundamental justice principles. It examines claims that technology will improve justice system efficiency and offers a model for evaluating e-justice systems that incorporates a broader range of justice system values. The emphasis is on the complicated relationship between privacy and transparency in making court records and decisions available online.Part II examines the implementation of technologies in the justice system and the challenges it comes with, focusing on four different technologies: online court information systems, e-filing, videoconferencing, and tablets for presentation and review of evidence by jurors. The authors share a measuring enthusiasm for technological advances in the courts, emphasizing that these technologies should be implemented with care to ensure the best possible outcome for access to a fair and effective justice system.Finally, Part III adopts the standpoints of sociology, political theory and legal theory to explore the complex web of values, norms, and practices that support our systems of justice, the reasons for their well-established resistance to change, and the avenues and prospects of eAccess. The chapters in this section provide a unique and valuable framework for thinking with the required sophistication about legal change.Published in English.

Contracts as regulation model : applications and legal implications in over-the-counter financial markets - Borowicz, Maciej Konrad (European University Institute, 2016)
We develop a conceptual model of contracts as regulatory instruments in over-the-counter (OTC) financial markets. The model is informed by the functional understanding of financial regulation as addressing problems of counterparty risk, liquidity, information and systemic risk and structural understanding of regulation as a process of standard-setting, monitoring and enforcement. The justification of conceptualization contracts as regulatory instruments is found in the nature of the political economy considerations that inform the definition of certain contracts used in OTC financial markets. While many scholars rely on conceptualization of the said contracts as boilerplate, we argue that there exist important qualitative differences between boilerplate and regulatory contracts, which we link to a broader spectrum of interests taken into account in their definition in the process of standard-setting. The model and its application to loan and derivatives markets help to highlight the impact of governance features of the organization developing the contract and the regulatory competition to which the organization is exposed on the scope of the regulatory function. We also use a number of indicators and attributions to examine the effectiveness of regulatory contracts. While the contractual model displays some weaknesses in terms of both standard-setting (conflicts of interest) and enforcement (reliance on delegation) compared to its better established counterpart – the organizational model associated with exchanges – the contractual model helps to account for important self-regulatory features of OTC financial markets and offers suggestions as to how the structure of OTC financial markets can be improved.
Accepted: 2016-06-21T15:10:25Z
Keywords: Derivative securities; Financial risk management; Over-the-counter markets

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

The CISG as a Model Law: A Comparative Law Approach - Chianale, Angelo (Singapore Journal of Legal Studies, 2016)
In this article I adopt a comparative law approach to illustrate the coexistence of various models governing the sale of goods, and their classification on the basis of two main characteristics: the transfer of property and the opposition certainty/flexibility. I use this approach to analyse the United Nations Convention on Contracts for the International Sale of Goods. 1 Then I examine how theCISG influenced several national systems and can influence future attempts at regional harmonisation. I conclude with the reasons that in my opinion make the CISG a good model for the sale of goods (prestige, equilibrium and derogability), and with the desirable future developments.

Teaching Transnational Commercial Law in the African Context - Eiselen, Sieg (University of Western Australia Law Review, 2016)

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

Collective action in comparative and empirical perspective: towards a socio-legal theory - Fortes, Pedro Rubim Borges (University of Oxford, 2016)
This DPhil thesis enhances existing understandings of collective action through a comparative and empirical study. Empirical analysis of economic, political, juridical, and social dimensions of the Brazilian experience reveals that some central understandings in existing literature are not borne out in this empirical context. In particular, the assertion that low monetary incentives for individuals hinder growth in use of collective action is strongly challenged. The Brazilian experience is contextualised through comparative analysis of three legal traditions of collective action: class actions; collective redress; and civil public actions. The Brazilian system presents a setting with potential for regulatory enforcement of consumer protection law, but rare episodes of consumer compensation or the imposition of punitive damages on corporations. With low monetary incentives, the growth of collective actions is explained by non-monetary incentives and investment in social capital through development of institutional trust and legal institutions. Collective actors develop their organisational infrastructure and perform their roles as representatives through institutional dynamics of concentration, competition, cooperation, and deference. The coexistence of multiple institutional actors in the regulatory space reduces agenda control, increases opportunities for consumer participation, and increases oversight of regulatory capture. The categories of diffuse, collective, and homogeneous individual rights explain the role of law in establishing procedural pathways and special features. This study is broadened through analysis of the legal environment and the potential regulatory impact of collective actions on the social relationships between businesses and consumers. I also evaluate limitations and possibilities regarding access to justice, judicial economy, compensation, and deterrence. This thesis indicates the possibility of developing a socio-legal theory of collective action, which would enhance our understanding of the complex dynamics at play by going beyond analysis of the consumer experience as merely an economic transaction or a legal object, analysing them instead as a complex social relationship.
Keywords: Collective action; Consumer (protection); Consumer compensation; Droit de la consommation

Private Ordering of Exit in Limited Liability Companies: Theory and Evidence from Business Organization Contracts - Gomtsian, Suren (American Business Law Journal, 2016)
https://onlinelibrary.wiley.com/doi/10.1111/ablj.12087

'You wouldn't steal a car' vs 'information wants to be free' : regulatory failure of copyright law through the prism of systems theory - Gracz, Katarzyna (European University Institute, 2016)
The thesis aims at explaining current regulatory crisis of copyright law (understood as its inability to regulate social dynamics as regards production, reproduction, dissemination of and access to information goods) through the application of systems theory. It refers to the concept of autopoietic legal system in order to draft a model representing the ecosystem in which copyright law functions. This model not only allows for observing copyright regime as it stands currently but also for analysing how it evolved over time. It scrutinises the interdependencies between the legal system and other constituent elements of its ecosystem: politics, economy, art, science, technology, religion, mass media, education as well as non-functionally differentiated segments of society: circles of relatives and friends. The main goal of this analysis is to highlight the fact that the current regulatory crisis of copyright is the result of the legal system's failure to equally acknowledge all the diverse rationalities constituting its ecosystem. The primary hypothesis of the study is that the core of the problem may be attributed to the divergence between legal norms, and competing non-legal copynorms constructed in the process of co-evolution within various elements of the model in question. In the analysis all the relevant copynorms understood as segmented social norms regulating social dynamics with respect to production, reproduction, dissemination of and access to information goods have been reconstructed to indicate their potential to oppose legal regulations. The thesis pivots around the concept of reflexive justice which refers to the equal acknowledgement of colliding rationalities. It concludes with the firm statement that copyright law in the digital environment needs profound reform. The concept of reflexive justice as developed within the systems theoretical approach is perceived by the author of this thesis as the most promising starting point for the new philosophy of copyright law.
Accepted: 2016-05-17T13:43:06Z
Keywords: Copyright; Intellectual property; Sociological jurisprudence

The Admission and Enrolment of Foreign Legal Practitioners in South Africa under the Legal Practice Act: International Trade Law and Constitutional Perspectives - Hagenmeier, Cornelius; Shumba, Tapiwa; Mireku, Obeng (Potchefstroom Electronic Law Journal, 2016)
Globalisation requires ever closer co-operation between legal professionals hailing from different national jurisdictions. This interactive global environment has fostered growing international training and mobility among legal practitioners and the internationalisation of legal education. Increasing numbers of law students get trained in other countries as part of their undergraduate degrees or even come to foreign shores to obtain law degrees. Many students hailing from other African countries study towardsLLBdegrees at South African universities. Major commercial law firms ensure that they can offer in-house expertise on major foreign legal systems and co-operate with partner firms in other parts of the globe. The General Agreement on Trade in Services (GATS), to which South Africa is a party, is a multilateral agreement focusing on the liberalisation of trade in services amongst member countries. Services under the GATS system include legal services. The commitments made by South Africa under this agreement require that South Africa allows foreign legal practitioners to establish a commercial presence or be transferred to South Africa. The Bill of Rights entrenched in Chapter 2 of the South African Constitution guarantees fundamental rights including the right to equality and freedom of trade, occupation and profession. With the coming into force of the new Legal Practice Act 28 of 2014, which provides a legislative framework for regulating the affairs of legal practitioners, including their admission and enrolment, it is necessary to assess the extent to which the Act complies with the GATS rules and the South African Constitution. This paper examines the new Legal Practice Act 28 of 2014, and examines whether the Act addresses the conflicts that have always existed between the regulation of the legal profession and the admission of legal practitioners in South Africa with South Africa's commitments under the GATS system. Using the doctrinal legal method, it analyses and evaluates the rules governing the admission of foreign attorneys in South Africa from two perspectives. First, it considers them in the light of the international law obligations of the country and second it evaluates whether or not they comply with the South African Constitution, and more specifically with the Bill of Rights entrenched in the South African Constitution. While the new legislation may assist in ensuring the compliance of South Africa with the relevant GATS rules, it will depend on the regulations which still have to be promulgated to what extent the new legal framework will achieve the full compliance of South Africa with all relevant GATS rules. The paper concludes with recommendations for the reform of the Legal Practice Act. It argues that while the requirement to be a South African permanent resident in order to qualify for admission as an attorney may be justifiable in terms of GATS and in terms of South African constitutional law, it is not in South Africa's best interest to retain it. Consequently, the paper calls for the repeal of the permanent residence requirement for admission as an attorney in the county.
Keywords: Affirmative action; Designated groups; Employment equity; Equality; Minority group; Multi layered disadvantage; Situation sensitive

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Regional Powers and Leadership in Regional Institutions: Nigeria in ECOWAS and South Africa in SADC - Hulse, Merran (KFG The Transformative Power of Europe, 2016)
Regional powers are not always benevolent leaders when it comes to the building of regional institutions. While powerful states – particularly the “new” rising powers – may have a vested interest in regionalism as a means of projecting influence, regional powers may behave as coercive or benevolent leaders, or alternatively display an absence of leadership altogether. The drivers of varying regional power behavior can be attributed to their competing concerns regarding (economic) power, functional efficiency, international legitimacy, and neopatrimonial networks. This paper explores the varying behavior of Nigeria and South Africa in relation to the institutionalization of free trade areas and regional courts within their respective regions. Nigeria has displayed little leadership in ECOWAS trade integration due to domestic opposition; however, a newly-democratic Nigeria’s search for international legitimacy drove the establishment of the ECOWAS Court of Justice. Likewise, South Africa’s search for legitimacy drove its support for the SADC Tribunal, but the competing demands of different audiences led it to abandon this support. South Africa has also displayed leadership in relation to the SADC Free Trade Area; however, its neighbors perceive it as a self-interested, almost coercive actor. The findings suggest that the motivations for regional powers’ behavior vary across time and policy sectors, and that inconsistent behavior is driven by a change in the priority granted to different drivers.
Accepted: 2018-06-08T11:13:32Z https://refubium.fu-berlin.de/handle/fub188/21860

Foreign Direct Investments and Economic Growth of African Regions: A Comparative Study - Igbinosa, Sunday O.; Ikponmwosa, Noruwa Abu (UNILAG Journal of Humanities, 2016)
The paper examines the impact of Foreign Direct Investments (FDIs)on economic growth in the five regions of Africa, as well as identifies their respective drivers of growth. It employs the Ordinary Least Squares (OLS) multiple regression analysis to examine the relative impact of Foreign Direct Investments, balance of payments, trade openness, technology and quality of labour force on economic growth in each of the five regions between 1980 and 2012. The study finds that foreign Direct Investments (FDIs) have no significant impact on economic growth in the five regions of Africa. The impact of FDI on growth is positive in Eastern, Middle and Western Africa but negative in Northern and Southern Africa. Similarly, there are differentials in the drivers of growth in the five regions. While trade openness is a negative driver of growth in all regions of Africa except in Northern Africa, both balance of payments and quality of labour force have mixed impacts on economic growth in Africa. In addition, technological progress impacted growth in Middle, Southern Africa and Western Africa but it appears that lack of it retarded growth in Eastern and Northern Africa. The study calls for policy reform frameworks that encourage and boost foreign Direct Investment flows to all regions of Africa, particularly Direct Investments in critical sectors of the economies, as well as check the negative effects of foreign Direct Investments. Furthermore, it recommends that regional economic blocks in Africa should be resuscitated and supported to develop and promote intra-Africa trade and Investments.
Keywords: African regions; Drivers of growth; Economic growth; FDI; Foreign direct investment; Investments

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

Transparency and dispute settlements : a study of the agreements on sanitary and phytosanitary measures and technical barriers to trade - Karttunen, Marianna (European University Institute, 2016)
Transparency of trade regulations by all WTO Members is essential for open, fair and predictable trade relations. Because of the negative integration process followed by the WTO Agreements, a myriad of different regulations apply in all WTO Members and have the potential of affecting international trade. With the progressive lowering of tariffs since 1947, these differing regulations remain the most significant barriers to trade, and the most difficult to reduce. The Agreements on Sanitary and Phytosanitary (SPS) measures and on Technical Barriers to Trade (TBT) provide the most comprehensive frameworks to address the costs arising from such regulatory diversity, through extensive obligations on regulatory transparency and cooperation and introducing elements of positive integration. Does transparency, within the SPS and TBT Agreements prevent disputes from rising, or ensure all Members access necessary information to raise more and better disputes? Through a presentation of the legal obligations and institutional framework of the two agreements (Part I), an in-depth analysis of the issues encountered by WTO Members in the implementation of the two Agreements and raised as trade concerns in the SPS and TBT Committees (Part II), and a study of the factors leading to disputes and transparency's role in addressing them (Part III), this thesis will demonstrate that transparency as it exists under the two agreements has the potential to both complement dispute settlement, by giving equal access to information for Members to raise disputes, and substitute dispute settlement, by fostering dialogue between Members before their frictions escalate to formal disputes. In this sense, the strength of the WTO legal and institutional system goes well beyond its dispute settlement system, with enforcement of WTO obligations fostered by better information sharing and dialogue among Members themselves, through non-judicial means.
Keywords: Food adulteration; Food inspection; Foreign trade regulation; Non-tariff trade barriers; Produce trade

Remedies for passengers for flight delays caused by force majeure - Ko, Li-Juan (McGill University, 2016)
This thesis intends to justify the necessity to propose an alternative remedy mechanism to current air carriers' obligations in offering complimentary services to passengers in force majeure delays. This mechanism mitigates disputes arising from passengers' dissatisfaction with air carriers' services. The proposal is the result of extensive research arising from a fundamental question: Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure? The source of information for this thesis stems from a combination of the analysis of case law and statutes on one hand, and experience drawn from professional practice and cultural context on the other. This thesis discusses the intersection of international conventions, national legislation, and the practice and expectations of air carriers and their passengers. The thesis specifically examines and highlights the inadequacies of relying on existing international conventions to provide a harmonized solution for flight delay claims. In terms of national remedy mechanisms, research and analysis have been focused on the advanced aviation markets in the West, such as the US and the EU, and on the emerging markets in the East, such as Mainland China and Taiwan. The research and analyses reveal how national laws, which are deeply influenced by socio-economic, political and cultural factors, trigger distinct conflicts of interest between air carriers and passengers. During the course of reviewing the legal jigsaw and uncertainties in current legal practice, the findings revealed more issues. In brief, making more laws cannot guarantee an effective solution for flight delay claims, especially in different jurisdictions. Accordingly, the findings support that a novel solution, free from the uncertainties and complexities in the current legal framework, is needed to resolve passengers' claims or expectations resulting from force majeure delays. Essentially, this novel solution is to form an alternative remedy mechanism that includes a fund and codes of conduct. The fund will implement a risk-sharing function among stakeholders that will include passengers, air carriers and airport managing entities. To mitigate disputes, the proposed codes of conduct will include guidelines to operate the fund with the aim of mutual respect between passengers and air carriers. In so doing, the remedy mechanism will provide equitable answers to the question: "Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure?"
Identifier: https://escholarship.mcgill.ca/concern/theses/fn1071806
Keywords: Air carriers' obligation; Alternative remedy; Flight delay; Force majeure; Remedies

The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation

Contracts Governing the Use of Websites - Mik, Eliza (Singapore Journal of Legal Studies, 2016)
With the progressive transformation of the Internet from a romanticised instrument of freedom and self-expression into a commercial platform for digital distribution, most websites must be recognised as access interfaces to a wide range of content and services. This paper examines the contracts purportedly governing the use of such content and services. It explores the difficulties of establishing legal intention in a context that is not unambiguously commercial or transactional and contrasts popular beliefs with the basic principles of contract law. It draws a clear distinction between contracts governing traditional e-commerce exchanges, such as buying books on Amazon.com, and contracts governing the very use of websites. In the latter instance, the website (ie the resources made available thereon) constitutes the subject matter of the transaction. Equal importance must be attributed to the fact that such contracts are formed on websites and to the fact that they govern their use. The website user will question the existence of a contract on the basis that he did not have an intention to be legally bound, or had no awareness that a transaction was taking place. The website operator will argue that, objectively, all prerequisites of a legally enforceable agreement have been met. The outcome of the discussion will, to a large extent, depend on whether the user’s beliefs and expectations can be regarded as reasonable and on whether it is the user or the operator who deserves the protection of the objective theory of contract.

The resolution of jurisdictional conflicts under the common law and in the European Union - Mlambe, Richard Mike (University of Johannesburg, 2016)
The resolution of jurisdictional conflicts is one of the main functions of private international law. It provided rules to be applied when the courts of more than one country are seized of the same case in international litigation. In determining what that rule should be, regard must be had to the interest of all the relevant entities, namely, the parties to international cases and the courts dealing with such cases. The need to strike a balance is even more urgent in international commercial litigation where the outcome of the case normally has significant economic consequences. From this background, a study has been conducted of two major private international law regimes regarding their approaches to the resolution of jurisdictional conflicts, namely, the common‐law and the European Union (EU). This study is an inquiry into the suitability of each approach in the resolution of jurisdictional conflicts in international commercial cases. It is the view of the present author that each approach has advantages and disadvantages. The common‐law through the doctrine of forum non conveniens shows a greater ability to prevent forum shopping and to prevent injustices in specific cases. However, it is highly unpredictable. On the other hand, the EU approach through the lis pendens rule succeeds in ensuring predictability and certainty in the resolution of jurisdictional conflicts which is very crucial in international commercial litigation. However, its rigidity and inflexibility leads to the determination of international commercial cases by courts that are ill‐suited, thereby giving some room for forum shopping. It is therefore recommended that the two approaches should learn from each other so that their handling of international commercial cases is in line with the special nature of international commercial litigation. The common‐law approach should be made more predictable and the EU approach should allow the courts in the EU to determine which court is best suited to deal with an international commercial case.

The implications of Lagoon Beach Hotel (Pty) v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation - Moolman, Shirande (University of Pretoria, 2016)
This mini-dissertation explores the implications of Lagoon Beach Hotel (Pty) Limited v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation, as this case deals with the various problems that arise in cross-border insolvency. As a result of these problems and a certain amount of uncertainty when it comes to dealing with cross-border insolvency issues, many investors are reluctant to invest cross-border. This is due to the fact that multiple countries, each with their own laws concerning cross-border insolvency, are involved. Thankfully, the United Nations Commission on International Trade Law has provided a set of guidelines in this regard, namely the Model Law on Cross-Border Insolvency. Although South Africa has enacted the Cross-Border Insolvency Act 42 of 2000, and most of the provisions provided for in the Model law have been included in the legislation, the Act still remains inoperative. Throughout this dissertation the Lagoon Beach case will therefore be critically analysed. The analysis will start off with a discussion of the common law, as it is currently the legal position in South Africa. Thereafter a detailed analysis will be conducted of the various orders of court of the Lagoon Beach case and how the courts differed or agreed in their approach. Finally, the Lagoon Beach case will be discussed in light of the Act and the issues in the case will be solved hypothetically by applying the Act to the problems discussed throughout the dissertation.

Social legitimacy in the internal market : a dialogue of mutual responsiveness - Mulder, Jotte (European University Institute, 2016)
Social legitimacy is conventionally conceived to encompass an empirical notion based on the idea that, lacking societal acceptance, a (political or legal) regime will eventually disintegrate. This concern is reflected in the original compromise of 'embedded liberalism', which stands at the basis of the internal market of the European Union. The primary law set up of the internal market, indeed, shares the idea that the benefits of a joint commitment to free trade can only be achieved in a sustainable way if combined with an acknowledgement of domestic societal objectives within the same frameworks. Nevertheless, social legitimacy will eventually depend on the institutional design and structural rationales that embed societal values within such regimes and vice versa. This perspective is further developed, normatively, on the basis of the work of Karl Polanyi and adopted to critically assess the structural rationales that are developed within internal market adjudication, which the thesis approaches as a separate field of social ordering within the European Union. Thus, social legitimacy is developed as a requirement that perceives the legitimacy of internal market law on the basis of the extent to which it can respond and integrate social practice and values. On this point the thesis finds that the internal market lacks a sufficiently developed rationale or "common language" that is able to address the normative concerns of social legitimacy. Societal realities are often valued within a metric that risks doing violence to potentially genuine and worthwhile aspects of Member States' 'social spheres'. The thesis develops that the normative claims of social legitimacy are best addressed on the basis of a rationale of mutual responsiveness, which is considered a necessary but underdeveloped element of the constitutional form and social purpose of the internal market that is implicit in the constitutional theory of transnational effects. From a perspective of mutual responsiveness, the social purpose of the internal market is not to condition choices that necessarily require the market to trump the social sphere - or the opposite- to allow the social to necessarily trump the market. Mutual responsiveness advances a more holistic approach that conceives the market and the social, literally, as 'communicating vessels'. The normative concerns of social legitimacy and the potential of mutual responsiveness to address these normative claims are the central and connecting elements throughout the thesis.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

The transfer of ownership of movables in the context of international contracts of sale with specific reference to reservation of title clauses : a comparative study - Neibecker, Nadine (University of Johannesburg, 2016)
Please refer to full text to view abstract LL.M. (International Commercial Law)

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
https://research-repository.uwa.edu.au/en/publications/developing-efficient-dispute-resolution-solutions-for-internation The UWA Profiles and Research Repository
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

Democracy and Accountable Governance in the SADC Region - Omede, Jolade; Akindola, Rufus; Ngwube, Arinze (African Journal of Politics and Administrative Studies, 2016)
The call for democracy worldwide is based on the assumption that it allows citizens involvement on how they are governed. Being a representative system of government, democracy is projected to make political leadership responsive and responsible to the entire citizenry of the state. Southern Africa region has the most animated economy in sub –Sahara Africa, and democratic ideals appear more firmly established in the region compared to other regions in Africa. This has made the region, among others in the continent, the preferred choice of many migrants from different parts of the world. It is believed that the region has reached its Eldorado. However, a close observation of the politics of that region tends to suggest there has been the institutionalization of democratic rule without commensurate enthronement of responsible and accountable governance. This study systematically examined the political configurations of the region to concretely determine how the practice of liberal democracy in the sub-region has translated to accountable and responsible governance and its overall impact of the living standard of the citizens of the countries of that region. The paper examined accountable governance in the sense that leaders will be able to mange resource of the state for the well being of the populace. The reverse has been the case for the region. Southern Africa needs a developmental and capable state for socio-economic progress and sustainable democracy. This cannot be achieved without responsible political leadership, which would be responsive to the yearnings of the people. The mode of analysis was based on secondary sources and observation method. The paper adopted secondary and observation techniques as the mode of analysis
Keywords: Accountability; Democracy; Development; Governance; Leadership

Designing justice: a critical analysis of intellectual property rights within the fashion industry - Parbhoo, Sade (University of KwaZulu-Natal, 2016)
Designers are those individuals within our society with a desire and drive to create. In general designers can be found in all facets of industry and good designers (and ultimately good designs) are the very backbone upon a successful business is built. Designers are required to marry practical knowledge with artistic ability and we are reliant on their skills and to turn abstract ideas into formal designs for everything from the groceries we purchase, the cars we drive and of course, the clothes we wear. Whilst there is no definitive delineation of what a fashion design is, generally fashion designs relate to the creation of designs that focus on clothing, apparel and accessories. The style and functionality of the end products rest firmly within particular time frames, economic and socio-cultural environments within which particular designers find themselves. Accordingly the fashion design industry is never one that stagnates but rather is one that is constantly evolving. In South Africa, the fashion industry is blossoming. As an emerging economy, it is important to create opportunities and not barriers for entry into particular sectors for emerging entrepreneurs. The entire fabric of the fashion industry has certainly changed over time and these changes have brought an increased focus on issues of copying and counterfeiting. It is the contention of some in the industry that there is a need for stricter protection of the actual design in and of itself. Using intellectual property rights as a means of protecting fashion designs is very fitting as every new design begins with an idea, which then evolves, though a process of creative engagement and application of skill and labour to become the final original end product. Designers seeking to protect their designs would need to consider the provisions of the Copyright Act, the Designs Act and the Trade Marks Act. These Acts may in some instances provide a means for protect the actual design incidentally, i.e. by protecting the designer‟s rights in relation to reputation and goodwill associated with the goods whilst in others may afford protection to the design itself. The focus of this research will be a discussion of the legal mechanisms available to fashion designers in South Africa for the protection of their designs using their intellectual property rights and an assessment of whether the fashion industry is in need a stronger intellectual property regime than the current one.
Keywords: Design protection; Fashion industry; Intellectual property; Ownership; Retail trade; South Africa

Banking and financial insolvencies: the European regulatory framework - Parry, Rebecca; Omar, Paul J. (INSOL Europe, 2016)
IRep - Nottingham Trent University's open access institutional research repository
https://irep.ntu.ac.uk/id/eprint/28401/

Formation of Contract for the International Sales of Goods - Saleem, Saman Othman (Near East University, 2016)
The Convention for the International Sale of Goods called the Vienna Conference 1980 is an astute international statute that regulates the sale of goods globally. It has been ratified by about 83 countries of the world and countries that have not ratified it have at a point or the other made reference to it. Major economic players apart from England have ratified and have their courts pronounce on the CISG. The Convention provides for the well known elements of contract and also allows for the usage of standard user terms, for example, general terms known or related to certain goods. It is imperial to state that there are also certain regional statutes that are similar to the CISG although with varying differences. It is important to also mention that the CISG also has its lacunae and defects such as allowance for exemption, contents and so on. The CISG has been pronounced upon by courts across the world and has been seen to be highly justiciable.
Keywords: CISG; Convention; English Law; Iraq; United Nations

International Trade, WTO and Economic Development - Siddiqui, Kalim (World Review of Political Economy, 2016)
This article examines the existing literature on trade liberalisation and its effect on the economies of developing countries. It will also briefly examine the theory of comparative advantage which is seen as justification for global trade liberalisation under the auspices of the World Trade Organization. This process is also associated with greater openness, economic interdependence and deepening economic integration with the world economy. The study is important because once again the international institutions strongly advocate trade and financial liberalisation in developing countries. The proponents of trade liberalisation argue that multilateral trade negotiations would achieve these goals, and poor countries particularly would benefit from it. However, such policies may increase vulnerability and make developing countries further hostages of international finance capital. Adoption of open market policies in agriculture would also mean the abandoning of self-reliance and food sovereignty, which may have wider consequences in terms of food shortages, food prices and rural employment.

Affected persons in business rescue proceedings : has a balance been struck? - Silangwe, Thandeka (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: Buisness enterprises; Business failures; Corporate turnarounds; South Africa

An analysis of the impact of the sanitary and phytosanitary agreement on market access : case study on the SA/EU citrus dispute and AGOA dispute - Singh, Shikira (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: AGOA; African Growth and Opportunity Act; Cooperation Agreement; Market access; Sanitary and Phytosanitary (SPS) Agreement; Trade Development; Trade barrier; WTO; World Trade Organization

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
URI: https://repository.up.ac.za/handle/2263/56056
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation

The non-cooperative respondent in international arbitration proceedings : a comparative survey and evaluation of the leading arbitration rules - Venter, Johanlene (University of Johannesburg, 2016)
International arbitration has become accepted worldwide as the principal and, under certain circumstances the preferred method, of resolving international disputes between states, individuals, and corporations in almost every aspect of international trade, commerce, and investment. In general terms, it is expected that an international arbitration procedure is a much speedier method of dispute resolution than formal court proceedings. Although international arbitration holds many benefits for prospective users, there are some difficulties that may arise along the way. An increasingly frequent complaint concerns delays, particularly unconscionable delays and deliberate delaying tactics caused by the parties (i.e. claimant, respondent and/or the arbitrator) which frustrates the process. Arbitration derives from the consent between contracting parties. This implies that the contracting parties gave their consent that a dispute arising from the contract may be resolved by way of arbitration. This will also explain why default by any of the parties is prima facie inconsistent with the consensual nature of arbitration. It is suggested that default during international arbitration is most likely to occur and does not receive the same treatment as the equivalent in the context of formal state court proceedings. Essentially, the objective of this study is to articulate what the claimant can and should do during the arbitral process if and when the respondent is non-cooperative and obstructive in the arbitral process in an attempt to delay and/or destroy the procedure. This study also considers how tribunals should behave in order to promote fairness and the most efficient form of dispute resolution. The research method applied during this study is to conduct a comparative survey and evaluation of the leading arbitration rules available in order to establish what measures are put in place to overcome or mitigate the effects caused by the non-cooperative respondent.
Keywords: Commercial law; International commercial arbitration

Water as public property : a parallel evaluation of South African and German law - Viljoen, Germarié (North-West University, 2016)
With the introduction of the National Water Act 36 of 1998 (NWA) in South Africa’s water regulatory regime, the foundations of the country’s existing water law system changed fundamentally. The NWA was promulgated with the primary aim to reform the law relating to water resources. The preamble to the NWA states that water is “a scarce natural resource that belongs to all people.” Section 3 of the NWA continues along similar lines and stipulates that all water use rights fall under the centralised control of the state or public trustee to inter alia improve the distribution, management, use, conservation and equality of access to this scarce resource. Statutory transformation of this nature has inevitable and important legal implications. It has for example been argued that the changed system has brought about a reallocation and redefinition of property rights to natural resources; a transformation which will inevitably impact the nature, form, extent, limits and protection of access and use rights that can be acquired in water as a natural resource. In an effort to understand the extent of the legal transformation brought about by the concept of public trusteeship, this thesis considers the impact of the concept in the broader South African water law context. The concept of public trusteeship is a novel concept in South African jurisprudence, without established links to existing principles of law. This thesis subsequently focuses on how and to what extent the German property law concept of őffentliche Sache may inform the development and interpretation of the South African concept of public trusteeship as entrenched in the NWA. Consequently, this thesis commences with an exposition of information on the idea of property and the relevance and importance of the different property rights regimes against which both the South African and German property regimes can be evaluated. This is followed by a description of the South African property rights paradigm and its different property concepts. The research introduces a novel take on the discussion of the regulation of rights in natural resources in South Africa, namely a “stewardship ethic of public trusteeship”. As a stewardship ethic could potentially influence the regulation of property in natural resources and even perhaps the property regime within which water as natural resource is regulated in South Africa, the next section of the research proceeds with a historical account of the South African water law dispensation. Although the historical review indicates that the concept of public trusteeship is not part of South Africa’s common law heritage, some of its principles find application in the common law concept of res publicae. The conclusion is that the concept of public trusteeship does not merely (re-) introduce the res publicae concept into the South African water realm. The concept of public trusteeship is a novel concept that was statutorily introduced into the South African water regulatory framework in terms whereof “ownership” of water resources vests in the national government, and are consequently administered on behalf of the nation and generations yet to come. A separate section of the research analyses and contextualises the concept of őffentliche Sache as it functions in German law to offer new insight into the implications that the statutorily introduced concept of public trusteeship might have on water as property and the property regime within which water is regulated in South Africa. This guides the study to the next section of the research, which illustrates that the concept of őffentliche Sache is at the basis of the German water regulatory framework. The conclusion of the study proposes an understanding of the concept of public trusteeship in South Africa based on lessons learned from the German concept of őffentliche Sache.
Keywords: Constitutional property; German water regulatory framework; National Water Act; Property; Property rights regime; Public property; Public trusteeship; Res publicae; Water rights; Öffentliche Sache

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

The suitability of the CISG and OHADA for small and medium-sized enterprises engaging in international trade in West and Central Africa - Donfack, Narcisse Gaetan Zebaze (University of South Africa, 2015)
It is universally acknowledged that international trade and cooperation have become key drivers of SMEs. Indeed, the success of SMEs in the sales sector depends upon their capacity to conquer the foreign market and compete with larger companies. Many SMEs today, in particular those in Central and West Africa, are very much aware of this reality. However, because of differences between domestic laws and their maladjustment, many African SMEs still struggle to enter the international market and compete with larger companies. It is therefore obvious that any SMEs that want to succeed in international commerce today will be called upon to confront different regulations, whether domestic, regional or international, which are often shaped according to the realities and expectations of a particular environment. The challenge today is to regulate and harmonise these different legal systems, in order to render the law identical in numerous jurisdictions. This process of unifying the law internationally, in particular the law of sale, started in 1920 and culminated in 1988, with the implementation of the CISG. This Convention, which has become the primary law for international sales contracts, endeavours to deal with this problem of differences in law between states on a global scale, by attempting to achieve a synthesis between different legislations, such as civil law, common law, socialist law, and the law regarding industrialised and Third World countries. Even though the CISG appears to be a compromise between different legal systems, the fact remains that it is not yet applicable in many countries, especially those in Central and West Africa, which are mostly still ruled by domestic and regional law, namely the OHADA. The purpose of this study is to attempt to analyse and compare the OHADA’s Uniform Act Relating to Commercial Law to the CISG, in order to identify similarities and differences between the two, and to determine, with regard to the operating mode and structure of SMEs in West and Central Africa, which one of the two legislations is more appropriate.
Accepted: 2016-07-19T07:00:06Z
Keywords: CISG; Cameroon Civil Code; Cameroon contract law; Comparative law; Formation of a contract; Incoterms; International sales law; Internationalisation; OHADA law; Obligations of the buyer; Obligations of the seller; SMEs; Sales of goods; Termination of a contract

Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

Determinants and Growth Impact of Foreign Direct Investment in West African Economic and Monetary Union (1980-2010) - Laleye, Abimbola Nicaise (University of Lagos, 2015)
This study’s aim is to assess the trends and the macroeconomic determinants of FDI and to estimate its impact on economic growth, using West African Economic and Monetary Union (WAEMU) and its member countries (Benin, Burkina Faso, Cote d’Ivoire, Guinea Bissau, Mali, Niger, Senegal and Togo) as a case study. In order to achieve the objectives of the current study, the panel cointegration method is employed for the period that expands from 1980 to 2010. This method is constituted of three steps: first, running the panel unit root tests; secondly, run the panel cointegration tests to establish a long-run relationship between the included variables; and thirdly, to run the two models of this study. All this is supplemented by Granger causality test in order to determine the direction of causality between the two variables of FDI and economic growth in WAEMU and its member countries. The findings show that: (i) the variables market size, trade openness, human capital, infrastructure development, financial development, macroeconomic stability, exchange rate and political stability are significant determinants of FDI in WAEMU and in its member countries; (ii) not all the variables affect the same way FDI inflows in WAEMU and in each one of the WAEMU member countries; (iii) there is a positive relationship between FDI and economic growth which implies that FDI stimulates economic growth in WAEMU and its member countries; (iv) this study finds a causality relationship between FDI and economic growth, which runs from FDI to economic growth not from economic growth to FDI: meaning there is a unidirectional linkage between FDI and economic growth in WAEMU; (v) the study also finds that at cross-sectional level, FDI only causes economic growth, not the opposite: this implies that there is also a unidirectional linkage between FDI and economic growth in each WAEMU member country and its runs from FDI to economic growth. Therefore, it is important that the enabling environment should always be provided not only in WAEMU but also in its member countries in order to attract more foreign direct investment and further to stimulate the xiv country’s economic growth. Thus, this study recommends the followings, at the local or country level: first, improvement of the image of WAEMU countries. Rapid economic growth could result in an increase in foreign direct investment inflows, not only in WAEMU but in each one of the WAEMU member countries. But, this has to be done with more attention given to conditions (i.e. key variables) such as fair trade policy with abroad, development of infrastructure and financial system, availability of human capital through a sound human training and formation. At regional or WAEMU level, governments should set up policy that guaranties macroeconomic stability and political stability.
https://ir.unilag.edu.ng/handle/123456789/4079
Keywords: Co-integration; Determinants of FDI; FDI; Foreign direct investment; WAEMU; West African Economic and Monetary Union

The Modern Travelling Merchant: Mobile Communication in International Contract Law - Schroeter, Ulrich G. (Journal of Law, Society and Development, 2015)
The use of mobile communication devices such as mobile phones, smartphones, tablet computers or notebooks with access to the internet has become an everyday phenomenon in today's business world. However, whenever mobile communications are used for the purposes of contract formation, that is, the mobile dispatch of offers or acceptances, the mobility of the communicating parties raises important difficulties for the application of traditional legal rules: The fact that messages transmitted via phone, email or SMS can be dispatched and received Â at virtually any Â place on Â earth challenges the categories of private international law and international contract law, which are based on the (unspoken) assumption that parties communicate from their home country. The existing legal framework for cross-border contracts therefore hardly takes into account the possibility that parties may move across borders, and that the place of their communications may accordingly vary.The present article addresses the legal difficulties and uncertainties that crossÂ border Â mobile communication Â raises under international rules of law. It elaborates on the traditional role of the site of communication in this context before scrutinising how 'mobility friendly' the provisions Â of the relevant Â conventions Â developed Â by the United Nations, the Hague Conference for Private International Law and other organisations Â are. In doing Â so, Â it critically Â discusses Â in particular article 10(3) of the UN Electronic Communications Convention of 2005, the most recent attempt at regulating mobile communications. Finally, it identifies a number of problems that have hitherto been overlooked (as notably the interaction of article 10(3) of the UN Electronic Communications Convention with traditional private international law rules on the formal validity of contracts) and proposes appropriate solutions.
Keywords: Conflict of laws; Contract law; Electronic communication; Electronic contract formation; Mobile communication; Place of contracting; UN Electronic Communications Convention; m-commerce

Policy Options for Promoting Foreign Direct Investment in the Least Developed Countries - Sauvant, Karl P.; Mallampally, Padma (Transnational Corporations Review, 2015)
Foreign direct investment (FDI) plays an important role in the world economy and has the potential to contribute towards accelerating the process of economic growth and sustainable development in the least developed countries (LDCs). The paper provides a brief overview of recent trends and patterns in FDI flows to the LDCs, and then takes stock of the policies, programmes and measures pursued by host and home countries and by international organizations to stimulate FDI flows to LDCs and increase their benefits for these countries. It then lays out a number of policy proposals on how flows to LDCs, and the benefits associated with them, can be enhanced. Finally, it outlines some options for international action to strengthen such efforts – proposals and options that are also relevant to other developing countries.
Keywords: Development; Foreign direct investment; Least Developed Countries; policy options

International Standards for Commercial Mediators - To, Christopher (University of Stirling, 2015)
This paper talks about the international standards for commercial mediators. It introduces the standards of eight different jurisdictions and afterwards, evaluates whether there should be one accrediting standard for all international commercial mediators. In the introduction chapter, the paper talks about the problems with the current legal system and then explains the growth of mediation in today’s society. By discussing the nature and practice of mediation, whether mediation should be compulsory or voluntary in light of Article 6 of the European Convention on Human Rights, rationale of the various jurisdictions covered, the paper then talks about the attributes that make a good mediator as well as the accreditation and training of mediators. From chapter two to chapter nine, the paper focuses on eight jurisdictions in which mediation is firmly enshrined within one legal culture to those that are just embarking on the concept (namely Australia, New Zealand, Indonesia, Malaysia, India, Hong Kong, California and Canada). Each chapter talks about the developments of commercial mediation, law and institutions as well as training and accreditation of mediators within their respective jurisdictions. In the concluding chapter, it discusses whether there should be one accrediting standard for international commercial mediators by exploring the advantages and disadvantages of having one accrediting standard as well as the author’s analysis and point of view on the subject.
Keywords: Commercial mediator; International standards; Mediation; Mediator; Médiateur

The Role of Arbitration Institutions in the Development of Arbitration in Africa - Onyema, Emilia (2015)
This conference which held at the premises of the African Union Commission, Addis Ababa on 23 July 2015 examined the functions of arbitration institutions in Africa. The conferenced discussions focused on sharing experiences by users and providers for the effective administration of arbitration references in the continent. The conference was organised by Dr Emilia Onyema of the School of Law, SOAS. KEY ARTICLES : - Regional Arbitration Institution for ECOWAS: Lessons from OHADA Common Court of Justice and Arbitration ; - The Role of Arbitration Institutions in the Development of Arbitration in Africa ; - “Africa’s Century” – The rise of International Arbitration in Africa and what it means for users of Arbitral Institutions in Africa ; - Reawakening Arbitral Institutions for Development of Arbitration in Africa ; - Opening Up International Arbitration in Africa ; - Africa as a Viable Space for Arbitration: Role of National Courts and Laws - The Role of Counsel in Promoting African Arbitral Institutions ;
Pages: 1-160
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Conference

BRICS and Sub-Saharan Africa Trade Interdependence and Peace: Evidence Based on Revealed Comparative Advantages - Beyene, Hailay Gebretinsae (Journal of Law, Society and Development, 2015)
This study examined economic integration through trade between BRIGS (Brazil, Russia, India, China and South Africa) countries and sub-Saharan Africa. The study examines the comparative advantages of the two economic blocks with respect to the exportation of merchandise (food, agricultural raw materials, fuels, ores and metals, and manufactures). The findings of this study reveal the actual status of these two regions as economic partners in each of the five subsectors of merchandise exports.The Â trend Â shows Â that, Â with Â the Â exception Â of Â manufactures Â exports, the competitiveness of all subsectors of the merchandise Â exports ofÂ BRIGS is characterised by a Â declining Â trend. Â BRIGS has Â a Â comparativeÂ advantage in the world in the exportation of manufactures and fuels, and comparative disadvantage in the export of food, agricultural raw materials, and ores and metals. Â Interestingly, manufactures are Â continuously Â and consistently Â in a steadily rising trend. This is evidence that BRIGS's structural transformation towards higher valued-added commodities is proceeding well, which means that policy makers should be considering ways of enhancing it further.In the case of sub-Saharan Africa,Â with the exception of manufactures exports, it is found to have comparative advantages in all merchandise exports. Sub- Saharan Africaâ€™s competitive advantage is the highest in the exportation of ores and metals, followed by fuels, agricultural raw materials and food. Sub-Saharan Africa has a comparative disadvantage in the export of manufactures throughout the period considered in this study. This implies that the prospects of structural transformation to downstream of the higher value-added commodities export part of the supply chain are good: the slow pace of transformation towards higher value-added goods should therefore be demanding the attention of policy makers. The study has revealed that sub-Saharan Africa is more competitive than BRICS in the exportation of ores and metals, fuel, agricultural raw materials and food. On the other hand, BRICS is more competitive than sub-Saharan Africa in the export of manufactures.The study has also revealed that significant economic integration can be sustained Â between Â BRICS Â and Â sub-Saharan Â Africa Â in Â the Â exportation Â of all merchandise subsectors. Specifically, sub-Saharan Africa is a potential destination market for BRICSâ€™s exports of manufactures. Conversely, BRICS is also a potential destination market for sub-Saharan Africaâ€™s exports of ores and metals, fuel, agricultural raw materials and food.Economic integration between BRICS and sub-Saharan Africa favourably influences peace and stability in the regions. Sustaining peace and stability in these regions also favourably influences the wellbeing of the communities.
Keywords: BRICS; Economic integration; Sub-Saharan Africa; merchandise exportation; peace and stability; revealed comparative advantage; structural transformation

CISG and Regional Sales Law: Friends or Foes? - Coetzee, Juana (Journal of Law, Society and Development, 2015)
Economic co-operation and integration brings with it a need to harmonise mechanisms for the regulation of international trade, not only at a public-law level between states but also at a private-law level between traders inter partes. It is often forgotten that differences in the substantive law applicable to a contract function as a non-tariff barrier to trade. Because international trade facilitates economic development, the focus in this article is on the harmonisation of sales laws. Traditionally, private law harmonisation has been conducted by international private or inter-state organisations that specialise in the harmonising of law at a global level. Today, private organisations and groups devoted to harmonising business laws, as well as regional economic integration organisations, are also pursuing legal harmonisation. Global, regional and domestic laws now all exist in the same area of the law, which can give rise to duplication of efforts and problems with the co-existence of global and regional sales law. This article will discuss these issues with reference to the United Nations Convention on Contracts for the International Sale of Goods (CISG) and selected regional laws in considering whether regional harmonisation can act as a stepping stone towards increased harmonisation at a global level or whether it is to be viewed as a threat to global integration and harmonisation.
Keywords: CESL; CISG; Global harmonisation; Harmonisation of sales laws; OHADA; PACL; SADC; regional harmonisation

Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

Passivity rule: a comparison between European Union, United States and China - Casamassima, Stefano (LUISS Guido Carli, 2015)
Passivity rule: origin and reasons. Adoption of the European directive 25/2004 and its provisions. The adoption of the European directive by major member states and passivity rule in USA and China. The economic implications of passivity rule. Possible future developments.

Choice of the UNIDROIT Principles of international commercial contracts - Meer, Tiana Van der (University of Johannesburg, 2015)
LL.M. (International Commercial Law) The principle of party autonomy is a fundamental characteristic of private international law. The contracting parties’ freedom of choice regarding the law governing their contract is one which optimises the fundamental principle of party autonomy. It is generally accepted that a choice of a governing law by the parties should be respected by adjudicating bodies such as domestic courts and arbitral tribunals. It would often benefit contracting parties to choose a neutral legal system so that there will be a “fair playing field” in case a dispute arises between them. However, some domestic legal systems and regional, supranational and international commercial instruments limit the choice of law to that of a recognised domestic legal system. Accordingly, choosing the UNIDROIT Principles on International Commercial Contracts as governing law will, in most cases, not be a viable option for the parties concerned. Such a limitation on the choice of a governing law does not promote the fundamental principle of party autonomy, which is characteristic of private international law. Parties to an international commercial contract should be able to choose a non-state system of law to govern their contract. The UNIDROIT Principles of International Commercial Contracts provide a comprehensive, complete and easily obtainable system of law compiled by legal experts in the various fields which form part of international commercial law. It follows a via media system of law with regards to Civil Law and Common Law legal systems. This paper will discuss the principle of party autonomy, as well as the possibility of a choice of non-state law, in particular the UNIDROIT Principles of International Commercial Contracts, as the law governing an international commercial contract. The choice of law will be discussed with reference to the position taken in domestic courts as well as that in international arbitration. To review the impact and success of the UNIDROIT Principles in the realm of international commercial contracting, various international commercial instruments will be discussed.

The potential impact of the Hague principles on choice of law in international commercial contracts in the BRICS countries - Reddi, Saranya (University of Johannesburg, 2015)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: BRIC countries; Commercial law; Conflict of laws; Contracts (International law)

A comparison of Kenyan and South African law on security by means of movables - Koli, Natasha Mwende (University of South Africa, 2015)
This study compares the legal principles applicable in both South Africa and Kenya in the creation of security by means of movables. It identifies the forms of security that can be created in the two jurisdictions. The main focus will be on the creation, publicity, priority of security interest and enforcement of the said interests. The research will in addition establish the challenges (if any) that are encountered when creating security by means of movables in Kenya and identify practical solutions that can be adopted in order to improve the creation of security by means of movables in Kenya.
Accepted: 2015-10-16T08:35:59Z
Keywords: ACCESS TO FINANCE; Creation of security; Kenyan law; Lenders and security; Movable property; Secured transactions; Security; Security by means of movables; South African law

Cooperative Movements in the Western Highlands of Cameroon - Jiotsa, Albert; Okia, Timothy Musima; Yambene, Henri (Revue de géographie alpine, 2015)
Cooperative societies in the Western Highlands (West and North West regions) of Cameroon is an age old institution which started with the arrival of the European colonialists towards the end of the nineteenth century. The fertile soils of this region favors agricultural activities thereby giving rise to many cooperatives in the region. The cooperative societies that have been developed in these areas are the type found in sub Saharan Africa which has stood the test of time more than half a century whereby the other cooperatives elsewhere in the same country have failed. The question this article is about to provide answers is to what has made these cooperatives in the Western Highlands of Cameroon able to stand the test of time when others are quitting the scene. To come out with this scientific article we have implored the active participatory research methodology. The analysis shows that these cooperatives since their creation have been imploring certain innovative measures to make them adapt to the many constraints in their sector.
Number: 103-1
Keywords: Cameroon; adaptation strategies; constraints; cooperative movements; highlands

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

Economic and Empirical Analysis of Contractual Dispute Resolution - Miller, Samuel Mark (Vanderbilt University, 2015)
This dissertation uses Python-based programming to retrieve and analyze a sample of approximately 400,000 material contracts that companies filed with the Securities and Exchange Commission between 2001 and 2013, focusing on the dispute resolution mechanisms specified therein. The first chapter considers the effectiveness of two state-level efforts to attract dispute resolution business, examining how specialized “business courts” and the Revised Uniform Arbitration Act affected arbitration and choice-of-forum clause use in these material contracts. The second chapter examines whether and how companies and executives “customized” their arbitration clauses in response to Internal Revenue Code Section 409A, which increased both the likelihood and the complexity of potential disputes between these parties. The third chapter considers how companies and executives responded when the Supreme Court overturned the Ninth Circuit’s anomalous refusal to enforce employment-related arbitration clauses. Each chapter finds that contracting parties adjusted their dispute resolution provisions in response to the policy change(s) at issue – suggesting that for the sophisticated parties in my dataset, these provisions receive careful thought and are not mere “boilerplate.”
URI: http://hdl.handle.net/1803/11146
Keywords: Arbitrage; Arbitragem; Arbitration; Contracts; Dispute resolution; Econometrics

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
URI: http://webcat.warwick.ac.uk/record=b2766071~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

The Economics of tort law applied to Internet intermediaries : example of intellectual property - Lefort, Marine (École nationale supérieure des mines de Paris, 2015)
La responsabilité des intermédiaires d'Internet fait débat dans un univers numérique de plus en plus complexe. Les intermédiaires offrent des services en ligne. Ils créent ou facilitent des transactions entre des parties tierces (hébergement, e-commerce, fournisseurs d'accès…). A la fin des années 1990, un consensus s'est établi sur l'instauration d'une responsabilité limitée pour ces acteurs, dans le but de favoriser leur développement ainsi que celui d'Internet par des externalités croisées. Cependant, l'apparition régulière de nouveaux usages a induit des externalités négatives affectant certains agents économiques. La multiplication récente de décisions de jurisprudence parfois contradictoires, en particulier dans le domaine de la propriété intellectuelle, vient désormais remettre en cause cette exemption. Elle fait naître un risque juridique pour les intermédiaires d'Internet. Ces-derniers doivent alors prendre en compte ce nouveau contexte dans leurs modèles d'affaires. Notre recherche étudie les comportements spécifiques que la responsabilité des intermédiaires d'Internet engendre à travers l'exemple de la propriété intellectuelle. En premier lieu nous décrivons l'évolution historique de cette responsabilité. Nous développons ensuite un modèle théorique simple qui explore l'influence du risque légal dans un contexte de concurrence entre un intermédiaire et un ayant droit du copyright. Enfin nous étendons ce modèle de concurrence aux différents comportements de protection que peuvent choisir les intermédiaires.
Keywords: Competencia; Competition law; Concurrence; Economie du droit; Intellectual property; Intermédiaires d’Internet; Internet; Internet intermediaries; Law and Economics; Propriedade intelectual; Propriété intellectuelle

Cross border insolvency: new trends - Napolitano, Andrea (LUISS Guido Carli, 2015)
The EU regulation no. 1346/2000. The proposal for a modification of the regulation. New trends.

Joint Development of Offshore Polar Oil and Gas Resources and the United Nations Convention on the Law of the Sea - Abrahamson, John (Australian National University, 2015)
This thesis examines whether the establishment of Joint Development Zones (JDZs) for the development of offshore oil and gas resources in the Arctic and Southern Oceans can effectively resolve competing continental shelf and outer continental shelf (OCS) claims arising under the provisions of Article 76 of the United Nations Convention on the Law of the Sea (LOSC). One of the effects of global warming has been increased interest in oil and gas activity in the Arctic region, however there is significant concern as to the related environmental risks. The Environmental Protocol to the Antarctic Treaty currently suspends exploration for state parties for oil and gas in the Southern Ocean, however current exploration has been reported. A JDZ may be defined as an inter-governmental arrangement of a provisional or permanent nature, designed for joint exploration and exploitation of the hydrocarbon resources of the sea-bed. JDZs are generally based on agreements to suspend sovereignty claims and share offshore oil and gas in the JDZ region. The thesis was prepared to contribute to the prevention of potential international conflicts over offshore oil and gas resources. State claims may be based on historic claims, interpretation of treaties, and LOSC exclusive economic zone (EEZ), continental shelf, and OCS delimitation provisions. LOSC provides dispute resolution alternatives, including referral to the International Court of Justice and international arbitration. A significant number of states have, however, preferred to adopt JDZ agreements. The methods used for the thesis included analysis of LOSC maritime delimitation provisions, existing JDZ agreements, the terms of model JDZ agreements, and analysis of current Arctic and Southern ocean maritime boundary disputes. The principal thesis conclusions are: - JDZs can resolve resource disputes as demonstrated by the existing international state practice in adopting JDZs. JDZ regimes are not a universal panacea, however, and successful JDZs are based on the continued political support of the respective states; - LOSC maritime boundary delimitation provisions may not resolve boundary disputes, which can arise due to issues including conflicting sovereignty of land territory; - Specific Arctic and Southern Ocean disputed regions have similar characteristics to existing JDZs. JDZs may therefore potentially apply to resolve these disputes; - JDZs can potentially provide solutions for disputed boundaries, such as between United States/Canada (Beaufort Sea), United States/Russia (Bering Sea) in the Arctic Ocean region, and between United Kingdom/Argentina/Chile in the Southern Ocean; - JDZ should be adapted to better protect and preserve the marine environment, and to provide a significant liability regime similar to the Greenland regime; - JDZs should support a framework of regional governance, including Arctic Council or Antarctic Treaty representation in the respective JDZs; and - Potential game changing events may affect the use of JDZs in the future, including political and technological developments, and significant oil and gas discoveries. The result of the thesis conclusions is to prove the hypothesis that JDZs can effectively resolve resource conflicts in the Arctic and Southern Ocean regions.

How to copy a song with impunity : a legal perspective on copyright infringement cases for musical works - Rogowski, Adrian (Stellenbosch University, 2015)
Music has, and continues to play, an important role in society. It is therefore natural that more music composers enter the scene to capitalize upon this role that music has in society. It is however becoming more common place for music composers to start copying each other, either directly or indirectly. Fortunately, copyright laws have been developed to further protect the rights enjoyed by copyright holders, such as music composers, and these laws essentially protect the composers from the unlawful reproduction of their original music. Copying is, to some degree, inevitable, therefore, the question asked by this paper is to what extent is someone entitled to ‘copy’ from another person without it amounting to copyright infringement. In determining if there is copyright infringement, two tests must be applied and satisfied, namely, the causal connection test, and the substantial similarity test. Causal connection is usually met by establishing whether the alleged infringer had access to the original work. The substantial similarity test is the focus of this paper. The courts rely on this test to determine if that part which was reproduced from the original work is of substance i.e. if it is a part of the work which attributes uniqueness and quality to the original song. Of course, this test is notoriously difficult to understand and apply, hence the need for this paper to address the question on when there is substantial similarity in two works. This paper is of benefit to academics, authors (musicians) and lawyers, as not only is the substantial similarity test discussed from a theoretical point of view, but the question of when something is substantially similar is answered from a pragmatic point of view. It is hoped that this paper is used as a guideline in understanding and applying the substantial similarity test in music copyright infringement cases.
Keywords: Copyright; Copyright infringement; Music; Musical compositions

Reconsidering Distributions: A Critical Analysis of the Regulation of Distributions to Shareholders in the Companies Act of 2008, with Special Reference to the Solvency and Liquidity Requirement - Van der Merwe, Constant Pieter (Stellenbosch University, 2015)
The Companies Act 71 of 2008 introduces a completely new system for the regulation of distributions by a company to its shareholders. The preferred method for protecting the interests of creditors in distributions is now based on a solvency and liquidity test. Regrettably, the provisions setting out the requirements for distributions on the one hand and the solvency and liquidity test on the other have been poorly drafted. This thesis first explains and then applies an innovative interpretation theory to these provisions with a view to piecing together coherent content. The thesis finds that creative interpretations will not suffice in various places, meaning that substantive revision is required. The thesis concludes with brief amendment proposals and accompanying commentary.
URI: http://hdl.handle.net/10019.1/97133
Keywords: Business enterprises; Companies; Companies Act; 2008; Companies régulations; Company insolvency; Company liquidity; Insolvency; Régulations; Shareholders; South Africa

The Vienna Sales Convention and private international law - Wethmar-Lemmer, Marlene Muriel (University of Johannesburg, 2015)
The United Nations Convention on Contracts for the International Sale of Goods (the CISG or the Vienna Sales Convention) was adopted at a diplomatic conference of the United Nations held in Vienna during 1980. The Convention came into force on 1 January 1988. According to its preamble, the Convention is based on the premise that “the adoption of uniform rules which govern contracts for the international sale of goods and take into account the different social, economic and legal systems would contribute to the removal of legal barriers in international trade and promote the development of international trade”. The CISG has proven to be successful in its endeavour and currently has 74 member states representative of all legal traditions. As an international convention, the CISG has been lauded for its “simplicity, practicality and clarity”. Schlechtriem observed that the CISG has now gained worldwide acceptance. It has even been stated that the CISG has established a “world law on international sales” and that it has influenced several domestic sales laws. It is submitted that the CISG constitutes an important component of modern international commercial law or of the modern lex mercatoria. Therefore, a study that aims to establish a better understanding of the scope and functioning of the CISG and its relationship with domestic law, is of special relevance for the international business and legal community. The two basic methods of the unification of law, ie the unification of substantive law and the unification of private international law, have both been utilised in the field of the international sale of goods. The CISG is the most notable example of first mentioned method of unification.
Keywords: CISG; Choice of law clause; Conflict of laws; Contracts for the international sale of goods; Convention de Vienne; Export sales contracts; Lex mercatoria; Party autonomy; Sales; UNIDROIT Principles

Law and Development in West and Central Africa OHADA - Winship, Peter (SMU Dedman School of Law Legal Studies Research Paper, 2015)
This seminar paper considers whether OHADA - an experiment in unifying business law in African countries - has been a success. Following a prologue that explains the origins of the paper, the first part of the paper sets out basic information about the Organisation pour l’Harmonisation du Droit des Affaires en Afrique (“Organization for the Harmonization of Business Law in Africa,” known by the acronym OHADA). This part is followed by a review of law and development literature to assess the value of this literature for an evaluation of the success (or not) of OHADA. A third part then focuses on one specific uniform law, the law of secured transactions. The paper concludes that notwithstanding challenges the OHADA institutions exist and have produced uniform business laws for the formal business sector. Whether OHADA has been the cause of increased investment and trade requires studies that have not been carried out.
Keywords: African law; Secured transactions; commercial law; law and development; law reform; unification of law

Toward an Elaboration of a More Pluralistic Legal Landscape for Developing West African Countries: Organization for the Harmonization of Business Law in Africa (OHADA) and Law and Development - Hiez, David; Menétrey, Séverine (The Law and Development Review, 2015)
In Europe and especially in France, the African business law landscape, as well as the legal discourse, for developing West African countries is almost exclusively dedicated to OHADA, the Organization for the Harmonization of Business Law in Africa, created in 1993. While economic development in the Member States is the obvious underlying reason for the modernization and unification of African business law, the exact nature of such development remains uncertain, as does the manner in which a such result can or will be achieved. OHADA’s Uniform Acts are, with some minor exceptions, a carbon copy of French business law. The only goal is to increase international investment, which, in turn, is expected to generate economic development, but all without taking any notice of equality or social justice issues. That, without a doubt, is the reason why OHADA is constantly criticized as a law that benefits foreign investors, while remaining ineffective, even illusory, for local traders. To go beyond the criticism, the authors have decided to focus on the relationship between law and the informal sector and to draw lines between formal and informal rules in the business sector.
Keywords: Informal rules informal sector; OHADA (Harmonized Business Law in Africa); informal rules; informal sector

Employee participation and voice in companies: a legal perspective - Botha, Monray Marsellus (North-West University, 2015)
Recently, South African company law underwent a dramatic overhaul through the introduction of the Companies Act 71 of 2008. Central to company law is the promotion of corporate governance: companies no longer are accountable to their shareholders only but to society at large. Leaders should direct company strategy and operations with a view to achieving the triple bottom-line (economic, social and environmental performance) and, thus, should manage the business in a sustainable manner. An important question in company law today: In whose interest should the company be managed? Corporate governance needs to address the entire span of responsibilities to all stakeholders of the company, such as customers, employees, shareholders, suppliers and the community at large. The Companies Act aims to balance the rights and obligations of shareholders and directors within companies and encourages the efficient and responsible management of companies. The promotion of human rights is central in the application of company law: it is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a “social institution” should be enhanced and protected. Because corporations are a part of society and the community they are required to be socially responsible and to be more accountable to all stakeholders in the company. Although directors act in the best interests of shareholders, collectively, they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are important. The advancement of social justice is important to corporations in that they should take into account the Constitution, labour and company law legislation in dealing with social justice issues. Employees have become important stakeholders in companies and their needs should be taken into account in a bigger corporate governance and social responsibility framework. Consideration of the role of employees in corporations entails notice that the Constitution grants every person a fundamental right to fair labour practices. Social as well as political change became evident after South Africa's re-entry into the world in the 1990s. Change to socio-economic conditions in a developing country is also evident. These changes have a major influence on South African labour law. Like company law, labour law, to a large extent, is codified. Like company law, no precise definition of labour law exists. From the various definitions, labour law covers both the individual and collective labour law and various role-players are involved. These role-players include trade unions, employers/companies, employees, and the state. The various relationships between these parties, ultimately, are what guides a certain outcome if there is a power play between them. In 1995 the South African labour market was transformed by the introduction of the Labour Relations Act 66 of 1995. The LRA remains the primary piece of labour legislation that governs labour law in South Africa. The notion of industrial democracy and the transformation of the workplace are central issues in South African labour law. The constitutional change that have taken place in South Africa, by which the protection of human rights and the democratisation of the workplace are advanced contributed to these developments. Before the enactment of the LRA, employee participation and voice were much-debated topics, locally and internationally. In considering employee participation, it is essential to take due cognisance of both the labour and company law principles that are pertinent: the need for workers to have a voice in the workplace and for employers to manage their corporations. Employee participation and voice should be evident at different levels: from information-sharing to consultation to joint decision-making. Corporations should enhance systems and processes that facilitate employee participation and voice in decisions that affect employees. The primary research question under investigation is: What role should (and could) employees play in corporate decision-making in South Africa? The main inquiry of the thesis, therefore, is to explore the issue of granting a voice to employees in companies, in particular, the role of employees in the decision-making processes of companies. The thesis explores various options, including supervisory co-determination as well as social co-determination, in order to find solutions that will facilitate the achievement of employee participation and voice in companies in South Africa.
Keywords: CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Corporate law; Disputes; Economic democracy; Employee participation; Empowerment; Fairness; Industrial democracy; Joint decision-making; Labour law; Matters of mutual interest; Shareholders; Social justice; Stakeholders; Workplace forums

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Accepted: 2015-12-09T14:30:56Z
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

A comparative reappraisal of debt relief measures for natural person debtors in South Africa - Coetzee, Hermie (University of Pretoria, 2015)
The purpose of this thesis is to do a comparative reappraisal of debt relief measures available to natural person debtors in the South African insolvency law. Although the broader South African natural person insolvency system currently includes three statutory debt relief procedures, namely, the sequestration procedure regulated by the Insolvency Act 24 of 1936, the administration order procedure in terms of the Magistrates Courts Act 32 of 1944 and the debt review procedure found in the National Credit Act 34 of 2005, not all natural person debtors have access to the system. The majority of this marginalised group are debtors with no income and no assets (the so-called No Income No Asset (NINA) debtors). Also, only one measure provides real debt relief in the form of a statutory discharge of debt. Furthermore, the existing measures have developed in a haphazard fashion which has led to a multiplicity of procedures, regulators and forums that resulted in ineffectiveness, inequality and uncertainty. The larger system therefore lacks proper policy considerations. This thesis provides the reasons for reform by, amongst others, arguing that the present situation is unconstitutional as it unreasonably and unfairly discriminates against the NINA group of debtors in particular. It measures the broader South African system against internationally accepted principles of efficient and effective natural person insolvency regimes. In this regard it is found that the system as a whole is seriously deficient. With reference to international principles and guidelines as well as suitable attributes found in foreign jurisdictions, the thesis concludes with suggestions for real law reform. Both substantive and procedural recommendations are made.
URI: https://repository.up.ac.za/handle/2263/52372

A Comparative Study on Customs Tariff Classification - Colesky, Theo (University of Pretoria, 2015)
The field of customs is commonly referred to as that of imports and exports. It is perceived as a maze of processes, procedures, and forms required to enable a customs administration to perform their wide range of responsibilities. One of the responsibilities of a customs administration is the collection of duties, which necessitates classification of the goods in question. This study sets out to determine the extent of customs control in relation to tariff classification in South Africa. The starting point is the establishment of the foundations of customs, both internationally and in South Africa. After origin and valuation, tariff classification is the third technical customs-related focus area. An analysis of the responsibilities of the customs administration in South Africa confirms the importance of revenue collection and, subsequently, tariff classification. As a result of South Africa’s membership of the World Customs Organization, specific obligations in relation to tariff classification are incurred. The implementation and application of the international provisions are considered and compared in South Africa, Australia, and Canada. Not only is South Africa’s existing legislation considered, but also two new Acts. It is found that despite similarities in the implementation of the Harmonized System Convention into the legislation of the three countries, South Africa’s existing legislation makes the most detailed provision for the Harmonized System and its aids. This is based on the finding that the legislation in Australia and Canada, as well as the two new Acts in South Africa, do not have the same comprehensive provisions. A critical review of the varying processes of classification in the three countries suggests that more suitable and effective processes could be implemented in South Africa. In addition, a synopsis of some of the principles developed in case law is provided and compared. In relation to facilitation, the access to relevant information and the adequacy thereof, as well as the availability of rulings, are considered. Differences in the approach to dispute resolution in the three countries are furthermore provided. Proposals are made to address the discrepancies in the implementation and application of the legislation, the process of classification, the principles developed in case law, the enhancement of related guides, the publication of tariff classification rulings, and the extent of facilitation and dispute resolution. Finally it is recommended that an independent and expert tribunal is established to adjudicate technical customs matters.
URI: https://repository.up.ac.za/handle/2263/42838
Keywords: Comparative study; Customs tariff classification

The Investment Treaty Regime and Public Interest Regulation in Ghana: Perspectives in Constitutionalism and General International Law - Dagbanja, Dominic (University of Auckland, 2015)
There is extensive literature on conflict of legal norms and interests in international investment law. The dominant discourse is on the implications of treaty-based investment protection for sovereign regulatory autonomy. Mainstream scholarship critical of the scope and effect of investment treaties has taken the legal status of these treaties for granted. Little systematic attention has been paid to the capacity of states to make investment treaties and the obligations states can or cannot agree to under those treaties in light of their public interest obligations. Yet, this issue is of fundamental importance for three reasons. First, the case for states’ regulatory autonomy arises out of their primary duty to regulate in the public interest. This duty has its legal justification in national constitutions and international law. Second, treaty obligations are founded on the existence of legal norms necessary for the treaty to come into existence and which define the juridical consequences attached to the conclusion of the treaty. These matters are also determined by national constitutions and international law. Third, the limitations inherent in state-specific defences in international investment disputes settlement compel a proactive rethink of the conclusion of investment treaties and how they are interpreted. The question this thesis assesses with reference to Ghana then is: does a state that is legally required to act both under the terms of its constitution and international law in the public interest have the capacity to conclude investment treaties that expressly prevent or abridge the exercise of its public interest regulatory powers, and how should treaties adopted in breach of these obligations be interpreted? To address this question, three areas of public interest regulation that have featured prominently in investment arbitration serve as case studies: the jurisdiction of municipal courts, environmental protection and development policy. Based on the impact and potential limitations of standards of investment protection on these areas, the thesis argues that some treaties are incompatible with the public interest regulation obligations of Ghana under the Constitution and international law. The core proposition of the thesis is that the legal source and public purpose of the State’s powers prevent it from concluding agreements that directly prohibit public interest regulation or indirectly achieve that effect. Accordingly, the thesis proposes that the express and implied limitations on the duty to regulate in the public interest placed on investment treaty making powers of the State must inform the making of investment treaties and their interpretation. By its approach, this thesis establishes a principled basis for reflection on the limits to the State’s capacity to conclude investment treaties and on how they should be interpreted.
http://hdl.handle.net/2292/28285
Keywords: Ghana; Investment treaty; Investments; Public interest

The Disclosure and Use of Social and Environmental Information by Libyan Banks - Elsakit, Omer M (Griffith University, 2015)
There is increasing interest in social and environmental issues throughout the world, especially in developed countries, where governments, organizations, and society well recognise the impact of business activities on the environment and society. Consequently, companies have potentially no alternative but to behave in a responsible manner, socially and environmentally, and to prove this by disclosing information about their related conduct. In this regard, banks play two important roles: first, as providers of social and environmental information in much the same manner as nonfinancial companies; and second, as providers of finance, by encouraging—if not obliging—bank customers to consider society and the environment in their bank-financed projects. Banks fulfil the latter role by requiring social and environmental information from companies when making lending decisions. Only a few Libyan studies have examined social and environmental issues in relation to economic activity, and these have generally revealed low levels of disclosure practice by organisations, including banks, in these areas. In addition, many changes have taken place in the Libyan economy and banking sector in recent years, including the establishment of a market exchange; decreased government participation in economic activities; and increased growth of the private sector that results, especially in the banking sector, with the entrance of foreign investors. These changes have placed a new emphasis on bank operations and the participation of banks in the Libyan economy. Thus, studying Libyan banks, in terms of their role in the environment and society, has attracted growing interest. As such, the core objective of this thesis has been to investigate the position of Libyan banks in relation to social and environmental issues and disclosure by considering their dual role as both providers and users of such information.
Keywords: Banks and banking; Environmental policy; Finance and environment; Libya

The effectiveness of the e-commerce legal framework in selected African countries - Esanwa, Maryam Adetokunbo (University of KwaZulu-Natal, 2015)
Abstract not available.
Keywords: Africa; E-commerce; Electronic commerce; Information technology

A level playing field for "open skies": the need for consistent and harmonized regulation of Aviation - Fitzgerald, P. Paul (McGill University, 2015)
Various initiatives by regulators in different jurisdictions over the past two decades have completely reshaped the airline industry in ways that were unimaginable in 1992. From an industry dominated by Pan Am and Trans World Airlines (TWA), and newly privatized airlines such as British Airways, today's industry is dominated by government-owned intercontinental airlines based in the Middle East and carrying passengers the majority of whom are ultimately destined for States other than the States where the airlines are based. Insufficient thought has been given to whether this evolution is desirable, whether it involves profound competitive distortions or whether it is in the public interest that the majority of Australians visiting Europe are carried by an airline based in neither jurisdiction or that a similar claim might be made with respect to traffic between South Asia and the Americas. This thesis examines the events that have reshaped the international aviation industry over the two decades between 1992 and 2012. It will critically analyze the major developments and the regulatory responses and highlight some of the incompatible and disjointed regulations that are in effect at either end of international routes. It ultimately proposes that Australia, Canada, the European Union (EU), New Zealand and the United States (US) form a small international organization, to be known as the Open Skies International Aviation Block (OSIAB). OSIAB would be based on expanding the membership of the US-EU Joint Committee foreseen in the 2007 US-EU Open Skies Agreement and expanding its scope to cover every aspect of the regulation of international commercial aviation. This thesis argues such a forum is necessary to ensure that regulations in different countries are aligned so that competitive distortions potentially caused by regulatory disharmony are minimized, thus allowing the international airline industry to compete on the level international playing field that so many international agreements have promised to create.
Identifier: https://escholarship.mcgill.ca/concern/theses/nz8062944
Keywords: Aviation; Aviation regulation; Transport aérien

A critical appraisal of the misapplications of black economic empowerment and the common misperceptions that surround it - Govender, Prenisha (University of KwaZulu-Natal, 2015)
Broad-Based Black Economic Empowerment is a regulatory framework, which is unique to South Africa. This dissertation reflects upon the evolution of Broad-Based Black Economic Empowerment programme, from the commencement of apartheid to date. Broad-Based Black Economic Empowerment was implemented by government, with the objective of resolving the injustices created by the apartheid regime. Government seeks to achieve this objective by integrating the historically disadvantaged individuals within South Africa into the mainstream of the economy. However, the reality is that the implementation of the Black Economic Empowerment programme has not been entirely successful. This dissertation is a critical analysis of the application of Broad-Based Black Economic Empowerment and related legislation. It aims to highlight the challenges faced by government in enforcing the Broad-Based Black Economic Empowerment programme, with a particular focus on the following issues: fronting, misrepresentations and common misperceptions. This dissertation begins by reflecting upon the historical context of South Africa toward democratization, secondly it analyses the current applicable legislation and explores the current issues. This research shows that Broad-Based Black Economic Empowerment is essentially a work in progress programme as there is much room for improvement. Scholars have established that companies and other entities regularly circumvent the Act. Furthermore, many individuals misunderstand the programme and its purpose. The research concludes Broad-Based Black Economic Empowerment does have potential for success. In considering the approach taken by Malaysia, it is established that the key to overcome these major issues is education.
Keywords: Affirmative action programs; Blacks Economic conditions; Business enterprises; Employee empowerment

The regulatory function of contract law : comparative law and economics approach - Gramcheva, Lyubomira (European University Institute, 2015)
This thesis challenges the traditional view of national contract laws as facilitative regimes and argues that contract law on the national level has been progressively re-oriented to perform an efficiency-driven regulatory function. To develop the argument the thesis studies the contract law remedial regime of two common law and one civil law jurisdiction – the US, England and Bulgaria, in two specific contracts – the sale-of-goods and the construction contract. The introductory chapter puts the main theme in context and outlines the project. Exploring the limits of promissory theory and neoclassical economics, the second chapter develops an innovative interdisciplinary methodology joining the new institutional economics with the comparative law method. The third, fourth and fifth chapters offer taxonomies of remedies, types of contracts and remedial effects to set the stage for a meaningful comparison across the different legal traditions. Since economic theory has advanced most in the study of incentives generated by damages, the third chapter focuses on the latter remedy and shows that the common law classification of damage measures (expectation, reliance, restitution), on which traditional law-and-economics accounts are based, can be applied to study a civil law jurisdiction like Bulgaria. Distinguishing discrete and long-term contracts and demonstrating that the differentiation between sale-of-goods and construction contracts in the compared national legal systems does not necessarily go along the lines of the discrete/long-term distinction in economics, the fourth chapter argues that the positive comparison should be made with an eye on the market for substitute performances even if the compared factual scenarios are classified under different legal categories in the different jurisdictions. For the uninitiated, the fifth chapter reconstructs and criticises the standard economic model rationalising damages as incentives. The final chapter applies the approach developed here to contractual termination. The exemplary analysis identifies trends in the compared legal systems and suggests that all of them converge in charging the termination remedy with a regulatory function. Finally, I generalise to make some bolder claims about contract law.
Accepted: 2016-01-11T14:07:16Z
Keywords: Contracts; Law and economics; Public law (Economic aspects)

Business in West and Central Africa: The Legal Framework - an Introduction to the Laws of the OHADA - Hahn, Anne-Catherine; Darbellay Suso, Aline; Desax, Robert; Herzog, Sabine; Meyer, Manuel; Monnier, Philippe; Schnyder, Marion; Zemp, Rafael (Baker & McKenzie, 2015)

International taxation of cross-border digital commerce - Kadikov, Artem (University of Oxford, 2015)
This thesis discusses jurisdiction to tax cross-border digital commerce. The primary objective is to consider the reasons for the erosion of jurisdictional links, or nexus, between countries and taxpayers' digital activities and evaluate possible solutions for addressing such nexus erosion. Whilst it is argued that digital commerce is impossible to ring-fence due to digital technologies transcending all industries, the main focus of this research is on automated business models as case studies for the broader tax issues applicable across the entire digital economy. Using cloud computing, online advertising and e-tailing models as examples of digital commerce in the narrow sense, this thesis demonstrates that the proxies for establishing jurisdictional nexus have become increasingly fluid, thereby challenging the traditional international tax regimes for profits and consumption taxation. Numerous policy solutions have been proposed in order to rectify nexus erosion, including global and territorial tax models. Unlike the previous research in this area, this thesis focuses on the nexus elements of such proposals and assesses their viability in the light of the wider Internet governance jurisprudence. Global tax solutions, such as global e-commerce taxes and formulary apportionment, are analysed in the context of the international governance regime for the technical Internet infrastructure. Territorial virtual tax solutions, such as virtual permanent establishments, withholding taxes and destination cash flow taxes, are considered in the light of the Internet jurisprudence on the 'effects' and 'targeting' nexus standards. It is argued that, given the lack of technical and political infrastructure, none of the proposed routes would be viable from a practical perspective in the near future. It is concluded, therefore, that a practical solution would involve retaining the traditional profits and consumption tax models, whilst testing a narrow version of the digital targeting nexus standard as a backstop anti-abuse measure. It is envisaged that the limited anti-avoidance provision would subsequently pave the way for a comprehensive long-term solution, as digitisation continues to transform global commerce.
Keywords: Corporations; Digital commerce taxation; Double taxation; E-commerce taxation; Electronic commerce; International Trade; International business enterprises; Internet governance; Internet jurisdiction; Internet taxation; Jurisdiction to tax; Taxation

Equal treatment as a principle to guide the regulation of intangibly transferred content : a case study on e-books using the examples of copyright exhaustion, reduced rates of VAT and fixed book pricing - Linklater, Emma (European University Institute, 2015)
Using e-books as a case study, this thesis considers whether the principle of equal treatment could play a role in driving more consistent and rational regulation of markets where content is available in both tangible and intangible formats. At present, although the content is the same, these formats are often subject to different rules. This difference in treatment has opened up discussions about whether current legal frameworks should be amended and in these discussions actors with very different standpoints have consistently invoked the language of equality to justify their varied stances. However, in these discussions there is no clear elaboration of what equality means or how it can be used, leading to abstract debates and eventually to arbitrary decisions. The thesis attempts to fill this gap by building a framework based on outcome equality to decide if intangible book formats should be treated ‘like’ tangible ones. It uses the objective underlying the existing rule as the standard for establishing likeness or difference and advocates that functional equality, rather than formal equality, is desirable because this takes account of the differences in the functionalities between content formats: Intangibility impacts on the functioning of the rule in question (e.g. quantitatively increased ease of circulation and copying) and it is only if these impacts can be neutralized that functional equality can be achieved. The framework is applied to the case studies of copyright exhaustion, reduced rates of VAT and fixed book pricing. These have been chosen in recognition of the range of decision-making powers between the national and EU levels in this cultural sector. Overall, the analysis shows that rationality can be inserted by using equal treatment as a guide, but that consistency is more difficult to achieve given the interaction between national and EU influences in the book market.
Keywords: Copyright; Cultural policy; Electronic publishing; European Union countries; Intellectual property

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (Working Together to Deliver - Sakha Sonke, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Accepted: 2016-11-08T12:11:22Z Artwork Medium: PDF Interview Medium: PDF
Keywords: Southern African Transport Conference; Transportation

Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (University of Cape Town, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.
Keywords: International Trade; International Trade Law; Investments

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Challenges of Transnational Trademark Law Practice: The Case of Nigerian Companies’ Brands in OAPI States - Nwabueze, Caroline (Revue générale de droit, 2015)
Nigeria industrial growth has turned the country into an indispensable economic support for its neighbours. Only for the case of Cameroon, Nigeria has been the leading supplier with respectively 22% and 17.8% of imports in 2011 and 2012 with trade amounting to 328 billion FCFA per annum. This results in part from Nigerian companies’ exportations in local markets. Nigerian trademarks related to cosmetics, furniture, electronics, and pharmaceutical goods abound in neighbouring countries. However, a strengthening of Nigerian companies in regional markets encompasses strategies to avoid infringing on the trademark rights. Such strategies should include the consideration of special trademarks features by different institutions of the intellectual property (IP) system in the relevant neighbour export markets. This is by the mere fact that the legal status of those goods, although physical property, relies mainly on the material law applicable, which is trademark in the present case. Because the principle of territoriality requires that trademark protection be sought in the place where the goods are sold—and trademark applications filed in each country in which protection is sought—, Nigerian companies planning to outsource some business activity in neighbour markets will seek compliance with trademarks norms applicable in the Organisation africaine de la propriété intellectuelle (OAPI) of which those countries—Benin, Cameroon, Chad, and Guinea—are part. The trade partnership between companies from a common law trademark background on one hand, and civil law intellectual property community on the other, inevitably raises some frictions and trademarks issues. This article analyses the trademark challenges arising from Nigerian companies’ business decision to enter OAPI markets and export goods and services. The article firstly underlines the issues to be taken into consideration, including registration and enforcement of the companies’ marks in OAPI. Then the paper simultaneously reviews the dissimilarities issues between the Nigerian Trademark Act and the OAPI Trademark System to which the Nigerian companies are confronted. If trademark protection makes it easier for an enterprise to access transnational markets, the establishment of a Trademark Community with neighbouring countries helps for sure national industries to establish partnerships with other firms for sustainable development in the areas such as production, marketing, distribution or delivery of goods and services. In light of the trademark harmonisation in the European Union internal market, the present paper concludes by recommending the creation of a Trademark Community in the West and Central African region between Nigeria and its neighbouring countries. La croissance industrielle du Nigeria a fait de ce pays un soutien économique indispensable pour ses voisins. Pour ne citer que l’exemple du Cameroun, le Nigeria en a été le principal fournisseur avec respectivement 22 % et 17,8 % des importations en 2011 et 2012 et des importations dont la valeur s’élève à 328 milliards fr. cfa par année. Ceci résulte en partie des exportations des compagnies nigérianes vers les marchés locaux. Les marques de commerce nigérianes dans le domaine des cosmétiques, des meubles et des produits électroniques et pharmaceutiques abondent dans les pays voisins. Cependant, le renforcement des compagnies nigérianes dans les marchés régionaux englobe des stratégies pour éviter d’enfreindre les droits de propriété industrielle et commerciale. Dans le cadre de ces stratégies, les différentes institutions qui régissent la propriété intellectuelle (PI) dans les marchés d’exportation des pays voisins pertinents devraient prendre en compte des caractéristiques particulières relatives aux marques de commerce. Ne serait-ce que du simple fait que le statut juridique de ces produits, bien qu’ils soient des biens physiques, repose principalement sur le droit substantiel applicable, le droit de la marque de commerce dans ce cas. Parce que le principe de territorialité nécessite que la protection de la marque de commerce soit demandée dans le territoire où les biens sont vendus, et que cette protection doit être demandée dans chaque pays individuellement, les compagnies nigérianes qui prévoient externaliser des activités commerciales dans des marchés voisins chercheront à se conformer aux normes en matière de marques de commerce qui sont applicables au sein de l’Organisation africaine de la propriété intellectuelle (OAPI), dont font partie le Bénin, le Cameroun, le Tchad et la Guinée. Le partenariat commercial entre des entreprises soulève inévitablement, et ce, tant du point de vue de la common law que celui du droit civil, des frictions et des problèmes lorsqu’il s’agit de marques de commerce. Le présent article analyse les défis relatifs aux marques de commerce découlant de la décision commerciale des entreprises nigérianes de faire leur entrée dans les marchés de l’OAPI et d’y exporter des biens et services. L’article souligne premièrement les problèmes qui doivent être pris en considération, dont l’inscription et la mise en application des marques des entreprises membres de l’OAPI. Ensuite, ce texte examine simultanément les problèmes résultant des différences entre la Nigerian Trademark Act et le système de marques de commerce de l’OAPI, système auquel les entreprises nigérianes sont confrontées. Si la protection des marques de commerce facilite l’accès aux marchés transnationaux pour les entreprises, la mise en place, avec les pays voisins, d’une communauté en matière de marques de commerce aide assurément les industries nationales à établir des partenariats avec d’autres entreprises dans le but d’assurer un développement durable dans des domaines tels que la production, la commercialisation, la distribution ou la livraison de biens et services. À la lumière de l’harmonisation des marques de commerce dans le marché intérieur de l’Union européenne, le présent article conclut en recommandant la création d’une communauté de marques de commerce dans la région de l’Afrique occidentale et centrale, et qui réunirait le Nigeria et ses pays voisins.
Keywords: Afrique occidentale; Commerce transnational; Communauté de marques de commerce; Community trademark; Compagnies nigérianes; Enforcement; Intellectual property; Marque déposée; Mise en oeuvre; Nigerian companies; OAPI; Principe de territorialité; Principle of territoriality; Propriedade intelectual; Propriété intellectuelle; Trademark practice; Transnational trade; Western Africa

The sui generis and intellectual property protection of expressions of folklore in Africa - Nwauche, Enyinna Sodienye (North-West University, 2015)
This thesis articulates an optimum framework for the protection of expressions of folklore in Africa using a number of African countries – South Africa, Kenya, Ghana and Nigeria as case studies. This thesis argues that the existing sui generis and intellectual property rights protection in African countries are grossly inadequate in protecting expressions of folklore in these countries. An optimum framework for the protection of expressions of folklore would constitute a combination of the positive and negative protective model elaborated and implemented through a human and people's rights framework that recognises that communities that produce expressions of folklore should own and control how their intellectual property is protected. While a positive protective model explores how intellectual property rights such as copyright, trademarks, designs and performances may protect expressions of folklore through the endowment of such rights on communities, negative protective models examine how state and national competent authorities protect expressions of folklore on behalf of communities. An optimum framework for the protection of expressions of folklore recognises that regional and international perspectives are critical for the protection of folklore in third party countries and expressions of folklore that occur in contiguous countries. A regional perspective is important for Africa countries because of two regional intellectual property organisations in Africa (ARIPO – African Regional Intellectual Property Organisation) and OAPI (African Intellectual Property Organisation) that have established minimum standards for the protection of expressions of folklore. Norm setting and standards in international organisations such as WIPO (World Intellectual Property Organisation); UNESCO (United Nations Educational Cultural and Scientific Organisation); and the WTO (World Trade Organisation) significantly impact the protection of expressions of folklore in Africa. A human and peoples' rights framework explores how national and regional legal systems in Africa recognise entitlements of communities in the protection of the expressions of folklore they produce. In this regard, the normative framework of communities in terms of their customary law is also explored.
Keywords: ARIPO; African Regional Intellectual Property Organization; Communities; Customary law; Expressions of folklore; Ghana; Indigenous people; Intellectual property; Intellectual property rights; Kenya; Nigeria; Peoples' rights; South Africa; Sui generis; WIPO; World Intellectual Property Organization

Exploring shared governance as an alternative institutional model for the Southern African development community - Nyathi, Mkhululi (University of Pretoria, 2015)
The Southern African Development Community (SADC) was initially established as a coordination conference in 1980 and was transformed into a treaty organisation in 1992. Challenges of lack of coordination, inefficiency and lack of policy harmonisation led to the amendment of the Treaty in 2001. While the amendment of the Treaty served to address some of the challenges of the organisation, it failed to address the core challenge of the democratic deficit inherent in SADC s governance framework. While the SADC Treaty has as part of its principles and objectives the observance and promotion of democracy and the rule of law, both in its own processes and in its Member States, the design of the SADC institutions does not reflect these normative values. Governance of SADC is characterised by excessive executivism under the overarching powers of the Summit of Heads of State or Government. This democratic deficit is most prominently evidenced by the suspension and eventual disbandment of the SADC Tribunal, the only judicial organ of the organisation. The suspension and disbandment of the Tribunal, in addition to the obvious issue of legality that it raises since it was done in the absence of Treaty amendment, also raises the fundamental question of decision making in SADC in general, as the current treaty framework does not provide for meaningful conversation between and among the key institutions of SADC in matters involving policy formulation and implementation. There is also no institution with a strong oversight role in SADC. There is need for constitutional change in SADC if the organisation is serious in its commitment to achieve its objectives, which it has defined as its Common Agenda. This study proposes a treaty based reform process that is informed by the institutional model of shared governance. One of the several core tenets of this model is that in an organisation, there should be meaningful conversation among the internal stakeholders before a decision is made. For such conversation to be meaningful, there should be the broadest possible exchange of information among the components of an organisation. The proposals made by this study include transforming the Secretariat into an effective institution that formulates SADC laws and policies as well as their implementation frameworks; creation of a SADC parliament that would play a meaningful role on the amendment of the SADC Treaty and in the adoption of the budget; and an independent and accessible judicial body with significant powers of review. Shared governance as conceptualised in this study is not a substitute for, nor does it compete with related concepts like constitutionalism, separation of powers, the rule of law and participatory democracy, but in fact complements them. In addition to these proposals, there is a recommendation for the adoption of a robust access to information regime in which the shared governance institutional model would be anchored. There is also a recommendation for a new regime of law making through community legal instruments that would be directly applicable in Member States as opposed to the largely ineffective protocols.
URI: https://repository.up.ac.za/handle/2263/52280
Keywords: Civil society engagement; SADC; Southern African Development Community

Corporate Social Responsibility , Oil Exploration and the Niger Delta Question - Obi, Emeka Anthony (Oman Chapter of Arabian Journal of Business and Management Review, 2015)
The intricate relationship between corporate organizations and their environment is one that is supposed to be based on mutual interdependence. This is because the organization depends on the environment for its inputs, while the environment also needs the organization for its sustenance. This therefore calls for a symbiotic relationship between them. It is this realization that gave birth to the concept of Corporate Social Responsibility (CSR). This paper tries to look at the application of the concept as it concerns the oil companies operating in the Niger Delta region of Nigeria within the ambit of the Niger Delta question. The study employs the systems theory as an analytical framework. It tries to situate the concept of CSR within the general neglect by successive governments of this region that sustains the entire Nigerian state. The implication of the above is that a better understanding of the problem of CSR in the Niger Delta region becomes easier when juxtaposed with the attitude of the Nigerian state towards the region over the years. It is the summation of the paper that the oil companies have not been very proactive in this regard and as such have been perceived by their host communities as enemies and exploiters instead of partners. The study concludes by insisting that while the oil companies should be more proactive, the government on her part should step up the tempo in ameliorating the deplorable condition of the golden goose.
Keywords: CSR; Corporate Social Responsibility; RSE; Responsabilité Sociale de l'Entreprise

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (Conference Proceedings, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing

Stuck in a time warp: security interests in chattel mortgages and the bills of sale legislation in Nigeria - Otabor-Olubor, Iyare (International Company and Commercial Law Review, 2015)
IRep - Nottingham Trent University's open access institutional research repository
Number: 11

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

CISG and the freedom of form principle vs. reservations under Article 96 of the CISG - Pohl, Małgorzata (Transformacje Prawa Prywatnego, 2015)
This article aims to present the consequences of a state’s declaration to opt-out from the freedom of form principle, under article 96 of the united nations Convention on Con tracts for the international sale of goods 1980 (CISG). In practice, problems have developed as whether or not to apply the freedom of form when a contract is concluded between two business entities, where one has its place of business in an article 96 CISG reservation state, and the other does not. The issue concerning the reservation’s effects has led to the creation of “two schools of thought” established by the doctrine and case law in this respect. it is the author’s intention to present the proper methodology of the interpretation and application of articles 12 and 96 CISG bearing in mind the various opinions in this respect. In the author’s opinion, in such situations the court should follow the rules of private international law to seek an answer as to whether or not the obligation of written form applies. Some of the CISG Contracting states that currently maintain an article 96 Cisg dec laration, refrain from withdrawal of their declaration despite the fact that the prerequisites for such a reservation are no longer met, as their domestic legal systems do not impose a written form requirement, as was the case at the time when the Cisg was negotiated. In the author’s opinion, in cases where the rules of private international law point to the law of such a state, the courts should, in practice, refrain from following the article 96 Cisg reservation, i.e. no freedom of form, and should instead apply the less formal domestic law as to the form.

The complex case for another hard look : transnational pharmaceutical regulation and the pedagogical role of courts - Rizzi, Marco (European University Institute, 2015)
The thesis argues for a 'pedagogical' role for courts in the US and EU in ameliorating the increasingly transnational regulation of pharmaceutical product safety through complementary monitoring of the outputs of regulatory processes. The study is divided into two parts. First, the thesis explores the regulatory institutional design in the US and EU. The parallel development of the FDA and EMA suggests that both markets have achieved consolidated domestic/regional regulatory frameworks, which do however show multiple weak spots. These vulnerabilities are aggravated by a strong push towards transnationalisation of regulatory procedures: domestic systems are now permeated by potentially disruptive exogenous elements (e.g. the ratification of transnationally negotiated protocols and increasing reliance on foreign clinical trials data). The thesis explores issues of effectiveness of safety delivery and legitimacy of rule-making processes to suggest scope for improvement in both areas. The second part considers the potential contribution of the judiciary, particularly national courts in the US and EU, to investigate whether the exercise of complementary judicial governance can enhance the effectiveness and legitimacy of an otherwise essentially closed and self-perpetuating system. A selection of cases grounds the claim that, through liability litigation, courts have the capacity to improve the safety levels delivered by regulation and thereby to contribute to output-based legitimacy of the institutional design. This claim is tested in light of acknowledged strengths and limitations of court processes and with regard to differentiating elements at the national level, particularly regarding access to justice. The concluding argument reassembles the results of the study to recommend the existing tool of domestic litigation as a response to certain vulnerabilities in pharmaceutical regulation. The 'hard look' doctrine described by Sheila Jasanoff grounds the normative claim for a 'pedagogical' role for courts, enhancing regulation beyond the outcome of isolated cases – ad adiuvandum rather than contra.
Accepted: 2015-11-04T16:35:28Z
Keywords: Drugs; European Union countries; Pharmaceutical industry; Pharmaceutical regulation; Pharmaceutical right; United States

Public-private cooperation in transnational regulation - Schmidt, Rebecca (European University Institute, 2015)
This thesis examines the emergence of transnational regulatory cooperation between public and private actors. It inquires why a private regulator and an international organisation may enter into a cooperation agreement in order to regulate particular issues, and what this tells us about the relationship between ‘expertise,’ ‘authority’ and ‘legitimacy’ in particular domains of global governance. The argument put forward in the thesis is that different types of regulators cooperate because, in an unsettled global space with no hierarchical framework, it is necessary for them to acquire sufficient authority to secure compliance with their regulatory agenda. In order to acquire and maintain such authority, regulators must be perceived as legitimate and their regulation as effective. Cooperation can open venues for participation and deliberation and for the exchange of necessary competences (particularly expertise); and thus ultimately can help regulators establish and strengthen their authority. Another important finding of this research is that cooperation can develop into more long-lasting network structures. These networks are often of a multi-level nature. As such, they traverse local, national, and international spaces. The thesis then develops the idea of ‘networks of constitutionalization’ to describe the observation that bilateral arrangements as examined here generate ordering effects which extend beyond the two parties. Consequently they become the basis for norm creation and adoption for different types of actors located in the networks formed around the issue area. Thus, even in pluralistic structures, eventually a certain kind of constitutionalization can emerge putting into question sharp divisions between ‘pluralist’ and ‘constitutionalist’ interpretations of a developing global (legal) order. This work also encompasses two case studies: the ISO 26000 process, whereby the ‘private’ technical standard setter ISO concluded separate cooperation agreements with the ILO, the OECD and the UN Global Compact; and a case study on ‘Sport and Environment’ that focuses on the long-standing cooperation between the IOC and the UN Environmental Programme.
Accepted: 2015-04-16T14:24:52Z
Keywords: International Law; Law and Globalization

More than 25 years of the contracts for the international sale of goods (CISG): Rethinking the role of the CISG in the SADC region - Shumba, Tapiwa (Speculum Juris, 2015)
The Convention on Contracts for the International Sale of Goods (CISG) has proved popular, particularly outside Africa. However, only a few States have adopted it in Africa, with only two in the Southern African Development Community (SADC). Taking into account the role that African countries have played in the United Nations Commission on International Trade Law (UNCITRAL) and the creation of the CISG, it has always been pertinent to look at whether SADC Member States should adopt the CISG as an instrument for harmonising the law of international sales in the region. Since it came into force, only two SADC Member States (Lesotho and Zambia) have ratified the convention. There is apparent reluctance from the rest of SADC Member States to ratify the convention despite calls to that effect and the genuine need for legal harmonisation. The article revisits the call for the ratification of the CISG in SADC and considers other realistic alternatives to ratification.

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions

Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York, 1958) - UNCITRAL (United Nations, 2015)

Teaching and research in international insolvency law: challenges and opportunities - Veder, Michael; Omar, Paul J. (INSOL Europe, 2015)
IRep - Nottingham Trent University's open access institutional research repository
https://irep.ntu.ac.uk/id/eprint/27282/

Synthetic securitisation in South African law - Wessels, Francois Claassens (University of Pretoria, 2015)
The objective of this thesis is to critically analyse synthetic securitisation schemes in South African law as synthetic collateralised debt obligations using primarily credit default swaps (CDSs). This transpires from the perspective of primarily company law, and secondarily securities law and the law of contract. It includes a contextualised study of these schemes with regards to their origins, their significance regarding the recent financial crisis, and their rationales micro-economic influence and Basel capital requirements. Not only are the participants, such as parties acting in a primary role and secondary role and special-purpose institutions, studied, but also the obligations between these parties, such as the CDS contract, and the meaning of commercial paper, the legal nature of credit-linked notes, the business of a bank, and the influence of recent case law. It also includes a consideration of synthetic securitisation schemes in terms of the Collective Investment Schemes Control Act 45 of 2002. Furthermore, the role of systemic risk and moral hazard is explained, as well as the interaction between synthetic securitisation schemes, credit rating agencies and the function of risk management. The CDS is compared with insurance contracts, and a discussion of the 2014 International Swaps and Derivatives Association Credit Derivative Definitions is incorporated. For legal comparison, the South African model is compared with Canadian law and its unfunded credit derivatives in the light of recent regulation, and compared to German law and its prevalence of funded credit derivatives. Finally, suggestions are made as to the future of synthetic securitisation schemes.
URI: https://repository.up.ac.za/handle/2263/53208
Keywords: Company law; Debt obligation; Securities Law; Securitisation; South Africa; Titrisation

A comment on debt relief options for insolvent consumer debtors in South Africa - Xulu, Anele Innocentia Nombuso (University of KwaZulu-Natal, 2015)
The paper will be focused on examining the debt relief options available for consumer debtors in South Africa. This paper will look at the relationship between the National Credit Act 34 of 2005 and the Insolvency Act 24 of 1936. Further, it will examine the relationship between the provisions of section 74 of the Magistrates’ Courts Act 32 of 1944. The paper will conclude by looking at debt relief options available for consumer debtors in the United States of America and in England and Wales and will make comparative comments and recommendations on how we can adopt some provisions into our own insolvency system.
Keywords: Consumer credit; Debt relief; Debtor and creditor; Insolvency; Insolvency Act; National Credit Act; South Africa

A Standing Question: Mortgages, Assignment, and Foreclosure - Zacks, Eric A; Zacks, Dustin A (The Journal of Corporation Law, 2015)
“Banks are neither private attorneys general nor bounty hunters, armed with a roving commission to seek out defaulting homeowners and take away their homes in satisfaction of some other bank’s deed of trust.” This Article examines the judicial treatment of mortgage assignments across various jurisdictions in the foreclosure context. Although some courts do permit debtors to challenge suspicious or problematic assignments, most have ignored such problems and denied standing to debtors attempting to assert assignment-based defenses. This is particularly surprising given the widespread and well-documented problems with foreclosure “robo-litigation,” including backdated documents, fraudulent notarizations, and unauthorized signatures. Despite the abuse of process by foreclosing entities, courts have permitted foreclosures to continue unabated and, in some instances, have even precluded the possibility of discovery to debtors seeking to ensure that title and assignments are legally valid. Judicial ambivalence about formal compliance by mortgage assignors and assignees in the foreclosure context is somewhat ironic given most courts’ routine enforcement of instruments against debtors who do not formally comply with all contractual terms. Current adjudicative approaches to mortgage assignment are seemingly disconnected from the devastating reality of the home mortgage crisis and its causes. Moreover, there are several rationales that would support a more robust enforcement of technical compliance with assignment procedures, including the need for procedural equity, title certainty, and public records integrity. Thus, as evidence exists that banks are still making many of the same problematic mistakes regarding transfer documentation, courts can perform an essential monitoring role as an important spur towards reform. Although it would not address all of the underlying causes of the housing crisis, an adjudicative approach that liberally permits challenges to mortgage assignments would encourage lenders and servicers to be more circumspect in their foreclosure processes.

A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, Izelle (Stellenbosch University, 2014)
Trusts are used for a variety of purposes, both in South Africa and abroad. Like so many other entities, trusts often do not function only in one jurisdiction and may therefore be exposed to international double taxation. South Africa, like most other states, enters into bi-lateral double taxation treaties, to limit the effects of international double taxation. Most of these treaties are based on the OECD Model Tax Convention on Income and on Capital (the OECD MTC). The South African trust is a unique creature. It is not based on the dual ownership concept on which most common law trusts are based, yet, it is not a juristic person either. The question that this research aims to address is how South Africa will interpret and apply certain provisions of the OECD MTC to trusts. Although the South African position is investigated, it is compared to the positions of the United Kingdom, Canada and the Netherlands. The dissertation starts with an analysis of the trust law in each of the relevant states, followed by an overview of the taxation regime governing trusts (and the parties thereto) in each state. The status of double taxation treaties and their interpretation are examined before certain critical provisions of the OECD MTC are analysed to determine how South Africa will apply these provisions to trusts. Hence it is explored whether a trust will be regarded as a person, whether it may be a resident and a beneficial owner for purposes of the OECD MTC. Furthermore, possible solutions for conflicts of attribution in the application of double tax conventions to trusts are investigated. The dissertation concludes that South Africa will regard a trust as a person for purposes of the OECD MTC. Moreover, some types of trusts may be viewed as residents and as beneficial owners for purposes of the OECD MTC. The solution proposed in the OECD’s Partnership Report should be applied to resolve conflicts of attribution involving trusts.
URI: http://hdl.handle.net/10019.1/95878
Keywords: Double taxation; Income tax; International taxation; OECD Model Tax Convention; South Africa; Taxation; Treaties; Trusts and trustees

An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Law and Development à L'Africaine: Evidence from the OHADA's Harmonization Process - Simo, Regis Yann (African Yearbook of International Law, 2014)
Until recently, doing business in developing countries, and in Sub-Saharan Africa in particular, was associated with high risk. Although each investment decision is associated with some risk, there are always obligations incumbent on host States in that regard. However, when domestic law is too obsolete to match the requirements of an evolving investment and commercial environment which it is supposed to regulate, and when its effects are unpredictable, one of the fundamental conditions for attracting investment goes missing. This eventually underscores the need for a legal reform. The phenomenon of 'globalisation' on the one hand, and the need for (developing) countries to integrate their economies into the global market, on the other hand, considerably accentuated the postulate of development through law.Against this background, some African countries, at the dawn of the 1990s, felt a need to 'modernise' their legal systems for the major part inherited from colonialism. In this vein, they entrusted a supranational organ, the OHADA, to perform that legal reform. This paper is an attempt to test the OHADA against the discourse of law as a development engine. Furthermore, this is an assessment of the extent to which OHADA, as a legal tool, could be useful in serving the purpose of regional integration and economic growth in Africa.
Keywords: Africa; Comparative Law; Law and Development; Law and economics; Law and finance; OHADA

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

The position of the whistle-blower in South African law - Isparta, Louise Dorothy (University of South Africa, 2014)
The position of the whistle-blower is known to be a precarious one, with the whistle-blower often either regarded as a hero or a reprehensible traitor. Various pieces of legislation have attempted to remedy their precarious position, especially within the employment relationship, and in which the whistle-blower more often than not has the most to lose. The study at hand has the specific objective of comparing the position of the whistle-blower in terms of South African Law, against 16 specific measurables, and in comparison with the position of the whistle-blower in New Zealand, Australia (Victoria) and the United Kingdom. In the main, the protection offered to the whistle-blower within the South African context, is embodied within the Protected Disclosure Act 26 of 2000 (hereinafter referred to as the “PDA”).In examining the protection afforded to the whistle-blower in South Africa, it is concluded that the framework involved extends much further than just the mere provisions in the PDA. However, there are admitted challenges in respect of this framework as discussed, both legislative and non-legislative, especially in respect of duties of disclosures placed on persons in circumstances in which concurrent protection is not afforded to the whistle-blower. With reference to the comparison in respect of the measurement parameters set, it was found that the PIDA (UK) meets the least amount of the measurements set, with the PDA A (Australia, Victoria) meeting the most of the measurements; the PDA NZ is equally balanced in meeting and not meeting the measurements and the PDA meeting less of the measurements than not, but still meeting more than the PIDA. It was found that had it not been for the catch-all provision contained in section 4 (1) (b) of the PDA, the PDA would have ranked last.
Keywords: Disclosure of information; Lanceur d’alerte; Protected Disclosure Act; Protected disclosure; Public Interest Disclosure Act; Whistle blowing; Whistle-blower

Complex ownership structures, banks' capital structure and performance - Zedek, Nadia (Université de Limoges, 2014)
Cette thèse examine l’impact de la structure actionnariale sur la structure du capital et la performance des banques commerciales européennes sur la période 2002-2010. Elle est composée de trois essais empiriques. Le premier chapitre teste l'effet de la divergence entre les droits de contrôle et les droits pécuniaires d'un actionnaire ultime sur l’ajustement du ratio du capital à son niveau optimal et sur l’offre de crédit par les banques. Les résultats montrent qu’en présence de divergence entre les droits de contrôle et les droits pécuniaires, les banques n’émettent pas du capital pour augmenter leur ratio et, au contraire, elles réduisent leur taille en ralentissant leur offre de prêts. Le chapitre 2 teste l’effet de cette divergence sur la rentabilité et le risque bancaires en temps normal et en temps de crise. Les résultats montrent que bien qu'une divergence entre les droits de contrôle et les droits pécuniaires soit associée en temps normal à une rentabilité plus faible et un risque plus élevé elle a, à contrario, amélioré la rentabilité et contribué à la résilience des banques pendant la crise financière de 2007-2008. Le troisième chapitre teste si le réseau des actionnaires auquel la banque est liée au sein d’une chaîne de contrôle affecte la relation entre la diversification et la performance. Les résultats montrent que la présence des investisseurs institutionnels dans les chaînes de contrôle aide les banques à tirer des bénéfices lorsqu’elles diversifient leurs activités.
Keywords: Actionnariat; Banques; Banques européennes; Capital; Capital Structure; European Banking; Ownership; Structure du capital

The effects of the South African anti-dumping and competition measures upon foreign direct investment - Sibanda, Omphemetse S. (Journal of Business and Retail Management Research, 2014)
Since the dawn of democracy South Africa has embarked in a process of dismantling protectionist business and trade policies, and made the country’s stream of commerce one of the preferred globally. The country’s sound competition and trade policies, natural resource endowments, market size and regional influence, attracted foreign businesss and foreign direct invetsment (FDI). Equally the country has been under pressure to protect the domestic industries from injurious competition and business, through sector specific laws, anti-dumping and countervailing duties laws, investment and competition regime. The concern has been the likilelihood of the introduction of trade and competition barriers, and the allienation of FDI. This paper critically examines the impact the country’s antidumping and competition law and practice upon foreign direct investment. Domestic industries have never been shy to file anti-dumping and anti-competition suits against foreign companies, sometimes even when there might be a public outcry. Relevant examples of these suits include the famous Wal-Mart anti-competition case, and recently the Brazilian frozen fowl meat anti-dumping case.
Keywords: Anti-Dumping; Competition; Consumers; Divestment; Domestic Industry; Investments; Protection; Tariffs

Harmonising Public Procurement in the SADC - Harpe, Stephen de la (Journal of Law, Society and Development, 2014)
The promotion of international trade is seen as one of the important instruments to ensure development in developing nations and regions. The history of the World Trade Organisation (WTO) and the drafting of many regional and similar international trade agreements are evidence of this. The Southern African Development Community (SADC) is no exception.1 It is therefore strange that many states that are members of the WTO and actively encourage the opening up of international borders to free trade do not include public procurement2 in such free trade arrangements. This is particularly evident in developing states. If the WTO Government Procurement Agreement (GPA), which is a plurilateral agreement, is considered it is clear that many states do not wish to open their internal markets to competition in the public procurement sphere. It is therefore not surprising that public procurement has been described as the last rampart of state protectionism (Ky, 2012). Public procurement is an important segment of trade in any country (Arrowsmith & Davies, 1998). It is estimated that public procurement represents between 10% and 15% of the gross domestic product (GDP) of developed countries and up to 25% of GDP in developing states (Wittig, 1999). Unfortunately, governments often expect private industry to open up national markets for international competition but do not lead the way. Except for the limited use of pooled procurement,3 no specific provision is at present made for the harmonisation and integration of public procurement in the SADC. In view of the proximity of the member states, the interdependency of their economies and the benefits that can be derived from opening up their boundaries to regional competition in public procurement, the possibility of harmonisation and deeper integration in this sphere needs to be given more attention. The importance of public procurement in international trade and regional integration is twofold: first, it forms a substantial part of trade with the related economic and developmental implications; secondly, it is used by governments as an instrument to address socio-economic issues. Public procurement spending is also important because of its potential influence on human rights, including aspects such as the alleviation of poverty, the achievement of acceptable labour standards and environmental goals, and similar issues (McCrudden, 1999). In this article the need to harmonise public procurement in the SADC in order to open up public procurement to regional competition, some of the obstacles preventing this, and possible solutions are discussed. Reference is made to international instruments such as the United Nations Commission on International Trade Law (UNCITRAL), the Model Law on Public Procurement and the GPA. In particular, the progress made in the Common Market for Eastern and Southern Africa (COMESA) with regard to the harmonisation of public procurement, which was based on the Model Law, will be used to suggest possible solutions to the problem of harmonising public procurement in the SADC.

Political and Economic Integration in the SADC: Reforming the Energy Sector Regulatory System - Jobodwana, Z. Ntozintle (Journal of Law, Society and Development, 2014)
The Southern Africa Development Community (SADC), the African Union (AU) and other African regional economic communities (RECs) have as their ultimate objective the political and economic integration of the African continent. The SADC is home to a number of countries, all of them striving to improve their investment climate to attract foreign investors by reducing the costs of doing business in the region. One way of achieving this is by setting targets for and speeding up political and economic integration, improving interconnectivity and thereby enlarging the market size and enhancing its attractiveness. The SADC region still suffers from high levels of energy poverty through low access levels in all countries except South Africa and Mauritius. Numerous studies have shown that greater regional trading and cooperation on power development within the SADC could substantially reduce investment and operational costs as well as carbon emissions. The need for a regional power trading pool and regional cooperation grew out of the power utilities’ recognition of the vulnerability of individual countries if each continued to pursue a policy of self-sufficiency rather than out of a desire to minimise the social or financial costs of the region’s power. The power sector in southern Africa is undergoing tremendous reforms, more especially since the establishment of the Southern African Power Pool (SAPP) in August 1995. The SADC, however, faces serious challenges that include diminishing surplus generation capacity and the need to ensure that SADC citizens have equitable access to electricity at affordable prices. To meet these challenges, treaties and protocols have been adopted but are failing to deliver at the implementation stage. This article reviews the SADC energy-electricity regulatory framework in the context of economic and political integration and recommends the establishment of an independent regional regulatory authority to oversee the implementation of integrated holistic energy and air pollution control and prevention, and a common climate change policy. Such a regulator would be a highly resourced regional institution that will liaise with international institutions. This independent regional authority will serve as a catalyst for regional economic integration. It will also have a mandate to introduce and coordinate the establishment of an SADC regional emissions trading scheme that will contribute to managing the mitigation of greenhouse gases (GHGs) and the implementation of global warming adaptation strategies in the region.
Keywords: Climate change; Economic integration; Energy regulation; GHGs; Global warming; Political integration; Regional independent regulatory authority; SADC; SAPP; Treaty regime; UNFCCC

Essays in competition policy - Khimich, Aleksandra (Université Toulouse 1 Capitole, 2014)
Dommage économique causé par les cartels: une évaluation pour les pays en voie de développement (En collaboration avec Marc IVALDI, L'École d'économie de Toulouse et CEPR et Frédéric JENNY, ESSEC Business School, Paris) : La détection et la sanction des cartels reste toujours d'une grande importance pour les autorités de la concurrence développées en raison d'une compréhension claire de leur danger potentiel, et donc des avantages de leur dissuasion. Néanmoins, les pays en développement ont souvent du mal à créer ou à renforcer leur autorité de la concurrence - l'exécution d'une division antitrust est coûteuse et la preuve à l'appui concernant les avantages potentiels est toujours manquante. Présente étude fournit la preuve quantitative manquante. Elle propose une évaluation du dommage économique total causé par les cartels en termes de chiffre d'affaires affecté par les pratiques collusoires ainsi qu'en termes de profits excessifs des ententes découlant de surcharge des consommateurs. Les résultats suggèrent que le préjudice économique totale estimé en termes de profits excessifs divisés par le PIB correspondant peut atteindre jusqu’à 1%. En outre, comme la probabilité annuelle maximale de découvrir une entente déjà existante est estimée à environ 24%, il est suggéré que le dommage économique réel dépasse nos estimations, au moins quatre fois. / Évaluation de la précision des outils proposés dans les lignes directrices sur les fusions (En collaboration avec Marc Ivaldi, L'École d'économie de Toulouse et CEPR et Jérôme Foncel, EQUIPPE, Université de Lille) : Présente étude propose une évaluation complète de la précision de deux outils proposés par les lignes directrices sur les fusions les plus avancés - le critère traditionnel HHI et un plus récent UPP - et défini les conditions économiques qui favorisent les prédictions trompeuses. Les simulations de Monte-Carlo sont utilisées pour créer des économies qui sont utilisés pour mesurer les effets des fusions et d'évaluer la performance des outils d'évaluation choisis. Les résultats suggèrent que le test HHI à une capacité très faible de déterminer le potentiel de l'augmentation des prix lorsqu'il est appliqué à un marché de produits différenciés. Dans son tour, le test UPP peut aussi être très trompeur, même si l'on a une information parfaite sur les principaux ingrédients nécessaires pour le calculer. L’étude démontre que certains d'erreurs de type I et de type II se produit parce que les tests de type UPP par construction ne tiennent pas compte de la ‘pression’ sur le prix subie par le partenaire de fusion. Elle aussi explique comment ce dernier peut être réglé en tenant compte du degré de transmission croisé correspondant. / Le rôle du degré de transmission croisé dans les évaluations des fusions : Présente étude démontre que l'ignorance de l’effet de transmission croisé, et en particulier de son signe, peut conduire à des conclusions erronées dans presque toutes les étapes d’évaluation d’une fusion, y compris la procédure de définition du marché et l'évaluation des effets coordonnés et unilatéraux. Par conséquent, l’étude aussi offre un examen des propriétés de l'ensemble de la matrice des degrés de transmission dans un cadre suffisamment général et en même temps plus pratique pour les concentrations horizontales et tire les caractéristiques exactes des systèmes d'offre et de demande qui affectent le signe du degré de transmission croisé.
Keywords: Cartels; Competencia; Competition law; Concurrence; Conditions économiques; Droit international; Pays en voie de développement; Politique de la concurrence

The transfer of movables in the international commercial context – a comparison of German and South African law - Lengyel, Martin (University of Johannesburg, 2014)
L.LM. (International Commercial Law) Please refer to full text to view abstract
Keywords: Contracts (International law); Germany; International Commercial Law; Law of property; Property; South Africa

Proposal for a regulation on a common European sales law - Ciceri, Eliane (LUISS Guido Carli, 2014)
Historical development. Five W of CESL. Common European sales law.

The strategic importance of regional economic integration to multinational companies (MNCs) : a study of South African MNCs' operations in the SADC - Egu, Mathew Eleojo (University of South Africa, 2014)
Though the strategic importance of regional economic integration to multinational companies (MNC) has been researched extensively internationally, this concept has not been studied in South Africa. In fact, there is a growing nostalgia that with the South African Development Community (SADC) moving towards its set macroeconomic convergence targets; regional economic integration eventually leads to macroeconomic stabilisation. This ultimately becomes the root of growth in a region that has been severely affected by globalisation, financial crises, increasing government debt and budget deficit problems. This study, hence, tries to find out how the critical decisions of South African MNCs are made when operating within regional markets. Consequently, statistical econometric models were developed to test time-series data from 1980-2011 using the best (most efficient) linear unbiased estimator (BLUE) ordinary least square regression technique. An analysis was then done to investigate how South African firms have been able to gain maximum benefits by adopting the SADC as its major trading bloc in Africa. The study’s findings showed that the major barriers that impede MNCs of South African origin from penetrating these markets were custom duties, direct and indirect tariffs. It was observed that this would only be reduced by regional integration. Determined to critically interrogate the problems detailed in this research, three hypotheses were tested, analysed and subsequent interpretation of the findings revealed that South African MNCs contribute positively to regional economic growth and investment in the SADC. Furthermore, the study found out that although these factors were important, they were not the only variables that stimulated the competitiveness of South African MNCs in the SADC region. The literature review sections of this study found that the adoption of strategic management initiatives by MNCs improved the operation of transnational companies in South Africa. A comparison between the value of South African MNCs, as well as, other explanatory variables, and the Gross Domestic Product (GDP) of both South Africa and the SADC using time series data for the period 1980-2011 indicated that there was a positive relationship between the contribution of MNCs to South Africa’s economy and the GDP of both South Africa and the SADC. This proved that there is a significant link between MNC growth and national/regional productivity. In conclusion, the study established that the findings of the literature review were theoretically in sync with the empirical analysis. Also, the outcome of this study concurred with the findings of similar research. In essence, regional trade arrangements are an increasingly important element of the global trade environment, of which the move by South Africa’s MNCs to operate in the SADC market was a positive one. Finally, the study found out that for these firms to be successful in the international business arena, business management decisions need to be made, only after a detailed strategic analysis of the significance of regional economic integration is considered. This integrative framework certainly determines the operational efficiency, survival and profitability of most MNCs that operate within the region.
Accepted: 2014-10-01T07:01:54Z
Keywords: FDI; Foreign direct investment; Macroeconomic convergence; Macroeconomic stability; Mergers & acquisitions; Multinational companies; Regional Economic Community; Regional Trade Agreements (RTAs); SADC; South Africa Development Community; Strategic management

Arbitration in administrative contracts : comparative law perspective - Lin, Ching-Lang (Institut d'études politiques, 2014)
Il a été longuement discuté de savoir si le système d'arbitrage est applicable pour régler les litiges administratifs qui concernent certains contrats administratifs ou d’autres sans rapport avec le contrat administratif. Dans cette thèse, les trois questions spécifiques sont analysées tour à tour : (1) Est-il possible pour un arbitre ou un tribunal arbitral de trancher des questions relevant du droit administratif? (2) Y a-t-il, ou devrait-il y avoir, des limitations à l'autorité des arbitres et des tribunaux arbitraux? (3) Enfin, après la délivrance d'une sentence arbitrale, quel rôle devrait jouer l'État dans la phase de contrôle judiciaire? La première question concerne l'arbitrabilité et a été discutée dans la première partie (FIRST PART: ARBITRABILITY). La deuxième question a été discutée dans la deuxième partie (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Enfin, sur la dernière question a fait l’objet d’une troisième partie (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). Dans cette thèse, nous avons comparé les systèmes de quatre pays (Canada, Chine, France, Taïwan). En conclusion, nous pouvons donc conclure que l’évolution de la conception du contrat administratif implique de nombreux aspects, y compris les aspects juridiques, économiques, politiques et même culturels. Le développement de la fonction de contentieux administratif, comme ‘’subjectivement orienté" ou "objectivement orienté" aura une incidence sur l'acceptation de l'arbitrage en matière administrative. Dans l'ensemble, l'arbitrage sera plus acceptable dans les systèmes dont la fonction est plus ‘’subjectivement orientée" que dans ceux dont la fonction est "objectivement orientée". While arbitration has traditionally been considered as a means to resolve private disputes, its role in disputes involving administrative contracts is a crucial question in administrative law. In brief, the three specific questions are (1) Can arbitrators or arbitral tribunals decide issues involving administrative law? and (2) Is there, or should there be, any limitation on the authority of arbitrators or arbitral tribunals? (3) Moreover, after the issue of an arbitration award, what role should the State play in the judicial review phase? The first question, the issue of arbitrability, is discussed in part 1 (FIRST PART: ARBITRABILITY). The second question will be discussed in part 2 (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Finally, on the question of what happens after the arbitration award, we will discuss judicial review in part 3 (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). We compare legal systems between the four countries: in France, in Canada, in China and in Taiwan. We believe that an administrative contract, at least in its function and conception, is gradually becoming different from a private contract. Innovation with respect to administrative contracts will also reflect the concentration and function of the administrative litigation systems in each country. In addition, the “objective” or “subjective” function of administrative litigation will also affect the degree of arbitrability, as well as arbitration procedures. Taken together, arbitration will be more acceptable in systems whose function is more “subjectively oriented” than in those whose function is “objectively oriented". Finally, “the arbitration of administrative matters” traditionally has been an important question in administrative and arbitration law. In the future, we will continue to see it shine in the doctrine and jurisprudence of both the administrative and arbitration law fields.
Keywords: Administrative litigation system; Arbitrability; Arbitrabilité; Arbitrage; Arbitragem; Arbitration; Arbitration award; Contentieux administratif; Contrats administratifs (exécution); Judicial review; Litige; Légalité objective; Objective and subjective function; Prerogative of administrations in contracts; Sentence arbitrale (contestation); Études comparatives

Employees Contract of Employment and Wrongful Dismissal From Service - Ugbele, Sunday; Utobo, O. J. (African Journal of Politics and Administrative Studies, 2014)
Contract of employment was long acknowledged as a subject of genuine and voluntary agreement whose construction or determination should be founded on due notice of the parties thereto. Action for wrongful dismissal would lie if an employment was disturbed, interfered or meddled with, in defiance of the rights of the parties under the contract. The objective of this study was, among others, to determine what constituted a valid contract of employment and remedies for wrongful dismissal. The qualitative and documentary method of data collection was adopted by reference to relevant literature and statutory authorities. From the data gathered, and content analyzed, we found that no law could foreclose an employment from determination, nor could an irregular or wrongful dismissal stand. It was recommended, inter alia, that beside the need to repeal the Public Officers (Protection) Act, both the employer and employee should, in their official dealings, respect the sanctity of their contract, and permit reasonable future modifications thereto as could lawfully enhance the life of the contract and their legitimate desires.

The compatibility of Australian and South African private international law with the Hague Principles on Choice of Law in International Commercial Contracts - Adams, Faadhil (University of Johannesburg, 2014)
In 2006 the governing body of the Hague Conference on Private International Law furnished the Secretariat with a mandate to conduct a series of feasibility studies on the development of an instrument, relating to the choice of law in international contracts. The outcome of these studies was largely successful, finding that there was a need for an instrument of this nature and additionally it would be welcomed by the international legal community. In 2009 the Permanent Bureau of the Hague Conference on Private International Law was invited to form a Working Group (WG) to draft a soft-law instrument affirming party autonomy in international contracts on an international level. The Hague Principles on Choice of Law in International Commercial Contracts (P) was, thus, born. The P were drafted by a panel of experts representing the majority of the world’s legal systems. The working group commentary (WGC will be used to refer to the commentary, whilst WG will be used to refer to refer to the working group itself) which provided the discussions in respect of, and the reasoning behind, the principles has been invaluable in writing this dissertation. The purpose of this dissertation is to investigate the compatibility of Australian and South African law with the P. One of the aims of the P mentioned specifically in the preamble is that these principles are to be used by countries as a model with which to develop their own rules of private international law. A study of the current law as it stands in comparison to the P marks the first step in this exercise, through finding where the law differs we can begin to bridge the disparity between a specific country’s legal system and that of the P. Should the P become an important part of the private international law discourse comparative studies such as this will become common-place. The fact that the principles were drafted as a soft-law instrument is in line with the growing world trend. The flexibility that is achieved through the use of a soft-law instrument may lead to greater legal certainty down the road as contracting parties and international lawyers alike become more familiar with the principles. This familiarity may lead to consensus among experts from around the world and eventually invite the prospect of a binding instrument being drafted
Keywords: Australia; Conflict of laws; Contracts; Contracts (International law); South Africa

Human capital disclosure in corporate annual reports - Adelowotan, Michael Olajide (University of South Africa, 2014)
It is generally acknowledged that human capital intangibles are major value drivers in the new economy characterised by information and technology. The main purpose of this study is to examine the extent to which companies listed on the Johannesburg Stock Exchange disclose information on human capital related issues. The study combined both qualitative (literature reviews and content analysis) and quantitative (survey questionnaire) methods to collect data of 60 corporate annual reports (CARs) of listed companies in South Africa from survey questionnaires administered on various categories of preparers and users of these CARs. The study made use of 91 human capital disclosure checklists developed from literature reviews for the purpose of data collection. The data analysis was done with the aid of Atlasti-a qualitative data analysis software and SPSS- a quantitative data analysis software. The findings show that majority of the items on the disclosure checklist are not yet disclosed in the CARs even though most of the items on the checklist are adjudged to be useful for organisational value creation. In view of the initial findings of this study, a human capital disclosure framework is recommended.
Keywords: Annual report; Corporation reports; Discretionary disclosures; Human capital; Human capital disclosure framework; Intangible assets; Intangible property; Intellectual capital; Mandatory disclosures; Personnel management

Substantive equality, affirmative action and the alleviation of poverty in South Africa : a socio-legal inquiry - Katiyatiya, Luyando Martha (Stellenbosch University, 2014)
Substantive equality is a constitutional imperative, hence the need for strategies that attempt to realise it for the sake of genuine social reconstruction. The principle of equality runs through all other rights in the South African Constitution. Be that as it may, equality is an elusive concept, which makes its achievement an ambitious task. Nonetheless, there are strategies that attempt to bring to the fore the ‘substance’ of the concept in order to ensure the actual realisation of socio-economic benefits. Such strategies include, among others: social security, education, economic empowerment, skills development and affirmative action. This study will focus on the latter of these strategies, namely affirmative action. Although affirmative action is practised around the world, one of the (many) criticisms of the policy is that it fails to bring about substantive or structural change. In other words, it may change the racial and gender composition of the classroom or the workplace, but does not address the challenges that cause the disadvantages of marginalised groups in the first place. It is arguable that affirmative action has increased inequality in South Africa by benefiting the apex of the class structure and not the majority of the population living in abject poverty. This study develops a theoretical analysis of the link between status (race, sex and ethnicity) and socio-economic disadvantage, and the central question that the study addresses is the following: How can the policy of affirmative action be redesigned to ensure that it benefits the socio-economically disadvantaged? A secondary question that is investigated is whether affirmative action can contribute to the development of human capacities in the context of poverty alleviation. It is arguable that substantive equality facilitates the adoption of strategies (such as affirmative action) to address socio-economic inequality, poverty and social exclusion. The research suggests that a paradigm shift is necessary in order to reconceive of affirmative action as a policy that does not only focus on ensuring ‘equitable representation’ of disadvantaged groups in the workforce or the classroom, but also provides for the development of human capacities. This can be achieved if one adopts an expansive view of affirmative action and if one utilises class as one of the numerous criteria for determining the beneficiaries of the policy.
URI: http://hdl.handle.net/10019.1/86607
Keywords: Affirmative action programs; Equality before the law; Politics and government; Public welfare; Social conditions; South Africa

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Harmonising the law of sale in the Southern African Development Community (SADC) : an analysis of selected models - Shumba, Tapiwa (Stellenbosch University, 2014)
It is generally recognised that diversity of laws may act as a barrier to the development of trade, both at international and regional level. In a globalised era, trade is necessary for economic development and ultimately for the alleviation of poverty. Although the WTO has done extensive work towards the removal of tariff barriers, there is also a need to focus on addressing non-tariff barriers which include legal barriers to trade. Institutionalised legal harmonisation at an international level has provided the necessary impetus for the development of harmonised laws in the area of international trade. The creation of regional economic communities within the purview of the WTO has also given rise to the necessity of legal harmonisation to facilitate intra-regional trade. A number of regional economic communities and organisations have noted legal harmonisation as one of their areas of regional cooperation. This study focuses on the need to harmonise the law of international sale within the SADC region in order to facilitate cross-border trade. The study points out that the harmonisation of sales laws in SADC is important for the facilitation of both inter-regional and intra-regional trade with the aim of fostering regional integration, economic development and alleviating poverty. Although the necessity of harmonising sales laws has been identified, no effort to this end exists currently in the SADC region. This study addresses the mechanisms by which such harmonisation could be achieved by analysing three models which have been selected for this purpose, namely the CISG, the OHADA and the proposed CESL. The main issues addressed include whether SADC Member States should adopt the CISG, join OHADA, emulate the CESL or should use any of the other instruments as a model for creating a harmonised sales law for SADC. In conclusion, it is observed that SADC has its own institutional and operational mechanisms that require a process and instrument tailor-made for the unique needs of the region. It is recommended that SADC should create its own common sales law based on the CISG but taking into account lessons learnt from both the OHADA system and the CESL. A number of legislative, institutional and operational transformative and reform mechanisms are recommended to enable the creation of such a community law and ensure its uniform application and interpretation.
Keywords: Africa; Economy; Foreign trade promotion; International unification; Mercantile law; Regional disparities; SADC; Southern African Development Community; Trade law

The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration

Modernizing and harmonizing international contract law: the CISG and the Unidroit Principles continue to provide the best way forward - Dennis, Michael J. (Uniform Law Review, 2014)

International sales contracts in Congolese law : a comparative analysis - Kahindo, Nguru Aristide (University of South Africa, 2014)
To regulate and facilitate are the main functions of legal rules. These purposes are achieved by a harmonised legal system by which the law becomes identical in numerous jurisdictions. The process to unify the law of sale internationally started in the 1920s and culminated, in 1988, in the implementation of the CISG. This Convention intends to provide clarity for most international sales transactions by regulating the formation of contracts, and the rights and obligations of the seller and the buyer resulting from the contract. The CISG has these days enjoyed much ratification and influenced a number of legislation reforms worldwide. Despite the role it played during the drafting process of the CISG, the DRC has not yet ratified it. Instead, the country continued to rely, until recently, on colonial legislations which had become out-dated, and inadequate to meet modern international sales contracts requirements. The situation appears to have been improved a year ago as the effect of the adoption of OHADA law whose Commercial Act is largely inspired by the CISG. Because the introduction of OHADA law in the DRC is very recent, this study intends to assess the current state of Congolese sales law by comparing it with the CISG and South African law, which is non-CISG but modernised. The comparative study aims at establishing whether current Congolese law, as amended by OHADA law, is sufficient or has shortcomings; if it has some, it aims to identify those shortcomings, and make suggestions for their improvements. After discussion, it has been discovered that the ratification of OHADA law has significantly improved Congolese domestic sales law. Given that there remain certain unresolved shortcomings in Congolese international sales law, however, the study ends by a proposal for the accession of the DRC to the CISG in order to fill them.
Keywords: Congo (Democratic Republic); Congolese contract law; Congolese sales law; Contracts; Export sales contracts; Formation of the contract; International sales law; OHADA law; Obligations of the buyer; Obligations of the seller; Sale of goods; South Africa; South African contract law; South African sales law

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

An evaluation of the predictive value of bank fair values - Ehalaiye, Oludimu Oluseun (Victoria University of Wellington, 2014)
This thesis examines whether the net asset fair values of banks possess predictive ability for the banks’ future cash flows and earnings. This is an important issue considering the arguments for and against the wider use of fair value accounting for banks’ financial instruments and the claim by some that fair values during economic recessions (where markets may be illiquid) are irrelevant and largely unreliable. A number of studies have found that the explanatory power of bank fair values when compared to traditional historical cost are more value-relevant based on capital market reactions. However, there is a very limited literature on how bank fair values are related to the future performance (e.g. earnings and cash flow) of banks. This study fills this gap by providing empirical evidence on the relationship between U.S. bank fair value disclosures and banks’ future performance as measured by operating cash flows and earnings over a three-period future horizon. Furthermore, the thesis provides evidence on the relationship between bank fair values, in terms of the levels classification introduced during the 2008 global financial crisis, and the future performance of banks, thus showing whether market illiquidity affected the underlying relationships. The study examines two distinct periods. The first study period, 1996-2005, was based on annual data of banks with minimum total assets of $US150 million as of year 1996. The second study period from 2008-2010 (this period encompassed the global financial crisis period and also the levels classification of bank fair values according to SFAS 157), was based on quarterly data of banks with minimum total assets of $US150 million as of the first quarter of 2008. The thesis provides strong evidence that there is a predictive relationship between bank fair values and future bank performance. The evidence is strong during the first study period from 1996 to 2005 where the current net asset fair values of on-balance sheet financial instruments of banks were significantly associated with future operating cash flows and operating earnings of such banks over a three-year future time horizon. However, the predictive relationship between net asset bank fair values and operating cash flows is stronger than the predictive relationship between net asset bank fair values and operating earnings. In the second study period, from 2008 until 2010 the empirical results show strong evidence that there is a predictive relationship between level 1 and level 2 bank fair values and future operating cash flows. The findings from the empirical results were that the current quarter’s level 1 and level 2 net asset fair values of banks were significantly associated with the future quarters’ operating cash flows of such banks. The level 3 net asset fair values of such banks in most cases were not significantly associated with the banks’ future quarterly operating cash flows. The corresponding relationships for operating earnings were that the current quarter’s level 1 net asset fair values of banks were positively associated with the future quarters’ operating earnings of such banks. However, the level 2 net asset fair values of banks were negatively associated with the future quarters’ earnings of such banks. This result is in contrast to the results obtained when the predictive relationship between level 2 bank fair values and future operating cash flows was evaluated, where it is found that both level 1 and level 2 net asset bank fair values are positively related to future quarterly bank cash flows. Further empirical analysis showed that a possible reason behind this disparity was that there was a structural change in the relationship between bank operating cash flows and operating earnings over the course of the first and second study periods, where, in particular, for the second study period (which includes the period of the global financial crisis) there was a systematic downward bias in operating earnings relative to the operating cash flows of the sampled banks. This in turn makes operating earnings a poor proxy for operating cash flows during the second study period. The findings from this study provide confirmation that net asset fair values have predictive ability as argued by Ball (2008); Barth (2006b) and Tweedie (2008). The study findings that net asset fair values have predictive ability is consistent with the FASB’s view that the asset values shown in firm financial statements should communicate information about the potential future financial performance of the affected firms (FASB 2010:17). Furthermore, the study also confirms that objectively determined bank fair values based on market prices rather than model based bank fair values provide greater predictive value in relation to future performance as measured by operating cash flows. Lastly, this thesis showed that during the first study period (where there was no financial crisis) that bank size, capital adequacy and growth prospects, had little impact on the results obtained, while for the second study period, there were cases where bank size and bank capital ratios did have a significant impact on the predictive relationship between bank fair values and future cash flows. The study contributes to the fair value accounting and accounting standard-setting literature and highlights that fair values have predictive ability, especially with respect to future operating cash flows of banks, both during and outside of periods of financial crisis.
Keywords: Economic forecasting; Fair value; Predictive value

Globalization and Private International Law in Commonwealth Africa - Oppong, Richard (University of Arkansas at Little Rock Law Review, 2014)

Alternative Dispute Resolution (ADR): An Overview of Some Common Mechanisms, and their Strengths and Weaknesses in Context - Perrin, Harry (The Plymouth Law & Criminal Justice Review, 2014)
Alternative Dispute Resolution, or ’ADR’, offers parties in dispute an alternative to traditional court-based litigation, which is often seen as slow, costly and ineffective. ADR frequently involves a neutral third party who will settle or facilitate resolution of the dispute. This paper examines three common ADR mechanisms, adjudication, arbitration and mediation, and explores their relative advantages and disadvantages in different contexts.
Keywords: ADR; Adjudication; Alternative dispute resolution; Arbitration; Construction adjudication; Mediation; Negotiation

Addressing the legal issues of an innovative start-up company - Samoylov, Vlad (Victoria University of Wellington, 2014)
Before examining the substance of the law it is necessary to discuss the contrast between law and practice. It is important to keep in mind that the letter of the law is sometimes not what is done in practice. This realisation is often referred to as the “law and society perspective.” Advocates of this perspective treat legal doctrine as more than just a closed system because they recognise that there are other external influences at play. Beyond the law, people are also influenced by other factors such as social roles, morals, religion and culture. For example, university researchers have an external incentive mechanism outside of IP law. Such researchers frequently prefer to publish their results and discoveries in academic journals rather than file for patents. A patent cannot be granted where there has been a publication. However the researchers are motivated by other incentives such as access to research funds and the attainment of professorship. The Law and Society perspective highlights the fact that the formal processes, which are provided for by the law are at times substituted by informal customs and understandings. An information technology (IT) firm that contributed to this paper by participating in an interview (Interviewee A), provided a good example of such an occurrence. Rather than use any of the formal IP modes of protection which are discussed in the following sections of this paper, ‘Interviewee A’ uses a very unorthodox strategy to protect their IP. They said: “we rely on employment contracts, code of conduct, and especially personal ethics and behaviour to protect our IP. We therefore have a company culture that encourages teamwork and cooperation”.
Keywords: Intellectual property; Product safety standards

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

A macro-financial theory of corporate financing and forecast modelling of market movements - Sutton, David (Victoria University of Wellington, 2014)
This thesis identifies a gap in existing theories of corporate finance. This gap is an implication of a Keynesian-Minskian analysis of markets and market-based economies. From a founding theoretical perspective rooted in the view that markets are not reliably efficient the case is developed that past price trend extrapolation is an important factor in corporate financing decisions. At a macro-financial level, companies repurchase equity over periods of strong market rises, while increasing debt at the same time. During periods of sustained, substantial market decline debt is retired and large new equity issues occur. This change in corporate financing is implicitly expensive as relatively low prices are realised for the new stock issued at these times. These factors suggest that conventional theories of corporate financing decisions that rely on corporate rationality and optimisation do not provide a compelling fit with observations in the period 1980-2012. Moreover, inference to Minsky’s (1986) argument that companies are compelled through market declines to shore up their balance sheets provides a better fit with the evidence. These arguments form the basis for the development of the ‘extrapolative expectations’ theory of corporate finance. The second major development in this thesis draws on the theoretical development outlined above to create market movement description and prediction models. These models operate on data drawn from the US Standard & Poors 500 index over the period 1980-2012. Two primary models are developed using binomial logistic regressions. The dichotomous dependent variables are drawn as quarters of market rise (1) or no rise (0), and market falls (1) or no fall (0), respectively for the ‘buy’ model and the ‘sell’ model. Variables tested and those found to add to an explanation of the dependent variables include: corporate debt flows, corporate equity flows, corporate dividend flows, interest rates, market volumes, and historical market levels. Each variable is tested for up to ten lags (two-and-a-half years). Collectively, the variables add to our understanding of those factors influencing (or at the least, signalling) market levels, enabling quarter ahead market forecasts to be made with greater accuracy than arises from an assumption of a random walk. This conclusion crystallises the view that company macro-financial flows and prices are an important cause or signal of future market direction.
Keywords: Corporate financing; Financial Accounting; International Accounting; Macro-financial; Minsky

Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Accepted: 2015-01-15T16:55:51Z
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Regulating trade in petroleum under the WTO Regime: trade rules vs. reality of the petroleum industry - Bitenov, Gani (McGill University, 2014)
This thesis critically assesses the effectiveness of WTO legal rules in the regulation of international trade in petroleum and highlights potential conflicts between competing resources of energy from the WTO regime’s perspective. The theoretical framework of the thesis is built on the concepts used in natural resource economics, trade theories and international relations. On the basis of Hotelling’s rule of natural resource economics, it proposes a model that reconciles the use of petroleum and the development of renewable sources of energy in the power generation sector, which prospectively can be adopted with respect to the transport sector and other sectors involving energy use. The proposed model may improve global sustainable development. However, it is argued that WTO rules are not properly designed to regulate trade in petroleum and, if applied without due respect to specific issues pertaining to the petroleum industry, would obstruct the achievement of the social optimum, and detrimentally affect the national economies of WTO members and global welfare in general. To improve the WTO system, I propose a reformation of its normative ideology through the introduction of the strategic trade policy theory in complement to the neoclassical theory of trade, at least when trade in energy is concerned. On the basis of the study of the applicability of WTO rules to trade in petroleum and a review of proposals put forward by other scholars to improve the regulation of trade in energy, it is argued that the most effective way to improve the trading regime is to negotiate a new general agreement on trade in energy.The role of the WTO in the regulation of trade in energy is analyzed through a regime management theory borrowed from international relations studies. It is argued that the WTO as a regime manager is capable of improving the regime by properly maintaining the existing equilibrium and by initiating, and leading in negotiations of a new equilibrium.
https://escholarship.mcgill.ca/concern/theses/ws859j68h
Keywords: Petroleum industry and trade; Trade regulation; WTO trade rules

Three Essays on Financial Distress and Corporate Bankruptcy - Chen, Donghui (McMaster University, 2014)
This thesis explores three important issues in financial distress and corporate bankruptcy: bankruptcy venue choice and creditor recovery, the efficiency of Chapter 11 corporate bankruptcy and distressed exchanges, and the bankruptcy ripple effect on peer firms’ investment policy.
Keywords: Bankruptcy; Contagion effect; Corporate Bankruptcy; Distress exchange; Efficiency; Financial distress; Forum shopping; Insolvency

Three theories of Lex Mercatoria - Cuniberti, Gilles (Columbia Journal of Transnational Law, 2014)

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Accepted: 2014-07-14T15:02:04Z
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments

The impact of the unfair commercial practices directive (2005/29/EC) on contract law - Đurović, Mateja (European University Institute, 2014)
This thesis examines the relationship between the law on unfair commercial practices and consumer contract law. The thesis develops the claim that Directive 2005/29/EC, on unfair commercial practices (UCPD) has had a strong impact on the content of consumer contract law, despite the declaration concerning the independence between both branches of law contained in Article 3(2) UCPD. In order to substantiate this claim, the thesis examines the implications for consumer contract law of the main components of the regulatory regime laid down by the UCPD, namely, (1) the notion of average consumer, (2) the duty to trade fairly, (3) the duty of information and (4) the remedies. By looking both at the theoretical underpinnings and at the actual operation of this regulatory regime, the thesis casts light on the way in which the UCPD has shaped consumer contract law. The thesis further shows that this is an ongoing phenomenon whose ramifications may be far-reaching, for it implies that the UCPD is powerfully fuelling the Europeanization of contract law.
Accepted: 2015-02-09T12:46:29Z
Keywords: Consumer protection; Contracts; European Union countries

Establishing an international registration system for the assignment and security interest of receivables - Jon, Woo-Jung (Oxford University, 2014)
Legal systems around the world vary widely in how they deal with the assignment of receivables. This legal variety makes it difficult for financiers to conduct their international receivables financing business. This thesis suggests an International Registration System for the Assignment and Security Interest of Receivables (‘IRSAR’) and proposes a model international convention for the IRSAR (‘proposed IRSAR Convention’), which could help financiers to overcome the obstacles they currently encounter. Under the proposed IRSAR Convention, the international assignment of receivables would be regulated by a unified legal system with respect to priority and perfection. The IRSAR would facilitate international project financing. Furthermore, the IRSAR would enable companies to raise finance from greater ranges of investors around the world through international receivables financing and to dispose of non-performing loans more easily. The proposed IRSAR Convention would succeed the UN Convention on the Assignment of Receivables in International Trade in the attempt of establishing a registration system for international assignments of receivables. The proposed IRSAR Convention confines its scope of application by defining the assignor (or the security provider), inventing the concept of ‘Vehicle for the International Registration System’ (‘VIRS’). The proposed IRSAR Convention applies where the assignor or security provider is a VIRS. An assignment of a receivable where the assignor is a VIRS and a security interest in a receivable where the security provider is a VIRS could be registered in the IRSAR. Under the proposed IRSAR Convention, priority of assignments of and security interests in receivables is determined by the order of registration in the IRSAR. The proposed IRSAR Convention would be a receivables version of the Cape Town Convention. With respect to the contents and effect of registration, it would prescribe a notice-filing system along the lines of that adopted in the UCC Article 9. With respect to the operation of the registration, it would adopt an automatic online registration system operating 24 hours a day, 365 days a year like the International Registry under the Cape Town Convention.
Keywords: Comparative law; Contract; Property law; Restitution; Tort

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

Chapter 4 offer regulation under the 2008 Companies Act - Labuschagne, Frederik J. (University of Pretoria, 2014)
Chapter 4 of the Companies Act of 2008 aims to regulate offers to the public of securities and is reviewed against the principles which underscore the regulation of offerings. An overview of the historical development of the company which is parallel to the regulation of securities shows the crystallized principles which are compared against the development and enactment of the current regulatory regime. The concept of “complete law” as key element to effective regulation is discussed and applied in the review of Chapter 4 determining the effectiveness of the dispensation. The three determining concepts of regulation: the “offer,” “securities” and “public” are studied against the definitions which determine regulation and the inclusion of secondary market regulation of unlisted securities. Serious shortcomings in the process are identified. These errors, together with the practical problems of defining and regulating the secondary market in Chapter 4 read with the remainder of the delineating definitions, concludes that the current system is not in line with the principles of regulation and the Grundnorm of fraud prevention, resulting in Chapter 4 falling under the concept of “incomplete law” resulting in a high probability of enforcement failure and inefficiency. A comparative overview related to the jurisdictions of the United Kingdom and the United States follows with recommendations aimed at amending Chapter 4 relating to the regulatory regime in toto as well as the regulation of unlisted securities in the secondary market.
URI: https://repository.up.ac.za/handle/2263/45981
Keywords: Companies Act; Offer regulation

A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa

A critical discussion on foreign direct investment in the multilateral trade system and development in SADC - Nhlakanipho, Macmillan Zikalala (University of KwaZulu-Natal, 2014)
Development is understood to be an economic process that aims at a constant improvement of the well-being of all individuals who have the right to participate and benefits from the fruits of development. Development is also a right that requires a progressive realisation by governments, international communities and private sectors to the satisfaction of all individuals. A progressive realisation of this right requires a vibrant economy, which can be acquired through International trade and Foreign Direct Investment (FDI). It is in this context that this thesis has attempted to discuss the influence of FDI and International trade on development. The discussion was initiated by focusing on the history of the multilateral trade system (MTS) by looking at various Ministerial rounds of both the General Agreement on Tariffs and Trade (GATT) and the World Trade Organisation (WTO). In this discussion the thesis found that, whilst there are various multilateral political frameworks regulating trade, FDI is subject to regional and domestic political frameworks. The thesis also discussed development in relation to the millennium development goals (MGDs). It was established the goal eight of the MDGs requires the integration of poor countries into the MTS so that they can be able to exploit their comparative advantage. This goal influenced the launching of the Doha Development Agenda (DDA) at the Doha round in 2001. However, the thesis also established that conclusion of the DDA has been progressing at a slow pace. Therefore it has not yielded substantial results for poor countries. The failure to conclude the DDA has led to an increase of Regional Trade Agreements (RTAs), which some scholars view as a supplement of multilateral trade integration. However, the SADC region has not been able to conclude their integration objectives due to the fact that many member states belong to other RTAs. In the case of FDI the thesis established that FDI is accompanied by a wide range of resources for host countries, which can be utilised for enhancing development. However, it was also established that the SADC has not been able to attract lucrative FDI due to a wide range of factors that impede FDI. On this finding, a case study was employed on four countries in the region, namely Angola, Botswana, South Africa and Zimbabwe.
Keywords: Economic Policy; FDI; Foreign direct investment; International Trade; International economic relations; Investments

Legitimation of the economic community of West African states (ECOWAS): a normative and institutional inquiry - Nwankwo, Chidebe (Brunel University, 2014)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University LondonThis study is an attempt at determining the normative legitimacy of the Economic Community of West African States (ECOWAS). At its core, it scrutinizes the current mandate of the organization following the layering of economic integration objectives with human rights protection, sustenance of democracy, and the rule of law. The study discusses the elements of legitimacy across disciplines mainly, international law, international relations and political science. Legitimacy is eventually split along two divides, the normative and descriptive/sociological aspects. The study traces the normative content (shared/common values) underlying integration in Africa, concluding that integration has been born on new ideals such as human rights, democracy and the rule of law. Expectedly, Regional Economic Communities (RECs) as building blocks of the prospective African Economic Community (AEC) under the African Union (AU) regime are mandated to play a vital role in moving the continent forward upon these values. The inquiry is extended to the institutions of ECOWAS to determine their capacity to effectively implement the new mandate of the organization and operate supranationally. In the process, key legal and institutional shortcomings are discussed, particularly in relation to national institutions. It is argued that while human rights protection enhances the normative legitimacy of ECOWAS, it must not be pursued in isolation. Economic integration and protection of citizens’ rights are co-terminus and mutually reinforcing. Hence, community institutions must reflect this link if they are to be effective. The study concludes on the note that, while ECOWAS possesses layers of legitimacy, and have carried out legitimation steps, it cannot be considered a legitimate organization if Member States continue to be non-compliant with community objectives and if key legal questions remain unaddressed. It is submitted that ECOWAS is merely undergoing legitimation, whether it can eventually be considered a legitimate organization is dependent on addressing the identified challenges
Brunel University Research Archive
Keywords: AU; Democracy; ECOWAS; Human Rights; Humanitarian Intervention; Legitimacy; Peace and Security; Regional integration

The action for injunction in EU consumer law - Ogorzałek, Magdalena (European University Institute, 2014)
In 1998 the European Union adopted a new self-standing instrument of collective enforcement - the Action for Injunction. Until then, the main focus was on the improvement of the position of the individual consumer through the adoption of substantive consumer law directives. The Injunction Directive provides for a general framework on consumer law enforcement in national and cross-border litigation. Qualified entities, public agencies and/or consumer organisations, are granted legal standing. National courts are bound to mutually respect the standing of EU wide registered qualified entities. Outside these clear-cut rules on the mutual recognition of standing, the Injunction Directive remains largely silent. The implementation into 28 Member States swiftly revealed the rather limited harmonising effect. The thesis investigates and explains how despite the legally approved diversity, the Injunction Directive contains the potential to turn diversity into convergence. The key to understanding the potential is the thesis of dualism of enforcement measures. Read together with the Annex the Injunction Directive establishes the deep interconnection between collective and individual enforcement, of substantive and procedural enforcement, of judicial and administrative enforcement. The different levels and means of enforcement should not be regarded separately but should always be looked at in their interplay, in their mutual institutional design and their mutual impact. Evidence for convergence can be found in the Invitel judgment of the ECJ and in the practice of consumer organisations via co-ordination actions across borders by which they overcome the boundaries of collective vs. individual or judicial vs. administrative enforcement. Regulation 2006/2004 re-adjusts the dualistic structure of enforcement in favour of public bodies and promotes convergence through para-legal means, through new modes of enforcement, through co-operation and co-ordination outside courts and in open interaction between administrative bodies, to which consumer organisations are admitted on approval only.
Accepted: 2015-02-09T14:17:54Z
Keywords: Consumer protection; European Union countries; Injunctions

The role of competitors in the enforcement of state aid law - Pastor Merchante, Fernando (European University Institute, 2014)
State aid law is made up of rules and procedures whose main characters are the Member States – as the addressees of the norms – and the Commission – as their enforcer. The prominent position of these two actors often overshadows the impact that the administration of the rules on State aid has on private undertakings, be it the beneficiaries of State aids or their competitors. This thesis is concerned with the latter. The aim of the thesis is to assess the extent to which competitors may rely on the rules on State aid to protect themselves against the potentially harmful effects of subsidies and other forms of state, financial assistance to firms. This endeavour raises two challenges. The first challenge is to identify the channels through which competitors may voice their interest in the context of a system of governance to which they are in principle alien. This is the issue of access. The second challenge is assess the likelihood that the Commission shall heed to the concerns voiced by competitors. In other words, the challenge is to gauge the power of influence that competitors may exert through each of these channels. This is the issue of leverage. In order to carry out this inquiry, the thesis scrutinizes the means of redress available to competitors before national courts (“private enforcement”), as well as the opportunities that they have to make their voice heard in the course of the Commission’s procedures (“public enforcement”) – namely, the possibility to lodge complaints, the possibility to participate in the consultation phase of Article 108(2) TFEU and the possibility to seek the judicial review of State aid decisions.
Accepted: 2015-02-09T14:56:15Z
Keywords: Antitrust law; European Union countries; Government aid; Restraint of trade; Subsidies; Unfair Competition

Competition law and standard essential patents : oscillating between protection of patent rights and access to standards - Petrovčič, Urška (European University Institute, 2014)
This thesis explores the way in which EU and U.S. antitrust rules address opportunistic conducts that emerge in the context of standard essential patents (SEPs). The analysis finds that the two systems have very different scopes in addressing those practices: conduct lawful under U.S. antitrust law is condemned by the EU competition law and vice versa. In contrast to other fields of antitrust, the differences between the EU and U.S. approach do not arise from the application of different legal standards, but rather reflect the core divergences in the statutory texts that address unilateral practices. The analysis also shows that both in the European Union and in the United States, competition authorities have tried to increase the scope of competition law—first, by stretching the antitrust doctrines outside established borders, and second, by advocacy measures designed to avoid opportunism related to SEPs. The thesis shows, nonetheless, that both approaches are problematic and a more cautious strategy is needed to avoid the risk of injecting imbalance in the standardization context.
Accepted: 2014-10-02T12:32:07Z
Keywords: Antitrust law; Competencia; Competition law; European Union countries; Patent licenses; Unfair Competition; United States

Copyright and developing countries a critical examination of recent developments in copyright law with particular reference to the impact on developing countries and access to educational materials - Siphepho, Nomvuyo Nicole (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Copying processes; Copyright; Developing countries; Instructional materials industry

The requirement of consent for the transfer of shares and freedoms of movement : toward the liberalization of private limited liability companies : a comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law - Vicente, Lécia (European University Institute, 2014)
Toward the Liberalization of Private Limited Companies – A comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law’, I try to shed light on the dynamics of private limited liability companies (PLLCs), and how they can be legally designed to become efficient units of economic development in Europe and the United States. I take a social sciences approach to the legal question: How does the design of clauses establishing restrictions on transfer of shares of private limited liability companies affect investment made in these companies and their consequent development? To answer this question, I develop two parallel lines of investigation. First, I undertake an embedded historical study to trace the evolutionary patterns of PLLCs in six countries. Furthermore, I longitudinally track the standards of behavior of market agents in the selected jurisdictions. Second, I develop my legal research by looking at an anomaly regarding the transfer of shares and changes in the ownership structure of these business organizations. Transfer of shares in PLLCs is, for the most part, regulated by default rules which impose restrictions on transfers. Typically, the parties do not contract around these default rules. The anomaly lies in the fact that, even though shareholders of these companies do not opt out of these rules, shareholders often ignore them and/or breach them at a later stage.
Keywords: Business enterprises; Corporate law; Limited liability; Private companies

Economies of scope, modularity and property rights in software technologies - Özaygen, Altay (Université Evry-Val-d’Essonne, 2013)
Cette thèse étudie le rôle des différents régimes de propriété intellectuelle (DPI) et évalue ses conséquences sur l'industrie du logiciel. En outre, ce travail porte sur l'équilibre entre deux modèles de logiciels, celui des logiciels privés et celui des logiciels libres et open source, et cherche à évaluer leurs effets sur la performance des entreprises. Ainsi nous discutons dans un premier article les facteurs clés de la cinquième révolution technologique à travers le concept de paradigme technoéconomique (Freeman et Perez, 1988) et nous considérons l'open source comme le principal de ces facteurs. D'autre part, nous étudions les trois aspects des technologies logicielles. Les caractéristiques structurelles des logiciels, c'est-a-dire les économies de gamme (Panzar et Willig, 1981; Teece, 1980) et la modularité (Parnas, 1972; Langlois et Robertson, 1992) représentent les deux premiers. Le régime de propriété intellectuelle, qui est a l'origine des particularités institutionnelles du logiciel (Mazzeloni et Nelson, 1998b), représente le troisième aspect. Au sein de cette thèse nous utilisons différentes méthodologies et considérons plusieurs technologies logicielles pour répondre à nos questions de recherches. Les économies de gamme de logiciels sont étudiées à travers une simulation multi-agents. La recherche sur la modularité est effectuée par une analyse des brevets sur la technologie d'indexation de vidéo. La question des DPI est examinée dans deux chapitres différents. Dans un premier chapitre, une analyse de données de panel est faite pour démontrer l'effet du brevetage et de la contribution au projet du noyau Linux sur la performance des entreprises. Le second chapitre traite quant à lui d'un cas particulier où l'innovation ouverte est réalisée par un groupe de recherche en ingénierie du logiciel au sein d'Alcatel-Lucent Bell Labs, Nozay, France. Ces exemples uniques ne peuvent conclure sur aucune tendance macro sur l'industrie du logiciel, mais cette thèse vise à alimenter les discussions sur les droits de propriété intellectuelle au sein de l'industrie du logiciel.
Keywords: Analyse de brevets; Industrie – Logiciels; Intellectual property; Logiciels libres; Modularity; Open source; Propriedade intelectual; Propriété intellectuelle; Software industry

Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.

Copyright : rebalancing the public and private interests in the areas of education and research - Wang, Jia (Stellenbosch University, 2013)
The general public should have wide access to copyrighted materials for education and research. However, since the current copyright law system subtly favors copyright holders, it is time to re-evaluate copyright law to ensure it meets its original purpose of promoting the learning of the society. The research primarily focuses on how to broaden copyright limitations and exceptions for the public to access and use learning materials. Within the framework of the copyright law system, other mechanisms that allow users to access copyrighted materials at a reasonable price also are considered. Such mechanisms include an efficient collective copyright management system and various licensing schemes. In an information network environment, it is time for developing countries to reform copyright law in order to promote education and research. It is hoped the findings of this study not only benefit South Africa and People's Republic of China, but also provide insights and guidelines to other developing countries with similar conditions.
URI: http://hdl.handle.net/10019.1/85834
Keywords: China; Copyright; Economic aspects; Education and copyright law; Effect of copyright on ICT; Freedom of information and opinion; Globalization and education; Information and communication technology; Intellectual property; South Africa

The influence of the Consumer Protection Act 68 of 2008 on the common law of sale - Barnard, Jacolien (University of Pretoria, 2013)
The purpose of this thesis is to investigate to what extent the Consumer Protection Act 68 of 2008 (CPA) influences the common law of sale in South Africa. “Common law of sale” refers to the essentialia of sale (the minimum characteristics that parties must have consensus on to conclude a valid sale). The parties must have consensus on the intention to buy and sell, the things sold and the purchase price. The common law of sale also refers to the common law duties of the parties, the duties of the seller in particular (conversely therefore the rights of the buyer). The primary duties of the seller which will be investigated are: a. the duty of safe-keeping (including and investigation into the passing of benefit and risk doctrine); b. the duty of delivery and transfer of ownership; c. the warranty against eviction; and d. the warranty against latent defects. The primary common law duties of the buyer to pay the purchase price and accept the thing sold are included in the investigation as well. The formalities required in certain sale agreements, that wording must be in plain language as well as the buyer’s cooling-off rights are also investigated. An investigation into the influence of the CPA on the common law of sale in South Africa warrants a systematic framework and modus operandi which are: a. an investigation into the historical background of the common law of sale and its principles in the Roman law and Roman-Dutch law; b. a critical analysis of the position where the CPA is not applicable (the common law position); c. an extensive analysis and critical evaluation of the relevant provisions of the CPA and the influence thereof on the common law of sale; d. a comparative analysis of the appropriate provisions in Scotland and Belgium; e. a conclusion of the influence of the CPA on the common law of sale (whether the particular common law of sale principle is confirmed, amended or excluded in terms of the Act); and f. recommendations (taking into account the comparative analysis) regarding the rectification of uncertainties and ambiguities that arose as a result of the investigation. It is also important to remember that the existing principles of the common law of sale will still be applicable for transactions and agreements which fall outside the application of the Act. The golden rule to keep in mind when investigating the influence of the CPA on the common law of sale is to determine which approach and interpretation will be most beneficial to the consumer.
https://repository.up.ac.za/handle/2263/32798
Keywords: Common law of sale; Consumer Protection Act; South Africa

Business income and passive income in the UN model double taxation convention - Mascia, Susanna (LUISS Guido Carli, 2013)
The historical evolution of the UN model convention. The UN model convention’s subjective and objective scope. The determination of active income: current points of difference between the UN and OECD models. The determination of passive income: differences and similarities between the UN and the OECD model conventions. Transfer pricing.

Three Essays on Bank Lending and Corporate Finance - Chen, Liqiang (McMaster University, 2013)
This thesis includes three essays on several important topics in empirical finance: Chief Executive Officer (CEO) risk-taking incentives, the cost and syndicate structure of bank loans and corporate investments with internal funds. This thesis contributes to these aspects of finance literature and the three essays are presented in Chapter 2, 3 and 4. The first essay investigates how implicit contractual relationship between creditors and borrowers attenuates the conflict of interest between creditors and shareholders that arises from CEO compensation contracts when a corporation can be considered a nexus of explicit and implicit contractual relationships among stakeholders. We find that bank loans for firms with CEOs who are provided with risk-taking incentives have higher spreads and shorter maturities. A relationship between the lender and its borrower mitigates the influence of incentives for CEO risk-taking on loan spread and loan maturity. Such a relationship is especially beneficial for informationally opaque firms. The results are robust to the endogeneity of relationships and the simultaneous determination of loan spread, loan maturity and collateral requirements. Our results highlight the importance of the interaction between explicit and implicit contractual relationships to a firm’s borrowing cost. The second essay investigates the effects of a borrowing firm’s CEO risk-taking incentives on the structure of the firm’s syndicated loans. The conflict of interest between creditors and shareholders arising from CEO risk-taking incentives is a major concern of borrower moral hazard for syndicate lenders, which require intensive monitoring by lead arrangers in a syndicate. When CEO risk-taking incentives are high, syndicates are structured to facilitate better due diligence and monitoring efforts. These syndicates have a smaller number of total lenders and are more concentrated, and lead arrangers will retain a greater portion of the loan. Moreover, we examine the factors that affect the link between CEO risk-taking incentives and syndicate loan structure. CEO risk-taking incentives have a lesser effect on the syndicate structure when lead arrangers have a good reputation and have a prior lending relationship with a borrowing firm. By contrast, CEO risk-taking incentives have a greater influence on syndicate structure when borrowing firms are informationally opaque, are financially distressed or have low growth prospects. The third essay studies corporate investments with internal funds when firms face real investment friction using a sample of U.S. oil companies from 2003 to 2011 before and after the 2008 financial crisis. We show that firms’ capital expenditures are more sensitive to their lagged cash holdings than to their contemporaneous cash flows. By making investments with realized cash holdings, firms can avoid the investment adjustment costs that are incurred when investing with uncertain cash flows. We also show that cash flow policies are affected by liquidity constraints following the 2008 financial crisis: firms build up more cash reserves from cash flows, cut back payouts and raise more debt to maintain cash holdings.
Keywords: Bank lending; Cash flows; Cash holdings; Corporate Finance; Executive compensation; Financial Management; Investments; Managerial incentives

Arbitrating and Mediating Disputes: Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, 2013)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.

Legal aspects of privately financed infrastructure projects (PFIPs) in China: the case for international standards - Liang, Shuang (University of Leeds, 2013)
This thesis discusses the reform and improvement of Chinese legislation on Privately Financed Infrastructure Projects (PFIPs), to develop the PFIP model in China, under the protection of Chinese laws, so that its implementation in China may reach international standards. Existing Chinese laws are found to be insufficient in reducing risks to PFIPs because of certain shortcomings. Therefore, it is necessary to reform and improve Chinese legislation on PFIPs, to prevent their failure. The Legislative Guide and Model Provisions drafted by UNCITRAL are treated as the international standards to guide Chinese legislation reform on PFIPs. Other countries’ laws on PFIPs provide supplementary reference. This thesis addresses its aim in four steps: First, the current Chinese legislative and institutional framework on PFIPs is reviewed, with discussion on establishing a more appropriate legislative and institutional framework, to facilitate the development of PFIPs in China through the principles of transparency, fairness, long-term sustainability and the elimination of undesirable restrictions. Second, Chinese laws on the concessioner selection procedure in PFIPs are reviewed, with discussion on possible improvements to the laws to achieve international standards of fairness and transparency. Third, current Chinese laws and policies which affect the various contracts involved in PFIPs are reviewed, with discussion on these may be improved to achieve international standards. Fourth, the PFIP dispute settlements that may be used in China are reviewed, with discussion on the necessity to remove certain undesirable restrictions in relevant Chinese laws. Following the rapid rise in the practical use of PFIPs in China, this thesis offers a strong theoretical basis for suggesting a reform of Chinese legislation on PFIPs. It also provides a general basis for any national reform of laws on PFIPs in any other countries.

The advent of OHADA Cooperatives companies - An Insight into management control - Monkam, Cyrille (Revue de l'ERSUMA, 2013)
The stability of a cooperative society depends in part on the effectiveness of its leaders. To maintain this efficiency, management actions are always subjected to control by a number of people and structures that have been assigned by the legislature. They have a preventive control (consisting of an alert procedure and management expertise) and accounting control whose main goal remains the search for transparency in the management of social affairs. The guarantee of this transparency is achieved by the various sanctions that threaten managerial leaders in both their personal property and their freedom. This threat will make the cooperative a viable economic entity and also protects the interests of its members.
Keywords: Control; Cooperatives leaders; Interest; Management; Sanctions; Transparency

The Proposal for a Common European Sales Law And the Convention on the International Sale of Goods: Friends or Foes? - Calomme, Caroline (Europeanisation of Private Law, 2013)
This essay examines the relationship between the proposal for a Common European Sales Law and the Convention on the International Sale of Goods in B2B transactions and its future outcome on the law applicable to international commercial transactions: friends or foes? In order to do so, the analysis is comprised of six elements. The first section asks what threat the legal relationship between the two instruments poses. The second section evaluates how and to which extent business behaviour plays a role in the reliance on optional instruments. The next section inspects the level of achievement of the CISG from a diplomatic, legal and business perspective. Subsequently, the consequences of the European instrument on the legal environment are explored. Next, a series of examples illustrate whether the relationship between the two instruments is one of competition or of cooperation. Lastly, the future prospects for both instruments are looked at. In the end of this research, it is submitted that the CISG will enhance the chances of success of the CESL in the long term even though it is likely to affect its popularity for commercial transactions in the short term. Reversely, the CESL will pose a threat to the CISG in the beginning but it will progressively encourage the modernisation of international trade law instruments.

Law harmonization and local specificities – a case study: OHADA and the law of contracts - Fontaine, Marcel (Uniform Law Review, 2013)
Unifying or harmonizing the laws of different countries means replacing, to respective degrees, the existing national laws with common rules.1 The merits of law unification or harmonization may seem to be obvious. They have been repeatedly described. Law diversity is an obstacle to trade between countries. Engaging in a commercial operation with a partner of another legal system immediately raises the question of which law will govern the relationship, with the consequence that, for one of the parties, the contract will be subject to unfamiliar rules (perhaps even for both parties if the law of a third party is determined to be applicable).

Unlocking Africa's poverty trap : holistic approach to BOP investment in agribusiness - Suzuki, Elli (Massachusetts Institute of Technology, 2013)
This paper identifies subsistence farming as a significant opportunity for poverty reduction and economic development in sub-Saharan Africa. By taking a holistic, standardized, and bundled approach, this paper proposes an innovative business model that enables small-holder farmers to access affordable extension services, technical assistance and financial scheme, thereby improving their overall productivity level.

The Enforcement of Arbitral Awards in Cameroon - Tumnde, Taylor (Social Science Research Network, 2013)
The increase in international trade creates a growing number of disputes between parties from different countries. Arbitration has become the most preferred mechanism to solve disputes in international trade. If a party does not voluntarily comply with an award, the successful party must apply for recognition and enforcement of the award in order to obtain the remedies. Cameroon is one of the major business markets in West and Central Africa, several companies committed to arbitral procedures are likely to have assets in Cameroon. This means that if a party fails to honour an award, an enforcement procedure may begin within a Cameroonian court. The enforcement procedures in Cameroon are sufficient and do comply with international standards. The most used and important instruments for recognition and enforcement are the United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958 and the Uniform Act on Arbitration 1999 in the OHADA territory, to which Cameroon is a signatory State. According to this Convention and the Uniform Act, an arbitral award may be refused enforcement under certain grounds laid down in them. There are various types of arbitral awards contemplated by the Cameroonoan legislature and will be herein examined to see how they can be enforced in Cameroon. An analysis of the legal situation in Cameroon confirms that there are problems associated with the enforcement of arbitral awards. These problems are not, however, connected with the concept of arbitral awards, but rather with the entire judicial system in Cameroon. Even though an enforcing party can do little to overcome these problems, certain measures can be taken in order to ease the enforcement procedure
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Cameroon; Enforcement; OHADA

The collection of value added tax on online cross-border trade in digital goods - Van Zyl, Stephanus Phillipus (University of South Africa, 2013)
Technological advances have had a major impact on traditional retail shopping changing it from a physical undertaking to a completely digitised experience where consumers buy digital media online. VAT systems that do not specifically provide for, or which have not been adapted to cope with, technology-driven advances, generally do not provide for the adequate levying and collection of VAT on cross-border digital trade. The South African VAT system is no different. The taxation of e-commerce should not artificially advantage or disadvantage e-commerce over comparable traditional commerce, or unnecessarily hinder the development of e-commerce. This thesis determines whether the South African VAT Act 89 of 1991 in its current form, can be applied adequately to raise and collect VAT on cross-border digital transactions. Where shortcomings in the VAT Act are identified, the harmonised VAT rules of the European Union (EU), together with the Organisation for Economic Cooperation and Development (OECD) proposals on consumption taxes, are analysed and discussed to seek possible solutions and make recommendations.
Keywords: Anonymising technology; B2B transactions; B2C transactions; BIT-rate tax; Banker-customer confidentiality; Blocked VAT account; Consumption taxes; Cross-border digital trade; Electronic commerce; Electronically supplied services; European Union; European Union countries; Fractionated VAT; OECD; South Africa; Taxation; VAT collection model; Value-added tax

Some reflections on the prospects for the harmonization of international business laws in Africa : OHADA and beyond - Fombad, Charles Manga (Africa Today, 2013)
The evidence of developments in the harmonization of international business laws shows that Africa is lagging seriously behind. There are still some skeptical voices about the need for and the value of harmonization of international business laws, but such voices are now in a minority. The aim of this paper is to assess the prospects for harmonizing international business laws in Africa. The main contention is that the debate today in Africa is not whether or not there should be harmonization of international business laws, but how this should be done. The paper reviews the imperatives for harmonization and the options that exist and then focuses on the present approach to harmonizing business laws in Africa under the auspices of the Organization for the Harmonization of Business Laws in Africa, better known under its French acronym, OHADA. Based on the critical review of the weaknesses and strengths of the OHADA regulatory framework, the paper suggests ways in which the agenda to develop a harmonized and modern set of business laws in Africa can be achieved.

Open-source software and the rationale for copyright protection of computer programs - Karjiker, Sadulla (Stellenbosch University, 2013)
The rationale for the legal protection of copyright works is based on the perceived need to encourage the creation of works which are considered to be socially beneficial. By awarding authors proprietary rights in their creations, copyright law allows authors the ability to earn direct financial returns from their efforts, and, thus, copyright law provides the required incentives for authors to create copyright works. Since the early days of commercial software development, copyright protection has been extended to computer programs; thus, by providing such protection it was assumed that their production should be encouraged, and that without such protection they will not be produced to the extent required by society. Comparatively recently, we have witnessed large-scale production of open-source software, which is licensed on generous terms, giving users the right to freely use, modify and redistribute such software. By adopting such licensing terms, the authors of open-source software are unable to charge licensees a fee for permission to use their software, which is the reward which copyright assumes authors seek to create such software. This development has made it necessary to re-evaluate the rationale for copyright protection of computer programs, and determine whether the continued protection of computer programs is justifiable. This study seeks to first establish a coherent theoretical justification for copyright protection, which it is submitted should be an economic justification, rather than a moral justification. The legal analysis in this work seeks to establish whether the copyright protection of computer programs is consistent with the economic justification for copyright protection. In particular, the analysis focuses on the current scope of copyright protection, and seeks to establish whether such protection is excessive, stifling creativity and innovation, and, thus, imposing too high a social cost. It is contended that copyright doctrine has generally sought to minimise these costs, and that current scope of copyright protection of computer programs leaves enough creative room for the production of new software. Despite the fact that the effect of open-source software licences is that authors are unable to earn the direct financial rewards which copyright enables authors to earn as an incentive to create such software, their authors continue to have financial incentives to create such software. Commercial firms who invest in open-source software do so because they seek to provide financially-rewarding related services in respect of software, or because it serves to promote sales in their complementary products. Similarly, the participation of individual computer programmers is largely consistent with the standard economic theories relating to labour markets and the private provision of public goods. Individuals are principally motivated by economic motives, such as career concerns. Copyright protection gives participants the choice to opt for the direct financial rewards which its proprietary protection enables, or the more indirect financial rewards of open-source software development. It is submitted within this research that rather than undermining the rationale for copyright protection of computer programs, the development of open-source software has illustrated that copyright protection allows for the emergence of alternative business models, which may be more economically advantageous to authors.
URI: http://hdl.handle.net/10019.1/80044
Keywords: Computer programs; Copyright law; Intellectual property; Open-source software

A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch University, 2013)
Arbitration as a mode of dispute settlement has been growing steadily all over the world. The momentum for commercial arbitration in particular was provided by the 1985 UNCITRAL Model Law on International Commercial Arbitration (“the Model Law”). Legislation based on the Model Law has been enacted in many countries. The arbitration laws of three of these countries, Kenya, Nigeria and Zimbabwe, are selected for consideration in this dissertation because of their common origins, similar statutes, similar problems, shared experiences, and their regional distribution. As the writer’s arbitration practice is based in Kenya, that jurisdiction is the primary, albeit not the only, source and foundation for this work, the focal point of reference and the citations from the law and practice incorporated in this research. The work consists of three chapters. Chapter one is a brief introduction and an overview of arbitration. This is followed by the statement of the research question, the justification for the research, methodology and the structure and content of the dissertation. Chapter two describes the legal and contextual framework for the investigation of the research questions in the selected jurisdictions of Kenya, Nigeria and Zimbabwe. Customary Law arbitration is included as a significant feature of African arbitration law. The UNCITRAL Model Law, the Arbitration Act, 1995 (Kenya), the Arbitration and Conciliation Act, 1988 (Nigeria), the Arbitration Act, 1996 (Zimbabwe), the Arbitration Act, 1996 (England), and the South African Draft Arbitration Bill are all used as legislative or statutory points of reference in the discussion of the research questions. Chapter 3 contains the main focus of the dissertation in which six recurrent arbitration problems in Kenya are discussed in the context of domestic arbitration. The research investigates (i) the illusiveness of consent as the basis for consensual arbitration (ii) jurisdictional challenges (iii) the procedural powers of the arbitral tribunal (iv) the disruptive effect of adjournments and postponements on the arbitral process (v) constraints on the granting of interim relief and (vi) the enforcement of the arbitral award. Original, creative and innovative proposals in response to these problems include: the express legislative recognition of the manifestation of consent in both the verbal and written forms of the arbitration agreement, the use of the constructive dispute resolution technique, statutory recognition of customary law arbitration, the use of an expedited arbitration procedure, the award of exemplary and punitive damages in arbitration, a code of sanctions to facilitate the arbitration process, and a simplified method of enforcement and execution of the arbitral award. The dissertation concludes with reflections on the future of arbitration in Africa, and the need for modernization and harmonization of arbitration laws for peaceful resolution of disputes and serious conflicts across Africa. The aim of this study is best illustrated by a short story: In the early nineties there was a man, untrained in any known discipline, who strutted court corridors, trade centres and market places, carrying a placard advertising himself to lawyers, traders and marketers as “An Arbitrator and Private Judge”. He attracted business, charged a handsome percentage fee on the value of the claim, was duly paid, until officialdom caught up with him and put paid to his burgeoning career as “Arbitrator-Judge”. But the reckless enthusiasm spawned by his wit and imagination, and the idiosyncratic practices in dispute resolution persisted and are manifest in Kenyan arbitration culture today. The need to remove bad practices, avoidable impediments, and inefficiency in the arbitration culture of Kenya in order to make its procedures and processes more efficacious, is the heart of this study.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Comparative law; Dispute resolution; Kenya; Nigeria; Zimbabwe

Análisis y modelización de la adopción de los sistemas de recomendación en el comercio electrónico - Cabal Cruz, Claudia Constanza (Universidad Internacional de Andalucía, 2013)
Tesis doctoral (Lectura 07/02/2013). Director: Francisco José Martínez López (Universidad de Granada). Tribunal: Martínez López, Francisco José, Univ. de Huelva, presidente; Padilla Meléndez, Antonio (secretario); Ortigueira Sánchez, Manuel (vocal); Luna Huertas, Paula (vocal); García Ordaz, María Mercedes (vocal). Se puede afirmar que la historia de las relaciones entre los individuos y las organizaciones se divide en dos, antes y después de la aparición de Internet, la penetración de los PC y de la banda ancha. En el campo organizacional, las Tecnologías de la Información y las Comunicaciones (TIC), se refieren al amplio espectro de tecnologías de base de los Sistemas de Información, y que se constituye en un importante recurso, que facilita la continua adaptación del Sistema de Información a los cambios internos y del entorno. La aplicación de los sistemas de información a las actividades organizacionales, caso concreto que nos interesa, el marketing, se constituye en una herramienta para que la empresa se mantenga competitiva en el mercado. Las relaciones de intercambio desarrolladas en los mercados electrónicos posibilitan la comunicación bidireccional entre las partes y entre cada una de ellas y el propio medio, exigiendo a las organizaciones implementar un marketing interactivo en términos de producto, precio, distribución y comunicación, en el que consumidor dirija el proceso de intercambio. El desarrollo del comercio en los mercados electrónicos y las aplicaciones de los sistemas de información al marketing, han tomado características del comercio tradicional y han sido adaptadas al electrónico, caso específico la adaptación que han realizado una gran cantidad de empresas comerciales en la Web a las recomendaciones a sus usuarios a través de los sistemas de recomendación (RS), entendidos como sistemas que realizan recomendaciones de productos que están buscando, o basadas en sus gustos o preferencias. Este es tema central de este trabajo, pero no enfocado a su parte técnica, sino a la comprensión de los factores que explican el comportamiento online de los consumidores frente a los RS de determinada website (WS), por lo que se propone un modelo teórico, sustentado por once hipótesis principales y otras subordinadas, la cuales son el resultado de la integración reflexiva de la Teoría de la Acción Razonada, de la adaptación Trust-TAM y de la Teoría del Comportamiento Planeado. Del análisis y corroboración del modelo, se puede concluir que el proceso de adopción del sistema de recomendación de cierto website se conforma sobre la base que a) el usuario percibe la opinión de otros con respecto al uso de los sistemas de recomendación en general y del particular de un determinado website; b) el grado de confianza que le merece al consumidor la interacción e información proporcionada por el sistema de recomendación; c) la percepción de utilidad de uso del sistema de recomendación que tiene su usuario; y d)la actitud del individuo hacia el sistema de recomendación de un website particular.

Some perspectives on durability and change under modern African constitutions - Fombad, Charles Manga (International Journal of Constitutional Law, 2013)
A major cause of political and constitutional instability in post-independence Africa was the ease with which political leaders subverted constitutionalism by arbitrarily changing constitutions to suit their political agendas. During the constitutional reforms of the 1990s many provisions were introduced in most African constitutions aimed at limiting the ability of governments to abusively change constitutions. Because of the critical importance of controlling the process of constitutional change to entrenching constitutionalism, this paper attempts to critically examine and analyze some of the different control devices that have been introduced. The objective is to see to what extent they may help not only to promote constitutionalism but also enhance constitutional durability and stability. The first part considers why it is important for constitutional designers to include special procedures to regulate and control the constitutional amendment process. The second part examines the different amendment patterns in a number of selected African countries. The third part considers the practical implications of the various control devices in terms of their actual and potential impact on the nurturing and growth of constitutionalism on the continent. The paper concludes that although there has been some progress, more changes still need to be introduced to check the problem of arbitrary constitutional change in Africa.

The concept ‘fairness’ in the regulation of contracts under the Consumer Protection Act 68 of 2008 - Stoop, Philip Nicolaas (University of South Africa, 2013)
The thesis analyses the concept ‘fairness’ in consumer contracts regulated by the Consumer Protection Act 68 of 2008, mainly from the perspective of a freedom and fairness orientation. It discusses the evolution of ‘fairness’ as background to a more detailed discussion of the classification of fairness into substantive and procedural fairness. The thesis examines dimensions of fairness, factors which play a role in the determination of fairness, and fairness- oriented approaches in an attempt to formulate a framework for fairness in consumer contracts. The main aspects that should be taken into account to justify a finding of fairness, or to determine whether a contract is fair, are identified. This analysis addresses, too, the extent to which the fairness provisions of the Consumer Protection Act are appropriate (with reference to the law of South Africa, Europe, and England).
Keywords: Consumer contracts; Consumer protection law; Contracts; Contractual fairness; Freedom of contract; Law of contract; Liberty of contract; Procedural fairness; Standardized terms of contract; Substantial fairness

Investment Protection in the Framework of the Treaty of Harmonizing Business Law in Africa (OHADA) - Houanye, Paulin; Shen, Sibao (Beijing Law Review, 2013)
A few years ago, African contribution of the world trade was only around 2%. The investors, except those who are exploiting natural resources, never want to dare dispensing their fund in Africa. The reason of this situation was very simple. The majority of investors denounce the juridical insecurity and also the political preponderance across the African continent. With human and natural resources abundant, Africa is regarded as a continent equipped with a great potential of development. The years of independences in Africa saw being born in many States, of the organizations trying to solve these difficulties and to reinforce their capacities by the constitution of international organizations acting in all the fields. But it is only in the year 1990; some organizations appeared in the continent and knew of real rise thanks to the liberal and democratic economic policies. This article wishes to present an assessment of seventeen years implementation of the African Harmonization of Business Law Treaty of 1993. Firstly, it will describe the system from an institutional point of view and hence from a normative point of view. Secondly, during the course of this essay, there will be a focus on analysis of OHADA’s laws, its system and its potential impact. In addition, the article will concentrate on OHADA’s appropriateness in the business sector and necessary guarantees it must offer for a successful investment partnership with foreign investment.
Keywords: African Development; Harmonization; Harmonization Business Law; Investment Law; Investments; Regional integration; Rule of Law

Common Court of Justice and Arbitration: A Supranational Institution for the Administration of Commercial Disputes in Africa - Ogwezzy, Michael C. (Nordic Journal of Commercial Law, 2013)
Due to the expansion of business transaction across the globe, the private sector demands an adequate legal framework that is sufficiently clear, modern, predictable and transparent to permit investment with a sense of security. The Organisation for the Harmonisation of Business Law in Africa (Organisation pour l’harmonisation en Afrique du Droit des Affaires) is generally known by its French acronym OHADA. As long-standing idea, the foundation of the OHADA Treaty was first laid during a meeting of finance ministers of the members of the franc CFA1 area held in Ouagadougou, Burkina Faso, in April 1991. A group of experts, led by Senegalese Justice Keba Mbaye, was appointed to conduct a feasibility study on a form of legal collaboration designed to promote economic integration and attract investments.2 Identifying low investment as a major obstacle to economic growth, Keba Mbaye presented his report to the French-speaking African summit in Libreville, Gabon, in October 1992, recommending the creation of a supranational organization comprising the entire franc area. The recommendation was adopted and a steering committee of three experts were appointed and tasked with drafting an international instrument as well as identifying the areas of law to be harmonized. The OHADA was established through the treaty of Port Louis in Mauritius on 17th October, 19933 The treaty is open to any Member State of the Organization of African Unity (AU) as well as any other non-member of the AU invited to join with the common agreement of all the Member States.4 The OHADA has progressively become the common business law in anglophone and francophone African countries, taking the best from the civil law and the common law systems.5 The OHADA provides its Member States with 1) a single, modern, flexible and reliable business law adapted to each country’s economy; 2) arbitration as an appropriate and trustworthy way to settle disputes; and 3) an opportunity for training judges and judicial staff and ensuring their specialisation. In May 2003, the uniform OHADA business law came into force in the sub-Saharan African States of Benin, Burkina Faso, Cameroon, Central African Republic, Comoros, Congo, Ivory Coast, Gabon, Guinea, Guinea Bissau, Equatorial Guinea, Mali, Niger, Senegal, Chad, Togo and later the Democratic Republic of the Congo. The OHADA Treaty secures a legal framework for the conduct of business in Africa.6 Pursuant to Article 53 of the OHADA Treaty, any member State of the African Union may become a member, if it wishes to do so.7 Many countries are currently giving active consideration to joining the OHADA common system of business law.8 Most of the countries have a French colonial heritage, with the exception of the Democratic Republic of the Congo (former Belgian colony), Guinea-Bissau (former Portuguese colony), Equatorial Guinea (former Spanish colony), and Togo and Cameroon (formerly under partly British and partly French colonial rule). French is also an official language in most of the countries and many OHADA sources are only available in French. 9 It is interesting to know that the Council of Ministers of the OHADA organisation which is the legislative organ of the organisation have adopted the following uniform business law: the general commercial laws, corporate laws and rules concerning different types of joint ventures, laws concerning secured transactions, debt recovery and enforcement laws, bankruptcy laws, arbitration law, accountability law, and law regulating contract for the carriage of goods by roads.10 The OHADA treaty established the Common Court of Justice and Arbitration (CCJA) which is a supranational11 judicial institution based in Abidjan, Ivory Coast.12 2.
Number: 2

The problem of systemic violation of civil and political rights in Cameroon : towards a contextualised conception of constitutionalism - Enonchong, Laura-Stella (University of Warwick, 2013)
Post-independent Cameroon has grappled with the problem of systemic violation of civil and political rights (CPR) despite a transition from single party dictatorship to multiparty democracy in the 1990s. Various legislative measures including the adoption of a supposedly ‘rights friendly’ constitution in 1996 have done little to ameliorate that problem. This thesis adopts a concept of constitutionalism, based on contemporary international standards, to analyse the problem of CPR violations from the perspective of the constitutional arrangements in Cameroon. It examines the system of separation of powers, the method of securing judicial independence and the mechanisms for judicial review. The argument is made that the problem can be attributed in part to the predominant influence of the French civil law system in Cameroon’s bijural legal system. Although for historical reasons, Cameroon operates both the English common law and the French civil law, constitutional developments have continued to be influenced by the latter which lends itself to practices that are not sufficiently supportive of constitutionalism as defined herein. The thesis, however, goes further to explore how the constitutional system could be reinforced to provide a more conducive framework for the protection and enhancement of CPR. Drawing on two strands of arguments, one highlighting features of the common law system that can be more supportive of constitutionalism and the other which highlights the value of indigenous antecedents of constitutionalism, the thesis proposes the development of a contextual model which is more reflective of Cameroon’s peculiar legal and socio-political circumstances. It proposes what is described as an Optimal Integrative Approach (OIA) as a framework for developing a contextual model, more conducive for the protection and enhancement of CPR in Cameroon.
URI: http://webcat.warwick.ac.uk/record=b2689324~S1
Keywords: Cameroon; Civil rights; Constitutional law; Human rights; International law and human rights; Politics and government

The Problem of the Taxation of Internet Transactions - Asada, Dominic (Current Jos Law Journal, 2013)
Accepted: 2017-08-16T12:06:13Z

Applicable law in investor-state arbitration: the interplay between national and international law - Elisabeth Kjos, Hege (Oxford University Press, 2013)
This book examines the law, national and/or international, that arbitral tribunals apply on the merits to settle disputes between foreign investors and host states. In light of the freedom that the disputing parties and the arbitrators have when designating the applicable law, and because of the hybrid nature of legal relationship between investors and states, there is significant interplay between the national and the international legal order in investor-state arbitration. The book contains a comprehensive analysis of the relevant jurisprudence, legal instruments, and scholarship surrounding arbitral practice with respect to the application of national law and international law. It investigates the awards in which tribunals referred to consistency between the legal orders, and suggests alternatives to the traditional doctrines of monism and dualism to explain the relationship between the national and the international legal order. The book also addresses the territorialized or internationalized nature of the tribunals; relevant choice-of-law rules and methodologies; and the scope of the arbitration agreement, including the possibility of host states presenting counterclaims in investment treaty arbitration. Ultimately, it argues that in investor–state arbitration, national and international law do not only coexist but may be applied simultaneously; they are also interdependent, each complementing and informing the other both indirectly and directly for a larger common good: enforcement of rights and obligations regardless of their national or international origin.
https://ora.ox.ac.uk/objects/uuid:a52424f2-4c14-4cc1-a452-6d926a0a02fe https://library.oapen.org/bitstream/handle/20.500.12657/33860/453473.pdf
Keywords: Arbitral tribunals; Choice-of-law rules; Foreign investors; Host states; International law; Investor-state arbitration; National law; OAPEN

Common Problems Affecting Supranational Attempts in Africa: An Analytical Overview - Fagbayibo, Babatunde Olaitan (Potchefstroom Electronic Law Journal, 2013)
Ever since the colonial era, attempts have been made throughout the various regions of Africa at building supranational units chiefly for administrative and legal convenience. Examples of such attempts include the Federation of Rhodesia and Nyasaland, the East African High Commission and the federations in former French West and Equatorial Africa, all of which were attempts at forging a supranational nation state. These experiments laid the foundation for further supranational initiatives in post-colonial Africa. In this respect, every region in Africa has either experimented with or is currently experimenting with the idea of supranational regional organisations. This article aims at investigating selected attempts at supranationalism on the continent, the successes and failures of such experiments, and the lessons to be learnt from them. As Africa embarks on the journey of solidifying its unity through the establishment of leviathan continental institutions, efforts should be geared towards building on the experiences of past and present experiments at the sub-regional level. Such experiments offer instructive lessons as they are rooted in similar historical and social contexts.
Keywords: African integration; Central African Economic and Monetary Community; East African Community; Economic Community of West African States; OHADA; Southern Africa Customs Union; Supranationalism; West African Economic and Monetary Union

Legal Innovation for Development: The OHADA Experience - Frilet, Marc (Legal Innovation and Empowerment for Development, 2013)
The World Bank legal review gathers this input from around the world and compiles it into a useful resource for all development practitioners and scholars. The subtitle of this volume, legal innovation and empowerment for development, highlights how the law can respond to the chal-lenges posed to development objectives in a world slowly emerging from an economic crisis. The focus on innovation is a call for new, imaginative strategies and ways of thinking about what the law can do in the development realm. The focus on empowerment is a deliberate attempt to place the law into the hands of the poor; to give them another tool with which to resist poverty. This volume shows some of the ways that the law can make an innovative and empowering difference in development scenarios. Development problems are complex and varied, and the theme of innovation and empowerment naturally has a broad scope. Consequently, this volume reaches far and wide. It considers the nature, promise, and limitations of legal innovation and legal empowerment. It looks at concrete examples in places such as Africa, the Asia-Pacific region, and Latin America. It considers developments in issues with universal application, such as the rights of the disabled and the effectiveness of asset recovery measures. The theme of legal innovation and empowerment for development complements substantive and institutional sensibilities in current development policy. Substantively, development policy discourse seems to have moved away from tacking hard toward statist policy or neoliberal policy. Although this brief introduction cannot do justice to the richness and complexity of these contributions, it does consider each focal point in turn.

A Comparative study of some issues relating to Corporate Insolvency Law in Nigeria and South Africa - Habi, Halita Mafo (University of Pretoria, 2013)
No abstract available

Bridging the GAAP? : IFRS in accounting practice - Hartmann, Berit (Jönköping International Business School, 2013)
This thesis investigates how International Financial Reporting Standards (IFRS) come to act within an organizational context. In particular, the thesis explores how the requirements for goodwill accounting and leasing influence organizational calculative practices, transforming and shaping operations management. Drawing on actor-network theory, this study moves away from a priori distinctions, following the construction and mobilization of accounting numbers across institutionalized boundaries within and around the organization. The empirical investigation took place in a large, worldwide active media group that is listed on a European stock exchange. The group is a particular interesting setting because of its diverse business structure and its German code-law accounting roots. Business combinations are a major growth factor within the industry and a high degree of decentralization in the organization placed responsibility for investment decisions at low hierarchical levels. Goodwill accounting and impairment testing were therefore highly significant calculative practices in the group. The study finds that the constitutive role of the financial reporting standards in the organization both solves tensions and dilemmas around the number and creates new ones when crucial interests are lost in translation. These tensions and dilemmas arise between the aim of standardization and closure for the construction of a legitimate value of the future, and the aim to mobilize numbers in order to motivate and create value for a future. Originally intended for the financial representation of organizational substance and performance, the standards become associated with operations management activities, helping to create the faithful records that sum up the organization. This interrelation helps to close concern around the representation of the future in a ‘fair’ value by distributing the calculative practices over a wide network of actors spanning inside and outside the organization. However, the relationship also forces a connection between calculations and ambitions that otherwise would have preferred to stay separate. This thesis offers a new perspective on IFRS implementation by emphasizing organizational activities. Through a focus on integration and the link between financial and management accounting, the ‘implementation problems’ highlighted in previous literature gain a refined theorization. When taking organizational practice seriously, integration becomes a process that may find temporal stability but will never be final. In the process, conflicts might be solved but new dilemmas will arise. In turn, concepts like decision usefulness, comparability and earnings management cannot exist in a stable form but are rather constructed in networks that disregard commonly assumed boundaries inside and around the organization.
JIBS Dissertation Series, ISSN 1403-0470 ; 094 URN: urn:nbn:se:hj:diva-23148 OAI: oai:DiVA.org:hj-23148 DiVA, id: diva2:689238
Keywords: IFRS; International Financial Reporting Standards

Entrepreneurial financing decisions, venture capital ownership and bargaining power - Heughebaert, Andy (Ghent University, 2013)
It is widely acknowledged that entrepreneurial companies play a key role in shaping a local economy. Entrepreneurial companies are a source of growth and innovation for an industry and provide jobs for the local population. However, entrepreneurs of high growth oriented companies rarely have the capital to finance their innovative ideas themselves and therefore also have to accept the risks associated with assessing and acquiring the necessary finance resources from other investors. The goal of this dissertation is to study the impact of venture capital (VC) finance on such entrepreneurial finance decisions. Although VC investors are a highly focused and specialized kind of investors that offer a wide range of differentiated services, it is to date still unclear how VC investors may reduce agency costs for other potential investors. The first study of this dissertation studies the effect of VC finance and associated VC ownership for finance decisions from other investors who have the potential to invest in these companies. This study demonstrates that VC ownership results into a larger supply of finance for the entrepreneurial company. Second, I find that VC ownership results into an even larger positive effect on capital investment decisions from equity investors as VC finance is typically also associated with the implementation of an equity-oriented corporate governance mechanism in entrepreneurial companies. VC ownership does not have an effect on the supply of finance from financial debt investors, however. Nevertheless, I find that debt finance is equally available for companies with VC ownership as compared to companies without VC ownership, which is a surprising result given the high risk associated with high growth companies that raise VC finance. Another important finding of this study is that the positive effect of VC ownership is stronger for repeated VC finance versus non-repeated VC finance. In fact, these results indicate that the effect of VC finance for entrepreneurial companies’ finance decisions is considerably larger if VC investors commit to further finance the company. The second study of this dissertation extends the first study and explores the effect of VC ownership on entrepreneurial finance decisions in different institutional settings. Although the effect of VC ownership is not limited to one specific institutional context, this study shows that its impact on entrepreneurial finance decisions is stronger in countries with a better quality of law enforcement and in countries where the entrepreneur is able to obtain a fresh start after bankruptcy. Specifically, in countries with a better enforcement of law, VC investors are more effective in reducing agency problems between entrepreneurs and potential investors. The attractiveness of a fresh start after bankruptcy will also be higher for an entrepreneur who raised VC finance, as VC investors focus more on maximizing the value of their portfolio rather than on the survival of individual firms. The third study acknowledges the fact that VC investors are not all equal and explores which VC investor types have more bargaining power versus the entrepreneur and how such differences in VC investor bargaining power affect company valuations in VC investment rounds. VC investor bargaining power is important because company valuations are the outcome of negotiations between the VC investor and the entrepreneur. We show that university VC firms and government VC firms negotiate lower valuations compared with independent VC firms. The proprietary deal flow of university VC firms and the limited competition in niche markets in which government VC firms compete will directly increase their bargaining power versus the entrepreneur, which these VC investor types then further exploit by negotiating lower company valuations compared with independent VC investors. Although differences in VC investor type did not affect entrepreneurial finance decisions in the first and second study, they do affect the equity stake that an entrepreneur will have to give up in order to raise VC finance and in order to a have a greater access to entrepreneurial finance from potential investors in the future.
http://hdl.handle.net/1854/LU-4096609
Keywords: Bargaining power; Financing decision; Venture capital

A Comparative Analysis of the Efficacy of the General Anti-Avoidance Rule as a Measure Against Impermissible Income Tax Avoidance in South Africa - Kujinga, Benjamin Tanyaradwa (University of Pretoria, 2013)
This thesis comparatively analyses the SA income tax general anti-avoidance rule (GAAR) in s 80A-L of the Income Tax Act 58/1962 and similar rules in Australia, Canada, the UK and the judicial doctrines in the US and the UK. It is argued that, while the SA GAAR may serve as a deterrent, it is going to have limited efficacy against impermissible tax avoidance due to the uncertainty it creates. It is argued that uncertainty will cause judicial activism to protect permissible tax avoidance, extensive and inconsistent judicial interpretation and confusion amongst taxpayers and SARS as to what constitutes permissible or impermissible tax avoidance. This thesis ends by recommending certain amendments, based on the comparative analysis, to the SA GAAR which can reduce uncertainty and thus improve it efficacy.
URI : https://repository.up.ac.za/handle/2263/33430
Keywords: General Anti-Avoidance Rule; Income tax; South Africa

Development of a uniform insolvency law in SADC : lessons from OHADA - Leno, Ngaundje Doris (Journal of African Law, 2013)
This article argues that, with the global or cross-border nature of many corporate activities, there is an increasing need for a uniform insolvency law approach to the financial distress of a corporation in the Southern African Development Community. In doing so, the article highlights lessons the community may learn from the Insolvency Act of the Organisation for the Harmonization of Business Law in Africa. Emphasis is given to that organization’s success in developing a uniform insolvency act (ie one which is directly applicable in its contracting states). The article also proposes a number of recommendations.
Accepted: 2014-02-28T11:57:54Z
Keywords: Africa; Bankruptcy; Business law; Financial distress; Insolvency Act; Insolvency law

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.
Accepted: 2016-05-20T09:04:41Z URI: https://repository.up.ac.za/handle/2263/52731

The Quest for a Supranational Entity in West Africa: Can the Economic Community of West African States attain the Status? - Lokulo-Sodipe, Jadesola O.; Osuntogun, Abiodun J. (Potchefstroom Electronic Law Journal, 2013)
To reflect the growing trends in the international scene and in furtherance of the objective of its Revised 1993 Treaty, the Economic Community of West African States (ECOWAS) summit in December 2006 revolutionised the structure of ECOWAS by re-designating the Executive Secretariat into a quasi-independent commission headed by a President with a Vice President and seven commissioners. The rationale behind the revision was to make ECOWAS a supranational entity. This article considers whether or not a supranational system is essential for the attainment of ECOWAS' objectives. It asks if the conditions for an effective supranational system are in place in the West African sub-region which could provide a solid foundation for its success and why the quest for a supranational system has not yielded any fruitful result in West Africa. It argues that a retreat from the quest for supranationalism and a return to an inter-governmental system would be a retreat rather than the way forward, and expresses the need for the course of action to be sustained courageously till the impact of integration begins to emerge, and the disguised, patriotic impulse of states to protect their national sovereignty gives way to the full manifestation of ECOWAS as a supranational entity.
Number: 3
Keywords: Community Court of Justice; ECOWAS Commission; Intergovermental organisation; Regional integration; Supranational entity

A Proposed discharge dispensation for consumer debtors in Tanzania - Maghembe, Ngwaru Jumanne (University of Pretoria, 2013)
The Tanzanian private sector is growing, partly due to the state’s efforts to conform to the global economy. As the economy expands and the National Microfinance Policy of 2001 is realised, more and more credit has been made available to consumers. As a direct consequence of the increase of credit, the number of over- indebted consumers in Tanzania is on the rise. The current debt relief system is regulated by the Tanzanian Bankruptcy Act no. 9 of 1930, a piece of colonial legislation. Unfortunately this law is ineffective, costly and outdated. Some of the problems identified in this study with this debt relief regime include the lack of a cost- effective alternative to bankruptcy and its total reliance on the judiciary, an institution that is itself overburdened and requires reform. The purpose of this study is to make recommendations for the reform of the current debt relief system and propose a debt relief dispensation for consumer debtors in Tanzania that will efficiently cure over- indebtedness. A wide comparative investigation was undertaken in this study of selected common law, civil and mixed legal systems that have substantial experience with the boom in over-indebted consumers now facing Tanzania. A number of solutions were borrowed from these systems that may potentially solve Tanzania’s debt relief problem. One of the main findings of this thesis is that, over time, developed jurisdictions that rely on credit in the private sector appear to be converging on the same type of procedures and moderate philosophies for consumer debt relief. These include less judicial supervision for debt relief procedures, less freedom of choice for over-indebted consumers when it comes to the type of procedures available, and mandatory surplus income repayments for debtors who can afford it. In order to address the problems of the Tanzanian debt relief system, this thesis proposes a complete overhaul of the administration of debt relief procedures in Tanzania and the introduction of a combined alternative to bankruptcy that consists of three joint procedures. A number of amendments are also proposed for the Bankruptcy Act no.9 of 1930. This thesis states the status of legal developments as they were in the selected jurisdictions on 31 December 2012.
https://repository.up.ac.za/handle/2263/32961
Keywords: Bankruptcy Act; Current debt relief system; Tanzania

The Legal Effects of EU Agreements - Mendez, Mario (Oxford University Press, 2013)
Examining the legal effects of EU concluded treaties, this book provides an analysis of this increasingly important and rapidly growing area of EU law. The EU has concluded more than 1,000 treaties including recently its first human rights treaty (the UN Rights of Persons with Disability Convention). These agreements are regularly invoked in litigation in the Courts of the member states and before the EU courts in Luxembourg but their ramifications for the EU legal order and that of the member states remains underexplored. Through analysis of over 300 cases, the book finds evidence of a twin-track approach whereby the Court of Justice of the European Union (CJEU) adopts a maximalist approach to Treaty enforcement, where EU agreements are invoked in challenges to member state level action whilst largely insulating EU action from meaningful review vis-à-vis agreements. The book also reveals novel findings regarding the use of EU agreements in EU level litigation including: the types and which specific EU agreements (including the types of provisions) have arisen in litigation; the nature of the proceedings (preliminary rulings or direct actions) and the number of occasions in which they have been addressed in challenges to member state or EU action and the outcomes; who has been litigating (individuals, institutions, or member states) and which domestic courts have been referring questions to the CJEU. The significance of the judicial developments in this area are situated within the context of the domestic constitutional ramifications for member state legal orders thus revealing a neglected dimension in the constitutionalization debates, which traditionally emphasized the ramifications of internal EU law for the domestic constitutional order without expressly accommodating the constitutional significance of this external category of EU law nor the different challenges that this poses domestically.
Accepted: 2013-12-31 23:55:55
Keywords: Constitutionalization; Creative Commons; Cultural and strategic groupings; Direct effect of European Union law; Domestic courts; EU courts; EU law; EU level litigation; EUconcluded treaties; European Court of Justice; European Union; European Union law; GATT; General Agreement on Tariffs and Trade; International law; Treaty enforcement; WTO; World Trade Organization

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification

Challenges to political and economic intergration in Africa : A socio-Legal perspective - Mwanawina, Ilyayambwa (North-West University, 2013)
This study is concerned with integration efforts on the African continent. This study sets out to investigate the politico-legal and economic impediments to regional and continental integration efforts in Africa. The documents, processes, and organs of the African Union, as the main continental organisation, are the focal point of this study. In order to achieve this, the study primarily adopted a qualitative approach since the literature involved in this work could not be reduced to a quantitative concept. The study ensured that the premises and the conclusions in this work conform to the principles of reliability and validity and in addition the elimination of bias in this was curtailed by validation and triangulation. This was achieved by the fact that the arguments in this work were not only based on qualitative arguments but, where possible, quantitative data was brought in to validate/ triangulate the qualitative arguments. Evidently, the study would have been incomplete if it did not discuss and evaluate the many regional economic communities that have been established to further the objectives of the Treaty establishing the African Economic Community. One of the major premises that this study discovers is that there is a direct and demonstrable relationship between democracy and economic progress; genuine and sustainable development has to be fostered primarily by securing peace and stability on the African continent. Some of the other key findings of the study include that; a) the ultimate goal of the African Union is full political and economic integration leading to the United States of Africa; b) overlapping memberships to a custom unions are highly detrimental to the state since it has to subscribe resources and political will to two or more different arrangements. c) overlapping memberships cause confusion, inertia and most importantly legal uncertainty thereby stifling trade liberalisation efforts; d) many African states still guard their sovereignty closely and that many perceive that yielding their sovereignty to a continental body is tantamount to losing their independence; e) the African Union infrastructure still lacks supra-national and national institutions that are capable of implementing its values; f) the African Union infrastructure does not contain an institutionalised mechanism for the promotion and management of Union affairs at national level; g) the NEPAD initiatives, the APRM process and the functions of the Peace and Security Council play a positive role in African politico-legal and economic development. It has however been shown that these mechanisms are more reactive than preventative and as such intervene too late in the internal affairs of member states; h) armed conflicts cause a reduction in the per-capita Gross Domestic Product growth rate of a nation experiencing a civil war/ conflicts. i) the African Union has regressed from the original timelines of the African Economic Community. The highest regression being Phase 2 which involves the most critical element of strengthening of African regional integration arrangements and the harmonisation of policies concerned. A thirteen (13) year postponement is noted in this regard. j) Africa's poor intra-trade performance is also attributed to the limited progress among African countries in fostering structural transformation. This structural transformation relates to the building of roads, bridges, railway lines and power grids; In order for the African continent to re-position itself in an attempt to harness the benefits of regional integration, some of the recommendations that the study makes are that; a) the African Union grant supra-national status to institutions of the Union for the equitable and speedy attainment of integration; b) the Union and member states should as soon as possible create mechanisms with decision making powers to manage Union affairs at regional and national level; c) the operationalization of the Pan African Parliament should be pursued with the utmost determination to bring the Parliament to full functionality as a Continental legislative body; d) the operationalization of the African Court of Justice and Human Rights be completed as soon as possible in order to allow the body to function as a fully-fledged continental judiciary. This will ensure that the development of integration jurisprudence from an international law perspective is not delayed. The Court will also pursue the enforcement of Human rights norms and practices; e) the Union should further lead the continent in the following sectors with clear and predictable deliverables; i) the establishment and upgrading of regional land, air, and other means of transportation and communication; ii) the creation of a cross-border power and energy generation and distribution network; iii) the establishment, advancement, and diversification of regional financial and commodity markets; iv) the establishment of a regional higher education system by facilitating wider access through specialization in regional integration; The study further acknowledges that these recommendations are not conclusive since the study of regional integration is still at its infancy and many other ideas on how to strengthen African regional integration still await discovery.

Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Nzero, Ignatious (University of Pretoria, 2013)
The Zimbabwean economy rapidly declined over the past two decades. A record hyperinflationary environment and a collapse of the financial service sector coupled by lack of external lines of credit created a difficult operating environment for corporate businesses. Businesses thus either closed down operations or resorted to survival strategies. Corporate mergers and acquisitions emerged as natural favoured strategies in implementing survival corporate restructuring transactions. However, the success of such strategies largely depends on the effectiveness of the merger regulatory framework, that is, its ability to promote beneficial corporate restructuring transactions on one hand and to maintain the competitive structure of the market on the other hand. This research analyses the current merger regulatory framework in Zimbabwe and assesses whether it is suited to promote beneficial corporate restructuring transactions implemented through mergers and acquisitions without unnecessarily distorting the competitive structure of the market. Employing the failing firm doctrine as the focal point, the research identified a number of shortcomings within the current merger regulatory framework that impacts upon its ability to effectively promote beneficial corporate mergers and acquisitions without sacrificing the competitive market structure. Selected comparative jurisdictions were used to draw various lessons for Zimbabwe. The aim of the comparative study was not to provide an exhaustive analysis of these jurisdictions but to identify specific arrears that can be used to develop and suggest an effective merger regulatory framework for Zimbabwe. In order to remedy the identified shortcomings inherent within the current Zimbabwean merger regulatory framework, this thesis proposes a number of amendments to the current Competition Act [Chapter 7:01] of 1996. These proposed amendments are aimed at bringing clarity, flexibility and strengthening the merger regulatory framework including the institutions tasked with such. The research is primarily a legal analysis of the Zimbabwean merger regulating statute and its implications on any decisions made by the competition authority. As such, the thesis states the status of legal development in Zimbabwe and the selected comparative jurisdictions as of 31 July 2013.
URI: https://repository.up.ac.za/handle/2263/53211

Climate change and Africa : the normative framework of the African Union - Pallangyo, Daniel Mirisho (North-West University, 2013)
There is enough evidence on how climate change consequences will adversely affect Africa despite the fact that it is the continent that has least contributed to the problem. The international climate change regime recognises Africa's vulnerability to climate change and provides for special treatment under the United Nations Framework Convention on Climate Change (the UNFCCC). Thus, the international climate change regime presents an opportunity for African countries to adapt and mitigate the consequences of climate change through the UNFCCC mechanism. However, the international climate change legal regime has not been able to adequately assist African countries to address the consequences of climate change under the vulnerability principle. Although the current international climate change regime requires developed countries to reduce their greenhouse gas (GHG) emissions, Africa needs to take steps itself to address the problem, because it is most vulnerable to the consequences of climate change. The African Union (AU) could play a great role in ensuring that the international climate change regime addresses the consequences of climate change in the region. This could be done through fostering strong African common positions during international climate change negotiations. A strong common position could strengthen African bargaining power and might result in more funding, capacity building and technology development and transfer for adaptation and mitigation programmes under the UNFCCC-Kyoto Conference of Parties. However, reaching a strong common position requires the cooperation of the AU member states. In this context, African regional integration is an opportunity for the AU to foster such cooperation among member states. The Treaty Establishing the African Economic Community (the Abuja Treaty), the Constitutive Act of the AU and the Protocol on the Relations between the AU and Regional Economic Communities (RECs) prioritise regional economic integration and call for states' cooperation, but the call has not yet been heeded. To realise deep and viable African integration, there must be a well-structured institutional and legal framework that defines the relationship between the AU, the AEC and the RECs. African regional integration is also seen as an avenue whereby the AU can create its own regional climate-change regime. In this regard, the AU's and RECs' normative framework on climate change is examined in order to assess whether it adequately integrates climate change issues. This study finds that although Africa is most vulnerable to the consequences of climate change, the AU's and RECs' normative framework on climate change is weak and inadequate to address the problem. The Framework should integrate climate change issues in order to achieve sustainable development. The AU should also ensure that member states ratify the relevant treaties and protocols (the Maputo Nature Convention and the Protocol establishing the African Court of Justice and Human Rights) that have not yet been ratified in order that they may become operational. The Maputo Nature Convention puts sustainable development in the forefront of attention as a reaction to the potentially conflicting environmental and developmental challenges facing the continent (such as climate change), but it is not yet in force. This work finds that human rights law can strengthen the AU's role in addressing climate change through its normative framework. The human rights approach to climate change under the African Charter on Human and Peoples' Rights (the Banjul Charter) is a viable avenue because human rights law forms the basis for states' responsibility based on human rights obligations and principles. The extraterritorial application of the Banjul Charter presents an avenue for AU institutions such as the Human Rights Commission and the African Human Rights Court to curb the effects of climate change through a human rights lens. The future of the AU is presented within the context of a set of recommendations that identify strong African regional integration as an avenue through which the AU can foster the cooperation of member states to address the consequences of climate change in the AU's and RECs' normative frameworks. General recommendations are made on the need for the international climate change regime to pay more attention to issues of funding, capacity building and technology development and transfer on the basis of the vulnerability principle and in relation to the principles of equity and common but differentiated responsibilities and respective capabilities. Also, the AU needs to strengthen its legal and institutional structures to ensure deep African integration that is capable of addressing common challenges such as the consequences of climate change.
Keywords: African Charter on Human and Peoples Rights; African Economic Community (AEC); Climate Change; EAC Treaty; ECOWAS Treaty; Human rights; International climate change regime; Normative framework; Regional integration; SADC Treaty; State cooperation; The Constitutive Act of AU

The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation

Interim Measures in International Commercial Arbitration: A Comparative Study of the Egyptian, English and Scottish Law - Shalaan, Wael S. E. (University of Stirling, 2013)
Interim Measures are viewed as an essential means to protect parties‘ rights in international commercial arbitration disputes. Most Arbitration Laws and Rules have recognised the arbitral tribunal‘s power to grant such measures. The success of this system relies on the court‘s assistance of the tribunal during the process. This relationship between the tribunal and the court is something vague under Egyptian Law, since there are no clear rules addressing the matter. Hence, this research examines the theories that explain the tribunal‘s authority and the relationship with the authority of the court. This study uses a comparative analytical approach in terms of analyzing relevant legal texts to determine the optimal legal approach to the issue. The purpose of the study is to address deficiencies in the Egyptian law – the Code of Civil Procedure and Egyptian Arbitration Law – and compare it with English, Scottish Arbitration Acts and international arbitration systems, laws, and practices. The findings of this research offer several recommendations that could help achieve a successful and smooth arbitration process. This study identifies and explains types of interim measures and explores the international practice of every type. It gives some important recommendations for future development and improvement of the Egyptian law. It also makes general recommendations that would help improve the efficiency of the English and Scottish laws.
Keywords: Egyptian Arbitration Act; English Arbitration Act; Interim Measures; International Commercial Arbitration; Provisional Measures; Scottish Arbitration Act

Cession of Life Insurance Policies in securitatem debiti : a Practical Perspective - Sunkel, Kelly (University of Pretoria, 2013)
The security cession of the rights under life policies marries two separate areas of the law: The Law of cession and the Law of Insurance. This makes for a complex union since varying common law and statutory principles find application, and in reality trade practices also play a role. In theory a cession in securitatem debiti may take one of two possible constructions, namely a pledge or a fiduciary security cession, and each has its own advantages and disadvantages. Disparity arose when judicial preference was given to the pledge construction while academics preferred the other. The problem, however, was larger than a disagreement as to the better construction. The underlying problem was that there was a lack regarding clarity as to the practical operation of security cession of life policies, in addition to the problems surrounding the construction thereof. As a solution to this problem some academics have suggested legislative intervention. The South African Law Reform Commission, nevertheless, advised against it in 1991 and was of the opinion that the issue was one which our courts would eventually solve. In the 22 years since then, our courts have merely confirmed its preference for the pledge construction. The intricacies of security cessions of life policies have seen no further judicial development. It is probable that the courts do not have enough practical information at hand to advance this area of the law. An investigation into the operation of such cessions in practice was thus necessary. The outcome of the practical investigation reveals that legislative intervention is indeed a viable solution especially since the issues are too complex for the courts to solve. As part of this work, legislation has been drafted and it is recommended that this is inserted into the Security by Means of Movable Property Act .
Keywords: Life Insurance; Security Cession

Legal risk and compliance risk in the banking industry in South Africa - Terblanché, Janet René (North-West University, 2013)
The Basel Committee on Banking Supervision has defined operational risk, legal risk and compliance risk. However, the definitions might not be adequate for countries with a hybrid legal system, such as South Africa. This study aims to provide a practical solution to the problems faced by countries with a hybrid legal system wishing to comply with the Basel Committee’s standards. It is argued that compliance, compliance risk and regulatory risk should all be viewed as constituent components of legal risk, and in turn necessarily also of operational risk in a hybrid legal system. Legal risk is a wide concept which includes all aspects of a legal system, while compliance risk is a narrower concept which only includes the codified aspects of a legal system. Legal risk therefore includes compliance risk. However, the opposite is not true as compliance risk does not include legal risk, and the two concepts are decidedly shown not to be synonymous in a mixed legal system.
Keywords: Basel Committee; Compliance; Compliance risk; Legal compliance; Legal risk; Operational risk; Regulatory compliance; Regulatory risk

Direct taxation and the internal market: assessing possibilities for a more balanced integration - Yevgenyeva, Anzhela (University of Oxford, 2013)
The role of the Court of Justice of the European Union in the process of direct tax integration in the European Union (EU) has been widely discussed in the academic literature, while another important actor, the European Commission, has attracted much less attention. The Commission’s input is commonly perceived to be limited to the right of legislative initiative. This study questions such an oversimplified interpretation and draws a more nuanced picture of EU tax harmonisation by integrating an analysis of the complex regulatory approaches adopted by the Commission for the establishment and smooth functioning of the Internal Market. It is argued that the past decade brought a notable change in the Court-dominated pattern of direct tax integration. This change is apparent first in the evolution of enforcement strategies under Articles 258 and 260 TFEU; and second, in the increased reliance upon non-binding regulatory measures. Both developments have strengthened the role of the Commission, supplying it with more possibilities for influencing national direct tax systems, despite the reluctance of Member States to agree upon legislative harmonisation. Against this background, the procedural and substantive problems associated with these instruments require closer examination. The normative scope of this research covers the key procedural problems related to the infringement procedure and non-binding regulatory measures. The empirical component explores the Commission’s enforcement and coordination practices, drawing particular attention to two case studies: the tax treatment of losses in cross-border situations and exit taxation. Following the analysis of enforcement and coordination in the field of direct taxation, the study argues the need and proposes potential solutions for (i) the developing of a more comprehensive procedural framework for the infringement procedure and non-binding regulatory acts; (ii) the strengthening of accountability mechanisms; and (iii) the enhancing of the effectiveness of their application.
Keywords: Direct taxation; EU Law; Enforcement; European Law; Exit tax; Good governance; Infringement procedure; Internal Market; Non-binding coordination; Soft law; Tax coordination; Tax integration; Tax treatment of losses; Taxation

Written Arbitration Agreements: What Written Arbitration Agreements? - Yu, Hong-Lin (Civil Justice Quarterly, 2013)
First paragraph: This article considers the issue of an oral arbitration agreement in relation to the New York Convention. As Townsend once said "[a]rbitration offers a means to an end, and the end is to the resolution of disputes." This end would be extremely difficult to achieve without the approval of national courts. Fortunately, with 146 signatory countries signed on the New York Convention on the Recognition and Enforcement of Arbitral Awards 1958 (The New York Convention), the success of this Convention has attracted businessmen into using arbitration to resolve their disputes. Nevertheless, a voluntary arbitration cannot be commenced without a valid arbitration agreement. Setting out to achieve harmonisation in the enforcement of arbitration agreements, art.II of the New York Convention provides the written requirements to be followed by all 146 signatory countries. Accordingly, written requirements for arbitration are imposed upon all signatory countries and they are obliged under the convention to recognise all arbitration agreements which are made in writing.
Keywords: Arbitration agreements; Comparative law; Convention d'arbitrage; France; New York Convention awards; New Zealand; Oral contracts; Scotland

New Frontiers on Legal Enforceability of Collective Agreements in Nigeria - Zechariah, Matthias (Current Jos Law Journal, 2013)
The objectives of this research paper are: to examine the status of collective agreements under the common law; highlight impacts of statutory intervention on common law perception of collective agreements, and discuss how the National industrial Court (NIC) and the Constitution of the Federal Republic of Nigeria 1999 (as altered) have broadened the horizon of enforceability of collective agreements in Nigeria. Reliance is placed principally on statutes, judicial decisions, textbooks written by learned authors as well as international best standard and practices championed by the International Labour Organization (ILO) and practices in some foreign jurisdictions. The ﬁndings of the research were that under the common law, collective agreements are ordinarily not binding, they are considered as a ‘gentleman's agreement‘, a product of a trade unionist's pressure, binding only in honour or on the goodwill of the parties thereto, unless and until it is incorporated expressly or impliedly into the contract of employment. However, statutory intervention has slightly altered the common law notion of collective agreements, e.g. where the Minister of Labour and Productivity is empowered to declare, by order, that part or the whole of an agreement deposited in his ofﬁce is binding on the parties. Furthermore, with the enactment of the NIC Act and the listing of the NIC in the 1999 Constitution as a superior court of record (following the alteration of the Constitution, necessitated by the N.U.E.E. V BPE case), the Court now has exclusive jurisdiction to adjudicate on a wide range of labour matters, industrial relations and application of international best practices such as the standard and principles of the International Labour Organization (ILO), and practices in foreign jurisdictions. It has been argued that the enforceability of collective agreements is in tandem with international best practices, which the NIC can readily give effect to, if it is pleaded and established/ proved as a fact. This has invariability expanded the frontiers of enforceability of such agreements. Therefore, the common law position on the status of collective agreements has been rendered otiose and obsolete, giving way to the sparkling provisions of enforceability guaranteed by the NIC Act and the Constitution respectively. Notwithstanding, it is highly recommended that parties to a collective agreement should expressly state their intention whether or not to be bound; the duration of the agreement should be stated and whether, and when, it should, be reviewed; experts and other stakeholders should be properly consulted before an agreement is entered into; an arbitration clause may be included in case a party breaches its own part of the agreement. Industrial democracy ought to be promoted in all sectors. Strikes and lock outs should be used only as a last resort for enforcing compliance with a collective agreement, because these industrial actions cause devastating effects on the economy and on the lives of the citizenry generally.
Accepted: 2017-08-16T13:03:49Z

Users' entitlements under the fair dealing exceptions to copyright - Shay, Richard Michael (Stellenbosch University, 2012)
This thesis analyses current South African copyright law to ascertain the proper interpretation and application of the fair dealing provisions contained in the Copyright Act 98 of 1978. Copyright law ensures that authors’ works are not used without their consent, which they can grant subject to compensation or conditions attached to the use. Fair dealing exceptions allow the general public to use copyright works for certain purposes without the copyright owner’s consent and without paying compensation. These provisions are intended to balance copyright owners’ interests with the interest that members of the public have in using copyright works for socially beneficial purposes. These provisions typically allow the use of a copyright work for the purposes of research or private study, personal or private use, criticism and review, and news reporting. Unfortunately there is no South African case law concerning the fair dealing provisions, and the application of these exceptions remains unclear. This study aims to clarify the extent of application of the fair dealing exceptions to copyright infringement so that courts may be more willing to consider foreign and international law and in doing so develop South African intellectual property law. The social and economic policy considerations underlying the fair dealing exceptions are considered to determine their function. International conventions relating to copyright and neighbouring rights are examined, specifically the provisions allowing exceptions to copyright. The legislation and case law of Australia and the United Kingdom are analysed to determine the proper interpretation and application of these statutory defences. This knowledge is then used to inform South African law. The Copyright Act 98 of 1978 does not contain a fair dealing exception for parody and satire. Australian legislation does contain such an exception, and it is analysed in that context. An exception for parody is proposed for South African law, and the need for and application of this provision is considered. The constitutionality of the proposed exception is evaluated in terms of its impact on the constitutional property rights of copyright owners.
Keywords: Australia; Copyright law; Fair dealing; Fair use; Great Britain; Intellectual property; South Africa; Trademarks

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/12719/Hedaraly_Saleha_2012_memoire.pdf
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

Statutory regulation of forced sale of the home in South Africa - Steyn, Lienne (University of Pretoria, 2012)
The home of a debtor has never enjoyed specific statutory protection against forced sale in the individual debt enforcement and insolvency procedures in South Africa. In Jaftha v Schoeman and Others; Van Rooyen v Stoltz and Others (2005 (2) SA 140 (CC)) and Gundwana v Steko Development CC and Others (2011 (3) SA 608 (CC)), the Constitutional Court recognised that in the individual debt enforcement process execution against a debtor's home, even where it has been mortgaged in favour of a creditor, may constitute an unjustifiable infringement of the right to have access to adequate housing, provided by section 26 of the Constitution. The effect of these decisions is that, in every case in which a creditor seeks to execute against a person's home, a court must consider "all the relevant circumstances" to determine whether execution is justifiable, in terms of section 36 of the Constitution. The absence of a properly constructed framework, incorporating clear substantive and procedural requirements, within which these recently established principles must be applied, has led to divergent approaches in the courts and a lack of clarity regarding circumstances in which execution against a debtor's home will be permitted. Further, courts have not considered the impact of section 26 and other rights on the position where a debtor's home is realised by the trustee of an insolvent estate in terms of the Insolvency Act 24 of 1936. This has given rise to a number of unanswered questions as well as to a lack of predictability that potentially hold adverse consequences for bond finance, commerce, and the economy generally. The need to balance the competing interests emphasises the necessity for a coherent contextual framework within which forced sale of a debtor's home may occur. This thesis examines issues surrounding forced sale of a debtor's home in South Africa. It compares the position in other legal systems and suggests mechanisms and an appropriate method, or process, for inclusion in statutory provisions to regulate the forced sale of a debtor's home in both the individual debt enforcement and insolvency procedures in South Africa.
Keywords: Forced sale; Vente forcée

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

Disability, discrimination and equal opportunities : a comparative labour law study - Harmse-Truter, Laurentia (University of Johannesburg, 2012)
This study aims to investigate the different ways in which the position of people with disabilities can be addressed. Antidiscrimination legislation can play a very important role. Efforts to create equal opportunities must, however, not be limited to legislative initiatives and policy declarations. There is an urgent need for education and training of this minority group. 7 Systematic efforts to heighten public awareness of civil rights and in particular the recognition of the rights of the disabled community are imperative. This study aims to bring home the truth that "disability rights are an idea and ideal whose time has come. ,, When addressing the issue of disability discrimination (or for that matter any kind of discrimination) several principles need to be addressed, the most important being the following: The meaning of the concept of "equality" needs to be established. The fact that all people are equal, does not necessarily mean that all people must be treated the same. When speaking about disability discrimination one must know who forms part of the protected class. For that reason the first issue that must be addressed is the definition of "disability": This leads to the next question, namely which individuals should be protected by anti-discrimination laws and should they benefit from affirmative action measures? What is meant by the term "discrimination"? Is it at all permissible to distinguish between groups of people and, if so, when and which standards are to be applied? What role can anti-discrimination legislation fulfil in the struggle for equality? When dealing with anti-discrimination legislation, what is required in order to prove discrimination and what remedies must be available to an aggrieved party? Normally, in case of criminal action proof is required beyond reasonable doubt and in case of civil action on the balance of probabilities. 10 Civil action offers more effective remedies, but should it be punitive in nature (by awarding damages to the aggrieved party) or non-punitive (by putting the aggrieved party in his/her "rightful place")? What sort of enforcement mechanism is needed? Is it a task for the ordinary tribunals or rather a special body created for that purpose? What defences should be available to an employer accused of discriminatory practices? Who should benefit from enforcement? Only the individual victim or all members of that group? Is anti-discrimination legislation sufficient or is something in addition called for? If positive measures are required, what form must these measures take? This study will address these questions specifically with relation to people with disabilities.The "equality principle" will first be studied. Thereafter the concept of "disability" will be defined. There is a movement away from a medical model of disability towards a social model that takes account of the disabling effects of attitudes and structural barriers on the position of disabled people. Then the concept of "discrimination" will be addressed. Discrimination has many different forms and can take place in different contexts In the following chapter possible solutions to the problem of disability discrimination will be raised. Thereafter follows an important comparative analysis of different jurisdictions on international, supra-national and national level. Different jurisdictions have reached different stages in addressing this problem. The factual analysis of each jurisdiction will include the existence of any anti-discrimination legislative measures, the scope of the protected class, applicable employment provisions, defences available to employers, and the success achieved in addressing the problem. The contentious issue of affirmative action measures will also be addressed. By drawing inferences from the comparative study, suggestions will be made for future developments in South Africa. The conclusion is reached that it is imperative for South Africa to draft disability anti-discrimination legislation that takes account of the needs of this minority group. Legislative initiatives, however, are not enough and must be supported by various programmes aimed at the disabled themselves and the community that they live in. Only then can human rights become a reality also for people with disabilities.
Keywords: Comparative law; Discrimination; Employment; Labour law; People with disabilities

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

From Port Louis to Panama and Washington DC: Two Regional Approaches to International Commercial Arbitration - Bashi Rudahindwa, Jonathan (European Journal of Law Reform, 2012)
In recent decades, regional efforts have been made to reform and harmonize the rules governing international arbitration. These efforts have resulted in the adoption of regional instruments governing commercial arbitration in specific areas. This paper analyzes the arbitration regimes created at a regional level in Africa and America, and particularly focuses on arbitral institutions that were created within the Organization for Harmonization of Business Law in Africa (OHADA) and within the Organization of American States (OAS). The objective of the paper is to identify any advantages provided by either regime, which can help improve regional and international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Political Economy of the Harmonisation of Business Law in Africa - Ntongho, Rachael (Journal of Politics and Law, 2012)
This paper examines the current dynamics of regulatory reforms in Africa and its implication on the continent. It analyses the highly political struggle for regulatory dominance of business law in Africa and how this interacts with the preferences and power of select international actors. It illustrates that the struggle between Francophone and Anglo-Saxon sections of society for OHADA to reflect their ideological stance is having a negative effect on the harmonisation process.

Regionalism : lessons the SADC may learn from OHADA - Leno, Ngaundje Doris (THRHR, 2012)
Meeste Afrikastate is klein en het nie die vermoë om effektief aan prosesse van die Wêreldhandelsorganisasie deel te neem nie. Hierdie onvermoë, saam met ander faktore, is die hoofrede vir die voortgesette marginalisering van die kontinent in die globale ekonomie en handel. Ten einde effektief aan genoemde prosesse deel te neem en in die voordele van die geglobaliseerde wêreld te deel, moet Afrikastate integreer. Regionalisme of integrasie is nie ’n doel op sigself nie maar is nodig vir die ekonomiese groei van Afrikastate. Dit skep groter markte vir handel en belegging en is ’n aansporing tot groter effektiwiteit, produktiwiteit en mededingendheid. In die lig hiervan stel die artikel drie kernargumente. Die eerste is dat regionalisme voordele bied wat Afrikastate kan ontgin ten einde marginalisering op globale vlak te oorkom. Die tweede argument is dat, terwyl die Suider-Afrikaanse Ontwikkelingsgemeenskap (SAOG) poog om besigheidsreg te harmoniseer, die Organisation for the Harmonisation of Business Law in Africa (OHADA) (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) as voorbeeld kan dien aangesien dit reeds die grondslag gelê het vir die harmonisering van besigheidsreg in Afrika. Die derde argument is dat die SAOG-tribunaal verbeter moet word ten einde ’n meer regionale regsraamwerk binne die SAOG daar te stel. In hierdie verband belig die artikel sommige voordele van regionalisme in Afrika, die lesse wat die SAOG by OHADA kan leer, die voordele van ’n geharmoniseerde besigheidsreg teen die agtergrond van die OHADA-ondervinding en die moontlike wyses waarop die SAOGtribunaal verbeter kan word.

Financial liberalisation and economic growth in ECOWAS countries - Owusu, Erasmus Larbi (University of South Africa, 2012)
The thesis examines the comprehensive relationship between all aspects of financial liberalisation and economic growth in three countries from the Economic Community of West African States (ECOWAS). Employing ARDL bounds test approach and real GDP per capita as growth indicator; the thesis finds support in favour of the McKinnon-Shaw hypothesis but also finds that the increases in the subsequent savings and investments have not been transmitted into economic growth in two of the studied countries. Moreover, the thesis also finds that stock market developments have negligible or negative impact on economic growth in two of the selected countries. The thesis concludes that in most cases, it is not financial liberalisation polices that affect economic growth in the selected ECOWAS countries, but rather increase in the productivity of labour, increase in the credit to the private sector, increase in foreign direct investments, increase in the capital stock and increase in government expenditure contrary to expectations. Interestingly, the thesis also finds that export has only negative effect on economic growth in all the selected ECOWAS countries. The thesis therefore, recommends that long-term export diversification programmes be implemented in the ECOWAS regions whilst further investigation is carried on the issue.
Keywords: ARDL-Bounds testing approach; Capital accounts liberalisation; Co-integration; ECOWAS; Economic Community of West African States; Economic growth; Economic stablization; Financial crises; Financial liberalisation; Ghana; Interest rates liberalisation; Ivory Coast; Monetary Policy; Nigeria; Stock market developments

Arbitrability in the context of Ghana's new arbitration law. - Mante, Joseph; Ndekugri, Issaka (International arbitration law review, 2012)
Examines the approach of Ghana's Alternative Dispute Resolution Act 2010 to the question of arbitrability. Reflects on the concept of arbitrability under international law, the relevant trends emerging from case law, and the approach adopted by the Ghanaian High Court in Attorney General v Balkan Energy LLC. Reviews the Act's arbitrability exemptions, their implications for international arbitration in Ghana, the potential jurisdictional challenges under the legislation and how its provisions could be amended to increase its conformity with international trends on arbitrability.
https://rgu-repository.worktribe.com/output/246672/arbitrability-in-the-context-of-ghanas-new-arbitration-law
Keywords: Arbitrability; Arbitrage; Arbitragem; Arbitration; Comparative law; Ghana; International commercial arbitration; Jurisdiction

Board Structure, Ownership Concentration and Intellectual Capital - Zhang, Meiyi (Victoria University of Wellington, 2012)
This thesis investigates the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure. This thesis is motivated by the limited post-IFRSs (International Financial Reporting Standards) adoption intellectual capital disclosure studies carried out in a less stringent regulatory environment of New Zealand, and limited research addressing the determinants of the level and value relevance of intellectual capital disclosure. Based on an application of agency theory, cost-benefit theory and value relevance approach, this thesis argues that firm-specific factors are expected to have a significant impact on the level and value relevance of intellectual capital disclosure. Within the agency theory, board structure and ownership concentration mitigate agency costs by enhancing the monitoring function of the board over managers’ opportunistic behaviour, which consequently influence the level of intellectual capital disclosure. In addition, as New Zealand has less tough rules in relation to board structure and ownership concentration, it is expected that these relationships will be more easily identified in the New Zealand context. Second, as most of the intellectual capital disclosure is voluntary, this disclosure is subject to a firm’s cost-benefit analysis. Cost-benefit theory suggests that a firm should not fully disclose its information unless the benefits outweigh the costs of the disclosure. Therefore, the level of intellectual capital disclosure is also influenced by the factors that determine the costs and benefits of the disclosure. Finally, this thesis adopts the value relevance approach to measure the quality of the disclosure. It is expected that the factorsassociated with the level of the disclosure also influence the value relevance of the intellectual capital disclosure. This thesis is based on a sample of 155 firms listed on the New Zealand Exchange covering a total of 519 firm-years over the period between 1 January 2008 and 31 August 2011. A self-developed disclosure index and multiple regression analysis are employed to test the hypothesised relationships. Overall, the results indicate that the average level of intellectual capital disclosed by New Zealand listed firms is low and the human capital component is the most frequently disclosed intellectual capital component. The results provide strong evidence that board structure characteristics, including board size and independence, have a significant positive impact on the level of intellectual capital disclosure. There is strong evidence for a non-linear relationship between ownership concentration and the level of intellectual capital disclosure, which is robust to various types of intellectual capital (i.e. human, relational and structural capital). The results show marginal evidence that board gender diversity has a positive impact on the level of intellectual capital disclosure. In terms of the value relevance of intellectual capital disclosure, only board size has a positive impact on the value relevance of the intellectual capital disclosure. In the individual component analysis, board independence is found to have a significant positive impact on the value relevance of the human and relational capital disclosures. This thesis provides the most recent evidence on the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure in a less stringent regulatory environment of New Zealand. These findings have important implications to regulators, and assist information users in the interpretation of the voluntary intellectual capital disclosure.

Reflections on finality in arbitration - Roodt, Christa (De Jure, 2012)
Ondersoek na die Finaliteit van 'n Arbitrasiebevel Hierdie artikel oorweeg die Telcordia- en Lufuno-sake vanuit die oogpunt van die finaliteit van 'n arbitrasiebevel. Die vraag wat te berde kom, is wanneer 'n arbitrasiebevel finaliteit bereik waar 'n saak voor meer as een forum (arbitrasie en staatlike howe), in meer as een jurisdiksie gevoer word. Die prosedurele meganismes wat Amerikaanse en Suid-Afrikaanse howe tydens die Telcordia-dispuut toegepas het asook hul onderskeie benaderings tot res iudicata, het 'n groot mate van ooreenstemming getoon. Dit is te verstane dat die afhandeling van 'n internasionale proses vertraag kan word deur bepaalde grondwetlike regte wat die spoed van die afhandeling van 'n saak kan beÃ¯nvloed. Nietemin, indien die reg op 'n billike verhoor op enige stadium in die verrigtinge gepleit mag word, word 'n geleentheid geskep vir die dispuut om vryelik te eskaleer gedurende die verhoor. Dit kan die hofproses oopstel vir misbruik en die afhandeling van die geskil vertraag. Die minderheidsbeslissing in Lufuno skenk 'n mate van oorweging aan die potensiële negatiewe implikasies hiervan. Die finaliteit van die geskilbeslegtingsproses kan na behore bestuur word aan die hand van 'n wyer interpretasie van res iudicata in internasionale dispute en 'n meer geredelike ondersoek hierna, op die hof se inisiatief. Die moontlikheid dat die Telcordia-dispuut verder bespoedig sou kon word, word ondersoek met verwysing na die New York Konvensie op die Erkenning en Afdwing van Arbitrasiebevele van 1958, en aan die hand van aanbevelings wat deur ander gerekende internasionale liggame uitgereik is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

A regulatory framework for the trans–boundary transportation of dangerous goods in Southern Africa : an environmental perspective - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2012)
The goal of this dissertation is to analyse the extent to which the South African legal framework governing the trans-boundary transportation of dangerous goods, provides for the regulation of environmental aspects in terms of dangerous goods transportation. The dissertation examines the role of regional and sub-regional laws in this regard in an effort to ascertain whether there is sufficient legal certainty and harmonisation of laws for environmental regulation. No specific law currently exists in South Africa regarding the regulation of dangerous goods transportation, rather the regulation of dangerous goods is effected by a multiplicity of laws. This state of affairs illustrates the difficulty that exists and may be associated with the enforcement of the regulation of dangerous goods transportation. Despite this, the multiple laws vividly elucidate the fact that there is a considerable degree of environmental protection vis-a-vis dangerous goods transportation premised on the fact that all environmental impacts could never be avoided or eliminated, but can be reduced to an extent.

Theory of Choice of Law and Party Autonomy - Basedow, Jürgen (SungKyunKwan Law Review, 2012)

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Innovation and Intellectual Property: Strategic IP Management and Economics of Technology - Holgersson, Marcus (Chalmers University of Technology, 2012)
Innovations and technological developments have been recognized for their central importance for economic success and growth at least since the 1930s. Intellectual property (IP) and intellectual property rights (IPRs), such as patents, trade secret rights, and copyrights, have during more recent decades caught increasing attention, and, mainly due to various developments at macro level, IP has become an important source of competitive advantage at micro level in many industries. This has led to an increased importance of strategic IP management, and the related research field has been growing since the late 1990s. This thesis aims to contribute to this growing field, and the first purpose of this thesis is to explore and explain strategic and innovation related IP management practices, and the managerial and economic consequences of such practices. Apart from the growing importance of IP management in general, an increased focus on open and collaborative approaches for creating innovations has led to a need for new and adapted IP management skills. The second purpose of this thesis is therefore to develop managerial and economic frameworks, models, and tools to be used in the intersection between IP management and open innovation practices. These purposes are addressed in a cover paper and six appended research papers of theoretical/conceptual as well as of empirical nature, being based on interviews, questionnaires, patent statistics, and document studies. In connection to the first purpose the results show that, while many small firms have problems with properly benefitting from the patent system, large firms have increasingly developed their IP strategies, especially their patent strategies. The purpose is then not only to appropriate monopolistic returns from innovations but also to govern various forms of open innovation. Large firms were found to in a first step increase their patenting (in terms of quantity), and in a second step focus more on selective, quality-oriented, and internationalized patenting. Additional results show that the internationalization leads to a convergence in managerial choices of output markets for patenting worldwide, in parallel with market and technology diversification. Further, a case from mobile telecommunications illustrates the role of IP management in the governance of open innovation systems. Finally, two cases from the automotive industry illustrate the IP-related problems that arise in connection to divestments and other types of disintegrations (‘IP disassembly problems’), and how IP management can mitigate them. This leads to the second purpose, related to the development of models, tools, and frameworks for IP management in relation to open innovation. First, the thesis provides a conceptual framework of innovation openness, especially pinpointing the role of IPRs. This framework emphasizes three key dimensions of innovation openness: resource distribution, technology governance, and technology accessibility. Second, a framework for managing the IP disassembly problem is presented, enabling increased exit opportunities and decreased transaction costs. Third, a method for determining fair, reasonable, and non-discriminatory royalties in licensing collaborations is developed, applicable to multilateral licensing deals. It stands clear that contemporary IP management is not (and has never been) only about maximizing excludability. Strategic IP management must therefore be developed and integrated with technology and corporate management in order to foster success at the micro level of firms, and thereby also at macro level. Developments in IP management skills (e.g., sourcing, control, commercialization, licensing, valuation, pricing) and IP contracts will then most likely lead to increased efficiency of interorganizational technological relationships and quasi-integrated organizational forms, and thereby also to increased innovativeness and economic development.
ISBN 978-91-7385-761-1 Doktorsavhandlingar vid Chalmers tekniska högskola, Ny serie nr 3442 ISSN 0346-718X
Keywords: Adresse IP; Economie numérique; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Effectiveness of the Beneficial Ownership Test in Conduit Company Cases - Jain, Saurabh (Victoria University of Wellington, 2012)
Countries enter into double tax agreements with the economic objective of preventing double taxation of cross-border transactions. To achieve this objective, the contracting states agree reciprocally to restrict their substantive tax law. That is, a major policy of double tax agreements is to reduce double taxation of residents of states that are parties to the agreement. Residents of third states sometimes contrive to obtain treaty benefits typically by interposing a person or a conduit entity in one of the contracting states. In order to ensure that a resident of a contracting state who claims treaty benefits is entitled to them in substance, double tax agreements should be interpreted according to their substantive economic effect. Generally, double tax agreements follow the pattern of the OECD Model Tax Convention. The OECD Model Convention addresses the double taxation of dividends, interest and royalties, commonly collectively known as "passive income", in Articles 10, 11 and 12 respectively. These provisions usually operate by reducing withholding tax imposed by a source state on passive income that flows from the source state to a resident state. In order to prevent a resident of a third state from obtaining a source state withholding tax reduction by interposing a person or a conduit entity in the resident state, the OECD Model Convention requires the immediate recipient of passive income to be the "beneficial owner" of that income. That is, the OECD Model Convention requires the immediate recipient to be an owner in a substantive economic sense. Courts and commentators have difficulty in interpreting and applying the concept of beneficial ownership to conduit entities that are corporations, commonly referred to as "conduit companies". They have attributed the cause of the difficulty to the absence of a definition of the term "beneficial owner" in the OECD Model Convention. This thesis argues that the difficulty in applying the beneficial ownership concept to conduit companies has arisen not because of the absence of the meaning of the concept, but because logically and from an economic perspective the concept cannot be applied to companies in general, not to conduit companies in particular. The beneficial ownership test was meant to be a test of economic substance. From an economic perspective, the benefit or the burden of a contract entered by a company is economically enjoyed or borne by its shareholders. That is, in substance a company cannot be considered as owning income beneficially. From this consideration, it follows that conduit companies can never be considered entitled to treaty benefits. Nevertheless, the OECD Model Convention applies the beneficial ownership test to conduit companies pursuant to an assumption that at least in some cases conduit companies can be the beneficial owners of passive income. The Model Convention's assumption is based on the legal perspective that courts conventionally adopt. According to this legal perspective, companies hold income beneficially because they exist as separate legal entities from their shareholders. Courts find themselves battling these opposing perspectives when applying the beneficial ownership test to conduit companies. In order to make income tax law work efficiently, courts that are obliged to determine whether to honour claims to treaty benefits made by conduit companies have preferred to employ the legal perspective. Courts have justified this approach by adopting surrogate tests for the actual beneficial ownership test. Most of the surrogate tests do not relate to the concept of ownership at all. This thesis categorises the surrogate tests as "substantive business activity" and "dominion". By analysing reported cases, the thesis identifies deficiencies in these tests. One of the proposed outcomes of the thesis is to suggest an alternative approach for deciding conduit company cases. The thesis suggests that courts should consider an arrangement as a whole and investigate reasons for the existence of an immediate recipient of passive income in the specific corporate structure. The thesis also recommends amendments in the official commentary on Articles 10, 11 and 12 of the OECD Model convention in order to address the conceptual shortcomings inherent in those Articles.
Keywords: Double taxation; OECD Model Tax Convention; Tax law

Combating insider trading in Kenya's capital markets: challenges and opportunities for reform - Kotonya, Anne (University of Nairobi, 2012)
The capital markets are expected to play a pivotal role in the attainment of Kenya's development blueprint 'vision 2030.' It is, therefore, essential that obstacles to the attainment of a fair and efficient market are examined and rooted out. This study investigates the limitations of the Capital Markets Act in combating insider trading. It also examines whether reforms would promote a fair and efficient capital market. The study makes use of existing literature as well as decided cases to investigate the inadequacies in the formulation of and provisions for inside information, material pricesensitive information, publication of information, possession of information and disclosure of information in the Capital Markets Act. This literature draws out key learnings from other jurisdictions and analyses how legislation in developed economies treats challenges to the enforcement of insider trading laws. The doctrinal analysis is triangulated with results of a survey of practical experiences of legal practitioners in applying the Capital Markets Act. The findings affirm the existence of conceptual difficulties in determining the elements of the crime of insider trading. As a consequence, it is concluded that the present formulation of insider trading law is inadequate. The study, therefore, makes suggestions for reforms to the provisions on insider trading in the Capital Markets Act.

Full protection and security in International Law - Magnusson, Finnur (Universität Wien, 2012)
The thesis covers one of the investment standards of international investment law, namely the full protection and security standard. In Part I, the study is introduced in terms of structure and substance. Chapter 1 provides a description of the scope of the research topic and a definition of its terms and structure. Chapter 2 covers the historical development of the full protection and security standard. Part II deals with three fundamental issues concerning the standard: sources, interpretation and content. Chapter 3 contains a discussion dealing with the various sources of the standard. Each source will be studied independently. Chapter 4 will address general issues with regard to interpretation, such as to what extent the Vienna Convention on the Law of Treaties influences the process of interpretation. Chapter 5 deals with the content of the standard of full protection and security, including conceptual issues relating to the substantive elements of which the standard consists. Moreover, the chapter will ask questions as to which underlying issues are needed to explore when a due diligence assessment is made in order to determine whether a state has fulfilled its obligations to provide protection and security. Part III deals with issues relating to the violations of the standard. In Chapter 6, the violations of the standard and their many manifestations will be analyzed. The chapter will address whether certain fact-based scenarios can be established in which the standard is most commonly violated. Finally, Chapter 7 contains a summary of findings.
Keywords: Arbitral Awards; Bilateral Investment Treaties (BITs); Due diligence; Full protection standard; Full security standard; ICSID; International Investment Law; International law; Investment standards; Investments

Legal challenges of cross-border insolvencies in sub-saharan Africa with reference to Tanzania and Kenya: a framework for legislation and policies - Masoud, Benhajj Shaaban (Nottingham Trent University, 2012)
Although a substantial body of literature has developed in recent years in the area of cross-border insolvency, this scholarship has been dominated by scholars from the United States and Europe, so that a perspective from most of Sub-Saharan African (SSA) countries is lacking. This study addresses this perspective. It makes an in-depth examination and discussion of the challenges that SSA countries face in reform and application of cross-border insolvency law given the ever-growing multinational trade and investment. The study focuses on the risk of failure of SSA legislative processes to properly address the potential challenges of cross-border insolvencies in a manner that is sensitive to the local contexts and which provides a balance with international insolvency benchmarks. It examines cross-border insolvency theories; the global drivers for convergence of insolvency law through global insolvency norms; and the implications for cross-border insolvency regulations arising from cross-border trade and investment arrangements, such as the bilateral investment treaties, before considering the state and future of the legislative frameworks of SSA countries.
Nottingham Trent Institutional Repository (IRep) https://core.ac.uk/works/7793942/
Keywords: Cross-border Insolvency; Insolvency; International insolvency

The Business Trust and its role as an entity in the financial environment - Nel, Ebenhaéser Cornelis (Nelson Mandela Metropolitan University, 2012)
The trust figure in South Africa has undergone an interesting process of evolution during the last century – from a mere gratuity or private tax evasion tool to a proper family protection, business entity, investment, and structured finance vehicle. Its flexibility and multi-functionality positioned the trust as an ideal legal institution for many innovative ideas in the search for holistic business structures, economic empowerment transactions, general estate planning and risk protection initiatives, and ultimately, its application as financial instrument and structured finance entity. The development of both traditional and synthetic securitisation schemes in South Africa has been investigated, with some emphasis on the application of the special purpose institution, which may be in trust form. It is submitted that the application of the trust figure has developed without any significant contribution from the local legislator. A sound legal and regulatory framework is crucial for the creation of a strong future environment for legal and financial vehicles. The question is, however, whether the current South African legal framework for the application of the business trust, and also as a vehicle for financial instruments, is adequately sound and robust in light of the standards set in the international business and financial environment. It is submitted that the hybrid nature of the South African legal landscape is conducive for the development of sound legal systems in an ever-changing legal and economic reality. It is further submitted that in the development of proper legal frameworks, South Africa should position itself particularly in its context as a Southern African developing democracy. The South African trust development is compared with that of some foreign jurisdictions as well as with international conventions and treaties of relevance. Some recommendations for necessary changes are made and it is submitted that such future development of the trust figure should not take place haphazardly, but within the context of a structured regulatory model
NMU Archives and Exhibition Centre
Keywords: Asset-backed financing; Corporations; Taxation; Trusts and trustees

A legal analysis of the application of articles I and III of the GATT 1994 on the economic development of ECOWAS member states - Ogbonna, Joseph Ifeanyichukwu (Brunel University, 2012)
This dissertation examines the tension inherent in the relationship between the Economic Community of West African States (ECOWAS) as Member States Parties of the GATT/WTO and the GATT/WTO regime. It focuses specifically on the tension triggered off by the requirements of Article I – the Most-Favoured-Nation principle (MFN) and Article III – the National Treatment principle (NT) GATT 1994. It shows that while the non-discrimination principles are meant to promote trade liberalisation and economic growth, they produce the opposite effect in developing and least developed countries like ECOWAS and aggravate the tension between those countries and the WTO. It argues that the MFN is used to deny market access to the developing countries by exposing them to stiff but unequal competitive conditions and the NT to deny national governments the policy space to protect and promote national industries, employment and economic growth. It challenges the general assumption that the MFN and the NT are good and in the interest of all the WTO Members and rather identifies them as lynch-pins of economic development in the ECOWAS region. It also shows, contrary to the assumption of non-participation, how the ECOWAS High Contracting Parties are adapting their trading systems and harmonising their laws to the key provisions of Articles I and III of the GATT. It shows that the principles of non-discrimination are the outcome of the standard-setting procedures legally formulated as the SPS and TBT Agreements which favour the developed countries and how the Dispute Settlement Body has rejected the ‘aims-and-effect’ approach, taken a literal approach, overly emphasising trade liberalisation to the neglect of market access and economic development. This dissertation concludes that it is pre-mature for ECOWAS to assume Articles I and III obligations and recommends using the provisions of Article XXIV to build up effective influence through regional organisations and incrementally uniting to transform the GATT.This study is funded by the Brunel Law School
Keywords: ECOWAS; GATT; Tension; WTO; World Trade Organisation

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.

Public assets financing in Nigeria : the imperatives for legal reforms to unlock domestic financial resources and foreign capital for infrastructure development - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2012)
Infrastructure is one of the main parameters of economic growth and a country‘s competitiveness depends on the provision and maintenance of efficient and productive infrastructure assets. However, Nigeria, like most countries in Sub-Saharan Africa has the lowest quantity and poorest quality of stocks of infrastructure assets in the world and this phenomenally poor infrastructure has remained an impediment to development in the country. Decades of sub-optimal investment, poor maintenance culture and the fact that the required infrastructure investments could not be accommodated within the available fiscal space as a result of budgetary constraints have all contributed to the Nigeria‘s infrastructure deficit. The immediate outcome of this however is that the available infrastructure assets across the Nigerian landscape are in decrepit state and absurdly inadequate. Besides, the present demand for basic infrastructure services has grown astronomically out-stripping the supply capacity of the existing ones. Closing the infrastructure financing gap will however require increased investment by private investors through creative financing in an enabling legal and financial environment. Outside the budgetary constraints, the absence of efficient maintenance and management of infrastructure assets and quality service delivery by the public sector are some of the reasons why procurement of public infrastructure stocks by government through the traditional approach is no longer plausible and hence, the general appeal of the public-private partnership framework. However, despite all the potentials, the public private partnership technique in Nigeria has not made an appreciable impact in closing the infrastructure gaps due to lack of access to long-term financing. It is against this back-drop that this study has sought to investigate how reforms of the legal and financial infrastructure could widen access to financing through innovative financial resource mobilization in scaling-up infrastructure development and service delivery to the teeming Nigeria population. Therefore, the central thesis of this study is that the inadequacy of appropriate laws and inefficient financial system are partly responsible for the huge financing gaps in the Nigeria‘s infrastructure market and with the legal and financial reforms, an enabling legal and financial environment that would open up space for resource mobilization through innovative financing techniques and sources will be created thereby widening access to long-term financing and increasing the appetite for private investment in the nation‘s public infrastructure assets and services. So, the overarching objective of this thesis is to explore how legal and financial system reforms can facilitate the development of financial models and instruments that can help mobilize financial resources to fund infrastructure and bridge the huge infrastructure financing gaps in Nigeria in a sustainable fashion. Given the infrastructure poverty that constrains economic growth and development in Nigeria, the outcomes of this proposed study would help inform the need for the legal and financial system reforms to unlock resources in addressing the problems of financing gaps in infrastructure projects development in Nigeria. Besides, such outcomes based on the Nigerian experience in infrastructure financing and development may be turned into valuable knowledge for policy –making and further research in Nigeria. Copyright
https://repository.up.ac.za/handle/2263/24525
Keywords: Foreign capital; Infrastructure; Legal reform; Nigeria; Public assets

Codification of Contract Law: Some Lessons From History - Swain, Warren (University of Queensland Law Journal, 2012)

Trade agreements and bilateral trade in sub-Saharan Africa: Estimating the trade effects of the EU-ACP PTA and RTAs - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
This paper on Trade Agreements within SSA, is an assessment of the ex post bilateral trade effect of the European Union-African Caribbean Pacific Preferential Trade Agreement (EU-ACP PTA) and sub-regional regional trade agreements (RTAs) on bilateral trade involving SSA countries. The main objective is to find out if EU trade preferences and regional trade agreements within SSA had increased trade flows. Estimating a gravity model augmented with measures of trade agreements, the paper made use of bilateral trade flows and key gravity covariates from CEPII database on 73 countries (48 SSA and 25 EU countries) over the period 1960-2006. After controlling for the endogeneity of the trade agreement dummy, accounting for multilateral price resistance and zero-valued trade flows, the findings indicate that the EU-ACP PTA and RTAs within ECOWAS and SADC have a positive and significant impact on bilateral trade involving SSA countries. In some cases the relative impact of the sub-regional RTAs was found to be stronger than the EU-ACP non-reciprocal PTA. The results therefore indicate the need for developing countries especially within SSA to focus on expanding and integrating regional markets in order to significantly improve trade performance.
https://www.econstor.eu/handle/10419/65446
Keywords: Bilateral Exports; Developing countries; Domestic Trade; Gravity Model; International Trade; Sub-Saharan Africa; Trade Costs

Using observable trade data to measure bilateral trade costs in sub-Saharan Africa - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
Following closely the analytical approach adopted by Head and Mayer (2004) and Novy (2010), this paper derives a micro-founded bilateral trade cost measure for sub-Saharan Africa (SSA) as a function of observable domestic and inter-national trade data. The derived measure of trade cost by Novy (2010), consistent with the Ricardian and heterogeneous firm's models of trade, enables us to track changes in trade costs in SSA over time. This is a significant contribution to the trade cost literature in SSA because measures of many components of trade frictions in SSA have been unreliable. Based on bilateral trade data from BACI and production figures from the Trade, Production and Protection database by Nicita and Olarreaga (2007) for the period 1980-2003, our estimates of the tariff equivalent bilateral trade costs measure indicate that on average trade costs in SSA are relatively higher than other regions, confirming evidence which indicates trading costs in SSA to be the highest within the global trading system. The estimates indicate that SSA countries traded with each other at a lower cost than they did with other regions with the exception of the EU. Within SSA, member countries of economic blocs traded at relatively lower costs than trade with non-member countries. Using each of the main five economic blocs within SSA as a reference, overall average relative bilateral trade costs within bloc was significantly lower than across blocs. This paper therefore argues for increased efforts at regional integration within SSA to derive benefits from lower trade costs.
https://www.econstor.eu/handle/10419/65470
Keywords: Bilateral Exports; Gravity Model; Sub-Saharan Africa; Trade Costs

Understanding fiduciary duties: conflict of interest and proper exercise of judgment in private law - Valsan, Remus (McGill University, 2012)
This dissertation analyses the content and justification of the notion of fiduciary duties in private law relations. The thesis promotes the following understanding of fiduciary duties: in a legal relation where one party undertakes to act in the interests of another, and acquires decision-making authority over the other's interests, such party undertakes a core duty to exercise his best judgement in the other's interests. The core judgement duty requires a fiduciary to exercise judgement based on relevant considerations. While what constitutes a relevant consideration can be determined objectively, the weight to be ascribed to each relevant factor is left at the fiduciary's subjective appreciation.Due to the existence of this core duty, the law imposes a set of proscriptive duties. The proscriptive duties require a fiduciary to manage situations of conflict of interest. Their purpose is prophylactic: they aim to prevent self-interest (or another duty to exercise proper judgement) from affecting the reliability of fiduciary's judgement in a conscious or subconscious way. The proscriptive duties protect the core duty to exercise judgement and, as a result, the beneficiary's right to a proper exercise of judgement by the fiduciary.
https://escholarship.mcgill.ca/concern/theses/wd376141g
Keywords: Conflict of interest; Fiduciary duties; Judgment; Private law

Duty of Confidentiality: Myth or Reality? - Yu, Hong-Lin (Civil Justice Quarterly, 2012)
Explores the extent to which there is a duty of confidentiality in relation to the information used in arbitration proceedings. Considers how the duty is regulated by arbitration rules in different countries and whether there is a sufficient consensus to develop an internationally accepted principle of duty of confidentiality. Discusses which jurisdictions have an implied duty of confidentiality in the parties' arbitration agreement. Looks at how confidential information is defined in different jurisdictions, who is bound by the duty of confidentiality and the exceptions to the duty.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Confidential information; Confidentiality; Confidentialité; Information confidentielle

Corporate Governance and the Relationship between Default Risk and the Earning Response Coefficient - Zakaria, Nor Balkish (Victoria University of Wellington, 2012)
This study examines the effect of corporate governance on the relationship between default risk and the earnings response coefficient (ERC). Using a sample of 2,004 firm-years comprising 334 firms listed on the Bursa Malaysia over a six year period from 2002 to 2007, this study tests whether corporate governance mitigates the effect of default risk on ERC while controlling for the established determinants of ERC — beta, growth, earnings persistence and size. Using reverse regression, the study confirms that beta is negatively related to ERC and that growth, earnings persistence and size are positively related to ERC. Default risk is found to be negatively related to ERC thus confirming that beta is only a partial measure of risk relevant to ERC. Corporate governance — as indicated by audit quality, audit committee expertise and independence, and board independence and board shareholding — mitigates the negative effect of default risk on ERC. The results of the study hold both for the pooled sample of 2,004 firm-year observations and on a year by year basis for the 334 firms in the sample. The results are also found to be robust to various sensitivity tests including to alternative measures of the variables. The study thus provides systematic and comprehensive additional evidence on the determinants of ERC. Of itself this is an important contribution to the literature but especially so given that the evidence comes from Malaysia — an emerging economy — whereas the existing empirical literature relates mainly to developed countries.
Keywords: Corporate governance; Default risk; Earnings response coefficient

A Brief Analysis of the Disputes Arising from China-African Civil and Commercial Transactions - Zhu, Weidong (Journal of Cambridge Studies, 2012)
Keywords: Arbitrage; Arbitragem; Arbitration; China-African civil transactions; China-African commercial transactions; Disputes; Litigation

The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
URI: http://hdl.handle.net/10019.1/17849
Keywords: Privacy infringements; Privacy protection; Right of privacy

A Comparative Study of Contract Formation and Breach of Contract and Liability in China and OHADA Space Contract Laws - Traoré, Moussa Sékou; Xiao, Yongping (Journal of Politics and Law, 2011)
Chinese politicians and businessmen and their African counterparts are improving economic and commercial relations between them. This manifest interest of partnership needs a legal framework which guarantees equal and fair advantages to both parties. To reach this global aim, China and Africa must develop their collaboration in the domain of law. In the 80s China has adopted laws to reflect the country's economic and social demands such as Economic Contract Law (1981), Foreign Economic Contract Law (1985), General Principles of Civil Law (1987). Now, to better facilitate economic growth the National People's Congress (NPC) has unified China's various national specialized contract laws to obtain the “Uniform” Contract Law 1999. OHADA is a system that aims the harmonization of business law in Africa. This study aims to compare the two systems contract formation, breach of contract and liability for breach in order to have a legal frame more appropriate for business between China and this part of African Continent.

Aspects of the nature and online resolution of domain-name disputes - Hurter, Eddie (University of South Africa, 2011)
The thesis analyses selected aspects of domain-name law, mainly from the perspective of trade-mark law. It discusses the evolution of the domain-name system and how it operates as background to a more detailed discussion of the theoretical classification of domain names. The thesis then examines the interplay between trade marks and domain names, and the resolution of domain-name disputes resulting from the inherent tension between these two systems. The main principles of domain-name dispute resolution are identified by way of an analysis of the panel decisions handed down in terms of the international Uniform Dispute Resolution Policy (UDRP) and the South African domain name dispute resolution regulations. This analysis always addresses, too, the extent to which national trade-mark law principles (with reference to the laws of South Africa, the United Kingdom, and the United States of America) apply, and the extent to which this is appropriate.
Keywords: Abusive domain name registration; Cybersquatting; Dispute resolution; Domain names; ICANN; Intellectual property; Internet Corporation for Assigned Names and Numbers; Internet domain names; Nominet Dispute Resolution Service; Trademarks; Typosquatting; WIPO domain name processes; Well known trade marks; World Intellectual Property Organization

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Public employment and the relationship between labour and administrative law - Loots, Barbara Evelyn (University of Stellenbosch, 2011)
The focus of this study is the rights-based normative overlap of labour and administrative law in public employment. As the judiciary appeared to be unable to agree on a unified approach to the application of the rights to fair labour practices and just administrative action to public employment, it was clear that the complexity and multi-dimensional character of the debate required analysis of existing approaches to the regulation of the public employment relationship. The following initial research question was formulated: To what extent does (and should) the constitutionalised rights to fair labour practices (s 23) and just administrative action (s 33) simultaneously find application in the regulation of public employment relationships? In answering this question, certain realities had to be acknowledged, the most important being that the debate in question jurisprudentially revealed itself to be a jurisdictional turf-war between the Labour and High Courts, rather than proper consideration of the relevant substantive arguments and underlying normative considerations. This called for an additional dimension to be added to the research question, namely consideration of the extent to which the ss 23 and 33 rights are informed by variable and possibly different normative principles and whether these rights allow for cooperative regulation of public employment in accordance with the doctrine of interdependent fundamental rights. This became the primary focus of the study. In an attempt to simplify the debate, a deliberate decision was taken to limit the scope of the normative study to South Africa with its own historic influences, structures and constitutional considerations. The study shows that both labour and administrative law (as constitutionally informed) share concern for equity-based principles. This is evident from the flexible contextually informed perspectives of administrative law reasonableness in relation to labour law substantive fairness, as well as a shared concern for and approach to procedural fairness. Once simplified, and in the absence of any undue positive law complexity, the public employment relationship, at both a normative and theoretical level, furthermore shows no substantive status difference with private employment relationships. It is, however, accepted that there are job and sector-specific contextual differences. In the absence of substantive normative conflict between these branches of law and in the absence of a fundamental (as opposed to contextual) difference between public and private employment, there appears to be no reason to ignore the constitutional jurisprudential calls for hybridity, otherwise termed the doctrine of interdependence. The idea of normatively interdependent rights expresses the Constitution’s transformative vision (through the idea of flexible conceptual contextualism) and recognises that human rights may overlap. This also means that where such overlap exists, rights should be interpreted and applied in a mutually supportive and cooperative manner that allows for the full protection and promotion of those rights. In giving expression to the interdependent normative framework of constitutional rights, these norms (absent any substantive rights-based conflict) should then be used by the judiciary as an interpretative tool to align specific labour law and general administrative law in the regulation of public employment relationships.
URI: http://hdl.handle.net/10019.1/6683
Keywords: Administrative law; Employment law; Labour law

The external relations of company groups in South African law : a critical comparative analysis - Stevens, Richard Arno (University of Stellenbosch, 2011)
Groups of companies are part of the realities of the modern economic system. Despite the fact that such groups often function as a single economic entity, the legal point of departure remains that each company within the group of companies is a separate juristic person. The result of this is that a creditor of a company within the group can, in principle, only enforce his claim against the company which he contracted with or which caused him harm. Should he wish to claim from the holding company or other solvent companies within the group, he would have to rely on an exception to the doctrine of separate juristic personality, viz the possibility of piercing the socalled corporate veil. This dissertation is a comparative study of the extent to which the law protects a creditor of an insolvent company within a group. The applicable laws of Australia, Germany, New Zealand, the United Kingdom and the United States of America, were investigated and compared to the South African position. The dissertation concludes that the South African legal treatment of the problem is unsatisfactory and that the law should be amended through appropriate legislation.
URI: http://hdl.handle.net/10019.1/6883
Keywords: Company groups; Creditors; South African companies; South African law

Effectiveness and Remedies of the Arbitral Awards in OHADA’s System and in People’s Republic of China. - Samassekou, Mamoudou; Lianbin, Song (Journal of Politics and Law, 2011)
Today the arbitral justice has experienced an exceptional development. It is a universal phenomenon which requires the involvement of all economic and legal players of developed and developing countries.OHADA is a common business law and wish to secure legal security for regional and foreign economic agents by offering a vast economic space. The People’s Republic of China (PRC) is an emerging country which increases its economic outlets in a context of globalization. This natural interdependence will increase the scope of economic exchanges, which may generate some disputes in businesses. This article aims to compare two legal systems in the international commercial arbitration field: the legal system of OHADA and the PRC’s legal system; especially in the effectiveness and the remedies of the arbitrators’ decisions.
Number: 1

A Taxonomy of International Rule of Law Institutions - Romano, Cesare P.R. (Journal of International Dispute Settlement, 2011)
This article revises and updates a seminal article written by the author in 1998, which was the first attempt to tally how many and what kind of international courts and tribunals existed at that point in time. It contained a chart that placed international courts and tribunals in a larger context, listing them alongside quasi-judicial bodies, implementation-control and other dispute settlement bodies. The present article has three aims. The first is to provide an update, since several new bodies have been created or have become active in the last decade. The second aim is a bit more ambitious. It is time to revise some of the categories and criteria of classification used back in 1998. More than a decade of scholarship in the field by legal scholars and political scientists has made it possible to gain a better understanding of the phenomenon. The abundance of data over a sufficiently long time-span is making it possible to start moving away from a mere ‘folk taxonomy’ towards a more rigorous scientific classification. The hallmark of truly scientific classifications is that classifying is only the final step of a process, and a classification only the means to communicate the end results. Besides making it possible to discover and describe, scientific classifications crucially enable prediction of new entities and categories. Thus, the third aim of this article is to attempt to discern some trends and make some predictions about future developments in this increasingly relevant field of international law and relations.

Dispute Resolution in International Electricity Trade - Han, Baoqing (Energy Procedia, 2011)
International electricity trade disputes can arise at three key levels: state to state; investor to state; private party to private party. Parties may be more open to submission of their disputes to international arbitration. However, they should make proper arbitration options according to the types of disputes. At the same time, considering the risks facing dispute resolution, it is imperative to specifically design effective tools to mitigate these risks.
Keywords: Dispute resolution; Disputes; International Arbitration; International electricity trade; Risk mitigation

Can OHADA Increase Legal Certainty in Africa? - Beauchard, Renaud; Kodo, Mahutodji Jimmy Vital (The World Bank, 2011)
This paper describes the origins, structure, and practical impact of the Organization for the Harmonization of Business Law in Africa (OHADA). It analyzes the institutional framework created via the OHADA Treaty and the legal, jurisprudential, and functional challenges that OHADA Member States are still grappling with. Details of the nine substantive laws that have so far been ratified as uniform acts by means of the treaty have also been provided. The authors conclude that in making OHADA law effective, Member States face continuing and substantial resource deficits, institutional deficiencies, language ambiguities, and intransigent official attitudes toward the need for appropriate mechanisms for the pursuance and enforcement of OHADA laws and processes.

Multi-Membership and the Effectiveness of Regional Trade Agreements in Western and Southern Africa: A Comparative Study of ECOWAS and SADC - Afesorgbor, Sylvanus Kwaku; Van Bergeijk, Peter A. G. (Proceedings of the German Development Economics Conference, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe‟s preferential trade agreement). We find that  ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do),  SADC membership has a stronger impact compared to ECOWAS and  that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.

Comparative regionalism: a new research agenda - Börzel, Tanja A. (KFG The Transformative Power of Europe, 2011)
After the end of the Cold War, students of International Relations observed an expansion of inter-state activities at the regional level. Regional and sub-regional groupings appeared to gain momentum as the way in which countries cooperate and should cooperate to pursue peace, stability, wealth and social justice. The surge and resurgence of regionalism has triggered the proliferation of concepts and approaches. The focus of this paper will be on processes and structures of state-led regionalism driven by the delegation of policies and political authority to regional institutions. Based on this understanding of regionalism, the existing literature will be reviewed with regard to three general questions. These questions do not only require research across regions but also allow developing a common research agenda to accumulate knowledge generated about specific regions. First, what are the outcomes of regionalism? How can we describe and compare the results of the delegation of policies and political authority? Second, what are the drivers of regionalism? Why do some governments choose to delegate policies and political authority while others do not? Finally, what are the internal effects of regionalism? How does the delegation of policies and political authority impact back on the domestic structures of the states involved?
Accepted: 2018-06-08T07:36:10Z

Nigeria, oil and gas exploration and the Niger delta question : a study in corporate social responsibility - Bribena, E. K. (North-West University, 2011)
This thesis addresses issues of the Niger Delta question which represents one of the most intractable sources of socio-political destabilization in the Niger Delta region of Nigeria. The study is on the intricate dynamics amongst the Nigerian state, the transnational oi l corporations, the oil producing communities and the insurgent militia conflict. It investigates and explicates the "paradox of plenty" and the "resource curse", the "absentee government" and "state capture" and the debilitating effects of petroleum politics in Nigeria. The economic exploitation of the Niger Delta region's vast crude oil reserves by transnational oil corporations and government authorities is juxtaposed with the spectre of environmental degradation, human rights violations, and the recurrent rule of impunity. The protracted problems of the Niger Delta region thus, provide us with a pertinent analytical and contextual framework for the study of the dynamics and issues of transparency in other African petro-dollar states. It is argued in this study that the Niger Delta crisis is a conflict of values and fight for resources arising from decades of unacceptable standards of oil exploration and the absentee character of the Nigerian State. By its very nature, the study called for a qualitative approach, supplemented by unstructured interviews using aide memoirs with selected officials, on the basis of their innate knowledge of the subject matter. The legal comparative research method, with a historic component also played an integral role in this study. Some key findings and conclusions: 1. The study found that the Niger Delta crisis graduated from mère political agitations for state creation and provision of social amenities to extreme acts of hostage-taking and a twist of violence as a result of treating a major problem affecting the development of the Niger Delta people with levity for too long a period. 2. The study found that the on-going crisis in the Niger Delta region of Nigeria is a conflict of values and fight for resources amongst the oil-bearing people of the Niger Delta, transnational oil corporations and the Nigerian Government. 3. The study established some causal nexus between oil and poverty; oil and corruption; and, oil and human rights abuses. 4. That, the Niger Delta crude oil conflict is essentially a manifestation of state capture and inertia on the part of the Nigerian Government. 5. The study found that the Niger Delta economies are "criminalized" and are often characterized by conditions of anarchy and impunity. And this disorder is embedded in the dynamics of resource extraction, the nature and role of "shadow" state actors, as well as the interplay and patterns of relationships between organized criminal syndicates and the transnational oil corporations in the host communities. The study recommends, inter alia: I. That steps be taken by government to re-define its philosophy of national economic development from a state-driven to citizens-driven philosophy. To this end, Nigeria must seek to develop by developing its citizens, the aggregate of whose satisfactory living conditions should form the criteria for measuring national development. II . That effort must be made to steer the nation towards proper fiscal federalism. The present "food is ready" economy whereby federating units are enslaved to national "cake sharing" instead of value generation, discourages entrepreneurship and sustainable development. It promotes undue dependency on petroleum products, inequity and ethnic distrust. Ill. That Nigeria needs productive resource control, not just development in the sense of house and bridge building. What is needed is a noticeable leap in the standard of living in the Niger Delta. Thus, people and not federal accounts must be the object of improvement. IV. It is recommended that government should ensure robust, independent and co-ordinated oversight of the oil industry including its impact on human rights. V. Transnational oil corporations should undertake full corporate social responsibility and comprehensive assessment of the social and human rights impacts of all oil and gas projects, ensuring that adequate information is provided to affected individuals and communities and that the process is transparent. VI. It is strongly recommended that an Oil Pollution Liability Trust Fund should be established by the Federal Government in concert with oil companies. The fund will be made up of a percentage of tax levied on oil companies and a percentage of earnings of the Federal Government from oil. The fund should be used in ameliorating the conditions of the impacted environment and people. It is hoped that these findings and recommendations will go a long way in the quest for significant environmental and social improvements in the Niger Delta region of Nigeria.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Petroleum industry and trade

Exploring the limits of Western Corporate Social Responsibility Theories in Africa - Dartey-Baah, Kwasi; Amponsah-Tawiah, Kwesi (International Journal of Business and Social Science, 2011)
Corporate Social Responsibility (CSR) is about the relationship of organisations with society as a whole, and the need for organisations to align their values with societal expectations. Generally, CSR practice in Africa is thought to be adopted from Western business theories although there is evidence to suggest that Western CSR theories are not totally applicable in Africa. This is due to differences in drivers or causes of CSR in the West and in Africa, as well as cultural and managerial traits in Africa. This paper explores the limits of Western CSR Theories in Africa and argues that improved ethical responsibilities, incorporating good governance should be assigned the highest CSR priority in developing countries. It further adds that increased legislation, change in CSR priorities and the application of indigenous CSR theories such as Ubuntu, African Renaissance and Omuluwabi are means of countering the limits of Western CSR theories in Africa. Keywords: CSR, Western CSR Theory, Africa, Ubuntu, African Renaissance, Omuluwabi
Keywords: Africa; CSR; RSE; Renaissance; Ubuntu; Western CSR Theory

OHADA's Proposed Uniform Act on Contract Law: Formal Law for the Informal Sector - Dickerson, Claire Moore (European Journal of Law Reform, 2011)
The draft uniform act on contracts proposed for adoption by the Organization for the Harmonization of Business Laws in Africa ("OHADA") is a combination of continental and common-law concepts. To be effective in parts of the world where the informal sector is particularly important, for example in the 16 West and Central African states where OHADA currently operates, contract law must be particularly attentive to avoiding traps for the unwary. For this reason, enforcing gratuitous contracts may well be defensible, but requiring registration of commercial actors is not. The complexity of two OHADA laws applicable to contracts, however, increases the risk that law and norms will not overlap, creating just such a trap.
Keywords: Comparative law; contracts; norms

Common good and the concept of expropriation in international law on foreign investment: Determinacy of substance in legitimacy of structure - Falsafi, Alireza (McGill University, 2011)
This thesis, exploring the rule of law for international rules, offers a human bond of common good between determinacy of substance and legitimacy of structure of rules in order to evaluate international obligations of States in international law on foreign investment. In an in-depth exposition of the theoretical underpinnings and practices underlying the normative structure of rules in international law, the thesis critically questions the legal reasoning embedded in—and the authority of rules borrowed from—principles and precedents or moral and political evaluations by arbitrators in interpretation of States' contractual, customary, and treaty obligations in investment arbitrations. With crucial moral, political, social and economic ramifications for the constitutional functions of States and concomitant interests of their human members implicated in the concept of expropriation in international law, the thesis provides a framework of legitimacy in a common good approach with structural criteria of recognition and coherence for the interpretation of States' obligations in investment arbitration. Coherence brings to the fore conflicting demands of justice requiring fresh evaluation divesting a general rule of its authoritative force, and recognition brings to the fore the validation of the power to engage in moral and political evaluation. Together, these structural criteria offer a common good approach of legitimacy to test the authority of States' obligations and the power of arbitrators in hard cases. By virtue of these criteria, the thesis characterizes the nature of substantive property rights of corporations and corresponding obligations of States in foreign investment as contingent and consensual in contrast with the absolute and constitutional rights of human beings in human rights. Through coherence and recognition, the thesis also portrays a supreme status for customary international law for the normative structure and substance of States' contractual or treaty obligations in the interpretation of hard cases in international law on foreign investment. The thesis espouses a new horizon for legal reasoning in foreign investment arbitration that eschews the lex lata veneer for lex ferenda propositions manufactured from precedents and principles, on the one hand, and the sheen of law for the conception of justice of investor-State arbitrators, on the other, in cases of hard confrontation between the demands of justice.
https://escholarship.mcgill.ca/concern/theses/dv13zz300
Keywords: Expropriation; Foreign investment; International law

Copyright in the digital environment : ontologies of copyright and digital works - Filippi, Primavera De (European University Institute, 2011)
The advent of Internet and digital technologies has radically transformed the way information is being produced and consumed. The consequences for copyright law are twofold. While digital media provide new opportunities for authors to produce and disseminate their works to the public, they simultaneously encourage and facilitate copyright infringement. Traditionally, in order to ensure compliance with the law, the copyright regime could rely upon the properties of physical media to constitute a natural barrier against copyright infringement. As the medium went digital, however, its properties became a catalyst for infringement. Designed for the physical world, the structure of the copyright does not adequately address the issues inherent to digital media. Private regulation therefore came into play in order to resolve the problem. While restrictive licensing agreements combined with technological measures of protection purport to reestablish a technological barrier against copyright infringement, permissive licenses such as Creative Commons purport to reduce the scope of protection granted by default under the law. Although differing in method, these approaches share a common goal: to realign the properties of the work with the properties of the digital medium by readjusting the legal attributes and technical characteristics of digital copies. As a legal concept, however, the notion of a copy must be precisely defined. After performing an ontological analysis of the copyright regime within the scope of the Functional Requirements for Bibliographic Records and the Information Artifact Ontology, the research concludes that physical copies fundamentally differ from their digital counterpart. While the former qualify as a token, the latter qualify as a class that is capable of multiple instantiations. Moreover, given that the identity of a digital copy can no longer be defined by its physical characteristics, it is fundamentally for the copyright license to determine the scope of the copy to which it refers.
Keywords: Copyright; Digital media; Electronic data processing; Intellectual property; Internet

The effects of state succession on cultural property : ownership, control, protection - Jakubowski, Andrzej (European University Institute, 2011)
The purpose of this study was to investigate the legal effects of state succession on cultural property. This is not a new topic of international law. Indeed, the attempts to provide a legal framework for the cultural aspects of state succession have been undertaken in international practice and legal scholarship since at least the mid-nineteenth century. Initially, these were strictly bound to the origin of the European nation-state, determining its territorial boundaries accordingly to ethnic and cultural divisions. However, the concept of cultural property in international law has evolved towards a broader, more human-oriented idea of cultural heritage. Such a conceptual shift has occurred in the last fifty years, marked by the gradual recognition of the fundamental role performed by cultural manifestations in the preservation of human dignity and the continuous development of all mankind. This study discusses to what extent the practice and the theory of state succession reflect this evolution. It attempts to reconstruct the principles regulating interstate arrangements with regard to such matters, contextualizing them in a broad historical and geographical framework. Particular attention has been paid to the question of state succession to international cultural heritage obligations. This piece of work explores their content, sources and status in state succession. It explains that nowadays the preservation and enjoyment of cultural heritage do not constitute the exclusive concern of state sovereignty. On the contrary, such values are of general interest to the international community as a whole. Therefore, the study advocates a new doctrinal approach, based both on the principles of international cultural heritage law and human rights law. This implies the limitation of the contractual freedom of states in the matter of cultural agreements, in favour of the continuity of international cultural heritage obligations in cases of state succession. Finally, the study proposes a list of guiding principles relating to the succession of states in respect of tangible cultural heritage, which may contribute to the further development of international practice.
Keywords: Cultural property; Property protection; State succession

Reformulating corporate residence: a coherent response to international tax avoidance - Loomer, Geoffrey (University of Oxford, 2011)
This thesis analyzes the concept of corporate residence, with particular reference to the law in the UK and Canada. It explores why corporate residence is relevant in tax policy, how corporate residence is understood in law, and how revenue authorities respond to the use and alleged 'abuse' of residence rules. Part I argues that the residence of taxpayers generally (individual or corporate) remains a relevant factor in international tax design, that taxation of corporations on the basis of residence has some justification, but that there is a disjunction between meaningful residence-based taxation and current definitions of corporate residence in domestic law and tax treaties. The formulations of residence based on incorporation, central management and control, and place of effective management, particularly as applied to multinational enterprises, are considered and are found to be deficient. Part II critically analyzes the major policy responses of the UK and Canadian governments to the exploitation of corporate residence. It argues that key legislative and administrative responses to international tax avoidance activities, for both outbound and inbound investment, are purportedly based on the acceptance of formal corporate residence yet undermine that concept in an effort to impose tax or refuse treaty relief based on where economic interests actually exist. The responses considered are the application of controlled foreign companies legislation to offshore subsidiaries, the invocation of treaty anti-abuse rules with respect to offshore intermediaries, and the use of overarching general anti-avoidance measures to challenge varied structures that rely on offshore entities. These haphazard anti-avoidance rules are overlaid with revenue authorities' indignation at the motivations that underlie many corporate relocations. It is argued that a more coherent approach would be to focus on the objective reality or unreality of corporate establishment, by reformulating corporate residence in domestic law and tax treaties.
Keywords: Economics Law; International business; International taxation; Multinational enterprises; Resident companies; Tax avoidance; Tax planning; Taxation

The dilemma of national security and international cooperation in outer space: space technology trade and proliferation controls and their impact on global civil space cooperation - Mineiro, Michael (McGill University, 2011)
In this thesis space technology trade and proliferation controls are analyzed, focusing on two substantive issues that illustrate the challenges and opportunities of reform. The first substantive issue examined is the challenge of domestic law and policy reform in light of international regulatory divergence. This issue is examined through a case study of the U.S. commercial communication satellite export control regime. The second issue is the international implications of space technology trade and proliferation control on global civil space cooperation. The unifying demonstration of this doctoral thesis is that States operate in an international legal system that perpetuates a self-justified security dilemma whose basis originates in the sovereign legal right of States to produce, procure, and maintain space technologies of a military nature. As a result, the international legal system governing space technology trade and proliferation creates a tension between perceived national security needs and the benefits of global cooperation.

Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern

Arbitration: One Size Does Not Fit All: Necessity of Developing Institutional Arbitration in Developing Countries - Namrata Shah, Niyati Gandhi (Journal of International Commercial Law and Technology, 2011)
Litigation in developing countries has many defects which has prompted a need for the development of alternative dispute resolution mechanisms. Arbitration, being one such substitutive mechanism as a type of private litigation is the most suitable for the same. This paper deals with the need to develop institutional arbitration to co-exist with ad hoc arbitration and scale it down to be available for dispute resolution in developing countries using an illustration of India. Certain recommendations to make institutional arbitration, which is considered to be appropriate for International commercial dispute resolution, suitable for domestic disputes in developing countries have been highlighted.
https://www.neliti.com/publications/28786/
Keywords: Arbitrage; Arbitragem; Arbitration; Developing countries; Institutional arbitration

Intellectual Property Law and Competition Law - Patel, Atul; Panda, Auro Aurobinda; Deo, Akshay; Khettry, Siddhartha; Mathew, Sujith Philip (Journal of International Commercial Law and Technology, 2011)
Competition law and intellectual property rights (IPRs) have evolved historically as two separate systems of law. There is a considerable overlap in the goals of the two systems of law because both are aimed at promoting innovation and economic growth. Yet there are also potential conflicts owing to the means used by each system to promote those goals. IP laws generally offer a right of exclusive use and exploitation to provide a reward to the innovator, to provide an incentive to other innovators and to bring into the public domain innovative information that might otherwise remain trade secrets. Competition authorities regulate near monopolies, mergers and commercial agreements with the aim of maintaining effective competition in markets. This article introduces the concept of IPRs and Competition law. It highlights important areas of conflict between the two laws and also deals with the Indian antitrust law. It concludes by trying to harmonize the conflicts.
Keywords: Competencia; Competition law; Intellectual property

Fairness in class action settlements - Piché, Catherine (McGill University, 2011)
To be made effective, class action settlements must be negotiated fairly, be perceived as fair and reasonable by the settlement parties such that they agree to their terms and substance, and be characterized as fair, reasonable and adequate by a court at the occasion of a settlement approval hearing. But how is settlement fairness defined, in a collective litigation context? By which process is the evaluation of fairness made and the approval given by the court? What role does the court correspondingly have, in that context? This thesis explores the legal policy and reasoning behind the mandatory judicial approval of class settlements, the process by which it is sought and obtained, the currently relevant factors and indicia of settlement fairness which support all decisions to approve, and the roles of the principal settlement actors, particularly the settlement judge. It suggests hypotheses for reform applicable to these approval processes, roles of the actors and standard of settlement fairness. These hypotheses are tested, for their plausibility, against empirical data obtained from the qualitative interviews of seventeen judges conducted by the author in four target jurisdictions that have similar approaches to class action settlement approvals, and where class action litigation activity is heavy: Quebec, Ontario, British Columbia, and the United States federal courts. Ultimately, the thesis proposes final recommendations for reform of the class action settlement approval procedure.
Identifier : https://escholarship.mcgill.ca/concern/theses/n009w645z
Keywords: Class action; Class action settlement; Settlement parties

International convention for the control and management of ships' ballast water and sediments, 2004 - Robe Hughes, Charlotte (Aix-Marseille Université, 2011)
Will harmonization of legislation relating to the management of ships’ ballast water be achieved, once IMOs’ 2004 Convention enters into force?

A comparative study: Arbitration agreement in OHADA and People's Republic of China arbitration laws - Samassekou, Mamoudou; Song, Lianbin (Journal of Politics and Law, 2011)
This article aims to compare the arbitration agreement of the OHADA legal system to that of the People's Republic of China. In the Chinese legal system the parties to a contract are required to have an arbitration agreement written before the occurrence of any incident in the execution of their contract. The parties must specify in advance, in the said agreement, the chosen arbitration institution for potential disputes. In the OHADA legal system, the parties are free to decide before or during execution of the contract of an arbitration agreement. They may also decide whether in case of a dispute, they would want to refer to an institutional arbitration or an ad hoc arbitration. According to the chosen legal system the consequences are different.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; China-OHADA

Revisiting the Depoliticization of Investment Disputes - Schneiderman, David (Yearbook on International Investment Law and Policy, 2011)
The chapter challenges claims about depoliticization in two different aspects. The first examined claim is that home states are disenfranchised from pursuing investment claims once they are lodged with ICSID. Is it the case that home states simply stay home? This chapter examines instances where home states may have played a role in investment disputes between contracting states. What the record generally reveals, however, is that home states involve themselves in disputes where ICSID hearings are imminent but not yet in play. The second, broader, reading of depoliticization maintains that disputes now are resolved without recourse to lowly politics but to ‘higher’ law. This more extravagant claim is vulnerable to the critique that investor-state dispute resolution is not emptied of political content but, instead, spills over with politics. As the regime implicates the capacity of public authority to act in a wide variety of regulatory contexts, the separation of law from politics is hard to credibly maintain. Not only are investor-state disputes embedded within regimes of political discourse and political power, the ambit of investment arbitrator discretion is so capacious that it can be said of arbitrators, as it has been said of the U.S. Supreme Court, that they can sensibly be regarded as political actors.
Accepted: 2024-06-14T19:55:42Z

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa

Market access and sustainable development: a legal policy analysis of the market access regime of the least developed countries under the WTO - Tania, Sharmin Jahan (Macquarie University, 2011)
"The main objective of the thesis is to examine whether improved market access for the exports of the least developed countries (LDCs) is a significant means for achieving sustainable development through trade. Further, it aims to examine whether LDCs face challenges in achieving their sustainable development in the existing market access regime... Recognising the specific needs of LDCs, the Preamble to the 'WTO Agreement' calls for positive efforts designed to ensure that LDCs secure a share in the growth in international trade commensurate with the needs of their economic development."
Keywords: Commerce; Developing countries; Exports; Foreign trade regulation; Free Trade; Sustainable development; WTO; World Trade Organization

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation

INCOTERMS as a form of standardisation in international sales law : an analysis of the interplay between mercantile custom and substantive sales law with specific reference to the passing of risk - Coetzee, Juana (University of Stellenbosch, 2010)
International sales contracts have very specific needs that stem from the multiplicity of legal systems which apply to such contracts. In addition to harmonised law, mercantile custom is able to address many of these needs. Mercantile custom represents usages which are clear, certain and efficient and are expected to be known and applied by merchants in a particular trade or region. To this extent mercantile custom fulfils an automatic harmonisation function. However, where a custom does not enjoy uniform application across all branches of trade, the harmonisation function of mercantile custom is limited, as is the case with trade terms. Trade terms reflect mercantile customs and usages which developed over a long time in order to simplify the trade in goods that are transported from one place to the other. They regulate the delivery obligations of the seller and buyer as well as associated obligations such as the passing of risk. Trade terms negate the need for elaborate contract clauses and appear in abbreviated form in contracts of sale. Although they provide a uniform expression of mercantile custom in a particular location or trade, the understanding of trade terms tend to differ from country to country, region to region or from one branch of trade to the next. The ICC INCOTERMS is an effort to standardise trade term definitions at the hand of the most consistent mercantile customs and practices. The aim of this study is to investigate the efficiency of INCOTERMS as a form of standardisation in international sales law. For purposes of the investigation the focus is limited to the passing of risk. Although national laws usually have a default risk regime in place, merchants still prefer to regulate risk by means of trade terms. This study will investigate the legal position in the case of FOB, CIF and DDU terms. An analysis of the risk regimes of a few selected national systems will show that each has their own understanding of these trade terms. The United Nations Convention on Contracts for the International Sale of Goods (CISG) does not refer to trade terms, but many commentators have concluded that the CISG risk rule is consistent with INCOTERMS. The study will discuss this in more detail. To determine the efficiency of INCOTERMS as a form of standardisation in international sales law, the study examines their characteristics, legal nature as well as their limited scope of regulation. Specific emphasis is placed on the interplay between the CISG and INCOTERMS and the possibility of some form of interaction and collaboration between the two instruments. It is concluded that collaboration between INCOTERMS and the CISG adds value to the international law of sales by increasing the efficiency of an international business transaction and thereby facilitating international trade.
Keywords: CISG; INCOTERMS; Mercantile custom; Standardisation

National legislative systems and foreign standards and regulations: The case of International Financial Reporting Standards adoption - Dima, Bogdan; Dima (Cristea), Stefana Maria; Moldovan, Nicoleta; Pirtea, Marilen Gabriel (MPRA Paper, 2010)
This study is focused on the linkages between the legislative families as descriptors of national legislative systems and International Financial Reporting Standards (IFRSs) issued by the International Accounting Standards Board (IASB). We consider such analysis as a case study for the more general issue of explaining the preferences of national regulators in the adoption of foreign norms, rules, standards and practices. By using a dataset of 162 jurisdictions and dummy variables designed to capture the current stage of IFRSs adoption and, respectively, the taxonomy of their legislative systems, we find that a full IFRSs adoption is more likely to occur in countries which have principles-based on legislative mono-systems. In addition, we observe that a strong rule of law, with an effective mechanism of property rights reinforcement, as well as the pre-adoption existence of a pro-growth set of public policies can contribute to the encouragement of IFRSs adoption.
Keywords: IFRSs adoption; Legislative families

Legal origins, legal institutions and poverty in Sub-Saharan Africa - Baldelli, Federico (LUISS Guido Carli, 2010)
The traditional and religious layer. The colonial layer. Law of independence. Law in Sub-Saharan Africa today. Common law and civil law in Sub-Saharan Africa. The consequences of legal origins. Legal origins and legal institutions in Sub-Saharan Africa. Legal origins and poverty in Sub-Saharan Africa. An econometric model.

A politico-legal framework for integration in Africa : exploring the attainability of a supranational African Union - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2010)
The emergence of the African Union (AU) is seen as an effort to reposition Africa for the challenges of contemporary global realpolitik and, in particular, it provides a road map towards the attainment of a political union. The institutional architecture of the AU, modelled after the European Union (EU), indicates an intention on the part of the architects of the AU to endow the organisation with supranational attributes. However, none of its institutions has as yet started to exercise supranational powers. It is against this background that this thesis explores the feasibility of transforming the AU from a mere intergovernmental organisation into a supranational entity. In the course of the investigation, it was found that a major obstacle to realising this is the absence of shared democratic norms and standards, a consequence of the unconditional membership ideology of the AU. This thesis argues that the starting point of closer integration in Africa should be the cultivation and adoption of shared norms and values. To address this, the study proposes that the AU design an institutional mechanism for regulating its membership. Using the African Peer Review Mechanism (APRM) as a case study, this study shows that it is possible to establish a regulatory regime based on strict adherence to shared fundamental norms and values. A major recommendation is the transformation of the APRM into a legally binding instrument for setting continental democratic standards, assessing whether member states fulfil these standards and ultimately determining which member states are qualified, based on objective standards, to be part of a democratic AU.
https://repository.up.ac.za/handle/2263/28573
Keywords: African Union; African peer review mechanism; Regional economic communities (RECs); Regional integration

The New African Law: Beyond the Difference Between Common Law and Civil Law - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Trends on the Harmonization of Contract Law in Africa - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Legal Challenges and Strategies for Comparison Shopping and Data Reuse - Zhu, Hongwei; Madnick, Stuart E. (Journal of Electronic Commerce Research, 2010)
New technologies have been continuously emerging to enable effective reuse of an ever-growing amount of data on the Web. Innovative firms can leverage the available technologies and data to provide useful services. Comparison-shopping services are an example of reusing existing data to make bargain-finding easier. Certain reuses have caused conflicts with the firms whose data has been reused. Countries in the European Union have implemented the Database Directive to provide legal protection for database creators, but the impact and the interpretation of the new law are unclear and still evolving. Lawmakers in the U.S. have not decided on a policy concerning database protection and data reuse. Both data creating and data reusing firms need to develop strategies to operate effectively in this uncertain environment. Comparison-shopping and other data reuse services face similar legal and strategic challenges. Thus we address these challenges in the broader data reuse context. We use economic reasoning to formulate strategies in anticipation of the likely policy choices and interpretations of existing legislation. Both data creating firms and data reusing firms should focus on innovative ways of using or reusing data to create differentiated products and services. For firms that gather data from multiple sources, they can also use the insights gained from integrated data to provide other value-added services.

A reformatory approach to state regulation of insolvency law in South Africa - Calitz, Juanitta Christelle (University of Pretoria, 2010)
https://repository.up.ac.za/handle/2263/30839
Keywords: Insolvency; South Africa; State regulation

The suitability of the South African corporate tax regime for the use of South African resident intermediary holding companies - Legwaila, Thabo (University of Pretoria, 2010)
An Intermediary Holding Company (“IHC”) is a company that is interposed between an ultimate holding company and the operating subsidiaries of a group of companies. The IHC operates at an international level such that either its holding company or its subsidiaries or both are located in a country foreign to the IHC. Its main functions are to acquire, manage and dispose of the assets of the group of companies and to facilitate structural flexibility of a group of companies. Investors have tax and non-tax reasons for conducting business using an IHC, and, depending on the reasons, they determine the location of the IHC based on the characteristics of potential host countries. This thesis analyses the suitability of the South African corporate tax regime for the use of South African-resident Intermediary Holding Companies. The South African government has the objective of promoting South Africa as a gateway for investment in Africa and for this reason the present research is important. Such an objective could be adversely affected by a corporate tax regime that is not suitable for the operations of an IHC. Furthermore, the Katz Commission recommended in 1997 that South Africa should consider introducing a regime that is suitable for the location of holding companies. In discharging its functions the IHC attracts liability for corporate income tax, capital gains tax, controlled foreign company tax and dividends tax. It also exposes itself to anti-avoidance measures such as thin capitalisation and transfer pricing provisions. The existence of such taxes and anti-avoidance measures in the tax system of a country may deter investors from locating an IHC in such country. Exchange control regulations could also adversely affect the ability of the IHC to perform its functions effectively, as their purpose is to restrict the movement of capital out of the country. The South African legal system contains all these taxes and anti-avoidance measures as well as exchange control provisions. However, it also contains tax instruments that alleviate the tax burden on an investor using an IHC such as the participation exemption, advance tax rulings and a network of tax treaties. Against this background this thesis analyses the South African corporate tax system to determine whether it is suitable for locating an IHC. In the analysis, a comparative study is done of the tax systems of two of the most effective IHC host countries, namely the Netherlands and Mauritius. In addition, a brief discussion of the special features contained in the tax systems of Belgium, Ireland and the United Kingdom outlines why these jurisdictions are not necessarily successful in attracting IHCs. The thesis also discusses harmful tax practices and the attitude of the international community towards countries that engage in harmful tax competition in order to determine the limits to which a country should use the tax system to attract investment. Finally, the thesis makes recommendations as to what adjustments could be made in order to enhance the suitability of South Africa to host an IHC. The thesis recommends a special dispensation as regards corporate income tax and exchange control that would apply to wholly-owned South African companies that own foreign subsidiary shares and loans that consist of 80% of the gross asset total of these companies.
Keywords: Intermediary Holding Company; South Africa; Tax; Taxation

On the Development of West African Accounting System - Moussa, Boka (International Journal of Business and Management, 2010)
The authorities of the West African Economic and Monetary Union UEMOA fully understand that accounting plays the significant role in the process of economic development and regional integration in the member states. They decided to establish a common new accounting system, called West African Accounting System (SYSCOA). The accounting system has been developed on the initiative of the Central Bank of West African States
Number: 5

Some comparative aspects of corporate rescue in South African company law - Loubser, Anneli (University of South Africa, 2010)
South African company law has provided for the rescue of financially distressed companies since 1926 when the statutory procedure of judicial management was introduced by the Companies Act 46 of 1926. Unfortunately, judicial management has never been regarded as a successful corporate rescue procedure and for most of its existence it has been severely criticised on many grounds. The Companies Act 61 of 1973 that replaced the Companies Act 46 of 1926 did very little to improve this situation and judicial management remained underutilised. As a result, the Companies Act 71 of 2008 now introduces two newly-created corporate rescue procedures in the form of business rescue proceedings and the compromise with creditors. This study analyses judicial management and the new corporate rescue procedures to establish whether the identified weaknesses of judicial management have been adequately and effectively addressed in the new procedures. A comparative study with similar procedures in England and Germany is undertaken to determine whether the South African legislature has delivered on its promise to create a system of corporate rescue that will meet the needs of a modern South African economy. Several weaknesses in the new procedures are identified and a number of recommendations are made to improve the relevant provisions and to assist in providing South African company law with an efficient and acceptable corporate rescue regime.
https://uir.unisa.ac.za/handle/10500/3575
Keywords: Bankruptcy; Business failures; Business recovery; Business rescue; Corporate insolvency; Corporate reorganizations; Corporate rescue; Corporation law; Debtor and creditor; Financial distress; Insolvency; Insolvency practitioners

Impact of Macro and Micro Governance Structures on Earnings Management - Houqe, Muhammad Nurul (Victoria University of Wellington, 2010)
This study examines the macro and micro level determinants of the quality of reported earnings. The prior literature suggests that both micro and macro variables impact on discretionary accruals choice in managing earnings. However, most of the studies on earnings management have been single country studies that have focussed only on micro variables as all firms within the samples examined have been subject to the same interplay of macro economic, legal, cultural and institutional frameworks. This study addresses this gap in the literature by using a sample of 156,906 firm year observations from 63 countries over the period 1998-2007 to examine the role of thirteen micro and macro variables in determining earnings quality. The macro variables studied include legal enforcement, political system, and control of corruption, culture and adoption of IFRS. Earnings management is estimated using the modified Jones model (Dechow et al. 1995) in a cross section (DeFond and Jiambalvo 1994; Francis et al. 1998). The results of the study indicate that macro and micro level variables have a strong impact on earnings management behaviour and thus earnings quality. The limits imposed by a country's legal, cultural and institutional setting on managerial discretionary accruals choices, strongly impact the quality of reported earnings. Future research on earnings management should therefore control both micro and macro level variables.
Keywords: Earnings management; Macro governance; Micro governance

International Investment Law and Media Disputes: A Complement to WTO Law - Peterson, Luke Eric (Transnational Corporations Review, 2010)
The recent high-stakes dispute between Google and China over censorship and cyber-security has spawned renewed discussion of the international trade law protections that internet and media companies may enjoy. Less recognized, however, is a perhaps more powerful legal tool in the arsenal of internet and media companies engaging in cross-border investments, namely international investment law.
Keywords: China; international investment; law; media

The participation of developing countries in the dispute settlement system of the WTO - Al. Shraideh, Saleh Adnan (Macquarie University, 2010)
International trade relations have become much more legalised under the World Trade Organization (WTO) than under the former international trade system created pursuant to the General Agreement on Tariffs and Trade (GATT). The Dispute Settlement Understanding (DSU) of the WTO clearly represents a shift toward a rule-oriented, legalistic and adjudicative approach, which is intended to enhance that status of, and confidence in, the WTO dispute settlement system. The approach is likely to ensure greater stability and predictability in the system by encouraging precise decisions on the merits of disputes and discouraging infractions. Its greater binding effect serves as a powerful disincentive to those Members who have a propensity to favour unilateral measures to solve international trade disputes. This is particularly beneficial for developing countries that sought a system which recognises their disadvantaged position compared to the greater bargaining and retaliatory power of developed countries. However, despite the positive assessment of the WTO dispute settlement system, the functioning of the system is working against the interest of developing countries in having an efficient dispute settlement system that considers their needs and deals fairly with their disputes. This thesis examines the participation of developing countries in the dispute settlement system of the WTO, and argues that they are in a disadvantageous position compared to their developed counterparts. The system's failure to effectively address or efficiently deal with this position is an evidence of its bias against and deficiency towards developing countries' participation. The thesis focuses on the problematic issues developing countries face throughout their use of the system. It also considers the role that the DSU has played in addressing these issues and the efficiency of that role in restraining and limiting their effect on developing countries' participation in the system. The thesis analyses some ideas on the reform of the DSU that have been proposed through WTO negotiations or literature, and discusses their applicability on the current dispute settlement system. Finally, the thesis employs these proposals along with its discussion on the subject to introduce a reformed model of the DSU which is more sensitive to developing countries' concerns in the system in order to help providing an understanding of how such modifications could be carried out in future reforms on the DSU.
Keywords: Conflict management; Developing countries; Foreign economic relations; GATT; General Agreement on Tariffs and Trade; International relations; Politics and government; WTO; World Trade Organization

The Role of South Africa in SADC Regional Integration: the Making or Braking of the Organization - Amos, Saurombe (Journal of International Commercial Law and Technology, 2010)
Read on Neliti

Reforming corporate governance: Protecting minority shareholder rights through a strong corporate law system - Deniz, Ozden (American University, 2010)
Keywords: Association law; Corporate governance; Corporate law; Minority shareholder (protection)

A critical evaluation of the interaction between sport and law in South Africa - Louw, André Mouton (Stellenbosch University, 2010)
This dissertation contains an evaluation of the interaction between law and sport in South Africa. The evaluation includes description of the main areas where laws (in the form of the common law, legislation and the relevant provisions of the Constitution of the Republic of South Africa, 1996) apply to sport, in the contexts of both amateur sport and the fast-developing professional sports industry. Apart from such descriptive content, the dissertation will also critically evaluate the appropriateness of the relevant laws and their application in the often atypical context of sport, as well as the courts' treatment of the relevant legal issues. In the process of providing such critical evaluation, and where relevant, the author includes a comparative analysis of the treatment of relevant legal issues in other jurisdictions (most notably the United Kingdom and European Union, which are especially relevant in light of the application of the 'European model' of sports governance and regulation, which applies to the major sporting codes in South Africa). In particular, the author critically evaluates the following aspects of the South African jurisdiction's treatment of the application of law to sport: - The South African system of public regulation of sport by the State (and, specifically, the issue of the race-based transformation of sport, which involves an apparent government-driven agenda and is unique to the South African jurisdiction); - The courts' treatment to date of the susceptibility of the conduct of sports governing bodies to judicial scrutiny (and of the nature of such bodies as voluntary associations); - Various aspects related to the application of employment laws to the employment of professional athletes in team sports; - The application of common law remedies for breach of contract in the professional sports employment context; - The potential application of the restraint of trade doctrine (in, as the author suggests, an extended_ form) in the context of the freedom of movement of professional athletes; The apparently unsatisfactory state of current South African law in respect of legal protection against commercial misappropriation of aspects of the persona of famous athletes (i.e. in the context of 'image' -or-,'publicity' rights as recognized in certain other jurisdictions); and - An evaluation of the extensive protection (especially in the form of specific legislation in South Africa) against ambush marketing of major sporting events. The author includes some concluding observations regarding the state of South African sports law as compared to other jurisdictions, as well as some comment on expectations for the future development and potential importance of the South African domestic jurisdiction in the application of law to sport.
URI: http://hdl.handle.net/10019.1/49490 There are three other contributors to this work numbering 15 p. in total.
Keywords: Comparative law; European Union; South Africa; Sports; United Kingdom

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara

Business law transplants and economic development: an empirical study of contract enforcement in Dakar, Senegal - Paquin, Julie (McGill University, 2010)
La création d'environnements attrayants pour les investisseurs est récemment devenu une priorité pour les spécialistes du développement, qui conseillent aux pays en voie de développement d'adopter les « meilleures pratiques » d'affaires utilisés dans les pays développés. Bien qu'on reconnaisse que le transfert de modèles juridiques d'un pays à un autre entraîne souvent des résultats décevants, la question du niveau de compatibilité requis entre les modèles transférés et le pays importateur est le plus souvent ignorée ou considérée comme une question technique relevant de la compétence des professionnels du droit locaux. Dans ce processus, pratiquement aucune place n'est faite au point de vue des utilisateurs finaux des nouvelles normes et institutions. La présente thèse se fonde sur une étude empirique de l'impact de la réforme du droit des affaires relativement en matière d'exécution des contrats. Dans une première partie, les hypothèses sur lesquelles les réformes actuelles se fondent sont examinées à la lumière de contributions provenant de divers champs disciplinaires. Divers facteurs considérés comme expliquant les effets limités des réformes entreprises jusqu'à présent sont présentés. La deuxième partie analyse le contenu de 30 entretiens en profondeur réalisés auprès de petites et moyennes entreprises de Dakar, Sénégal. Les entretiens révèlent que les PMEs dakaroises font preuve d'une grande flexibilité dans l'exécution de leurs contrats d'affaires, et que la qualité des institutions juridiques et judiciaires joue un rôle peu important dans les décisions qu'ils prennent à cet égard. L'environnement général dans lequel elles opèrent, qui se caractérise par la présence de contraintes financières importantes, un haut niveau d'inceritude et une grande interdépendance entre les entreprises, constitue le facteur le plus important pour expliquer le comportement des entreprises. La troisième part
https://escholarship.mcgill.ca/concern/theses/gm80hv75c
Keywords: Business law; Contract enforcement; Economic development; Senegal

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente